Communication Predicts Medication Self-Efficacy in Glaucoma Patients. - Carpenter, Delesha M; Blalock, Susan J; Sayner, Robyn; Muir, Kelly W; Robin, Alan L; Hartnett, Mary Elizabeth; Giangiacomo, Annette L; Tudor, Gail E; Sleath, Betsy L (Optometry & Vision Science, 2016)
Purpose: Medication self-efficacy, or patients' confidence that they can perform medication-related behaviors, is associated with better glaucoma medication adherence. Little is known about how to enhance glaucoma patients' medication self-efficacy. Our purpose is to examine whether patient-provider communication increases glaucoma patients' medication self-efficacy.Methods: During an 8-month cohort study of 279 glaucoma patients and 15 providers, two office visits were videotape-recorded, transcribed, and coded for six patient-provider communication behaviors. A validated scale was used at baseline and 8-month follow-up to assess patients' confidence in overcoming adherence barriers (adherence barriers self-efficacy) and carrying out tasks to use eye drops correctly (eye drop task self-efficacy). We ran two generalized estimating equations to examine whether more frequent patient-provider communication during office visits predicted increased patient adherence barriers self-efficacy and eye drop task self-efficacy at 8-month follow-up.Results: For each additional topic providers educated about, patients reported an average increase of 0.35 in self-efficacy in overcoming adherence barriers (p < 0.001). Patients also reported an average increase of 1.01 points in eye drop task self-efficacy when providers asked about patients' views of glaucoma and its treatment versus not (p < 0.001). Patients who asked more medication questions (p < 0.001) and African-American patients (p < 0.05) reported lower adherence barriers self-efficacy by 0.30 and 2.15 points, respectively. Women had a 0.63 lower eye drop task self-efficacy than men (p < 0.05).Conclusions: When providers educate glaucoma patients and assess patient views about glaucoma and its treatment, patients report higher medication self-efficacy. Providers should be aware that patients who ask more medication questions may have less confidence in their ability to overcome barriers to adherence.
Keywords: Patient Education -- Methods; Communication -- Methods; Antihypertensive Agents -- Therapeutic Use; Glaucoma -- Drug Therapy; Physician-Patient Relations; Medication Compliance; Female; Human; Ophthalmic Solutions; Self-Efficacy; Male; Prospective Studies; Young Adult; Aged; Middle Age; Aged, 80 and Over; Adult; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

Clinicians should establish partnership with patients to tackle compliance obstacles. - Misiano J (Ocular Surgery News, 2007)
A strategy to help patients remain on their glaucoma regimen is another key to compliance.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Physician-Patient Relations; Intraocular Pressure

Impact of COVID-19 on follow-up and medication adherence in patients with glaucoma in a tertiary eye care centre in south India. - Subathra, G; Rajendrababu, Sharmila; Senthilkumar, Vijayalakshmi; Mani, Iswarya; Udayakumar, B; Subathra, G N; Rajendrababu, Sharmila R; Senthilkumar, Vijayalakshmi A (Indian Journal of Ophthalmology, 2021)
Purpose: COVID-19 pandemic has affected the healthcare system worldwide hindering the continuum of treatment of chronic disease patients. The objective of the study is to analyze the barriers encountered by the glaucoma patients for the follow-up visit and medication adherence during the pandemic.Methods: This cross-sectional study included glaucoma patients who did not attend the scheduled appointment from April 1, 2020 to July 31, 2020 in a tertiary eye care center (88.21%). Eligible patients of age >18 years and advised antiglaucoma medication in Madurai Zone were interviewed with validated questionnaire through telephonic call.Results: 363 patients answered the questionnaire through telephonic interview. 57.3% of the patients were found to be non-adherent to medication. The main barriers for glaucoma follow-up visit during the pandemic were lockdown restriction, transport problem, and financial difficulties. The top barriers for medication adherence were non availability of medication (54.81%), financial difficulties (30.29%), did not feel much improvement with eye drops (20.19%). On multiple regression analysis, longer distance to hospital, low socioeconomic status, more than one antiglaucoma medication use, lack of awareness of glaucoma, non-complaint before COVID-19 and stress due to the pandemic were found to be significant factors for medication non adherence.Conclusion: COVID-19 pandemic has emphasized the need for reformation in health care system for accessibility of medical care to patients in rural areas. Decentralization of health system to primary care level and utilization of teleophthalmology should be considered by health care planners in future.

A Randomized Trial to Improve Adherence to Follow-up Eye Examinations Among People With Glaucoma. - Leiby, Benjamin E.; Hegarty, Sarah E.; Tingting Zhan; Myers, Jonathan S.; Katz, L. Jay; Haller, Julia A.; Waisbourd, Michael; Burns, Christine; Divers, Meskerem; Molineaux, Jeanne; Henderer, Jeffrey; Brodowski, Charles; et al. (Preventing Chronic Disease, 2021)
Introduction: Appointment nonadherence is common among people with glaucoma, making it difficult for eye care providers to monitor glaucoma progression. Our objective was to determine whether the use of patient navigators, in conjunction with social worker support, could increase adherence to recommended follow-up eye appointments.Methods: A randomized, controlled trial evaluated the effectiveness of an intervention that used patient navigators and social workers to improve patient adherence to follow-up eye care compared with usual care. Participants with glaucoma and other eye diseases (N = 344) were identified at primary care clinics in community settings through telemedicine screening of imaging and then randomized to enhanced intervention (EI) or usual care (UC). Data on participants' visits with local ophthalmologists were collected for up to 3 years from randomization. Groups were compared for timely attendance at the first visit with the local ophthalmologist and adherence to recommended follow-up visits.Results: Timely attendance at the first visit was higher for EI than UC (74.4% vs 39.0%; average relative risk [aRR] = 1.85; 95% CI, 1.51-2.28; P < .001). Rates of adherence to recommended annual follow-up during year 1 were 18.6% in the EI group and 8.1% in the usual care group (aRR = 2.08; 95% CI, 1.14-3.76; P = .02). The aRR across years 2 and 3 was 3.92 (95% CI, 1.24-12.43; P = .02).Conclusion: An intervention using patient navigators and social workers doubled the rate of adherence to annual recommended follow-up eye care compared with usual care in community settings, and was effective at increasing connections with local ophthalmologists. Interventions to further improve long-term adherence are needed.

A Survey of Glaucoma Surgery Practice Patterns in the Veterans Health Administration. - Olivieri, Daniel J; Lynch, Mary G; Cockerham, Glenn C; Greenberg, Paul B (Military Medicine, 2020)
Introduction: Glaucoma surgical practice patterns are not well described in the United States (US). This study aims to evaluate the indications for and potential barriers to glaucoma surgery in the Veterans Health Administration (VHA).Materials and Methods: An anonymous 10-question survey using REDCap (Nashville, TN) software was sent by mail (with web link) and email to ophthalmology chiefs at the 86 academically affiliated Veterans Affairs Medical Centers (VAMCs). Academic-affiliated VAMCs were selected because of their patient range and role in ophthalmic education. Non-responders received two reminder e-mails and two phone calls; the survey was closed after 6 weeks. The data were analyzed using descriptive statistics.Results: The response rate was 45% (39/86). Most respondents (92%) worked in an integrated eye clinic with both ophthalmology and optometry services. Almost half of the respondents (49%; 19/39) believed that laser trabeculoplasty (LTP) was an option for initial glaucoma therapy. Noncompliance was a commonly reported indication for LTP (95%), tube shunt procedures (65%), micro-invasive glaucoma surgery (59%), and trabeculectomy (48.7%). One third of the respondents believed that there were delays in glaucoma care. The respondents noted that significant barriers in access to surgery included lack of transportation (69%), scheduling challenges (62%), and delayed referral (62%).Conclusion: This survey of glaucoma surgery practice patterns highlights the growing role of LTP and suggests that non-compliance and access remain significant barriers to glaucoma surgical care within the VHA.
Keywords: Trabeculectomy; Glaucoma -- Surgery; Veterans; United States; Ophthalmology; Arthritis Impact Measurement Scales

Randomized controlled trial of an education-based intervention to improve medication adherence: Design considerations in the medication adherence in glaucoma to improve care study. - Rosdahl, Jullia A; Hein, Aaron M; Bosworth, Hayden B; Woolson, Sandra; Olsen, Maren; Kirshner, Miriam; Hung, Anna; Muir, Kelly W (Clinical Trials, 2021)
Background: Glaucoma treatment requires patients to follow daily, often times complex, eye drop regimens, but adherence is poor for many patients, putting them at risk for irreversible vision loss. A comprehensive approach is needed to address the challenges in the self-management of glaucoma. The purpose of this study is to improve glaucoma medication adherence in Veterans with medically treated glaucoma using an education-based intervention. Methods/design: This study is a single-site randomized controlled trial enrolling 200 Veterans and their companions, if companions are involved in their care. It has two arms: an intervention group and a control group. Participants in the intervention group receive an educational session with a non-physician interventionist and are provided with an AdhereTech smart bottle with the reminder functions activated. The control group is designed as an attention control such that they have a session on general eye health and are provided with a smart bottle but without the reminder functions activated. The primary outcome is the proportion of prescribed doses taken on schedule over 6 months following randomization according to the smart bottle. Secondary outcomes include intensification of glaucoma treatment, cost of intervention delivery, and cost-effectiveness of the intervention over 12 months. Discussion: The education-based intervention that we are testing is comprehensive in scope, to encompass a variety of barriers to adherence that glaucoma patients encounter, but personalized to address issues facing individual patients. Particular attention was given to feasibility in the real-world setting, as the high throughput of patients and lack of reimbursement for educational encounters in ophthalmology would limit implementation of a resource-intensive intervention.
Keywords: Medication Compliance; Glaucoma -- Therapy; Patient Education; Veterans; Health Education; Quality Improvement; Self Care; Randomized Controlled Trials; Treatment Outcomes; Ocular Hypertension; Descriptive Statistics; Confidence Intervals; Odds Ratio; Human

Adherence and Persistence with First-Line Therapy and Compliance with Glaucoma Guidelines Using Japanese Health Care/Pharmacy Claims Database. - Shirai, Chikako; Matsuoka, Nobushige; Nakazawa, Toru (Journal of Ocular Pharmacology & Therapeutics, 2021)
Purpose: This study evaluated Japanese patients' adherence to first-line therapy and physicians' compliance with the guidelines (GLs) for glaucoma in daily practice. Methods: This retrospective, noninterventional cohort study used a Japanese health care/pharmacy claims database from 2011 to 2016. We compared adherence based on the primary outcomes assessed as proportion of days covered (PDC) and persistence between patients who received first-line monotherapy followed by second-line fixed-combination therapy (GL-compliant cohort) and those who received first-line fixed-combination therapy (GL-noncompliant cohort). Furthermore, we explored treatment patterns, glaucoma consultation, and key factors associated with GL noncompliance. Results: Among 11,666 patients who received first-line therapy, 1,183 (10.1%) and 542 (4.6%) were in the GL-compliant and GL-noncompliant cohorts, respectively. Prostaglandin (70.7%) and subsequent prostaglandin/β blocker (BB) (20.9%) within 12 months were most used by the GL-compliant cohort. Prostaglandin/BB (48.9%) and carbonic anhydrase inhibitor/BB (51.1%) were prescribed for the GL-noncompliant cohort. The mean PDC [standard deviation (SD)], persistence rate (95% confidence interval), and consultation (SD) over 12 months were 60.9% (34.0), 16.0% (14.0-18.1), and 5.23 (3.21) times, respectively, in the GL-compliant cohort and 59.7% (35.8), 22.0% (18.6-25.5), and 4.76 (3.19) times, respectively, in the GL-noncompliant cohort. No significant differences were observed between the 2 cohorts. No clinically relevant factor associated with GL noncompliance was found. Conclusions: Around 5% of patients were prescribed a fixed-combination eye drop as first-line therapy not in accordance with GLs. The similarity of adherence and persistence between the 2 cohorts indicates that first-line fixed-combination therapy could be considered for glaucoma treatment.

An exploratory study of compliance to anti-glaucoma medications among literate primary glaucoma patients at an urban tertiary eye care center in South India. - Ramesh, Prasanna; Parthasarathi, Sathyan; John, Rajesh; Ramesh, Prasanna Venkatesh; John, Rajesh Kumar (Indian Journal of Ophthalmology, 2021)
Purpose: To understand the factors that explain compliance to anti-glaucoma medication (AGM) in terms of application,purchase, stocking and compliance behaviour.Methods: This was a cross-sectional study conducted in the outpatient department of an urban tertiary eye care center in South India. Interviews were completed with consenting, consecutive, literate primary glaucoma patients. The components of the questionnaire included duration, application, purchase, stocking and caregiver's role. Self-reported compliance in medication taking was tested for association with rest of the components by Chi-square test and discriminant analysis.Results: A total of 101 patients, aged 34-87 years, were interviewed. Majority (64.4%) were on AGM for more than two years. Early purchase was reported among 44.3% and stocking among 41.2%. Cost was high for income among 28.7%. Majority (91.1%) of them were not aware of side-effects. Fear of blindness was the major factor (68.1%) encouraging regular usage. Half (50.5%) of the patients though, still reported missing medication in the past month. Major reasons cited were relative priority (45.1%) and forgetfulness (35.3%). Self-reported compliance was not different by demographic variables or with responses to questions regarding duration (P = 0.070), application (0.825), time of purchase (0.272), stocking (0.598), and cost perception (0.415).Conclusion: Self-reporting of AGM compliance behaviour did not reflect with responses regarding application, purchase, stocking behaviour or cost perception. Awareness and knowledge of the above factors, with an aim of improving compliance by regulating counselling for even literate patients using AGM is called for.
Keywords: Glaucoma -- Epidemiology; Glaucoma -- Drug Therapy; Middle Age; Adult; Medication Compliance; Aged; Aged, 80 and Over; India; Cross Sectional Studies; Caregiver Strain Index

Preserved Versus Preservative-Free Latanoprost for the Treatment of Glaucoma and Ocular Hypertension: A Post Hoc Pooled Analysis. - Harasymowycz, Paul; Hutnik, Cindy; Rouland, Jean-François; Negrete, Francisco J. Muñoz; Economou, Mario A.; Denis, Philippe; Baudouin, Christophe (Advances in Therapy, 2021)
Introduction: To compare the tolerability and efficacy of a preservative-containing latanoprost (PCL) to a preservative-free formulation of latanoprost (PFL) in patients with open-angle glaucoma or ocular hypertension.Methods: A pooled analysis was performed of data from five published studies. The primary outcome was tolerability as evaluated by the severity of hyperemia. The secondary objectives were patient tolerance based on a composite ocular surface disease (OSD) score arising from ocular signs and symptoms, patient and investigator satisfaction, and a comparison of IOP-lowering efficacy.Results: There were three randomized controlled trials and two observational studies included in the analysis. Conjunctival hyperemia improved significantly in 25.6% (388) of patients switched to the PFL group versus 11.7% (117) of patients switched to the PCL group (p < 0.001). PFL was two times superior to PCL in reducing ocular hyperemia (odds ratio = 1.96; p < 0.001). The mean OSD composite score decreased by 32.2% in patients switched to the PFL group and 14.1% in the PCL group (p < 0.001). At 3 months, the mean IOP was similar between groups (p = 0.312).Conclusion: This post hoc pooled analysis confirmed the findings of the individual studies that PFL is as efficacious at reducing IOP as PCL but better tolerated. After switching to PFL, there was twice the improvement in the OSD composite score. PFL was twice as effective at reducing ocular hyperemia and other ocular signs. These findings suggest that PFL has features that may improve patient compliance, thereby potentially improving the IOP-lowering efficacy on a long-term basis.

Comparison of the Intraocular Pressure-Lowering Effect and Safety of Preservative-Free And Preservative-Containing Brimonidine/Timolol Fixed-Combination Ophthalmic Solutions in Patients with Open-Angle Glaucoma. - Kim, Joon Mo; Kim, Tae-Woo; Park, Sang-Woo; Park, Hae-Young Lopilly; Hwang, Young Hoon; Jeoung, Jin Wook; Kim, Chan Yun (Seminars in Ophthalmology, 2021)
Purpose: To compare the therapeutic efficacy and safety of newly developed preservative-free (PF) brimonidine/timolol fixed-combination (BTFC) ophthalmic solutions and a preservative-containing (PC) BTFC ophthalmic solution in patients with open-angle glaucoma.Methods: This study was conducted as a multicenter, randomized, open-label, parallel-group clinical trial to evaluate the efficacy and safety of PF BTFC as compared with PC BTFC in adult patients (aged ≥ 19 years) with open-angle glaucoma (OAG) and ocular hypertension (OHT). A total of the 106 patients were enrolled, with 53 patients each randomized to the two treatment groups and included in the analysis of the safety set (SS).After a washout period, patients with an IOP below 35 mmHg at 9 a.m. were enrolled. After a full ophthalmic and glaucoma examination, a total of 106 OAG and OHT patients were randomized to the PF group or PC group.All subjects were examined 4 and 12 weeks after first administration. At each follow-up visit, IOP was measured at 9 a.m. and 11 a.m. and the efficacy, safety, and compliance were evaluated. Throughout the study, all adverse events were recorded and monitored by the investigators.Results The mean IOP changes from baseline to 12 weeks at 11:00 a.m. were -3.45 ± 2.53 mmHg in the PF group and -3.65 ± 2.76 mmHg in the PC group (p < .0001 for both). The difference in mean IOP change between the two groups was 0.20 ± 2.65 mmHg, which was not significantly different. The proportion of patients with IOP reductions of ≥ 15% and ≥ 20% and IOP at all-time points in the PF group were not significantly different when compared with in the PC group. There were no specific differences between the two groups regarding the incidence of adverse events.Conclusions PF BTFC ophthalmic solution shows a similar efficacy and safety profile to that of PC BTFC.

New considerations for the clinical efficacy of old and new topical glaucoma medications. - MacIver, Sarah; Stout, Nicole; Ricci, Olivia (Clinical & Experimental Optometry, 2021)
Glaucoma is the most common form of irreversible blindness in the world. Lowering intraocular pressure (IOP) remains the only clinically established method of treatment to slow the progression of glaucoma. Primary open angle glaucoma is a disease of the optic nerve head and often is associated with changes to the trabecular meshwork that cause a reduction to aqueous humour outflow and an increase in intraocular pressure. Until recently, topical IOP lowering medication has been limited to the mechanisms of action of decreasing aqueous production and/or redirecting outflow to the unconventional uveoscleral outflow pathway. Both of these mechanisms neglect to treat or act on tissue that becomes altered from glaucoma. Latanoprostene-bunod 0.024%, a nitric-oxide donating prostanoid, netarsudil 0.02%, a potent Rho-associated protein kinase (ROCK) inhibitor and norepinephrine transporter inhibitor, and a once daily dosed fixed combination medication with netarsudil 0.02% and latanoprost 0.005% have recently come on the market. This paper will discuss and review the limitations to traditional IOP lowering glaucoma medications as well as the mechanism of actions and clinical efficacy of the new glaucoma medications. It will also discuss how the new class of glaucoma medications might help to overcome some known limitations in treatment and barriers to patient adherence.

Health care cost and benefits of artificial intelligence-assisted population-based glaucoma screening for the elderly in remote areas of China: a cost-offset analysis. - Xiao, Xuan; Xue, Long; Ye, Lin; Li, Hongzheng; He, Yunzhen (BMC Public Health, 2021)
Background: Population-based screening was essential for glaucoma management. Although various studies have investigated the cost-effectiveness of glaucoma screening, policymakers facing with uncontrollably growing total health expenses were deeply concerned about the potential financial consequences of glaucoma screening. This present study was aimed to explore the impact of glaucoma screening with artificial intelligence (AI) automated diagnosis from a budgetary standpoint in Changjiang county, China.Methods: A Markov model based on health care system's perspective was adapted from previously published studies to predict disease progression and healthcare costs. A cohort of 19,395 individuals aged 65 and above were simulated over a 15-year timeframe. Fur illustrative purpose, we only considered primary angle-closure glaucoma (PACG) in this study. Prevalence, disease progression risks between stages, compliance rates were obtained from publish studies. We did a meta-analysis to estimate diagnostic performance of AI automated diagnosis system from fundus image. Screening costs were provided by the Changjiang screening programme, whereas treatment costs were derived from electronic medical records from two county hospitals. Main outcomes included the number of PACG patients and health care costs. Cost-offset analysis was employed to compare projected health outcomes and medical care costs under the screening with what they would have been without screening. One-way sensitivity analysis was conducted to quantify uncertainties around model results.Results: Among people aged 65 and above in Changjiang county, it was predicted that there were 1940 PACG patients under the AI-assisted screening scenario, compared with 2104 patients without screening in 15 years' time. Specifically, the screening would reduce patients with primary angle closure suspect by 7.7%, primary angle closure by 8.8%, PACG by 16.7%, and visual blindness by 33.3%. Due to early diagnosis and treatment under the screening, healthcare costs surged dramatically to $107,761.4 dollar in the first year and then were constantly declining over time, while without screening costs grew from $14,759.8 in the second year until peaking at $17,900.9 in the 9th year. However, cost-offset analysis revealed that additional healthcare costs resulted from the screening could not be offset by decreased disease progression. The 5-, 10-, and 15-year accumulated incremental costs of screening versus no screening were estimated to be $396,362.8, $424,907.9, and $434,903.2, respectively. As a result, the incremental cost per PACG of any stages prevented was $1464.3.Conclusions: This study represented the first attempt to address decision-maker's budgetary concerns when adopting glaucoma screening by developing a Markov prediction model to project health outcomes and costs. Population screening combined with AI automated diagnosis for PACG in China were able to reduce disease progression risks. However, the excess costs of screening could never be offset by reduction in disease progression. Further studies examining the cost-effectiveness or cost-utility of AI-assisted glaucoma screening were needed.
Keywords: Glaucoma, Angle-Closure; Glaucoma -- Diagnosis; Aged; Cost Benefit Analysis; China; Health Care Costs; Artificial Intelligence; Human; Comparative Studies; Multicenter Studies; Evaluation Research; Validation Studies; Impact of Events Scale

Assessment of medication therapy adherence in glaucoma: scoping review. - Rosu, Amalia Mihaela; Coelho, André; Camacho, Pedro (Expert Review of Ophthalmology, 2021)
Introduction: Glaucoma is an asymptomatic disease, which can cause irreversible blindness, with a worldwide prevalence around 64.3 million people. Adherence to glaucoma treatment is crucial to control the disease and to prevent its complications. Low medication adherence results in a visual loss, which can leads to irreversible blindness. In this sense it is important to know and evaluate adherence to pharmacological therapy among patients with glaucoma. Areas covered: A scoping review was conducted, according to the methodology proposed by Arksey and O'Malley. The databases used were Medical Literature Analysis and Retrieval System Online (MEDLINE) and the Biblioteca do Conhecimento Online (B-on). Our research used as primary sources articles in Portuguese and English. Expert opinion: The identified adherence rates were very different, and the conditions how under medication adherence was assessed were highly variable. These conditions impossibilities a proper comparative study. Further efforts are needed to increase health literacy and thus identify and support patients with low medication adherence rates. It is important that health care personnel could improve patients' knowledge about the importance of medication adherence, glaucoma disease, and the consequences that result from the lack of treatment.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance -- Evaluation; Human; Systematic Review; Medline; Support, Psychosocial

Chronic Open Angle Glaucoma Guidelines: A UK perspective. - Stanford, Penelope (Insight: The Journal of the American Society of Ophthalmic Registered Nurses, 2020)
Keywords: Glaucoma -- Diagnosis -- United Kingdom; Glaucoma -- Therapy; Practice Guidelines; National Institute for Health and Care Excellence; Ophthalmic Nursing; Nursing Role; Education, Continuing (Credit); United Kingdom; Health Services Accessibility; Patient Education; Intraocular Pressure; Tonometry; Ophthalmic Solutions -- Therapeutic Use; Glaucoma -- Drug Therapy; Patient Centered Care; Support, Psychosocial; Medication Compliance

Comparison of adherence between fixed and unfixed topical combination glaucoma therapies using Japanese healthcare/pharmacy claims database: a retrospective non-interventional cohort study. - Shirai, Chikako; Matsuoka, Nobushige; Nakazawa, Toru (BMC Ophthalmology, 2021)
Background: Adherence to chronic therapies is crucial to prevent the progression of disease, such as glaucoma. However, only a limited number of studies have investigated them using real-world data in Japan. This study aimed to evaluate Japanese patients' adherence to fixed- and unfixed-combination eye drops as a second-line therapy for glaucoma in real-world practice.Methods: This retrospective, non-interventional cohort study utilized a commercially available Japanese healthcare database (MinaCare database). Medical/pharmacy claims data were collected from 2011 to 2016. The primary endpoint was adherence to medications, assessed by proportion of days covered (PDC) with medication during a 12-month post-index period. Meanwhile, the secondary endpoints included the persistence rate.Results: A total of 738 patients were included in this study: 309 and 329 in the fixed- and unfixed-combination cohorts, respectively. Prostaglandin analog (PG)/β-blocker (BB) was most commonly claimed in 241/309 (78.0%) patients in the fixed-combination cohort. In the unfixed-combination cohort, PG and BB were claimed in 130/329 (39.5%) patients, whereas PG and α2-agonist were claimed in 87/329 (26.4%) patients. Patients were more adherent to the fixed-combination than the unfixed-combinations (mean PDCs [SD], 79.1% [32.1] vs. 62.2% [38.0]; P < 0.0001). The proportion of patients with good adherence (PDC ≥ 80%) was also higher in the fixed-combination cohort (69.6%) than in the unfixed-combination cohort (48.6%) (P < 0.0001). During the 12-month post-index period, the persistence rate was higher in the fixed-combination cohort than in the unfixed-combination cohort (47.6% [95% confidence intervals (CI): 41.9-53.0] vs. 24.9% [95% CI: 20.4-29.7], P < 0.0001).Conclusions: Japanese patients with glaucoma preferred the fixed-combination therapies over the unfixed-combination therapies. Hence, fixed-combination therapies would contribute to the improvement of adherence.
Keywords: Pharmacy and Pharmacology; Glaucoma -- Drug Therapy; Japan; Antihypertensive Agents -- Therapeutic Use; Retrospective Design; Prospective Studies; Medication Compliance

Glaucoma medications: issues with adherence in a tertiary hospital in Nigeria. - ONWUBIKO, STELLA NGOZI; NWACHUKWU, NKIRU ZUADA; EZE, BONIFACE IKENNA (Family Medicine & Primary Care Review, 2020)
Background. Patient adherence with glaucoma medical therapy remains a global challenge. Objectives. To determine the prevalence of non-adherence and identify the determinants and deterrents to glaucoma medications in Enugu, southeast Nigeria. Material and methods. This study adopted a cross-sectional, descriptive, hospital-based survey involving 114 glaucoma patients on topical medications. They were recruited from the ophthalmic clinic of the University of Nigeria Teaching Hospital, Enugu. Information on their socio-demographic characteristics, clinical profile and issues of adherence with glaucoma medications were collected using a pre-tested, close-ended, interviewer–administered questionnaire. The data collected was analysed using SPSS version 21. Bivariate analysis was done to identify the associations of different factors of adherence with glaucoma medications. The level of significance was set at p < 0.05. Results. The participants were comprised of 58 males (50.9%) and 56 females (49.1%), with a mean age of 60.0 ± 14.8 years. Most were mainly on two or less glaucoma medications (92 (80.7%)) and were diagnosed with glaucoma for less than 5 years (73 (64.0%)). 42 (36.8%) participants were non-adherent with their glaucoma medications. Assisted administration of glaucoma medication was the most important determinant of non-adherence to medication. Gender, good/fair vision, distance from the pharmacy, knowledge of the disease and educational status also contributed. Cost was the major deterrent (59 (51.7%)) to adherence with glaucoma medications. Conclusions. The prevalence of non-adherence with medications among glaucoma patients in Enugu was high. Assisted drug administration was the most significant determinant, while the cost of drugs was a major deterrent to non-adherence with glaucoma medication.
Keywords: Glaucoma -- Drug Therapy -- Nigeria; Medication Compliance -- Nigeria; Tertiary Health Care -- Nigeria; Human; Nigeria; Prevalence; Cross Sectional Studies; Descriptive Research; Questionnaires; Data Analysis Software; Bivariate Statistics; Male; Female; Middle Age; Aged

New strategies for the management of ocular surface disease in glaucoma patients. - Voicu, Laura; Salim, Sarwat (Current Opinion in Ophthalmology, 2021)
Purpose Of Review: Glaucoma patients commonly suffer from ocular surface disease (OSD). As treatment strategies, medications and devices for the treatment of OSD as well as glaucoma surgical approaches evolve rapidly, it is important to consider their application to these patients.Recent Findings: OSD in glaucoma patients may lead to reduced reliability of diagnostic tests, decreased medication compliance, poor surgical outcomes, and overall decreased quality of life. Chronic use of topical glaucoma medications has been linked to the development of limbal stem cell deficiency, and the role of preservatives in OSD continues to be demonstrated. Preservative free glaucoma medications as well as new anti-inflammatory agents for the treatment of OSD are now available. Omega-3 fatty acid supplementation and punctal plugs have been shown to benefit glaucoma patients with OSD. Drop burden may be reduced through the use of the new sustained-release delivery systems, selective laser trabeculoplasty, and minimally invasive glaucoma surgery.Summary: There are multiple emerging strategies for managing OSD that may be applied to patients with glaucoma. With continued research and clinical experiences, we hope to better understand the multifaceted relationship between glaucoma and OSD and develop evidence-based algorithms for the management of these complex patients.
Keywords: Eyelid Diseases -- Therapy; Corneal Diseases -- Therapy; Lacrimal Apparatus Diseases -- Therapy; Dry Eye Syndromes -- Therapy; Conjunctival Diseases -- Therapy; Glaucoma -- Complications; Antiinflammatory Agents -- Therapeutic Use; Antihypertensive Agents -- Therapeutic Use; Glaucoma -- Drug Therapy; Quality of Life; Human; Pharmaceutical Additives -- Therapeutic Use; Intraocular Pressure -- Physiology; Ferrans and Powers Quality of Life Index; Scales

Visual demand, visual ability and vision standards for hairdressers - An observational study from Chennai, Tamil Nadu. - Janani, Suresh; Dhanalakshmi, Sankar; Rashima, Asokan; Krishnakumar, Ramani; Santanam, P; Santanam, P P (Indian Journal of Ophthalmology, 2021)
Purpose: The aim of this study was to create vision standards for various tasks performed by hairdressers and to assess the spectacle compliance and its impact at work.Methods: The observational cross-sectional study enrolled hairdressers in and around Chennai, Tamil Nadu. It was done in three phases: (i) Job profiling from visual task analysis, creating vision standards for various hairdressing tasks and arriving at test protocols; (ii) Comprehensive eye examination, and (iii) Assessment of spectacle compliance and its impact on work. Descriptive analysis using Microsoft Excel and SPSS (IBM SPSS Statistics Version 21.0) was performed.Results: There were 305 participants with a mean age of 48 (SD ± 12) years. The visual acuity demand was found to be 6/18 and N15, for distance and near, respectively. Appropriate spectacles were prescribed for 203 (67%) hairdressers. Even with the best possible refractive correction, a few hairdressers did not meet the distance (13) and near (11) visual acuity standard. In all, 54 hairdressers were referred for further examination to a tertiary eye care center for lenticular changes, retinal abnormalities, and glaucoma screening. Among the subjects who were dispensed with spectacles, 181 (86%) were available for telephonic spectacle compliance assessment, and 164 (90%) were compliant with spectacle usage at work. Improved visual ability was reported by 133 (81%) hairdressers at work.Conclusion: This study provides vision standards for hairdressers. From the visual task analysis, hairdressing tasks were found to be visually demanding and hazardous. The study emphasizes that providing appropriate spectacle correction showed a clinically evident positive impact at work.
Keywords: Refractive Errors -- Therapy; Refractive Errors -- Diagnosis; Refractive Errors -- Epidemiology; Visual Acuity; Cross Sectional Studies; Eyeglasses; Middle Age; India; Impact of Events Scale; Job Descriptive Index; Scales

Presentation of Infectious Keratitis to ED during COVID-19 Lockdown. - Power, Barry; Donnelly, Aaron; Murphy, Conor; Fulcher, Timothy; Power, William (Journal of Ophthalmology, 2021)
Objectives. To compare presentation of infectious keratitis during COVID-19 lockdown with previous years, assess relative severity, and compare outcomes between COVID-19 and pre-COVID-19 era groups. Methods. Acute presentations of infectious keratitis during a strict government-mandated COVID-19 lockdown period were analysed retrospectively (March–May 2020). Data were compared with the same periods in 2018-2019. The clinical notes of patients undergoing corneal scrapes were reviewed, and data were collected on treatment, culture growth, surgical interventions, visual outcomes, admission rates, and risk factors. Results. There were 37% fewer presentations of infectious keratitis to the ED in 2020 (N = 29, 47, and 45, respectively). Risk factor profiles and microbial data were similar across all periods. Admission rates and use of fortified antibiotics were lower in 2020. COVID-19 era cases recovered less vision (LogMAR 0.26, 0.67, and 0.45, respectively; p = 0.04) and were more likely to require surgical intervention (10%, 4%, and 2%, respectively; OR 3.4 (CI 0.7–17.9, p = 0.1)). Conclusion. A concerning fall in presentations of infectious keratitis to ED during the pandemic lockdown was observed. Though societal behaviour changed during the lockdown, our data suggest it is unlikely that the incidence of infectious keratitis fell significantly. It is unclear how and where these patients were treated. We postulate that lower levels of visual recovery and higher rates of surgical intervention may have been caused by delays in accessing care. To minimise avoidable ocular morbidity as COVID-19 resurges, we must communicate clearly with patients and health professionals on how to access available emergency eye care services.
Keywords: COVID-19 Pandemic; Stay-at-Home Orders; Keratitis -- Physiopathology; Keratitis -- Symptoms; Emergency Service; Outcomes (Health Care); Human; Severity of Illness; Comparative Studies; Antibiotics -- Therapeutic Use; Odds Ratio; Confidence Intervals; Retrospective Design; Vision; Patient Admission; Keratitis -- Risk Factors; Risk Assessment; Health Services Accessibility; Keratitis -- Epidemiology; Incidence; Sensitivity and Specificity; Visual Acuity; Keratitis -- Drug Therapy; Keratitis -- Surgery; Kruskal-Wallis Test

Glaucoma in Adults-Screening, Diagnosis, and Management: A Review. - Stein, Joshua D.; Khawaja, Anthony P.; Weizer, Jennifer S. (JAMA: Journal of the American Medical Association, 2021)
Importance: Glaucoma is the most common cause of irreversible blindness worldwide. Many patients with glaucoma are asymptomatic early in the disease course. Primary care clinicians should know which patients to refer to an eye care professional for a complete eye examination to check for signs of glaucoma and to determine what systemic conditions or medications can increase a patient's risk of glaucoma. Open-angle and narrow-angle forms of glaucoma are reviewed, including a description of the pathophysiology, risk factors, screening, disease monitoring, and treatment options.Observations: Glaucoma is a chronic progressive optic neuropathy, characterized by damage to the optic nerve and retinal nerve fiber layer, that can lead to permanent loss of peripheral or central vision. Intraocular pressure is the only known modifiable risk factor. Other important risk factors include older age, nonwhite race, and a family history of glaucoma. Several systemic medical conditions and medications including corticosteroids, anticholinergics, certain antidepressants, and topiramate may predispose patients to glaucoma. There are 2 broad categories of glaucoma, open-angle and angle-closure glaucoma. Diagnostic testing to assess for glaucoma and to monitor for disease progression includes measurement of intraocular pressure, perimetry, and optical coherence tomography. Treatment of glaucoma involves lowering intraocular pressure. This can be achieved with various classes of glaucoma medications as well as laser and incisional surgical procedures.Conclusions and Relevance: Vision loss from glaucoma can be minimized by recognizing systemic conditions and medications that increase a patient's risk of glaucoma and referring high-risk patients for a complete ophthalmologic examination. Clinicians should ensure that patients remain adherent with taking glaucoma medications and should monitor for adverse events from medical or surgical interventions used to treat glaucoma.
Keywords: Glaucoma -- Physiopathology; Glaucoma -- Therapy; Intraocular Pressure; Glaucoma -- Diagnosis; Glaucoma -- Complications; Health Screening; Human; Disease Progression; Prognosis; Vision Disorders -- Etiology; Vision Disorders -- Prevention and Control; Adult; Risk Factors; Eye -- Anatomy and Histology; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

Impact of a Social Worker in a Glaucoma Eye Care Service: A Prospective Study. - Hark, Lisa A; Madhava, Malika; Radakrishnan, Anjithaa; Anderson-Quiñones, Catherine; Robinson, Debra; Adeghate, Jennifer; Silva, Stephen; Zhan, Tingting; Adepoju, Tomilade; Dave, Yatee; Fudemberg, Scott J (Health & Social Work, 2019)
The purpose of this study was to evaluate the effects of a six-month social worker intervention for participants with a glaucoma-related diagnosis in an urban ophthalmic setting (N = 40). The social worker assessed common barriers to eye care, helping participants with transportation, access to low-vision resources, and supportive counseling. The Distress Thermometer, Patient Health Questionnaire–9, and a satisfaction survey were administered to determine the effect of the social worker intervention and participants' overall impressions of the social worker. The most common barrier to eye care was emotional distress (77.5 percent). There was a significant decrease in the number of participants with symptoms of major and moderate depression. Fourteen participants experienced a clinically relevant decrease in depression, 37 participants felt that the social worker's support addressed their issues, and 29 participants thought it helped them in managing their glaucoma. This study provides evidence that a social work intervention may improve care coordination and management of individuals afflicted with vision impairment due to glaucoma and other ocular diseases.
Keywords: Glaucoma -- Diagnosis; Eye Care; Health Services Accessibility; Social Workers; Patient Satisfaction -- Evaluation; Human; Urban Areas; Ophthalmology; Intervention Trials -- Evaluation; Transportation; Counseling; Clinical Assessment Tools; Questionnaires; Patient Attitudes -- Evaluation; Adult; Middle Age; Aged; Aged, 80 and Over; Male; Female; Prospective Studies; Pennsylvania; Data Analysis, Statistical; Wilcoxon Rank Sum Test; Summated Rating Scaling; Logistic Regression; Data Analysis Software; Descriptive Statistics

Identification and molecular characterization of Subramaniula asteroides causing human fungal keratitis: a case report. - Cultrera, Rosario; Torelli, Riccardo; Sarnicola, Caterina; Segala, Daniela; Mengoli, Andrea; Chiaretto, Giuseppina; Perri, Paolo; Sanguinetti, Maurizio (BMC Infectious Diseases, 2021)
Background: Keratitis due to by filamentous fungi are not easy to diagnose thus causing a delay in correct therapy. There are many descriptions of keratitis due to Candida, Fusarium and Aspergillus genera. Subramaniula genus has only recently been reported to cause human infections and there are few descriptions of eye infections due to this filamentous fungus. Diagnosis of fungal keratitis is usually based on microscopic and cultural techniques of samples obtained by corneal swabbing or scraping. Considering the amount of time required to obtain culture results it is wise to use other diagnostic methods, such as molecular analyses. Therapeutic options against these fungi are limited by low tissue penetration in the eye due to ocular barriers. We describe the first case of S. asteroides human keratitis treated with isavuconazole.Case Presentation: We describe a rare case of fungal keratitis unresponsive to antimicrobial treatment in a 65-year-old male patient without a history of diabetes or immunological diseases. He reported that the onset of symptoms occurred during a long holiday in Cape Verde Island. Initial treatment with topical antibiotics associated to steroids were ineffective, allowing a slow clinical progression of disease to corneal perforation. On admission in our Hospital, slit-lamp examination of the left eye showed conjunctival congestion and hyperemia, a large inferior corneal ulceration with brown pigment, corneal edema, about 3 mm of hypopyon and irido-lenticular synechiae. The slow clinical progression of the disease to corneal perforation and the aspect of the ulcer were consistent with a mycotic etiology. Molecular methods used on fungal colonies isolated by Sabouraud's dextrose agar cultures allowed the identification of Subramaniula asteroids from corneal scraping. Antimicrobial test showed a good susceptibility of this filamentous fungus to voriconazole and isavuconazole. Moreover, this fungal keratitis was successfully treated with isavuconazole, without side effects, observing a progressive clinical improvement.Conclusions: Molecular methods may be useful for the identification of filamentous fungal keratitis on scraping samples thus shortening the time of diagnosis. Systemic therapy by isavuconazole could be useful to treat the filamentous fungal keratitis, reducing the possible adverse effects due to the use of voriconazole by systemic administration.
Keywords: Corneal Ulcer -- Diagnosis; Fungi; Eye Infections, Fungal -- Diagnosis; Pyridines -- Therapeutic Use; Heterocyclic Compounds -- Therapeutic Use; Diagnosis, Differential; Corneal Ulcer -- Microbiology; Corneal Ulcer -- Drug Therapy; Antifungal Agents -- Therapeutic Use; Heterocyclic Compounds -- Administration and Dosage; Antifungal Agents -- Administration and Dosage; Organic Chemicals -- Therapeutic Use; Aged; Ophthalmic Solutions; Organic Chemicals -- Administration and Dosage; Eye Infections, Fungal -- Drug Therapy; Eye Infections, Fungal -- Microbiology; Male; Pyridines -- Administration and Dosage; Scales

American Academy of Optometry Microbial Keratitis Think Tank. - Szczotka-Flynn, Loretta B.; Shovlin, Joseph P.; Schnider, Cristina M.; Caffery, Barbara E.; Alfonso, Eduardo C.; Carnt, Nicole A.; Chalmers, Robin L.; Collier, Sarah; Jacobs, Deborah S.; Joslin, Charlotte E.; Kroken, Abby R.; Lakkis, Carol; et al. (Optometry & Vision Science, 2021)
Significance: Think Tank 2019 affirmed that the rate of infection associated with contact lenses has not changed in several decades. Also, there is a trend toward more serious infections associated with Acanthamoeba and fungi. The growing use of contact lenses in children demands our attention with surveillance and case-control studies.Purpose: The American Academy of Optometry (AAO) gathered researchers and key opinion leaders from around the world to discuss contact lens-associated microbial keratitis at the 2019 AAO Annual Meeting.Methods: Experts presented within four sessions. Session 1 covered the epidemiology of microbial keratitis, pathogenesis of Pseudomonas aeruginosa, and the role of lens care systems and storage cases in corneal disease. Session 2 covered nonbacterial forms of keratitis in contact lens wearers. Session 3 covered future needs, challenges, and research questions in relation to microbial keratitis in youth and myopia control, microbiome, antimicrobial surfaces, and genetic susceptibility. Session 4 covered compliance and communication imperatives.Results: The absolute rate of microbial keratitis has remained very consistent for three decades despite new technologies, and extended wear significantly increases the risk. Improved oxygen delivery afforded by silicone hydrogel lenses has not impacted the rates, and although the introduction of daily disposable lenses has minimized the risk of severe disease, there is no consistent evidence that they have altered the overall rate of microbial keratitis. Overnight orthokeratology lenses may increase the risk of microbial keratitis, especially secondary to Acanthamoeba, in children. Compliance remains a concern and a significant risk factor for disease. New insights into host microbiome and genetic susceptibility may uncover new theories. More studies such as case-control designs suited for rare diseases and registries are needed.Conclusions: The first annual AAO Think Tank acknowledged that the risk of microbial keratitis has not decreased over decades, despite innovation. Important questions and research directions remain.

Motivational interviewing or reminders for glaucoma medication adherence: Results of a multi-site randomised controlled trial. - Cook, Paul F.; Schmiege, Sarah J.; Mansberger, Steven L.; Sheppler, Christina; Kammer, Jeffrey; Fitzgerald, Timothy; Kahook, Malik Y. (Psychology & Health, 2017)
Objective:Nonadherence reduces glaucoma treatment efficacy. Motivational interviewing (MI) is a well-studied adherence intervention, but has not been tested in glaucoma. Reminder interventions also may improve adherence. Design:201 patients with glaucoma or ocular hypertension were urn-randomised to receive MI delivered by an ophthalmic technician (OT), usual care or a minimal behavioural intervention (reminder calls). Main Outcome Measures:Outcomes included electronic monitoring with Medication Event Monitoring System (MEMS) bottles, two self-report adherence measures, patient satisfaction and clinical outcomes. Multilevel modelling was used to test differences in MEMS results by group over time; ANCOVA was used to compare groups on other measures. Results:Reminder calls increased adherence compared to usual care based on MEMS,p = .005, and self-report,p = .04. MI had a nonsignificant effect but produced higher satisfaction than reminder calls,p = .007. Treatment fidelity was high on most measures, with observable differences in behaviour between groups. All groups had high baseline adherence that limited opportunities for change. Conclusion:Reminder calls, but not MI, led to better adherence than usual care. Although a large literature supports MI, reminder calls might be a cost-effective intervention for patients with high baseline adherence. Replication is needed with less adherent participants.
Keywords: Motivational Interviewing -- Methods; Glaucoma -- Drug Therapy; Medication Compliance; Reminder Systems; Human; Randomized Controlled Trials; Self Report; Patient Satisfaction; Treatment Outcomes; Analysis of Covariance; P-Value; Colorado; Oregon; Tennessee; Aged; Ocular Hypertension -- Drug Therapy; Male; Female; Chi Square Test; Comorbidity; Random Assignment; Prospective Studies; Drug Monitoring; Questionnaires; Aged, 80 and Over; Summated Rating Scaling; Coefficient Alpha; Regression; Variable; Pretest-Posttest Design; Power Analysis; Effect Size; Intraclass Correlation Coefficient; Coding; Checklists; Exploratory Research; Funding Source

Corneal Stiffness and Collagen Cross-Linking Proteins in Glaucoma: Potential for Novel Therapeutic Strategy. - Rahman, Najiha; O'Neill, Evelyn; Irnaten, Mustapha; Wallace, Deborah; O'Brien, Colm (Journal of Ocular Pharmacology & Therapeutics, 2020)
Biomechanical properties of the cornea have recently emerged as clinically useful in risk assessment of diagnosing glaucoma and predicting disease progression. Corneal hysteresis (CH) is a dynamic tool, which measures viscoelasticity of the cornea. It represents the overall deformability of the cornea, and reduces significantly with age. Low CH has also been associated with optic nerve damage and progression of visual field loss in glaucoma. The extracellular matrix (ECM) constituents of the cornea, trabecular meshwork (TM), sclera, and lamina cribrosa (LC) are similar, as they are predominantly made of fibrillar collagen. This suggests that biomechanical changes in the cornea may also reflect optic nerve compliance in glaucomatous optic neuropathy, and in the known increase of TM tissue stiffness in glaucoma. Increased collagen cross-linking contributes to tissue stiffening throughout the body, which is observed in normal aging and occurs at an accelerated rate in systemic conditions such as fibrotic and cardiovascular diseases, cancer, and glaucoma. We reviewed 3 ECM cross-linking proteins that may have a potential role in the disease process of increased tissue stiffness in glaucoma, including lysyl oxidase (LOX)/lysyl oxidase-like 1 (LOXL1), tissue transglutaminase (TG2), and advanced glycation end products. We also report elevated messenger RNA (mRNA) levels of LOX and TG2 in glaucoma LC cells to support our proposed theory that increased levels of cross-linking proteins in glaucoma play a role in LC tissue stiffness. We highlight areas of research that are needed to better understand the role of cross-linking in glaucoma pathogenesis, leading potentially to a novel therapeutic strategy.

Contact lens complications among wearers in Ghana. - Kobia-Acquah, Emmanuel; Akowuah, Prince Kwaku; Antwi-Adjei, Ellen Konadu; Forkuo, Philip Mensah; Koomson, Nana Yaa; Odotei, Samuel Odoi; Alabi, Emmanuel; Donkor, Richard (Contact Lens & Anterior Eye, 2021)
Purpose: Contact lens (CL) practice is relatively new in Ghana; a country where the geographical location (warm climate) lends itself to harsh environmental conditions (high humidity) known to influence CL wear. Recent studies suggest an increase in CL wear (corrective and cosmetic), yet, there are no studies about CL-related complications. This study sought to determine the complications associated with CL wear in Ghana.Methods: This was a retrospective cohort study. The medical records of contact lens wearers from five CL clinics in the two largest metropolises in Ghana, Accra and Kumasi, were reviewed. Included in the study were records of individuals who visited the clinics within the period of 2013-2016. Data on patients with contact lens-related complications were analyzed.Results: The prevalence of CL complications was 29.06 %. The mean ± SD age of patients with CL complications was 35 ± 15 years. Contact lens complications were more common in females (52.90 %). The majority of complications were in soft contact lens wearers (82.35 %). Refractive error correction was the most common indication for CL wear (61.76 %) among those with complications, followed by keratoconus (14.71 %), scarred blind eye (14.71 %), corneal ulcer (5.88 %) and anterior staphyloma (2.94 %). Contact lens complications reported were giant papillary conjunctivitis (41.18 %), corneal infiltrates (23.53 %), bacterial keratitis (14.71 %), corneal abrasion (11.76 %), dry eye (5.88 %) and corneal oedema (2.94 %). The causes of CL complication were inappropriate lens cleaning (29.41 %), poor hygiene (23.53 %), overnight contact lens wear (17.64 %), poor lens fit (14.71 %) and reaction to contact lens solution (14.71 %).Conclusion: Contact lens complications were more common in soft contact lens wearers in Ghana. Giant papillary conjunctivitis was the most common contact lens complication reported. Adherence to CL wear care regimen and good personal hygiene may prevent the majority of CL complications observed in Ghana.

Automated, Noncontact Intraocular Pressure Home Monitoring after Implantation of a Novel Telemetric Intraocular Pressure Sensor in Patients with Glaucoma: A Feasibility Study. - Koutsonas, Antonis; Walter, Peter; Kuerten, David; Plange, Niklas (BioMed Research International, 2018)
Purpose. Reliable and regular assessment of intraocular pressure (IOP) is important for the monitoring of patients with glaucoma. The purpose of this study was to evaluate the feasibility of a novel system for the automated, noncontact measurement of IOP. Patients and Methods. A first-generation telemetric IOP sensor was previously implanted in the ciliary sulcus of six patients with open-angle glaucoma during cataract surgery. Using this technology, automated noninvasive tonometry may be performed in a home setting. In the present study, a modified sleep mask and a modified eyepatch with incorporated coil antennae for measurements during nighttime and daytime, respectively, were tested on a single patient. Results. In this feasibility study, the 24 h wear of the prototype measuring apparatus was well tolerated. Three sequences of 24 h IOP measurements with at least 200 IOP measurements per day were performed (Sequence 1: mean 19.6 ± 2.7 mmHg, range 13.4–28.7 mmHg; Sequence 2: mean 21.0 ± 3.0 mmHg, range 13.1–30.5 mmHg; Sequence 3: mean 19.9 ± 2.4 mmHg, range 12.6–27 mmHg). Conclusions. For the first time, repeated and automated 24-hour measurements are possible using a prototype noncontact reading system after implantation of a novel telemetric IOP sensor in patients with glaucoma.
Keywords: Automation; Tonometry -- Methods; Biosensors; Prostheses and Implants; Eye Surgery -- Methods; Glaucoma -- Surgery; Home Diagnostic Tests -- Methods; Pilot Studies; Human; Telemetry; Uvea -- Surgery; Cataract Extraction; Masks; Eye Patching; Time Factors; Patient Compliance; Repeat Procedures; Postoperative Period

A STROBE-compliant case-control study: Effects of cumulative doses of topical atropine on intraocular pressure and myopia progression. - Teng-Chieh Yu; Tzu-En Wu; Yuan-Shen Wang; Shen-Fu Cheng; Shiow-Wen Liou; Yu, Teng-Chieh; Wu, Tzu-En; Wang, Yuan-Shen; Cheng, Shen-Fu; Liou, Shiow-Wen (Medicine, 2020)
Topical atropine has become a mainstream treatment of myopia throughout East and Southeast Asia, but it is uncertain whether long-term topical atropine therapy induces intraocular pressure (IOP) elevation and subsequent development of glaucoma. We then prospectively examined the effects of long-term atropine treatment on IOP.Our case series collected 186 myopic children who were younger than 16 years of age. Complete ocular examination data, IOP and refractive status measurements beginning in 2008 were collected for all participants. Participants were divided into two groups: 121 children who received atropine therapy at various concentrations were classified as the treated group, whereas 65 children who did not receive atropine therapy were classified as the untreated (reference) group. In the treated group, clinicians prescribed different concentrations of atropine eye drops according to their discretion with regard to the severity of myopia on each visit of the patient. We then calculated the cumulative dose of atropine therapy from 2008 to the patients' last follow-up in 2009. Furthermore, the treated group was then further divided into low- and high-refractive-error groups of nearly equal size for further analysis.There were no significant differences for the baseline refractive errors and IOPs between the treated and untreated groups. Both the low- and high-cumulative atropine dosage subgroups showed significantly lower myopic progression than the untreated group, but there was no significant difference between the two subgroups in terms of different cumulative dosages. All groups, including the untreated group, showed an increase of mean IOP at the last follow-up, but both low- and high-cumulative atropine dosage subgroups experienced a smaller increase of IOP. The mean IOP of all atropine-treated groups showed no significant increase in either low- or high-refractive-error eyes.This study revealed that topical atropine eye drops do not induce ocular hypertension and are effective for slowing the progression of myopia. The treatment effects are not correlated with the cumulative atropine dosages.
Keywords: Myopia -- Drug Therapy; Atropine -- Therapeutic Use; Muscarinic Antagonists -- Therapeutic Use; Female; Atropine -- Administration and Dosage; Child; Glaucoma; Prospective Studies; Ophthalmic Solutions; Muscarinic Antagonists -- Administration and Dosage; Case Control Studies; Male; Intraocular Pressure; Myopia -- Physiopathology; Tonometry

Old and New Drug Classes Expanding To Include Glaucoma Treatments. - Kish, Troy (P&T: A Peer-Reviewed Journal for Managed Care & Formulary Management, 2018)
Poor patient adherence is fueling keen interest in the development of drugs for glaucoma management. Several long-acting formulations of existing medications are in the early stages of development, as are new therapeutic classes such as guanylate cyclase activators.
Keywords: Drugs, Investigational; Glaucoma -- Drug Therapy; United States Food and Drug Administration; Ophthalmic Solutions; Dose-Response Relationship, Drug; Latanoprost; Intraocular Pressure; Patient Compliance; Enzymes; Bimatoprost; Prostheses and Implants; Eye

Overcoming Barriers to Eye Care: Patient Response to a Medical Social Worker in a Glaucoma Service. - Fudemberg, Scott; Amarasekera, Dilru; Silverstein, Marlee; Linder, Kathryn; Heffner, Paul; Hark, Lisa; Waisbourd, Michael (Journal of Community Health, 2016)
This paper investigates the patient response to a medical social worker in a glaucoma clinic. The literature suggests that medical social workers are effective in a variety of health care settings, yet the efficacy of a medical social worker in an adult ophthalmic setting has not been studied. We present the results of a retrospective chart review of 50 patients with glaucoma referred to a medical social worker between January 5, 2015 and June 31, 2015 in an outpatient clinic of an urban eye hospital. Clinical and demographic data, as well as the data from a quality of care questionnaire, were collected for each patient. Patients rated their interaction with the medical social worker as highly positive (mean = 4.75, 5-point Likert scale), and nearly 90 % of patients expressed interest in future contact with the social worker. Additionally, most patients reported that the social worker resolved the issues they were facing (61.1 %), supported them in seeing their ophthalmologist (70.6 %), and helped them to manage their glaucoma (69.7 %). Reported barriers to glaucoma care were emotional distress; cost of office visits and medications; lack of medical insurance; transportation; poor medication adherence; impairment of daily activities; follow-up adherence; and language. As vision loss from glaucoma is irreversible, it is important to detect and treat patients at early stages of the disease. Therefore, it is imperative for patients to regularly visit their eye care providers and adhere to treatment and follow-up recommendations. This study suggests that a medical social worker could play a pivotal role in helping patients with glaucoma overcome barriers to treatment and facilitate disease management.
Keywords: Eye Care; Health Services Accessibility; Patient Care; Glaucoma -- Prevention and Control; Community Health Centers; Human; Social Workers; Medical Practice; Glaucoma -- Complications; Referral and Consultation; Quality of Health Care; Middle Age; Male; Female; Race Factors; Glaucoma -- Diagnosis; Glaucoma -- Classification

Tele-glaucoma versus clinical evaluation: The New Jersey Health Foundation Prospective Clinical Study. - Chandrasekaran, Subhashini; Kass, William; Thangamathesvaran, Loka; Mendez, Nicole; Khouri, Peter; Szirth, Bernard C; Khouri, Albert S (Journal of Telemedicine & Telecare, 2020)
Introduction: Glaucoma, the second most common cause of blindness, is normally detected in clinic. With technological improvements, tele-glaucoma exams can identify these changes off-site. The quality of tele-glaucoma exams needs to be compared with that of traditional exams. This study's purpose was to validate the tele-glaucoma programme, which allows a physician comprehensive access to patients' data, by comparing results to clinical examinations.Methods: A prospective study of 107 subjects evaluated in clinic and then tele-glaucoma stations, which consisted of non-mydriatic fundus photography, puff-tonometry, auto-refraction and Optical Coherence Tomography (OCT). The OCT captured central corneal thickness, angle anatomy, cup-to-disc ratio (CDR), retinal nerve fibre layer distribution and posterior-pole ganglion cell complex data.Results: Intraocular pressure (IOP) comparisons between clinical and tele-glaucoma exams had strong positive Pearson correlation coefficients (0.8248 OD, 0.8672 OS). Strong positive correlations were seen for CDR (0.7835 OD, 0.8082 OS) as well as diagnosis (glaucoma, no glaucoma or glaucoma suspect). A moderate positive correlation was seen for return to clinic time (RTC). Tele-glaucoma had an average lower RTC (2.7 vs 3.9 months). Tele-glaucoma was more likely to elicit a non-glaucomatous diagnosis not found in clinic vs a diagnosis found only in clinic (18% vs 5% of subjects).Discussion: Tele-glaucoma allows for detecting glaucoma remotely. These advancements alleviate patient difficulties with obtaining adequate glaucoma screenings and helps ophthalmologists triage patients with more severe pathology. Our study indicates that our tele-glaucoma protocol is comparable to a clinical exam in its ability to detect glaucoma. Further studies will be needed for off-site testing and transferring data separately for analysis.
Keywords: Glaucoma -- Diagnosis; Telemedicine -- Administration; Diagnosis, Eye; Photography; Health Services Accessibility; Male; Waiting Lists; Sensitivity and Specificity; Intraocular Pressure; Aged, 80 and Over; Aged; Female; Prospective Studies; Adolescence; Middle Age; Young Adult; Adult; New Jersey; Ferrans and Powers Quality of Life Index; Interview Guides; Scales

Application of the Sight Outcomes Research Collaborative Ophthalmology Data Repository for Triaging Patients With Glaucoma and Clinic Appointments During Pandemics Such as COVID-19. - Bommakanti, Nikhil K.; Zhou, Yunshu; Ehrlich, Joshua R.; Elam, Angela R.; John, Denise; Kamat, Shivani S.; Kelstrom, Jared; Newman-Casey, Paula Anne; Shah, Manjool M.; Weizer, Jennifer S.; Wood, Sarah D.; Zhang, Amy D.; et al. (JAMA Ophthalmology, 2020)
Importance: During the coronavirus disease 2019 (COVID-19) pandemic, eye care professionals caring for patients with sight-threatening diseases, such as glaucoma, have had to determine whether some patient appointments could safely get postponed, weighing the risk that the patient's glaucoma could worsen during the interim vs the morbidity risk of acquiring COVID-19 while seeking ophthalmic care. They also need to prioritize appointment rescheduling during the ramp-up phase (when pandemic-associated service reductions are eased).Objective: To describe a flexible and scalable scoring algorithm for patients with glaucoma that considers glaucoma severity and progression risk vs the presence of high-risk features for morbidity from COVID-19, using information from a large data repository.Design, Setting, and Participants: In this cross-sectional study, patients with upcoming clinic appointments for glaucoma from March 16, 2020, to April 16, 2020, at an academic institution enrolled in the Sight Outcomes Research Collaborative (SOURCE) Ophthalmology Electronic Health Record Data Repository were identified. A risk stratification tool was developed that calculated a glaucoma severity and progression risk score and a COVID-19 morbidity risk score. These scores were summed to determine a total score for each patient.Main Outcomes and Measures: Total scores and percentages of clinic appointments recommended for rescheduling.Results: Among the 1034 patients with upcoming clinic appointments for glaucoma, the mean (SD) age was 66.7 (14.6) years. There were 575 women (55.6%), 733 White individuals (71%), and 160 Black individuals (15.5%). The mean (SD) glaucoma severity and progression risk score was 4.0 (14.4) points, the mean (SD) COVID-19 morbidity risk score was 27.2 (16.1) points, and the mean (SD) total score was 31.2 (21.4) points. During pandemic-associated reductions in services, using total score thresholds of 0, 25, and 50 points would identify 970 appointments (93.8%), 668 appointments (64.6%), and 275 appointments (26.6%), respectively, for postponement and rescheduling. The algorithm-generated total scores also helped prioritize appointment rescheduling during the ramp-up phase.Conclusions and Relevance: A tool that considers the risk of underlying ophthalmic disease progression from delayed care receipt and the morbidity risk from COVID-19 exposure was developed and implemented, facilitating the triage of upcoming ophthalmic appointments. Comparable approaches for other ophthalmic and nonophthalmic care during the COVID-19 pandemic and similar crises may be created using this methodology.
Keywords: Glaucoma -- Therapy; Pneumonia, Viral -- Epidemiology; Triage; Appointments and Schedules; Coronavirus Infections -- Epidemiology; Aged; Aged, 80 and Over; Ambulatory Care Facilities; Middle Age; Ophthalmology; Disease Outbreaks; Female; Male; Cross Sectional Studies

Pediatric Eye Injuries by Hydroalcoholic Gel in the Context of the Coronavirus Disease 2019 Pandemic. - Martin, Gilles C.; Le Roux, Gael; Guindolet, Damien; Boulanger, Etienne; Hasle, Denis; Morin, Emilie; Vodovar, Dominique; Vignal, Catherine; Gabison, Eric; Descatha, Alexis (JAMA Ophthalmology, 2021)
Importance: The coronavirus disease 2019 (COVID-19) pandemic has made alcohol-based hand sanitizers (ABHS) widely available in public places. This may warrant determining whether cases of unintentional ocular exposure are increasing, especially in children.Objective: To describe the epidemiologic trend of pediatric eye exposures to ABHS and to report the severity of the ocular lesions.Design, Setting, and Participants: Retrospective case series conducted from April 1, 2020, to August 24, 2020. Cases were retrieved from the national database of the French Poison Control Centers (PCC) and from a pediatric ophthalmology referral hospital in Paris, France. Cases of ocular exposure to chemical agents in children younger than 18 years during the study period were reviewed. Cases of ABHS exposure were included.Exposures: The following data were collected: age, sex, circumstances of exposure, symptoms, size of the epithelial defect at first examination, time between the incident and re-epithelialization, and medical and/or surgical management.Main Outcomes and Measures: Comparison of the number of eye exposures to ABHS in children between April to August 2020 and April to August 2019.Results: Between April 1 and August 24, 2020, there were 7 times more pediatric cases of ABHS eye exposures reported in the PCC database compared with the same period in 2019 (9.9% of pediatric eye exposures in 2020 vs 1.3% in 2019; difference, 8.6%; 95% CI, 7.4-9.9; P < .001). The number of cases occurring in public places increased in 2020 (from 16.4% in May to 52.4% in August). Similarly, admissions to the eye hospital for ABHS exposure increased at the same period (16 children in 2020 including 10 boys; mean [SD] age, 3.5 [1.4] years vs 1 boy aged 16 months in 2019). Eight of them presented with a corneal and/or conjunctival ulcer, involving more than 50% of the corneal surface for 6 of them. Two cases required amniotic membrane transplant.Conclusions and Relevance: These data support the likelihood of an increasing number of unintentional ocular exposures to ABHS in the pediatric population. To maintain good public compliance with hand disinfection, these findings support that health authorities should ensure the safe use of these devices and warn the parents and caregivers about their potential danger for children.

Patient-Reported Nonadherence with Glaucoma Therapy. - Wolfram, Christian; Stahlberg, Erik; Pfeiffer, Norbert (Journal of Ocular Pharmacology & Therapeutics, 2019)
Purpose: Effective glaucoma therapy relies to a great extent on the patients' ability to regularly self-administer eye drops. This study aimed to assess self-reported nonadherence and to identify potential barriers to adherence in glaucoma patients. Methods: Participants completed a 16-item questionnaire, designed to examine nonadherence rate and assess the therapy experience. Inclusion criteria stipulated treatment duration of at least 1 year. Nonadherence was defined as missing ≥5% of the prescribed pressure-lowering eye drops doses. Results: In total, 201 glaucoma patients aged 24-88 years were included. Mean treatment duration was 9.4 years. Nonadherence was reported by 30.3% of participants and 69.7% were reported to be adherent. Individuals who experienced side effects reported higher levels of nonadherence than those who did not (37.6% vs. 18.4%; P = 0.004). Eye drops with preservatives were used by 84.1% of participants, 11.9% were on combined preservative and preservative-free treatment, and 4.0% on preservative-free medication only. Self-reported nonadherence levels were 32.0%, 25.0%, and 12.5%, respectively, for each of these groups. Men reported higher rates of nonadherence than women (36.8% vs. 24.5%; P = 0.066). Age, social status, history of migration, severity of disease, and fear of blindness were not associated with significant differences in nonadherence levels. Conclusions: Nonadherence with glaucoma therapy is a significant barrier to therapeutic success for approximately one-third of patients. Nonadherence may be reduced if side effects are avoided. Preservative-free products may provide adherence benefits. The patient experience should be a key consideration when selecting appropriate treatments, to reduce nonadherence and optimize outcomes.
Keywords: Glaucoma -- Drug Therapy; Antihypertensive Agents -- Therapeutic Use; Pharmaceutical Additives -- Therapeutic Use; Patient Compliance; Ophthalmic Solutions -- Therapeutic Use; Aged, 80 and Over; Male; Aged; Injections; Ophthalmic Solutions -- Administration and Dosage; Young Adult; Antihypertensive Agents -- Administration and Dosage; Adult; Human; Female; Germany; Pharmaceutical Additives -- Administration and Dosage; Middle Age; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Social Readjustment Rating Scale

Why are there gender inequalities in visual impairment? - Ulldemolins, Anna Rius; Benach, Joan; Guisasola, Laura; Artazcoz, Lucía (European Journal of Public Health, 2019)
Background In high-income countries, the prevalence of blindness and visual impairment is higher among women, regardless of age although the mechanisms that produce these gender inequalities are not well understood. The objectives of this study were to analyse gender inequalities in the prevalence of blindness and visual impairment, age of onset, diagnosed and undiagnosed status and related eye diseases among visually impaired individuals. Methods Data were obtained from the 2008 Spanish Survey on 'Disability, Personal Autonomy and Dependency Situations' (n = 213 626) participants 360 blind (160 men and 200 women), and 5560 with some visual impairment (2025 men and 3535 women). The prevalence of blindness and visual impairment, age of onset of visual impairment and diagnosed and undiagnosed eye diseases was calculated. Hierarchical multiple logistic regression models were fit to test gender differences. Results Women were more likely to report visual impairment (crude OR = 1.6 [95% CI: 1.56–1.74]). Prevalence of diagnosed cataract was higher among visually impaired women (crude OR = 1.4 [95% CI: 1.25–1.67]) whereas undiagnosed eye disease (crude OR = 0.7 [95% CI: 0.64–0.81]) or diagnosed glaucoma (aORsex = 0.8 [95% CI: 0.65–0.93]) were more frequent among visually impairment men. These associations were not explained by age or educational level. Conclusions Strong gender inequalities were observed, with a higher prevalence of visual impairment and related cataracts among women, which could be related to gender inequalities in access to health care, and undiagnosed eye disease and related glaucoma among men, which could be related to their gender socialization resulting in less frequent and effectively use of health care services.
Keywords: Sex Factors; Health Status Disparities; Vision Disorders -- Diagnosis; Blindness -- Diagnosis; Age of Onset; Health Status; Human; Prevalence; Surveys; Spain; Autonomy; Male; Female; Multiple Logistic Regression; Odds Ratio; Confidence Intervals; Cataract -- Diagnosis; Glaucoma -- Diagnosis; Age Factors; Educational Status; Health Services Accessibility; Vision Disorders -- Therapy; Blindness -- Therapy; Socialization; Health Resource Utilization

Dorzolamide/Timolol Fixed Combination: Learning from the Past and Looking Toward the Future. - Konstas, Anastasios G.; Schmetterer, Leopold; Katsanos, Andreas; Hutnik, Cindy M. L.; Holló, Gábor; Quaranta, Luciano; Teus, Miguel A.; Uusitalo, Hannu; Pfeiffer, Norbert; Katz, L. Jay (Advances in Therapy, 2021)
The key clinical attributes of preserved dorzolamide/timolol fixed combination (DTFC) and the emerging potential of preservative-free (PF) DTFC are reviewed with published evidence and clinical experience. The indications and role of DTFC in current glaucoma management are critically discussed. Preserved DTFC became the first intraocular pressure (IOP)-lowering fixed combination (FC) approved by the US Food and Drug Administration (FDA) and remains one of most commonly used medications worldwide. The pharmacological properties of DTFC reflect those of its two time-tested constituents, i.e., the carbonic anhydrase inhibitor dorzolamide and the non-selective beta-blocker timolol. In regulatory studies DTFC lowers IOP on average by 9 mmHg (32.7%) at peak and by 7.7 mmHg (27%) at trough. In trials DTFC shows equivalence to unfixed concomitant therapy, but in real-life practice it may prove superior owing to enhanced convenience, elimination of the washout effect from the second drop, improved tolerability, and better adherence. PF DTFC became the first PF FC approved, first in unit-dose pipettes, and more recently in a multidose format. Cumulative evidence has confirmed that PF DTFC is at least equivalent in efficacy to preserved DTFC and provides a tangible clinical benefit to patients with glaucoma suffering from ocular surface disease by improving tolerability and adherence. Finally, we identify areas that warrant further investigation with preserved and PF DTFC.
Keywords: Ocular Hypertension -- Drug Therapy; Timolol; Carbonic Anhydrase Inhibitors; Drug Combinations; Antihypertensive Agents -- Therapeutic Use; Sulfur Compounds; Sulfonamides; Intraocular Pressure; Human; Tonometry; Clinical Assessment Tools; Scales

Increasing Engagement of African American Patients with Glaucoma during Medical Encounters: Creation of a Pre-visit Video. - Sleath, Betsy; Davis, Scott A.; Carpenter, Delesha M.; Robin, Alan L.; Muir, Kelly W.; Lee, Charles; Garcia, Nacire; Budenz, Donald L. (Optometry & Vision Science, 2020)
Significance: The developed video can be accessed by African American patients with glaucoma from across the United States on YouTube to learn why it is important to ask eye care providers any questions they might have about glaucoma and/or its treatment.Purpose: Our objective was to develop an educational video for African Americans with glaucoma to watch before their ophthalmology office visits to help motivate them to be actively involved in their care.Methods: The Social Cognitive Theory guided the development of the video. We conducted three focus groups with African American patients with glaucoma and three focus groups with providers who care for African American patients with glaucoma. The research team reviewed the transcripts of the focus groups and then developed a plan for video production.Results: The themes that both patients and providers felt should be covered in the video to motivate patient question-asking included the following: what is glaucoma, glaucoma treatment, glaucoma testing, and treatment adherence. Based on focus group results, the resulting video had one male African American physician and four African American patients covering the themes that emerged.Conclusions: Ophthalmologists and African Americans with glaucoma gave us excellent insight into developing videos to increase patient involvement during their visits.
Keywords: Consumer Participation; Videorecording; Patient Education -- Methods; Glaucoma -- Ethnology; Focus Groups; Female; Male; Aged; Communication; Office Visits; Middle Age; Physician-Patient Relations; United States; Social Readjustment Rating Scale

Journey to glaucoma care - trusting but uncertain and uninformed: a qualitative study. - Lu, Thomas C; Semsarian, Caitlin R; White, Andrew; Dunn, Hamish; Angell, Blake; Ford, Belinda; Keay, Lisa (Clinical & Experimental Optometry, 2020)
Background: This study aims to explore patient perspectives regarding their journey to glaucoma care and sought to understand the determinants that guide their access to tertiary glaucoma care.Methods: Twenty-nine patients who are glaucoma suspects or had definitive diagnosis of glaucoma were recruited from a large public glaucoma clinic and a private ophthalmology clinic in Sydney. Face-to-face, in-depth semi-structured interviews were conducted between April and December 2017. Interviews were recorded and transcribed verbatim. A framework method was used for thematic analysis of the data.Results: Thematic analysis resulted in the emergence of eight main themes. There was limited patient participation in decision making in their journey to glaucoma care. Consequently, there was great trust placed in the referring clinician. Patients valued their vision and therefore expressed a desire for high-quality care. They placed considerable trust in their specialist but were often unsure how to evaluate the quality of care received. Patients lacked an understanding of the cost of glaucoma care and for some, cost remained a barrier to the access of private care. There were variable experiences with waiting times and the journey to clinic, with many patients making concessions and requiring support to access care.Conclusion: This study is the first qualitative study exploring the perspectives of glaucoma patients in Australia and the determinants of access to care. These findings support and can inform development of patient-centred models of care furthering patient trust and empowerment.

Perspectives and impediment to eye care in caregivers of children with childhood glaucoma. - Rao, Aparna; Raj, Niranjan; Padhy, Debananda; Sarangi, Sarada; Sarangi, Sarada Prasanna (Indian Journal of Ophthalmology, 2020)
Purpose: To study the perceptions, attitude, knowledge of the disease, and impediments to seeking early eye care in caregivers of children with childhood glaucoma.Methods: The study included new and old children diagnosed with childhood glaucoma (which included congenital glaucoma and developmental glaucoma) at a tertiary hospital of east India. The caregivers were administered a video-based questionnaire through open-ended questions intended to collect demographic and other personal details such as caregiver's socioeconomic status, knowledge, attitude towards eye health, and other social barriers. The responses were analyzed using thematic analysis technique into different buckets such as social status, knowledge/attitude, and sociocultural beliefs while individual responses in each bucket were analyzed.Results: Of a total of 43 patients included,> 75% of patients came from places> 200 km from the eye care centre with> 50% coming from> 300 km. Most patients presented either <1 year (42%, n = 18) or> 3 years (52%, n = 22) with only 2% (n = 3) presenting between 1-3 years of age. The mother was the first person of contact to diagnose the eye abnormality in> 45% of patients. Comparing differences among children who presented within 1 year of first diagnosis and those that presented later, caregivers hailing from long-distance> 200 km from an eye care center, monthly income <5000 INR, and those with social/cultural taboos (like children's eyes should not be operated) were more likely to seek delayed eye care for congenital glaucoma, P < 0.001.Conclusion: Impediments in seeking early eye care for blinding diseases in children (including distance from the nearest hospital, low socioeconomic constraints, and sociocultural beliefs/taboos) mandate serious policies towards improving education about eye disease and eye health among caregivers.
Keywords: Attitude to Health; Eye Diseases; Health Services Accessibility; Female; Child; Mothers; Caregivers; Caregiver Strain Index; Personal Resource Questionnaire; Social Readjustment Rating Scale

Promising therapeutic drug delivery systems for glaucoma: a comprehensive review. - Singh, Rohan B.; Ichhpujani, Parul; Thakur, Sahil; Jindal, Sumeet (Therapeutic Advances in Ophthalmology, 2020)
The delivery of ophthalmic drugs is challenging despite easy accessibility via the ocular surface. Topical instillation of eye drops is a relatively easy and most commonly used as a conduit for drug delivery for treating a myriad of ocular morbidities, particularly involving the anterior segment, and has an additional benefit of avoiding the first-pass metabolism while passing through the systemic circulation. The primary challenges of drug administration through traditional methods include—inadequate patient education for proper drug instillation technique, compliance, adherence, and persistence. Various dynamic (choroidal and conjunctival blood flow, lymphatic clearance, and tear dilution) and static (namely, different layers of cornea, sclera, and retina including blood aqueous and blood–retinal barriers) ocular barriers limit drug delivery to the target ocular tissues. The maintenance of the therapeutic drug levels on the ocular surface for a prolonged duration is an added challenge, thus preventing persistent delivery for longer durations. These factors result in inadequate management, leading to poor prognosis in vision loss in as many as 27% of the patients diagnosed with glaucoma. We have reviewed the research and advancements in the development of novel and well-tolerated drug delivery systems with the common goal of overcoming the factors limiting adequate drug delivery to the target tissues in glaucomatous patients with traditional techniques. In the recent past, multiple research groups have successfully designed noninvasive, sustained drug delivery systems, promoting the efficacy as well as the feasibility of delivering topical drugs to the anterior segment.
Keywords: Drug Delivery Systems; Glaucoma -- Drug Therapy; Treatment Outcomes; Medication Compliance; Morbidity; Patient Education; Instillation, Drug; Glaucoma -- Prognosis; Survival

Glaucoma Care of Prison Inmates at an Academic Hospital. - Kanu, Levi N.; Jang, Inae; Oh, Daniel J.; Tiwana, Manpreet S.; Mehta, Amy A.; Dikopf, Mark S.; Vajaranant, Thasarat S.; Aref, Ahmad A.; Edward, Deepak P. (JAMA Ophthalmology, 2020)
Importance: Glaucoma care for prison inmates is underrepresented in the literature even though managing the treatment of such patients may provide unique challenges.Objectives: To evaluate the glaucoma profile of prison inmates treated at an academic ophthalmology center and to report on the medical and surgical management and follow-up metrics.Design, Setting, and Participants: This retrospective cohort study assessed data from 82 incarcerated patients treated at the glaucoma clinic, an academic referral center at the University of Illinois at Chicago, between January 2013 and December 2017.Main Outcomes and Measures: Diagnosis, glaucoma severity, medical and surgical interventions, and patient-reported medication adherence were recorded for each visit. Recommended and actual follow-up times were recorded and compared. Data analyses were conducted from January 2013 to December 2018.Results: In total, 82 patients (161 eyes) had 375 visits during the study period. All patients were male and ranged from 20 to 75 years of age (mean [SD] age, 50.8 [11.9] years). Most participants were black patients (65 [79.3%]). The most common diagnoses were primary open-angle glaucoma (POAG; 53 eyes [32.9%]) and POAG suspect (52 eyes [32.3%]). Glaucoma severity ranged from mild (25 of 77 eyes [32.5%]) to advanced (41 of 77 eyes [53.2%]). Overall, 59 patients (73.2%) were treated medically with up to 4 topical agents (40.0%). Of those treated, 70.0% of patients (95% CI, 57.7%-81.2%) reported medication nonadherence during at least 1 visit. Medication nonadherence was more common among those taking 4 different topical medications (21 of 24 [87.5%]) compared with others taking fewer medications (20 of 35 [57.1%]), for a difference of 30.4% (95% CI, 7.0%-53.6%; P = .02), and among those with advanced disease (22 of 26 [84.6%]) compared with glaucoma suspect (6 of 13 [46.2%]), for a difference of 38.4% (95% CI, 9.3%-67.5%; P = .02). Nineteen office procedures, including laser peripheral iridotomy and laser trabeculoplasty, were performed on 14 eyes. Seventeen incisional glaucoma procedures were performed on 15 eyes, including glaucoma drainage device implant (11 procedures [64.7%]) and trabeculectomy (3 procedures [17.6%]). Only 26.6% of return office visits (95% CI, 21.3%-32.3%) occurred within the recommended follow-up time frame. Furthermore, 93 patients (34.8%; 95% CI, 28.2%-40.0%) were seen more than 1 month after the recommended follow-up.Conclusions and Relevance: Despite incarceration in prison, where medication administration and appointment attendance are theoretically controlled, the results of this study suggested that substantial medication and follow-up nonadherence exists among inmates.
Keywords: Prisoners -- Statistics and Numerical Data; Academic Medical Centers -- Statistics and Numerical Data; Glaucoma -- Therapy; Trabeculectomy; Correctional Facilities; Antihypertensive Agents -- Therapeutic Use; Laser Therapy; Referral and Consultation; Aged; Adult; Retrospective Design; Male; Illinois; Glaucoma -- Epidemiology; Medication Compliance; Young Adult; Ocular Hypertension -- Epidemiology; Ocular Hypertension -- Therapy; Intraocular Pressure -- Physiology; Middle Age; Glaucoma -- Diagnosis

Barriers to Receiving Follow-Up Eye Care and Detection of Non-Glaucomatous Ocular Pathology in the Philadelphia Glaucoma Detection and Treatment Project. - Zheng, Cindy; Hu, Wanda; Tran, Judie; Siam, Linda; Berardi, Giuliana; Sembhi, Harjeet; Hark, Lisa; Katz, L.; Waisbourd, Michael (Journal of Community Health, 2016)
This cross-sectional study aimed to evaluate adherence rates and identify barriers to receiving follow-up eye care in participants diagnosed with significant non-glaucomatous eye pathology in the Philadelphia Glaucoma Detection and Treatment Project. This community-based project aimed to improve detection, management, treatment, and follow-up eye care of individuals at high risk for glaucoma in community-based settings. Participants throughout Philadelphia, Pennsylvania, USA were enrolled. After a comprehensive eye examination, follow-up recommendations were given to each participant. A telephone survey was administered to individuals diagnosed with non-glaucomatous ocular pathology 3 months after initial eye examination to assess rates of follow-up and to evaluate potential barriers to follow-up. Of the 1649 participants enrolled in this project, 249 (15 %) were diagnosed with significant non-glaucomatous ocular pathology requiring follow-up care. There were 143 (57 %) who responded to the telephone survey. Respondents had a median age of 72 years, and were predominately female (69 %) and African-American (64 %). Of the respondents, 36 (25 %) attended a follow-up appointment. Participants who did not remember the results of their examinations, did not remember their recommendations, and had not seen an eye doctor within the past year were less likely to make a follow-up appointment ( P = 0.04, 0.001 and 0.005, respectively). The Philadelphia Glaucoma Detection and Treatment Program was able to detect a significant amount of non-glaucomatous ocular pathology requiring follow-up care. Actual follow-up rates were sub-optimal. Further research is needed to determine interventions to overcome barriers and increase adherence with follow-up recommendations.
Keywords: After Care; Health Services Accessibility; Glaucoma -- Diagnosis; Eye -- Pathology; Program Evaluation; Cross Sectional Studies; Patient Compliance; Minority Groups; Descriptive Statistics; Data Analysis Software; Human; Questionnaires; Adult; Middle Age; Aged; Aged, 80 and Over; Male; Female; Funding Source

A Glaucoma-Specific Brief Motivational Interviewing Training Program for Ophthalmology Para-professionals: Assessment of Feasibility and Initial Patient Impact. - Newman-Casey, Paula Anne; Killeen, Olivia; Miller, Sarah; MacKenzie, Chamisa; Niziol, Leslie M.; Resnicow, Ken; Creswell, John W.; Cook, Paul; Heisler, Michele (Health Communication, 2020)
Our objective was to test the feasibility of, fidelity to, and initial impact of a brief, glaucoma-specific motivational interviewing (MI) training program for ophthalmic para-professionals. This prospective, mixed-methods study had two components, one for staff and one for patients. Staff fidelity to MI principles was graded through audio-recorded encounters after initial and final training sessions. After training, patients graded staff for adherence to autonomy supportive care. Semi-structured interviews with para-professionals elicited feedback about the training and about their ability to implement MI in the clinic. The impact on patient satisfaction with staff communication, eye drop instillation self-efficacy, and overall health activation was assessed using a survey pre- and post-training. Para-professionals met two of three program goals for MI skills and improved in their overall scores for MI fidelity. Para-professionals noted lack of time in the clinic as a significant barrier to implementing counseling. Patient satisfaction with staff communication increased after the training (p = 0.04) among patients who rated their staff above the mean for providing autonomy supportive care. The intervention did not improve patients' eye drop instillation self-efficacy or overall health activation. Training para-professional staff in brief, glaucoma-specific MI techniques is feasible and may improve patient satisfaction, though dedicated time in clinic is needed to implement MI counseling into glaucoma practice.
Keywords: Health Personnel, Unlicensed -- Education; Motivational Interviewing -- Education; Instillation, Drug -- Education; Ophthalmic Solutions -- Therapeutic Use; Glaucoma -- Therapy; Patient Satisfaction; Professional-Patient Relations; Medication Compliance; Outcomes of Education; Human; Prospective Studies; Multimethod Studies; Nonexperimental Studies; Semi-Structured Interview; Audiorecording; Program Evaluation; Pretest-Posttest Design; Communication; Self-Efficacy; Professional Compliance; Patient Autonomy; Clinical Trials; Program Development; Questionnaires; Professional Knowledge; Health Personnel, Unlicensed -- Psychosocial Factors; Scales; Summated Rating Scaling; Descriptive Statistics; Linear Regression; Models, Statistical; Convenience Sample; Midwestern United States; Health Knowledge; Confidence; Unpaired T-Tests; Wilcoxon Rank Sum Test; Chi Square Test; Fisher's Exact Test; Paired T-Tests; Adult; Ophthalmology; Open-Ended Questionnaires; Structured Questionnaires; Funding Source

A comparison of measures used to describe adherence to glaucoma medication in a randomised controlled trial. - Cate, Heidi; Bhattacharya, Debi; Clark, Allan; Holland, Richard; Broadway, David C. (Clinical Trials, 2015)
Background: Understanding the magnitude of non-adherence in pre-marketing clinical trials and clinical practice is essential. However, accurately measuring non-adherence to medication is problematic, and the variety of adherence measures and/or calculation methods has led to highly variable results. Purpose: To compare commonly used methods for measuring adherence to eye drop therapy in order to assess which methods achieve the most complete datasets over an 8-month monitoring period, to quantify the magnitude of variance in adherence estimations and to review the different methods used to calculate or interpret adherence data. Methods: Adherence was measured electronically for 8 months by participants administering eye drops using a Travalert® dosing aid. The mean number of Travalert dosing aid recorded doses administered over the monitoring period was used to calculate a percentage adherence score. In addition, the value of graphically presenting Travalert dosing aid data to classify patterns of adherence behaviour was explored. The validated Morisky Measure of Adherence Scale and questions requesting participants to report the Frequency of Missed Doses were two measures of self-reported adherence calculated for each participant. Finally, medication possession ratio was calculated from expected repeat prescription orders compared with actual repeat prescription orders. Results: For the 208 recruited participants, self-reported adherence was the most reliable method of collecting complete datasets over the 8-month period; 16% of self-reported adherence data were missing compared with 45% of Travalert dosing aid data missing at 8 months. The mean adherence measured over the monitoring period by the Travalert dosing aid was 77%. When adherence measures were dichotomised into adherent and non-adherent groups, the Travalert dosing aid found 54% of participants were adherent, compared to 60% Morisky Measure of Adherence Scale and 57% Frequency of Missed Dose self-report measures. However, there was poor agreement between the Travalert dosing aid measured adherence and self-report measures. Medication possession ratio was not a reliable measure of persistence with medication. Graphical Travalert dosing aid data presentation provided additional information about participant behaviour by indicating that most non-adherence was due to participants taking drug holidays rather than missing occasional doses. Conclusion: The analysis provided evidence about the inconsistencies between different monitoring strategies and adherence measures. Furthermore, the analysis highlighted the difficulties in collecting complete data for studies investigating chronic, slowly progressive conditions that require long-term follow-up. Future adherence studies could use multiple methods for quantifying and classifying adherence in parallel, both to maximise precision of adherence estimates and to facilitate comparison between studies. However, the authors are cautious of the effect of using multiple adherence measures on participant behaviour and their potential reactivity effects is an area for future research.
Keywords: Glaucoma -- Drug Therapy -- United Kingdom; Patient Compliance; Randomized Controlled Trials; Human; Ophthalmic Solutions -- Administration and Dosage; United Kingdom; Descriptive Statistics; Repeated Measures; Analysis of Variance; Kappa Statistic; Spearman's Rank Correlation Coefficient; Female; Male; Middle Age; Aged; P-Value; Self Report; Funding Source; Scales

Method of predicting glaucoma conversion proves to be faster. - Charters, Lynda (Ophthalmology Times, 2021)
The article discusses a study examined a new method for estimating the risk of glaucomatous conversion using deep learning predictions of the retinal nerve fiber layer (RNFL) thickness from optic disc photographs. Topics covered include the advantages of this method it feasibility for monitoring glaucoma risk in patients who were glaucoma suspects, and its ability to obtain updated predictions of glaucoma risk with the acquisition of more data over time.
Keywords: Glaucoma -- Diagnosis; Health Services Accessibility; Disease Progression -- Prevention and Control; Glaucoma -- Drug Therapy; Early Diagnosis; Tomography, Optical Coherence; Deep Learning; Ophthalmic Equipment and Supplies; Technology, Medical

The Use of Generic Medications for Glaucoma. - Tatham, Andrew J. (Journal of Ophthalmology, 2020)
The use of generic medicines has grown considerably in recent years providing considerable cost savings. In England, generic items represented 11.7% of prescriptions for glaucoma and ocular hypertension in 2009, increasing to 55.2% of prescriptions in 2018. Generics can be brought to the market quickly and at low cost as manufacturers are not required to repeat animal or clinical research on active ingredients already approved for safety and efficacy. Although there is no regulatory requirement for studies comparing branded and generic eye drops, several randomised crossover studies have been performed comparing branded and generic prostaglandin analogues. While most have shown similar intraocular pressure lowering, studies are of short duration and have not evaluated visual field endpoints. Furthermore, differences in inactive ingredients, pH, viscosity, levels of particulate matter, and degradation over time have been reported. Other potential problems with generic eye drops include differences in bottle design affecting adherence, problems with supply, and the possibility that reduced revenue for innovator companies will lead to reduced investment in new drug development. This article reviews the potential advantages and disadvantages of generic antiglaucoma medications.
Keywords: Drugs, Generic -- Therapeutic Use; Glaucoma -- Drug Therapy; Human; Systematic Review; Ocular Hypertension -- Drug Therapy; Cost Savings; Drugs, Prescription; Ophthalmic Solutions; Prostaglandins -- Analogs and Derivatives; Hydrogen-Ion Concentration; Viscosity; Particulate Matter; Drug Design; Medication Compliance; Treatment Outcomes

Promising therapeutic drug delivery systems for glaucoma: a comprehensive review. - Singh, Rohan B.; Ichhpujani, Parul; Thakur, Sahil; Jindal, Sumeet (Therapeutic Advances in Ophthalmology, 2020)
The delivery of ophthalmic drugs is challenging despite easy accessibility via the ocular surface. Topical instillation of eye drops is a relatively easy and most commonly used as a conduit for drug delivery for treating a myriad of ocular morbidities, particularly involving the anterior segment, and has an additional benefit of avoiding the first-pass metabolism while passing through the systemic circulation. The primary challenges of drug administration through traditional methods include--inadequate patient education for proper drug instillation technique, compliance, adherence, and persistence. Various dynamic (choroidal and conjunctival blood flow, lymphatic clearance, and tear dilution) and static (namely, different layers of cornea, sclera, and retina including blood aqueous and blood--retinal barriers) ocular barriers limit drug delivery to the target ocular tissues. The maintenance of the therapeutic drug levels on the ocular surface for a prolonged duration is an added challenge, thus preventing persistent delivery for longer durations. These factors result in inadequate management, leading to poor prognosis in vision loss in as many as 27% of the patients diagnosed with glaucoma. We have reviewed the research and advancements in the development of novel and well-tolerated drug delivery systems with the common goal of overcoming the factors limiting adequate drug delivery to the target tissues in glaucomatous patients with traditional techniques. In the recent past, multiple research groups have successfully designed noninvasive, sustained drug delivery systems, promoting the efficacy as well as the feasibility of delivering topical drugs to the anterior segment.
Keywords: Glaucoma -- Drug Therapy; Ophthalmic Solutions -- Therapeutic Use; Drug Delivery Systems; Technology, Medical; Noninvasive Procedures; Medication Compliance; Patient Education; Nanoparticles; Diffusion of Innovation; Contact Lenses; Glaucoma -- Prognosis; Drug Efficacy

Psycho-ophthalmology: Contributions of Health psychology to the assessment and treatment of glaucoma. - Méndez-Ulrich, Jorge Luis; Sanz, Antoni (Psychology & Health, 2017)
Background: Asymptomatic in its early stages, glaucoma is the second leading cause of blindness worldwide. While psychosocial factors are taken into consideration for a host of diseases such as cancer, heart disease and autoimmune conditions, to date, psychological issues have been ignored in the clinical management of glaucoma. Objective: This work reviews the most relevant contributions from a health psychology perspective for the assessment and treatment of glaucoma, which is emerging in the field of psycho-ophthalmology. Method: To provide scientific evidence regarding contributions of psychology to the comprehension of glaucoma, a bibliographic review of three databases (Psicodoc, PsycInfo and Medline) was conducted, spanning the period between 1940 and 2016. Results: This review yielded a total of 66 studies published in the period analysed and identified three areas where health psychology has made substantive contributions to glaucoma screening, monitoring and treatment: the emotional impact on patients suffering from glaucoma, the adherence to treatment and the effects of stress on intraocular pressure. Conclusions: A health psychology approach for research and therapy of glaucoma must focus on the management of the negative affect associated with the diagnosis, the optimisation of treatment adherence and the stress management of the intraocular pressure measurements.
Keywords: Glaucoma -- Diagnosis; Glaucoma -- Drug Therapy; Health Psychology; Ophthalmology; Human; Systematic Review; Medline; Psycinfo; Reference Databases, Health; Patient Compliance; Stress, Psychological; Intraocular Pressure; Vision Disorders -- Risk Factors; Glaucoma -- Complications; Anxiety Disorders; Depression; Chi Square Test; Ophthalmic Solutions; P-Value; Ocular Hypertension; Funding Source

The Prevalence of Undiagnosed Age-Related Sight-Threatening Diseases in Self-Proclaimed Healthy Individuals. - Lemmens, Sophie; Barbosa Breda, João; Van Keer, Karel; Jacobs, Tine; Van Landeghem, Ruben; De Boever, Patrick; Stalmans, Ingeborg (Journal of Ophthalmology, 2020)
Background. Age-related conditions such as glaucoma, age-related macular degeneration, diabetic retinopathy, and cataract have become the major cause of visual impairment and blindness in high-income countries. The aim of the current study is to investigate the prevalence of these eye diseases in a cohort of self-proclaimed healthy elderly and thus get a rough estimation of the prevalence of undiagnosed age-related eye conditions in the Belgian population. Methods. Individuals aged 55 and older without ophthalmological complaints were asked to fill in a general medical questionnaire and underwent an ophthalmological examination, which included a biomicroscopic examination, intraocular pressure measurement, axial length measurement, and acquisition of fundus pictures and optical coherence tomography scans. Information regarding follow-up was collected in those who received the advice of referral to an ophthalmologist or the advice to have more frequent follow-up visits, based on their study evaluation. Results. The cohort included 102 people and comprised 46% men (median age 70 years, range 57–85 years). Referral for additional examinations was made in 26 participants (25%). The advice to have more regular follow-up ophthalmologist visits was given to nine additional participants (9%). No significant correlations between baseline characteristics and the need for referral could be identified. Follow-up information was available for 25 out of 26 referred volunteers. Out of these, four underwent a therapeutic intervention based on study referral, up until 18 months after study participation. All four interventions took place in the age group 65–74 years. Conclusions. This study shows that, even in an elderly population with self-proclaimed healthy eyes and good general health, a significant proportion of subjects showed ocular findings that need regular follow-up and/or intervention. The frequency of prior ophthalmological examinations does not seem to be relevant to this proportion, meaning that everyone above 55 years old needs a routine ophthalmological evaluation.
Keywords: Undiagnosed Diseases -- Epidemiology -- Belgium; Glaucoma -- Epidemiology -- Belgium; Macular Degeneration -- Epidemiology -- Belgium; Diabetic Retinopathy -- Epidemiology -- Belgium; Cataract -- Epidemiology -- Belgium; Eye Diseases -- Epidemiology -- In Middle Age; Eye Diseases -- Epidemiology -- In Old Age; Aging; Self Report; Health Status; Human; Prevalence; Prospective Studies; Belgium; Middle Age; Aged; Aged, 80 and Over; Questionnaires; Tonometry; Microscopy; Diagnosis, Eye; Tomography, Optical Coherence; Male; Female; Descriptive Statistics; Referral and Consultation; Office Visits; Eye Diseases -- Therapy; Age Factors

Applying the resources and supports in self-management framework to examine ophthalmologist-patient communication and glaucoma medication adherence. - Sleath, B.; Carpenter, D. M.; Blalock, S. J.; Sayner, R.; Muir, K. W.; Slota, C.; Giangiacomo, A. L.; Hartnett, M. E.; Tudor, G.; Robin, A. L. (Health Education Research, 2015)
Little is known about how ophthalmologist-patient communication over time is associated with glaucoma patient long-term adherence. The purpose of our study was to examine the association between provider use of components of the resources and supports in self-management model when communicating with patients and adherence to glaucoma medications measured electronically over an 8-month period. In this longitudinal prospective cohort study, the main variables studied were ophthalmologist communication-individualized assessment, collaborative goal setting and skills enhancement. Patients with glaucoma who were newly prescribed or on glaucoma medications were recruited from six ophthalmology clinics. Patients' baseline and next follow-up visits were videotape-recorded. Patients were interviewed after their visits. Patients used medication event monitoring systems (MEMS) for 8 months after enrollment into the study, and adherence was measured electronically using MEMS for 240 days after their visits. Two hundred and seventy-nine patients participated. Patient race and regimen complexity were negatively associated with glaucoma medication adherence over an 8-month period. Provider communication behaviors, including providing education and positive reinforcement, can improve patient adherence to glaucoma medications over an 8-month period.
Keywords: Glaucoma -- Prevention and Control; Physician-Patient Relations; Communication -- Standards; Medication Compliance -- Evaluation; Self Care; Goal-Setting; Collaboration; Patient Education; Reinforcement (Psychology); Human; Prospective Studies; Videorecording; Descriptive Statistics; Questionnaires; Coefficient Alpha; Chi Square Test; T-Tests; Pearson's Correlation Coefficient; Female; Male; Aged; Aged, 80 and Over; Middle Age; Black Persons; Odds Ratio; Confidence Intervals; Race Factors; Funding Source

PHARMACOLOGIC TREATMENT AN OPTION FOR OPEN-ANGLE GLAUCOMA: Therapies can help manage disease, lowering and stabilizing IOP. - Dalton, Michelle (Ophthalmology Times, 2020)
The article reports on the advances and new options in the treatment of open-angle glaucoma which is the leading cause of irreversible blindness in the U.S. as of April 2020. Topics discussed include intraocular pressure (IOP) reduction as a modifiable risk factor for open-angle glaucoma, causes of IOP fluctuations including poor treatment compliance and genetics, and developments in the use of bimatoprost sustained release biodegradable implant.
Keywords: Pharmacological and Biological Treatments -- Methods; Glaucoma -- Surgery; Disease Management; Intraocular Pressure; Disease Progression; Individualized Medicine; Glaucoma -- Drug Therapy; Drug Therapy, Combination; Ophthalmic Solutions; Medication Compliance

Is laser trabeculoplasty the new star in glaucoma treatment? - Töteberg-Harms, Marc; Meier-Gibbons, Frances (Current Opinion in Ophthalmology, 2021)
Purpose Of Review: For decades, laser trabeculoplasty has been a well-proven therapeutic option in glaucoma management, and more recently, it has only gained in popularity. One reason for such popularity is that selective laser trabeculoplasty (SLT) is a therapy independent of patient adherence, which is typically low among glaucoma patients. Consequently, the number of studies on SLT has multiplied throughout the past years. This review provides an overview of studies on SLT from the last 12 months.Recent Findings: The studies on treatment outcome show a wide range of success rates of SLT reaching between 18 and 88%; however, study designs differ and many studies are not directly comparable. The prospective laser trabeculoplasty for open-angle glaucoma and ocular hypertension (LiGHT) trial has demonstrated good efficacy of SLT - 75% of the eyes achieved their target pressure without drops and 58% after a single SLT.Summary: SLT has proven to be effective in lowering IOP with satisfactory success rates even after single SLT. SLT is repeatable independent of patient's adherence.
Keywords: Anterior Eye Segment -- Surgery; Glaucoma -- Surgery; Laser Therapy -- Methods; Trabeculectomy -- Methods; Lasers -- Therapeutic Use; Ocular Hypertension -- Surgery; Ocular Hypertension -- Physiopathology; Glaucoma -- Physiopathology; Intraocular Pressure -- Physiology

Exophiala lecanii-corni keratitis presenting as a serpiginous pigmented superficial lesion: a case report. - Tomoko Miyakubo; Daisuke Todokoro; Yoshiyuki Satake; Koichi Makimura; Sumiko Miyakubo; Hideo Akiyama; Miyakubo, Tomoko; Todokoro, Daisuke; Satake, Yoshiyuki; Makimura, Koichi; Miyakubo, Sumiko; Akiyama, Hideo (Medicine, 2020)
Rationale: Patients with bullous keratopathy (BK) treated by Descemet stripping automated endothelial keratoplasty (DSAEK) have a compromised cornea, due to the administration of topical steroid, postsurgical use of contact lenses, and impaired barrier function of the corneal epithelium by BK. We report a case of Exophiala lecanii-corni (E lecanii-corni) keratitis presenting as a serpiginous pigmented superficial lesion after DSAEK.Patient Concerns: An 81-year-old woman who had undergone cataract surgeries, suffered from decreased vision in the left eye. She was diagnosed BK and she underwent DSAEK. Two months after DSAEK, a pigmented superficial lesion developed on the left cornea. The lesion migrated and recurred repeatedly and she was referred to our department. Best corrected vision was 20/220.Diagnoses: Light microscopy of a corneal scraping revealed branching fungal hyphae. Fungal culture showed growth of a black colony, identified as E lecanii-corni by ribosomal DNA sequencing.Interventions: We started topical treatment with 1% voriconazole and 1.5% levofloxacin. Antifungal susceptibility testing showed that the minimum inhibitory concentration of voriconazole was 0.06 μg/mL.Outcomes: The lesion scarred after treatment for 3 months, and left best corrected vision improved to 20/40.Lessons: Genus Exophiala is known as 1 of the "black molds" and a cause of chromomycosis. This is the first description of E lecanii-corni keratitis, and pigmented corneal epithelial lesions may be characteristic of this fungal genus.
Keywords: Eye Infections, Fungal -- Etiology; Keratitis -- Etiology; Fungi; Cornea -- Microbiology; Female; Keratitis -- Microbiology; Aged, 80 and Over; Cataract Extraction -- Adverse Effects

Combination drops may help patients challenged by multiple glaucoma meds: They can simplify dosing, improving adherence and ocular surface health. - Richman, Jesse (Ophthalmology Times, 2021)
The article outlines the use of combination drops (CD) for the management of glaucoma. Topics mentioned include the barriers to the successful multiple glaucoma medication adherence including cost and ocular surface toxicity, the advantage of compounded CD over traditional drops, and the benefits of an auto-refill program.
Keywords: Glaucoma -- Drug Therapy; Ophthalmic Solutions -- Therapeutic Use; Medication Compliance; Intraocular Pressure; Ophthalmic Solutions -- Economics

Awareness of ocular diagnosis, transportation means, and barriers to ophthalmology follow-up in the Philadelphia Telemedicine Glaucoma Detection and Follow-up Study. - Hark, Lisa A.; Radakrishnan, Anjithaa; Madhava, Malika; Anderson-Quiñones, Catherine; Fudemberg, Scott; Robinson, Debra; Myers, Jonathan S.; Zhan, Tingting; Adeghate, Jennifer; Hegarty, Sarah; Leite, Stela; Leiby, Benjamin E.; et al. (Social Work in Health Care, 2019)
Purpose: The purpose of this study was to assess factors affecting follow-up eye care in participants enrolled in the Philadelphia Telemedicine Glaucoma Detection and Follow-up Study, such as awareness of ocular diagnosis, availability of transportation methods, and reasons for missing eye care appointments. Methods: The sample included 172 participants who were randomized to the intervention group and contacted by the social worker. Results: A total of 155 participants completed the assessment form, which was used as an instrument to assess factors affecting adherence to follow-up eye care. The main reasons for missing eye exam appointments were feeling ill (38.1%, n = 59) and forgetting the appointment (34.2%, n = 53). In addition, 45 (29.2%) participants were unaware of or did not comprehend the severity of their ocular diagnosis. Common methods of transportation included public transportation (31.6%, n = 49), driving (29.7%, n = 46), and being driven (27.7%, n = 43) to their appointment. Conclusion: These results suggest that individuals in need of eye care may benefit from additional assistance of a social worker regarding ongoing eye exam appointment reminders and in-depth explanation of their ocular diagnosis.
Keywords: Eye Care -- Psychosocial Factors; After Care -- Psychosocial Factors; Transportation -- Methods; Health Knowledge; Appointments and Schedules; Human; Randomized Controlled Trials; Random Assignment; Patient Compliance -- Evaluation; Questionnaires; Female; Male; Adult; Middle Age; Aged; Aged, 80 and Over; Memory; Social Workers; Health Status; Support, Psychosocial; Funding Source

Inmates' Self-Reported Physical and Mental Health Problems: A Comparison by Sex and Age. - Lane, Charlene; Bratina, Michele P.; Antonio, Michael E. (Journal of Correctional Health Care, 2020)
The present study explored the impact of both age and sex on inmates' self-reported physical and mental health problems. The inmates were older adults (55 or older) and housed in one of four correctional institutions from a state located in the northeastern region of the United States. Overall, findings revealed female inmates more often reported currently taking prescribed medications for mental or emotional problems and previously having been diagnosed with mental health problems prior to incarceration. Also, comparing male and female inmates by age categories (59 and younger vs. 60 and older), the older group was more likely to report a variety of physical problems including arthritis, diabetes, and glaucoma. Research and correctional policy implications are discussed.
Keywords: Prisoners; Self Report; Health Status; Mental Disorders; Sex Factors; Age Factors; Human; Middle Age; Aged; Aged, 80 and Over; New England; Drugs, Prescription; Medication Compliance; Male; Female; Arthritis; Diabetes Mellitus; Glaucoma; Health Services Accessibility; Health Services Needs and Demand; Descriptive Statistics

How Low Vision Affects the Functional Ability of Patients and What You Can Do to Help. - Brown, Barbara (Insight: The Journal of the American Society of Ophthalmic Registered Nurses, 2020)
Keywords: Vision, Subnormal; Functional Status; Patient Care; Support, Psychosocial; Ophthalmic Nursing; Nurses -- Education; Office Visits; Patient Education; Patient Attitudes; Macular Degeneration -- In Adulthood; Adult; United States; Nurse-Patient Relations; Glaucoma; Corneal Diseases; Diabetes Mellitus -- Complications; Nursing Assessment

Providing Prescheduled Appointments as a Strategy for Improving Follow-Up Compliance After Community-Based Glaucoma Screening: Results from an Urban Underserved Population. - van Zyl, Tavé; Su, Zhuo; Zhou, Elaine; Wong, Ryan; Mohsenin, Amir; Rogers, Spencer; Tsai, James; Forster, Susan (Journal of Community Health, 2015)
To determine if receiving a prescheduled appointment is associated with an increased likelihood of complying with follow-up eye care among individuals identified as at risk for glaucoma during community-based glaucoma screening in an urban underserved population. This study sampled 362 individuals aged ≥30 years without known glaucoma from low-income, predominantly black/Hispanic neighborhoods in New Haven, Connecticut presenting to one of twelve community-based glaucoma screening events from May 2010 to October 2012. A quasi-experimental design systematically assigned 63 individuals identified as at risk for glaucoma into either intervention or control group with a 1:2 ratio. Individuals in the control group ( n = 41) received counseling on glaucoma and a recommendation for obtaining a follow-up appointment at the eye department of a local community health center, which offers affordable health services with income-adjusted fee discounts to uninsured, low-income patients. Those in the intervention group ( n = 22) received the same counseling and a prescheduled appointment at the community health center. The overall rate of follow-up compliance within 3 months of screening was 30 % (41 % in the intervention group; 24 % in the control group). Multivariate logistic regression analysis adjusting for sex, age, ethnicity, health insurance status, car access, living situation, and smoking status found that follow-up compliance was significantly associated with intervention (adjusted odds ratio 4.8; 95 % confidence interval 1.1-20.9). Providing prescheduled appointments can improve follow-up compliance after community-based glaucoma screening. This finding may be potentially applicable to community-based health screening for other preventable diseases.
Keywords: Vision Screening -- Evaluation; Appointments and Schedules -- Evaluation; Patient Compliance -- Evaluation; Medically Underserved; Urban Areas; Glaucoma -- Diagnosis; Human; Adult; Middle Age; Aged; Aged, 80 and Over; Male; Female; Connecticut; Quasi-Experimental Studies; Descriptive Statistics; Odds Ratio; Confidence Intervals; Multiple Logistic Regression; Questionnaires; Surveys; Self Report; Data Analysis, Statistical; Data Analysis Software; P-Value; Funding Source

Mini-vitrectomy; a simple solution to a serious condition. - Pakravan, Mohammad; Esfandiari, Hamed; Amouhashemi, Nassim; Veisi, Amir; Torkian, Pooya; Yazdani, Shahin (Journal of Ophthalmic & Vision Research, 2018)
Purpose: To evaluate the safety and efficacy of clear corneal approach irido-zonulo-hyaloido-vitrectomy, which we named “mini-vitrectomy,” in the management of pseudophakic aqueous misdirection. Methods: In this retrospective, non-comparative interventional case series, 24 eyes with diagnosis of pseudophakic aqueous misdirection were enrolled. Medical therapy with cycloplegics and laser therapy, including posterior capsulotomy and hyaloidotomy, was not effective in the management of the condition. The eyes underwent mini-vitrectomy, a simple technique in which iridotomy, zonulectomy, hyaloidectomy, and limited anterior vitrectomy were performed via a clear cornea incision. The main outcome measure was reformation of the anterior chamber, which was evaluated at day 1 and months 1, 3, 6, and 12. Results: The mean age of patients was 75.3 ± 11.3 years (range, 47 to 90), and 13 (54.2%) patients were women. Anterior chamber was deep in 22 patients (91.7%) at the last follow-up visit. The mean intraocular pressure (IOP) was 30.31 ± 1.9 mm Hg at presentation on 2.67 ± 1.09 glaucoma medications. IOP decreased significantly to 14.5 ± 4.6 mm Hg at 12-month follow-up. (P = 0.001). The number of glaucoma medications at final visit was 2.2 ± 0.9 (P = 0.21). Conclusion: Mini-vitrectomy is a simple, safe, and effective procedure in the management of pseudophakic aqueous misdirection, and it can be adopted by all ophthalmologists who are involved in glaucoma management and are not comfortable with the pars plana vitrectomy approach.
Keywords: Eye Surgery; Treatment Outcomes; Iris -- Surgery; Cornea -- Surgery; Eye Diseases -- Surgery; Human; Retrospective Design; Comparative Studies; Diagnosis, Eye; Refractive Errors -- Surgery; Anterior Chamber; Aged, 80 and Over; Middle Age; Female; Male; Office Visits; Intraocular Pressure; Ophthalmologists; Mydriatics -- Therapeutic Use; Laser Therapy; Surgical Wound; Aged

Micelles: Promising Ocular Drug Carriers for Anterior and Posterior Segment Diseases. - Durgun, Meltem Ezgi; Güngör, Sevgi; Özsoy, Yıldız (Journal of Ocular Pharmacology & Therapeutics, 2020)
Micelles have been studied in the targeting of drug substances to different tissues as a nano-sized delivery system for many years. Sustained drug release, ease of production, increased solubility, and bioavailability of drugs with low water solubility are the most important superiorites of micellar carriers. These advantages paved the way for the use of micelles as a drug delivery system in the ocular tissues. The unique anatomical structure of the eye as well as its natural barriers and physiology affect ocular bioavailability of the drugs negatively. Conventional dosage forms can only reach the anterior segment of the eye and are used for the treatment of diseases of this segment. In the treatment of posterior segment diseases, conventional dosage forms are administered sclerally, via an intravitreal injection, or systemically. However, ocular irritation, low patient compliance, and high side effects are also observed. Micellar ocular drug delivery systems have significant promise for the treatment of ocular diseases. The potential of micellar systems ocular drug delivery has been demonstrated by in vivo animal experiments and clinical studies, and they are continuing extensively. In this review, the recent research studies, in which the positive outcomes of micelles for ocular targeting of drugs for both anterior and posterior segment diseases as well as glaucoma has been demonstrated by in vitro, ex vivo, or in vivo studies, are highlighted.

Association of an Electronic Health Record-Linked Glaucoma Medical Reminder With Patient Satisfaction. - Varadaraj, Varshini; Friedman, David S.; Boland, Michael V. (JAMA Ophthalmology, 2019)
Importance: While dosing reminders for glaucoma medications have been shown to increase drug adherence, an outstanding limitation preventing broad adoption is difficulty linking reminders to medication in each patient's electronic health record (EHR).Objective: To examine the feasibility of implementing an EHR-linked, automated reminder system for glaucoma medications and assess patient satisfaction with it.Design, Setting, and Participants: In this prospective, cross-sectional study, patients receiving glaucoma medications were recruited from a university-based glaucoma clinic from April 2017 to January 2018. Analysis began in February 2018.Exposures: A web-based application was added to the EHR patient portal, allowing patients to configure telecommunication-based reminders for their glaucoma medications. For all potential participants, basic information was collected to determine risk of nonadherence with glaucoma medications. Those consenting to participate then answered questions on medication adherence, reminders, and their likelihood of using EHR-linked reminders. They then configured reminders using the EHR patient portal. After 3 months, they answered questions about their satisfaction with the system.Main Outcomes and Measures: Proportions of patients and high-risk patients willing to use the reminders, and patient satisfaction with the system.Results: Of 147 patients approached, 100 (68%) agreed to participate, of whom the majority were men (54 [54%]) and white (51 [51%]), with a mean (SD) age of 65 (12.4) years. There were no differences between those willing and unwilling to participate, except for a slightly lower self-reported medication adherence rate among those who participated (mean [SD], 91% [13.6%] vs 97% [6.0%]). Based on a previously validated risk assessment score, 9% (9 of 100) of participants were categorized as being at high risk for poor adherence (≥50% probability of nonadherence) compared with 11% (5 of 47) of nonparticipants. Of 100 participants, 94 ultimately configured reminders, of whom 89 (95%) completed follow-up. On follow-up, 74% (n = 66; 95% CI, 65-83) of participants found the reminders to be useful, 15% (n = 13) were neutral, and 11% (n = 10) found them not useful. Most participants (72 [81%]; 95% CI, 77-85) had help configuring reminders.Conclusions and Relevance: Electronic health records-linked reminders had good uptake and were well received among patients at a tertiary glaucoma clinic. These portals may represent a new and convenient method of allowing patients to link their glaucoma medications to automated reminders, although the generalizability of these results and the effect on glaucoma outcomes remains unknown.
Keywords: Reminder Systems -- Standards; Glaucoma -- Drug Therapy; Female; Prospective Studies; Middle Age; Aged; Adult; Cross Sectional Studies; Patient Satisfaction; Medication Compliance; Male; Clinical Assessment Tools

Safety and Efficacy of Scleral Lenses for Keratoconus. - Fuller, Daniel G.; Wang, Yueren (Optometry & Vision Science, 2020)
Significance: This study affirms the long-term safety and efficacy of scleral contact lens use in patients with keratoconus.Purpose: This study aimed to evaluate the safety and efficacy of contemporary scleral contact lenses in the visual rehabilitation of the keratoconic population.Methods: A retrospective study of keratoconic subjects examined between 2013 and 2018 was conducted. Subjects were included regardless of age, sex, pre-existing morbidity, or scleral lens design. Only eyes fit successfully with scleral contact lenses for ≥1 year were included. Exclusion criteria were prior corneal surgery, dystrophy, degeneration, and trauma.Results: A total of 157 eyes of 86 subjects met the study criteria. The mean Keratoconus Severity Score at initial fitting was 3.6 ± 1.0. Lenses were gas-permeable and nonfenestrated, with a mean overall diameter of 15.8 ± 0.6 mm and 70.1% toric scleral periphery. Physiological adverse events occurred in 9.6% of eyes, including microbial keratitis (0.6%), phlyctenulosis (0.6%), corneal abrasion (1.3%), contact lens-induced acute red eye (1.3%), corneal infiltrative events (1.3%), pingueculitis (1.3%), and hydrops (3.2%). Lens-related adverse events were documented in 55.4% of eyes. Adverse events related to surface issues included poor wetting in 1.9%, handling in 3.8%, reservoir fogging in 7.0%, lens intolerance in 7.6%, deposit in 8.9%, and broken lenses in 26.1% of eyes. The most common management strategies involved refits (54.0% of interventions), patient reeducation (29.5%), medical treatment (5.5%), surgical referral (6.8%), adjustment to wear time (2.5%), surface treatment (1.2%), and lens replacement (0.6%). Best-corrected distance logMAR visual acuity improved significantly from a mean of 0.50 in spectacles to a mean of 0.08 in scleral lenses (P < .0001). During the study period, 14.6% of eyes lost best-corrected scleral lens visual acuity, all from keratoconus progression.Conclusions: Consistent with other groups, our study demonstrates excellent safety and efficacy of scleral contact lenses in subjects with keratoconus.
Keywords: Corneal Diseases -- Therapy; Contact Lenses; Sclera; Male; Refraction, Ocular; Prosthetic Fitting; Equipment Safety; Female; Retrospective Design; Corneal Diseases -- Physiopathology; Visual Acuity -- Physiology; Adult; Treatment Outcomes; Adolescence; Middle Age; Patient Compliance; Young Adult; Scales

Dealing with the pressure of glaucoma management. - Greener, Mark (Prescriber, 2019)
Despite the availability of numerous treatments, glaucoma is still one of the leading causes of blindness in the UK. This article examines some of the factors that might be responsible, including poor compliance with eye drops and pressure on ophthalmology services, and discusses how these problems might be overcome.
Keywords: Glaucoma -- Psychosocial Factors; Glaucoma -- Drug Therapy; Uvea -- Physiology; Intraocular Pressure -- Physiology; Intraocular Pressure -- Evaluation; Drugs, Investigational; Intraocular Pressure -- Psychosocial Factors

Management of infective corneal ulcers in a high-income developing country. - AlMahmoud, Tahra; Elhanan, Mohamed; Elshamsy, Mohamed H.; Alshamsi, Hanan N.; Abu-Zidan, Fikri M. (Medicine, 2019)
Microbial keratitis is a major risk for corneal blindness worldwide. We aimed to study the clinical presentation and outcome of hospitalized patients having infective corneal ulcers.All patients who were diagnosed as microbial keratitis and were admitted to Al-Ain Hospital during the period July 2011-Dec 2016 were retrospectively studied. Patients' demography, predisposing factors, symptoms and signs at presentation, time to presentation after onset of symptoms, microbial isolates, hospital stay, and visual acuity (VA) outcome were studied.74 patients with corneal ulcers were hospitalized. 79.7% were males. The median (range) age was 44 years (1-91). 36.5% had trauma as a risk factor. The main presenting symptoms were pain (90.5%), red eye (79.7%), and decreased vision (63.5%). All patients had stromal infiltrate while 39.2% had hypopyon at presentation. The average time from the start of the symptoms to hospital presentation was 11 (1-90) days. The mean (range) hospital stay was 10.6 (1-60) days. Forty eyes were culture positive. Bacteria were identified in 27 eyes and fungus in 16. Pseudomonas aeruginosa (9 eyes) and Staphylococcus epidermis (5 eyes) were the most common bacterial islolates. Aspergillus (6 eyes) was the most common fungus species. 95.2% of the bacterial isolates were susceptible to the quinolone antibiotics group. Twenty eight (51.9%) patients had a vision worse than 6/60 in the affected eye.Corneal ulcer poses a significant threat to the sight of an affected eye. Trauma was the most common risk factor for corneal ulcers. Usage of eyes personal protective equipment for high risk occupations and earlier accessibility to health care may reduce the impact of corneal ulcers in our community.
Keywords: Corneal Ulcer -- Therapy; Corneal Ulcer -- Diagnosis; Child, Preschool; Adolescence; Corneal Ulcer -- Epidemiology; Retrospective Design; Risk Factors; Female; Infant; Aged; Developing Countries; Adult; Aged, 80 and Over; Male; Middle Age; Child; United Arab Emirates; Young Adult; Impact of Events Scale; Personal Resource Questionnaire; Scales

Polypharmacy in Older Adults: Practical Applications Alongside a Patient Case. - Nguyen, Timothy; Wong, Elaine; Ciummo, Francesco (Journal for Nurse Practitioners, 2020)
Polypharmacy is a common observation among older adults secondary to their complex medical needs requiring management with 1 or more medications. The use of numerous medications may result in medication-related problems such as inappropriate indications, therapeutic duplication, adverse effects, drug interactions, unnecessary medications, poor adherence, and a strain on health care resources. Nurse practitioners will be required to review and streamline the appropriate and safe use of medications in patients to minimize some of the highlighted concerns. This article uses a case-based approach to showcase various issues that a nurse practitioner may encounter as it relates to polypharmacy and pharmacotherapeutic considerations. Tools are also explored to assess polypharmacy in the field. • Polypharmacy is a prevalent concern among adults who may be taking a combination of medications. • This may result in various medication-related problems such as adverse effects, drug interactions, inappropriate therapy, or nonadherence. • It is important for health practitioners to be cognizant of the tools and methods to manage polypharmacy-related issues to optimize patient outcomes.
Keywords: Polypharmacy -- Adverse Effects -- In Old Age; Nurse Practitioners; Nursing Role; Inappropriate Prescribing; Female; Aged; Comorbidity; Physical Examination; Kidney Failure, Chronic; Glaucoma; Heart Failure; Hyperlipidemia; Hypertension; Osteoarthritis; Diabetes Mellitus, Type 2; Constipation; Heartburn; Insomnia; Adrenergic Beta-Antagonists; Timolol; Carvedilol; Metformin; Zolpidem; Acids, Acyclic; Statins; Antiinflammatory Agents, Non-Steroidal; Angiotensin-Converting Enzyme Inhibitors; Angiotensin II Type I Receptor Blockers; Platelet Aggregation Inhibitors; Patient Safety

Novel DSLT taking aim at glaucoma care. - Guttman Krader, Cheryl (Ophthalmology Times, 2019)
The article focuses on an investigational intraocular pressure (IOP)-lowering modality-direct selective laser trabeculoplasty (DSLT) being developed by BELKIN Laser as a first-line treatment for ocular hypertension (OHT) open-angle glaucoma and possibly for angle-closure glaucoma (OAG). Topics include remarks from Dr. Michael Belkin, inventor of DSLT and founder/ medical director of BELKIN Laser, the need to complete trials that show the efficacy and safety of DSLT, and concept behind the DSLT.
Keywords: Laser Therapy -- Methods; Trabeculectomy -- Methods; Glaucoma -- Surgery; Automation; Ocular Hypertension -- Prevention and Control; Health Services Accessibility; Treatment Outcomes; Ocular Hypertension -- Surgery; Technology, Medical; Drug Delivery Systems; Laser Therapy -- Economics; Trabeculectomy -- Economics; Intraoperative Period; Postoperative Complications; Minimally Invasive Procedures; Patient Compliance

Preferred practice pattern guidelines help identify POAG but are not always followed: Investigators determine that patient rates of adherence with gonioscopy are low. - Charters, Lynda; Al-Rajhi, Ali A. (Ophthalmology Times, 2021)
The article discusses the development of Preferred Practice Pattern (PPP) guidelines to help ophthalmologists not specialized to identify primary open-angle glaucoma (POAG) as of 2021. Topics covered include the recommendation of a periodic genioscopy to document angle status, the low gonioscopy patient adherence rates, and identification of patient adherence if one underwent the procedure within 12 months of initial POAG diagnosis. Also noted is a demographic chart on gonioscopy adherence.
Keywords: Practice Patterns; Practice Guidelines; Glaucoma -- Diagnosis; Patient Compliance; Diagnosis, Eye; Glaucoma -- Complications; Glaucoma -- Risk Factors

Demographic and socioeconomic barriers and treatment seeking behaviors of patients with infectious keratitis requiring therapeutic penetrating keratoplasty. - Shah, Hem; Radhakrishnan, Naveen; Ramsewak, Shivaa; Chiu, Stephan; Joseph, Sanil; Rose-Nussbaumer, Jennifer; Prajna, N; Prajna, N Venkatesh (Indian Journal of Ophthalmology, 2019)
Purpose: To understand demographic and socioeconomic barriers and treatment-seeking behaviors of patients with infectious keratitis requiring therapeutic penetrating keratoplasty (TPK) in a developing country.Methods: This prospective non-comparative questionnaire- based study included all patients presenting to Aravind Eye Hospital, Madurai with infectious keratitis that eventuated to TPK between November 2015 and October 2016. A structured questionnaire was administered on post-operative day 3 to collect data on the demographic details, predisposing factors, prior treatment received, and treatment expenditures.Results: In total, 227 patients underwent TPK between November 2015 and October 2016 for infectious keratitis. The majority of patients were males (n = 132, 58.1%), illiterate (n = 129, 56.8%), and had a family monthly income of less than INR 6000 (n = 142, 62.5%). Most of the patients (n = 163, 71.8%) had prior treatment with an ophthalmologist before presenting to our hospital. The mean distance travelled to reach our centre was 269.2 ± 298.5 km. The mean duration of disease before the presentation was 20.3 ± 21.1 days. Corneal smear was positive for fungus in 163 (88.1%) and Aspergillus was the most commonly isolated fungi in 55 (41.3%) cultures. The mean total cost of treatment was INR 8752.87 ± 7615.39 per patient. There was a positive correlation between the duration of the disease (rho 0.19, P = 0.0034) and the costs of treatment (rho 0.2, P = 0.0024) with the distance travelled by the patient.Conclusion: Patients who travelled a farther distance had a delayed onset of presentation and spent significantly more than their respective counterparts.
Keywords: Eye Infections, Fungal -- Epidemiology; Acanthamoeba Keratitis -- Epidemiology; Patient Attitudes; Corneal Ulcer -- Epidemiology; Socioeconomic Factors; Eye Infections, Bacterial -- Epidemiology; Corneal Transplantation; Male; Acanthamoeba Keratitis -- Surgery; Visual Acuity; Eye Infections, Fungal -- Surgery; Eye Infections, Bacterial -- Microbiology; Graft Survival; Female; Corneal Ulcer -- Surgery; Eye Infections, Bacterial -- Surgery; Adult; Corneal Ulcer -- Microbiology; Acanthamoeba Keratitis; Eye Infections, Fungal -- Microbiology; Prospective Studies; Middle Age

Corneal Infections Associated with Sleeping in Contact Lenses - Six Cases, United States, 2016-2018. - Cope, Jennifer R.; Konne, Nuadum Muriel; Jacobs, Deborah S.; Dhaliwal, Deepinder K.; Rhee, Michelle K.; Jia Yin; Steinemann, Thomas L.; Yin, Jia (MMWR: Morbidity & Mortality Weekly Report, 2018)
Contact lenses, when worn and cared for properly, are a safe and effective form of vision correction used by an estimated 45 million Americans. However, contact lens wearers are at risk for contact lens-related eye infections, especially when wearers do not practice proper contact lens wear and care habits. These infections, affecting the cornea and known as microbial keratitis (Figure), can lead to serious adverse health outcomes. Because contact lenses are regulated by the Food and Drug Administration (FDA) as medical devices, contact lens-related corneal infections should be reported to FDA as an adverse event. To illustrate their serious health implications, six cases of contact lens-related corneal infection, in which sleeping in lenses was reported as the main risk factor, are presented. Consequences of infection reported among the identified cases included the need for frequent administration of antibiotic eye drops, multiple follow-up medical appointments, and permanent eye damage. Health education measures directed toward contact lens wearers should emphasize raising awareness of the risks of sleeping in contact lenses as well as adherence to all recommendations for the wear and care of contact lenses. Additional measures are needed to educate eye care professionals about the need to report contact lens-related corneal infections to MedWatch, the FDA Safety Information and Adverse Event Reporting program (https://www.fda.gov/MedWatch/).
Keywords: Corneal Diseases -- Diagnosis; Sleep; Risk Taking Behavior; Eye Infections -- Diagnosis; Contact Lenses -- Adverse Effects; Adolescence; Female; Corneal Diseases -- Epidemiology; Eye Infections -- Epidemiology; United States; Adult; Middle Age; Male; Contact Lenses; Clinical Assessment Tools

Pearls for practicing in the COVID-19 era. - Krader, Cheryl Guttman (Ophthalmology Times, 2020)
Keywords: COVID-19 Pandemic; Ophthalmologists; Private Practice; Attitude of Health Personnel; Surveys; Stay-at-Home Orders; Glaucoma -- Prevention and Control; Emergency Care; Infection Control -- Methods; Office Visits; Telemedicine; Patient Education

Philadelphia Telemedicine Glaucoma Detection and Follow-up Study: Ocular Findings at Two Health Centers. - Hark, Lisa; Acito, Megan; Adeghate, Jennifer; Henderer, Jeffrey; Okudolo, Joseph; Malik, Kunal; Molineaux, Jeanne; Eburuoh, Rita; Zhan, Tingting; Katz, L. Jay (Journal of Health Care for the Poor & Underserved, 2018)
Abstract Blindness from glaucoma can be prevented by early detection and treatment. Telemedicine improves access to treatment in high-risk populations that face barriers to receiving adequate ophthalmic care. We used a practice-based telemedicine screening model at two health centers. Telemedicine imaging of the fundus and optic nerve, followed by a complete eye exam at the same location for participants with abnormal findings, unreadable images, or ocular hypertension (OHTN), was performed. A total of 182 participants were screened, of whom 108 qualified for a complete eye exam. Of these, 62 (34.1%) had abnormal images, 12 (6.6%) had OHTN, and 34 (18.7%) had unreadable images. Eighty-nine of the 108 (82%) returned for the complete eye exam. Predominantly, participants were African American with glaucoma suspect and cataract. Screening location was an important factor for follow-up. Assessment of the fundus and optic disc using telemedicine resulted in early detection of glaucoma and other ocular pathology.
Keywords: Glaucoma -- Diagnosis; Glaucoma -- Therapy; Telemedicine; Program Evaluation; Human; Randomized Controlled Trials; Primary Health Care; Diagnosis, Eye; Ocular Hypertension; Cataract; Vision Screening; Community Health Centers; Early Diagnosis; Male; Female; T-Tests; Wilcoxon Rank Sum Test; Fisher's Exact Test; Data Analysis Software; Middle Age; Aged; Funding Source; Prospective Studies

İstanbul Avrupa Yakasında Yaşayan Glokom Hastalarında Yaş Gruplarına Göre Farkındalık ve Tedaviye Uyum. - Tarakçıoğlu, Hatice Nur; Yıldız, Ayşegül Mavi; Sonbahar, Ozan; Yiğit, Ulviye; Özkaya, Abdullah (Medical Journal of Bakirkoy, 2019)
Objective: We aimed to compare the demographics, awareness about glaucoma, and adherence to the treatment between the young and old population of primary open angle glaucoma (POAG) patients. Methods: The POAG patients who were under follow-up in Bakırköy Training and Research Hospital Ophthalmology Clinic and were using medication since at least one year and volunteered for our survey were included this cross-sectional study between April and May 2018. Two surveys which included 13 questions and were used in previous studies were enriched with 6 additional questions and applied to the patients. The patients were divided into two groups according to the World Health Organization's classification in regard to age as ≤65 years (young patients) and >65 years (old patients) and compared in regards to the survey questions. Results: There was not statistically significant between the two groups in regards to gender, general awareness about glaucoma, regular followup, regular drug use, family history of glaucoma, disability in hand and arm movements, duration of glaucoma (p>0.05 for all). There was a statistical difference between the two groups in regards to the education level (the patients ≤65 years were more educated, p=0.03), awareness of blindness secondary to the disease (more frequent in the patients ≤65 years old, p=0.02), awareness of drug's brand (more frequent in the patients ≤65 years old, p=0.003), requiring assistance while using the drugs (more frequent in the group of patients >65 years-old, p=0.01), monthly number of forgetting the drug doses (more frequent in the group of patients >65 years-old, p=0.006), living alone (more frequent in the group of patients >65 years-old, p=0.02), and the number of used drugs (more frequent in the group of patients >65 years-old, p=0.03). Conclusion: It is obvious that the patients who are >65 years old will be less adherent to glaucoma treatment as they more frequently require assistance for drug use and live alone.
Keywords: Glaucoma -- Drug Therapy -- Turkey; Health Knowledge -- Evaluation -- Turkey; Medication Compliance -- Evaluation -- Turkey; Age Factors; Human; Turkey; Academic Medical Centers; Surveys; Cross Sectional Studies; World Health Organization; Child; Adolescence; Young Adult; Adult; Middle Age; Aged; Aged, 80 and Over; Family History; Disease Duration; Educational Status; Community Living

Challenges to topical drop adherence after cataract surgery: Ophthalmologists understand that patients prefer sustained-release technologies. - Matossian, Cynthia (Ophthalmology Times, 2020)
The article discusses the problem of patient adherence in the use of eye drops following cataract surgery. A review of related literature revealed that the likely reason for patient nonadherence include problems in difficulties in instilling eye drops such as manual dexterity, tremor, difficulty tilting the head back and visual impairment.
Keywords: Cataract Extraction; Ophthalmic Solutions; Medication Compliance; Delayed-Action Preparations; Postoperative Care; Glaucoma -- Drug Therapy; Steroids -- Therapeutic Use; Ophthalmologists; Steroids; Drug Combinations; Intraoperative Care; Patient Preference; Technology, Medical

Online Survey of Digital Reading by Adults with Low Vision. - Wu, Yueh-Hsun; Granquist, Christina; Gage, Rachel; Crossland, Michael D.; Legge, Gordon E. (Optometry & Vision Science, 2020)
Significance: Access to digital text is increasingly widespread, but its impact on low-vision reading is not well understood.Purpose: We conducted an online survey of people with low vision to determine what assistive technologies they use for visual reading, their preferred text characteristics, and the time they devote to reading digital and hard-copy text.Methods: One hundred thirty-three low-vision participants completed an online survey. Participants reported the nature and history of their low vision, their usage of different assistive technologies, and time devoted to five visual reading activities.Results: The three largest diagnostic categories were albinism (n = 36), retinitis pigmentosa (n = 20), and glaucoma (n = 15). Mean self-reported acuity was 0.93 logMAR (range, 0.1 to 1.6 logMAR). Mean age was 46 years (range, 18 to 98 years). Participants reported on percentage time spent reading using vision, audio, or touch (braille). Seventy-five percent of our participants did more than 50% of their reading visually. Across five categories of reading activities-work or education, news, pleasure, spot reading, and social networking-participants reported more time spent on digital reading than hard-copy reading. Eighty-nine percent of our participants used at least one technology from each of our two major categories of assistive technologies (digital content magnifiers and hard-copy content magnifiers) for visual reading.Conclusions: Despite the growing availability of digital text in audio or braille formats, our findings from an online sample of people with low vision indicate the continuing importance of visual reading. Our participants continue to use technology to access both hard-copy and digital text, but more time is devoted to digital reading. Our findings highlight the need for continued research and development of technology to enhance visual reading accessibility.
Keywords: Assistive Technology Devices; Reading; Vision, Subnormal -- Physiopathology; Communications Media; Young Adult; Male; Mobile Applications; Human; Surveys; Eyeglasses; Female; Visual Acuity -- Physiology; Middle Age; Aged, 80 and Over; Diagnostic Tests, Routine; Adult; Adolescence; Aged; Comparative Studies; Multicenter Studies; Evaluation Research; Validation Studies; Impact of Events Scale; Scales; Social Readjustment Rating Scale

Validation of a More Reliable Method of Eye Drop Self-Administration. - Freddo, Thomas F.; Ho, Derek Y.; Steenbakkers, Michelle; Furtado, Nadine (Optometry & Vision Science, 2020)
Significance: We propose an alternative method for eye drop self-administration. Similar IOP reductions were found with this method compared with clinician instillation. The alternative method of self-administration potentially benefits patients who have trouble successfully instilling drops.Purpose: The purpose of this study was to validate the efficacy of an alternative method of drop instillation.Methods: This study is a randomized controlled crossover clinical trial. Thirty participants were recruited. A drop of 0.5% timolol maleate was instilled into subject's eye on two separate visits. On one visit, eye drop instillation was by a trained clinician, and on the other, self-instillation using an alternative method was used. The order was randomly chosen. Intraocular pressure was measured before drop instillation and 2 hours after drop instillation. The investigator was masked during measurement, and an observer recorded the IOP measurements.Results: Mean ± SD IOP measurement before 0.5% timolol maleate instillation measured 13.89 ± 2.29 mmHg. An average reduction 3.75 ± 2.36 mmHg was found with clinician administration, and an average reduction of 3.32 ± 2.31 mmHg was recorded with the new method. No significance was found in IOP reduction between two groups P < .45. Percent reduction was 25.17 ± 16.21% and 24.38 ± 16.31% in clinician instillation and alternative instillation method group, respectively. No significant difference was found. This percentage reduction was similar to previously reported studies. No reported cases of eye infection or irritation were found in any case, within a 3-month follow-up period.Conclusions: We have proposed a more reliable method for instillation that provides a larger area for instillation and lessen the risk of contamination and patient's fear for eye drops. Similar efficacy was found compared with that of having a clinician directly administer the drop. This alternative method could potentially benefit patients who require topical eye drop therapy and result in increased compliance.
Keywords: Antihypertensive Agents -- Administration and Dosage; Intraocular Pressure -- Drug Effects; Ocular Hypertension -- Drug Therapy; Administration, Intraocular; Timolol -- Administration and Dosage; Crossover Design; Ophthalmic Solutions -- Administration and Dosage; Tonometry; Double-Blind Studies; Human; Adult; Reproducibility of Results; Young Adult; Female; Middle Age; Self Administration; Male; Comparative Studies; Multicenter Studies; Evaluation Research; Validation Studies; Scales

The differences between patient and optometrist experiences of contact lens hygiene education from the perspective of a Scottish university teaching hospital. - Hind, Jennifer; Williams, Olayinka; Oladiwura, Dilys; Macdonald, Elisabeth (Contact Lens & Anterior Eye, 2020)
Background: Contact lens related keratitis is a frequent presentation to acute ophthalmology services. Patients often do not recall being counselled regarding the safe use of contact lenses therefore fail to comply with guidance. This study aimed to identify the content and format of advice given to patients with contact lens keratitis concerning appropriate hygiene practices, determine their compliance with this and finally characterise optometrist practices regarding contact lens advice provided to patients.Methods: All adult patients presenting with contact lens related keratitis to the acute ophthalmology clinic were asked to complete a survey. Information was collected on lens type, format of advice received and compliance. Community optometrists were asked to complete an electronic survey on their contact lens review practices and routine patient education.Results: All patients surveyed recalled counselling on initiation of contact lenses; however 12% (6/50) were given no advice on return visits. This advice was in written format for 20% (10/50) of patients on initiation increasing to 32% (16/50) on renewal. Many patients slept (22%), showered (44%) or swam (36%) in lenses. 92% cleaned their contact lenses appropriately, but cases were washed infrequently (19% of cases cleaned < monthly) or with tap water (27%). All optometrists surveyed claimed to provide advice to patients in either written or verbal format for new and returning contact lens users. 49% (16/33) of optometrists gave written advice to patients on initial contact lens fitting, but only 1/33 continued with written advice for repeat customers.Conclusion: This study identified that although most patients were informed of appropriate hygiene requirements, compliance was poor. Optometrists regularly provide verbal advice but do not routinely offer written support and there is a mismatch between patient recollection and self-reported optometrist practice. It is suggested that patient education needs greater emphasis and both verbal and written information should be regularly provided on initial review and follow up assessments.
Keywords: Education, Medical; Academic Medical Centers; Contact Lenses; Self Report; Hygiene -- Education; Patient Compliance; Prospective Studies; Human; Scotland; Comparative Studies; Multicenter Studies; Evaluation Research; Validation Studies

Resource Planning in Glaucoma: A Tool to Evaluate Glaucoma Service Capacity. - Batra, Ruchika; Sharma, Hannah E; Elaraoud, Ibrahim; Mohamed, Shabbir (Seminars in Ophthalmology, 2018)
Background: The National Patient Safety Agency (2009) publication advising timely follow-up of patients with established glaucoma followed several reported instances of visual loss due to postponed appointments and patients lost to follow-up. The Royal College of Ophthalmologists Quality Standards Development Group stated that all hospital appointments should occur within 15% of the intended follow-up period.Aim: To determine whether: 1. Glaucoma follow-up appointments at a teaching hospital occur within the requested time 2. Appointments are requested at appropriate intervals based on the NICE Guidelines 3. The capacity of the glaucoma service is adequate Methods: A two-part audit was undertaken of 98 and 99 consecutive patients respectively attending specialist glaucoma clinics. In the first part, the reasons for delayed appointments were recorded. In the second part the requested follow-up was compared with NICE guidelines where applicable. Based on the findings, changes were implemented and a re-audit of 100 patients was carried out.Results: The initial audit found that although clinical decisions regarding follow-up intervals were 100% compliant with NICE guidelines where applicable, 24% of appointments were delayed beyond 15% of the requested period, due to administrative errors and inadequate capacity, leading to significant clinical deterioration in two patients. Following the introduction of an electronic appointment tracker and increased clinical capacity created by extra clinics and clinicians, the re-audit found a marked decrease in the percentage of appointments being delayed (9%).Conclusions: This audit is a useful tool to evaluate glaucoma service provision, assist in resource planning for the service and bring about change in a non-confrontational way. It can be widely applied and adapted for use in other medical specialities.
Keywords: Management -- Methods; Glaucoma -- Therapy; Academic Medical Centers -- Administration; Benchmarking -- Methods; Appointments and Schedules; Referral and Consultation -- Standards; Ophthalmology -- Standards; Intraocular Pressure; Patient Compliance; Human; Female; Male; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

Knowledge of medications among patients with glaucoma in Taiwan. - Ko, Mei Lan; Wei, Kai Lin; Ho, Yi-Jung; Peng, Pai Huei; Lu, Henry Horng Shing (Journal of the Formosan Medical Association, 2019)
Background/purpose: To investigate the knowledge and learning ability of glaucoma patients regarding their anti-glaucoma topical medications.Methods: Patients on regular follow-up at the Glaucoma Clinic at Hsin-Chu General Hospital were recruited. After detailed ocular examinations, the participants were asked to recall and identify their glaucoma eye drops. The same test was repeated 3 months later. The results of both tests, the learning ability of patients regarding their glaucoma drugs, and the relationship between learning ability and demographic variables were evaluated.Results: Two hundred eighty-seven glaucoma patients participated in this study. Of the study population, 25.8% and 57.1% could recall their topical mediation at the first and second tests, whereas 72.1% and 88.5% could identify their prescribed eye drops at the first and second tests, respectively. Approximately 34% of the participants showed improved knowledge at the repeat test, whereas 40% of the participants showed no improvement. Participants with a better learning ability were more likely to be younger, with a higher level of education, and with less visual field impairment.Conclusion: The knowledge of glaucoma patients regarding their prescribed medication was deficient in Taiwan. Physician effort could improve knowledge on the prescribed drugs. Patient-centered education should be considered, targeting elderly individuals, illiterate individuals, and those with loss of visual function to increase compliance with glaucoma medication.
Keywords: Attitude to Health; Medication Compliance; Ophthalmic Solutions -- Administration and Dosage; Glaucoma -- Drug Therapy; Intraocular Pressure; Logistic Regression; Aged; Middle Age; Taiwan; Adult; Female; Male; Drug Monitoring; Prospective Studies; Human

Effect of epidermal growth factor ointment on persistent epithelial defects of the cornea. - Moon, Hyun Sik; Li, Lan; Yoon, Hyeon Jeong; Ji, Yong Sok; Yoon, Kyung Chul (BMC Ophthalmology, 2020)
Background: Healthy corneal epithelium acts as a barrier against damage to the deeper structures in the eye. Failure in the mechanisms of corneal epithelization can lead to persistent epithelial defects of the cornea (PEDs) and can compromise its function. Epidermal growth factor (EGF) promotes the proliferation, migration, and differentiation of epithelial cells, endothelial cells, and fibroblasts during wound healing and may be beneficial in treating patients with PEDs. We, therefore, investigated the effect of EGF ointment on patients with PEDs.Methods: Fifteen patients with PEDs refractory to conventional treatment were treated twice a day with EGF ointment. Patient demographics and comorbidities were noted. The epithelial healing time was determined along with the primary outcome measures in the areas of the epithelial defects, visual acuity, visual analog scale (VAS) scores, and esthesiometer scores 1 month and 2 months after treatment.Results: Five eyes of herpetic keratitis (33.3%), 3 eyes of dry eye disease (20.0%), 3 eyes of bacterial keratitis (20.0%), 2 eyes of limbal stem cell deficiency (13.3%), 1 eye of diabetic neurotrophic keratitis (6.7%), and 1 eye of filamentary keratitis (6.7%) were associated with PEDs, respectively. Two months following treatment with EGF ointment, there was a reduction in the area of the epithelial defects (5.7 ± 3.9 to 0.1 ± 0.3 mm2) as well as a significant improvement in best-corrected visual acuity (0.9 ± 0.8 to 0.6 ± 0.5 LogMAR) and VAS scores (4.5 ± 1.2 to 2.5 ± 0.7) in 12 eyes (80%). Among these cases, the mean epithelial healing time was 5.5 ± 1.8 weeks. Amniotic membrane transplantation was performed on the remaining 3 (20.0%) patients that did not respond to EGF treatment.Conclusions: EGF ointment could reduce symptoms and promotes corneal epithelialization of refractory PEDs. It may, therefore, be well-tolerated and a potentially beneficial addition in the management of refractory PEDs.
Keywords: Wound Healing -- Drug Effects; Epidermal Growth Factors -- Administration and Dosage; Ointments -- Administration and Dosage; Corneal Diseases -- Drug Therapy; Epithelium -- Drug Effects; Epithelium -- Physiopathology; Female; Middle Age; Visual Acuity -- Physiology; Epithelium -- Pathology; Male; Adult; Aged, 80 and Over; Aged; Corneal Diseases -- Physiopathology; Time Factors; Corneal Diseases -- Diagnosis

The dropless future: SLT as a first-line treatment for glaucoma. - Chapman, Kristin O. (Ophthalmology Times, 2020)
The article examines the efficacy and safety of using selective laser trabeculoplast (SLT) in the treatment of patients with primary open-angle glaucoma (POAG). Topics discussed include progression of glaucoma medications for POAG, its efficacy in comparison to glaucoma drops, which may cause chronic toxicity and inflammation, and arguments for its cost-efficacy.
Keywords: Glaucoma -- Therapy; Laser Therapy -- Methods; Laser Therapy -- Trends; Trabeculectomy; Medication Compliance; Physicians; Patient Compliance; Cognition Disorders; Laser Therapy -- Economics; Ophthalmic Solutions

Glaucoma experts give perspectives on LiGHT trial: SLT vs. drops. - Gedde, Steven J.; Kahook, Malik Y.; Noecker, Robert J.; Radcliffe, Nathan M.; Rhee, Douglas J.; Samuelson, Thomas W.; Teymoorian, Savak "Sev" (Ocular Surgery News, 2019)
Keywords: Glaucoma -- Therapy; Laser Therapy -- Methods; Trabeculectomy -- Methods; Ophthalmic Solutions -- Therapeutic Use; Cost Benefit Analysis; Patient Education; Patient Compliance

Pandemic spurs paradigm shift in artificial intelligence. - Cimberle, Michela (Ocular Surgery News, 2020)
Keywords: COVID-19 Pandemic; Artificial Intelligence; Health Care Industry; Telehealth; Data Analytics; Health Services Accessibility; Patient Safety; Glaucoma; Disease Progression; Risk Assessment

Investigation of Approval Trends and Benefits of New Fixed-Dose Combination Drugs in Japan. - Kikuchi, Chikara; Ohno, Mifuyu; Izumo, Takafumi; Takahashi, Satoru; Aoki, Masayuki; Shimomura, Hitoshi; Kawano, Yohei; Shimada, Shuji; Aoyama, Takao (Therapeutic Innovation & Regulatory Science, 2020)
Background: New fixed-dose combination drugs (FDCs) had been developed in limited numbers in Japan. Since regulatory requirements were relaxed in 2005, 73 new FDCs have been approved by PMDA since 2006. In this study, we investigate trends in new FDCs and their benefits through a questionnaire survey provided to patients and pharmacists. Methods: The new FDCs were analyzed by therapeutic categories, first approval country and drug lag (DL). Questionnaire surveys were conducted on hypertension, bronchial asthma, and glaucoma in approximately 300 patients and 700 pharmacists in 66 hospitals to investigate the benefits of new FDCs. Results: The highest number of FDCs approved by the therapeutic category was 15 cardiovascular agents. The DL (median) was less than 1 year in several therapeutic categories including cardiovascular agents. The survey results showed that patient compliance improved in 30.8% of the bronchial asthma. Regarding the time and effort required to prescribe these drugs, 32.5% of pharmacists reported "slightly decreased" in bronchial asthma, while 32.0% reported "slightly increased" in hypertension. More than one-third (70.6%) responded "recommend" in bronchial asthma. Conclusion: The number of new FDCs markedly increased since 2006, and this presented new opportunities for the Japanese pharmaceutical industry. FDCs not only increase convenience to the patient but also improve patient compliance and the efficiency of pharmacist prescription processes. However, the rapid increase in new FDCs may cause confusion in the medical field, and new FDCs should be developed not only to improve convenience but also to consider the benefits they provide to patients, pharmacists, and physicians.
Keywords: Drug Therapy, Combination; Drug Approval -- Trends -- Japan; Human; Patients; Pharmacists; Hospitals; Cardiovascular Agents; Japan; Questionnaires; Surveys; Hypertension -- Drug Therapy; Asthma -- Drug Therapy; Glaucoma -- Drug Therapy; Pharmaceutical Companies -- Japan; Medication Compliance; Drugs, Prescription

Automated Framework for Screening of Glaucoma Through Cloud Computing. - Soorya, M.; Issac, Ashish; Dutta, Malay Kishore (Journal of Medical Systems, 2019)
In recent times, the use of computer aided diagnosis for detection of Glaucoma from fundus images has been prevalent. In the proposed work, a cloud based system is proposed for automatic and real-time screening of Glaucoma with the use of automatic image processing techniques. The proposed system offers scalability to the developers and easy accessibility to the consumers. The proposed system is device and location independent. The input digital image is analyzed and a comprehensive diagnostic report is generated consisting of detailed analysis of indicative medical parameters like optic-cup-to-disc ratio, optic neuro-retinal rim, ISNT rules making the report informative and clinically significant. With recent advances in the field of communication technologies, the internet facilities are available that make the proposed system an efficient and economical method for initial screening and offer preventive and diagnostic steps in early disease intervention and management. The proposed system can perform an initial screening test in an average time of 6 s on high resolution fundus images. The proposed system has been tested on a fundus database and an average sensitivity of 93.7% has been achieved for Glaucoma cases. In places where there is scarcity of trained ophthalmologists and lack of awareness of such diseases, the cloud based system can be used as an effective diagnostic assistive tool.
Keywords: Cloud Computing -- Utilization; Glaucoma -- Diagnosis; Health Screening -- Methods; Image Processing, Computer Assisted -- Methods; Automation; Human; Diagnosis, Computer Assisted; Image Interpretation, Computer Assisted; Information Technology; Glaucoma -- Prevention and Control; Disease Management; Sensitivity and Specificity; World Wide Web Applications; Software; Algorithms; Decision Making, Clinical; Funding Source

The views of compliant glaucoma patients on counselling and social support. - Lunnela J; Kääriäinen M; Kyngäs H (Scandinavian Journal of Caring Sciences, 2010)
Scand J Caring Sci; 2010; 24; 490–498 The views of compliant glaucoma patients on counselling and social support The purpose of this study was to describe the views of compliant glaucoma patients with good compliance on patient education and social support they received during their illness. The aim was to gain knowledge for developing patient compliance by means of promoting education and support methods. Twelve glaucoma patients with good compliance were interviewed, and the transcripts based on those interviews were analysed using content analysis. In the data, the participants described education and social support they had received from healthcare personnel, relatives and partly from their peers. Patient education emerged as the content, timing and methods of education. Social support emerged as emotional, informational and instrumental support, lack of support as well as patients’ activity. Consequently, patients need education and support from healthcare personnel as well as from their relatives to cope with glaucoma. The need for education and support is individual but the most important time for education and support is at the initial stages of the illness. The need for education and support is also evident when the patient’s treatment is changed or an operative procedure is performed. To conclude, the individual, patient-centred and properly timed education and support is a huge challenge for healthcare personnel because of the decrease in individual time for each patient. Therefore, new and timesaving methods of education and support should be developed.
Keywords: Patient Attitudes; Patient Compliance; Glaucoma -- Therapy; Support, Psychosocial; Patient Education; Human; Male; Female; Semi-Structured Interview; Qualitative Studies; Audiorecording; Adult; Middle Age; Aged; Content Analysis; Early Intervention; Patient Education -- Methods; Psychosocial Aspects of Illness; Physicians; Nurses; Self Care -- Education; Funding Source

Patterns of care for glaucoma patients in Korea from 2002 to 2013 using the national health insurance service claims data. - Seulggie Choi; Jin A. Choi; Jin Woo Kwon; Sang Min Park; Donghyun Jee; Choi, Seulggie; Choi, Jin A; Kwon, Jin Woo; Park, Sang Min; Jee, Donghyun (Medicine, 2018)
Due to the rapidly increasing life-expectancy, the prevalence of glaucoma has increased steadily in recent years. We aimed to evaluate the patterns of care and primary treatment strategy patterns in Korea according to glaucoma subtypes to assess the quality of care for glaucoma patients.In this serial cross-sectional survey, the claims data from the Korean National Health Insurance Service was used to identify and group glaucoma patients into primary open-angle glaucoma (POAG), primary angle-closure glaucoma (PACG), other types of glaucoma, and ocular hypertension from 2002 to 2013. Records for outpatient visits, hospitalizations, drug prescriptions, admissions, and surgical interventions were used to determine the patterns of care and identify primary treatment strategies.Both the prevalence (0.11% in 2002 to 0.43% in 2013) and incidence rates (0.06% in 2003 to 0.11% in 2013) for glaucoma increased over time. The mean number of outpatient visits increased (4.9-6.0 visits per year), while the proportion of hospitalized patients (2.3-1.0% of patients) and duration of hospital stay (4.5-3.4 days among hospitalized patients) decreased between 2002 and 2013 for patients with POAG. The proportion of patients not being managed by medication or surgery decreased, with POAG and PACG patients receiving medications increasing from 70.9% and 59.2% in 2002 to 88.4% and 63.3% in 2013, respectively. Finally, while the proportion of trabeculectomy decreased (22.2% to 10.0% of surgical procedures in 2002 and 2013, respectively), more patients with PACG have received iridectomy (59.3% to 86.0% of surgical procedures in 2002 and 2013, respectively).Between 2002 and 2013, the pattern of care for both patients with POAG and PACG has shifted toward management by outpatient visits and intervention with anti-glaucoma medications in Korea.
Keywords: Glaucoma -- Epidemiology; Glaucoma, Angle-Closure -- Epidemiology; Trabeculectomy -- Trends; Hospitalization -- Trends; Office Visits -- Trends; Infant; Child, Preschool; Child; Infant, Newborn; South Korea; Female; Aged, 80 and Over; Cross Sectional Studies; Glaucoma -- Therapy; Insurance, Health -- Statistics and Numerical Data; Aged; Adolescence; Prevalence; Male; Adult; Young Adult; National Health Programs -- Statistics and Numerical Data; Glaucoma, Angle-Closure -- Therapy; Incidence; Middle Age; Ferrans and Powers Quality of Life Index

TREATING DRY EYE IN GLAUCOMA. - Patel, Dharmendra (Dave) (Ophthalmology Times, 2018)
The article discusses a study on the need to diagnose and treat dry eye disease (DED) in glaucoma patients. Topics covered include the effects of preservatives in topical glaucoma drops, which when used long-term, increase failure risk in later glaucoma surgery, the link of dry eye disorders to decreased compliance in glaucoma medical treatment, and DED diagnosis methods and therapies for mild, moderate and severe DED patients, and minimally invasive surgical procedures.
Keywords: Glaucoma -- Therapy; Dry Eye Syndromes -- Therapy; Disease Management; Phacoemulsification -- Methods; Cataract Extraction -- Methods; Endoscopy -- Methods; Benzalkonium Compounds -- Therapeutic Use; Cornea -- Pathology; Ophthalmic Solutions -- Therapeutic Use; Dry Eye Syndromes -- Risk Factors; Eye Care; Cyclosporine -- Therapeutic Use

Therapy for Open-Angle Glaucoma. - Marshall, Leisa L; Hayslett, Renée L; Stevens, Gregg A (Consultant Pharmacist, 2018)
Objective: Review the clinical manifestations and treatment of primary open-angle glaucoma (POAG).Data Sources: Articles indexed in PubMed, Scopus, and Cochrane Library in the last 10 years using the key words "glaucoma," "open-angle glaucoma," and "'open-angle glaucoma' AND 'treatment.'" Primary sources were used to locate additional resources. ClinicalTrials. gov was used to locate unpublished studies.Study Selection and Data Extraction: Eighty-one publications were reviewed and criteria supporting the primary objective were used to identify useful resources.Data Synthesis: The literature included practice guidelines, review articles, original research articles, and product prescribing information for POAG.Conclusion: The POAG optic neuropathies result in optic disk damage and visual field loss. Ophthalmic medication therapy retards glaucoma progression, but many older patients require multiple medications to preserve vision and quality of life. An agent from the ophthalmic prostaglandin analog class is used as initial therapy in current practice because of the convenience of once-a-day administration and lower incidence of systemic side effects and slightly increased efficacy compared with other available ophthalmic medication classes. The other ophthalmic medication classes used in clinical practice include the beta-adrenergic blocking agents, the alpha-2 adrenergic agonists, and the carbonic anhydrase inhibitors. Proper ophthalmic eye-drop administration and medication adherence are imperative for preserving vision in POAG. Selective laser trabeculoplasty is a viable alternative to ophthalmic medications either initially or if a patient experiences ocular or systemic side effects from medication therapy. A modified prostaglandin analog was approved by the Food and Drug Administration in November 2017; its role in clinical practice is still evolving.
Keywords: Ophthalmic Solutions -- Therapeutic Use; Glaucoma -- Drug Therapy; Trabeculectomy; Glaucoma -- Surgery; Intraocular Pressure -- Drug Effects; Glaucoma -- Physiopathology; Systematic Review

Sustained-release implant offers long-term IOP control, preserved visual function: Bimatoprost SR represents a paradigm shift in glaucoma treatment. - Charters, Lynda (Ophthalmology Times, 2020)
The article reports that the bimatoprost implant from pharmaceutical firm Allergan has become the first intracameral, biodegradable, sustained-release implant dedicated to reduce intraocular pressure in patients with open-angle glaucoma or ocular hypertension. Topics mentioned include the ARTEMIS phase III study, the impact of the implant on the corneal endothelial cells, and patients' lack of adherence to eyedrop treatment.
Keywords: Glaucoma -- Drug Therapy; Ocular Hypertension -- Drug Therapy; Intraocular Pressure -- Drug Effects; Bimatoprost -- Administration and Dosage; Drug Implants; Delayed-Action Preparations; Clinical Trials; Patient Safety; Treatment Outcomes

Study on Incentives for Glaucoma Medication Adherence (SIGMA): study protocol for a randomized controlled trial to increase glaucoma medication adherence using value pricing. - Bilger, Marcel; Wong, Tina T.; Howard, Kaye L.; Jia Yi Lee; Ai Nee Toh; John, Geraldine; Lamoureux, Ecosse L.; Finkelstein, Eric A.; Lee, Jia Yi; Toh, Ai Nee (Trials, 2016)
Background: Many glaucoma patients do not adhere to their medication regimens because they fail to internalize the (health) costs of non-adherence, which may not occur until years or decades later. Behavioural economic theory suggests that adherence rates can be improved by offering patients a near-term benefit. Our proposed strategy is to offer adherence-contingent rebates on medication and check-up costs. This form of value pricing (VP) ensures that rebates are granted only to those most likely to benefit. Moreover, by leveraging loss aversion, rebates are expected to generate a stronger behavioural response than equivalent financial rewards.Methods/design: The main objective of the Study on Incentives for Glaucoma Medication Adherence (SIGMA) is to test the VP approach relative to usual care (UC) in improving medication adherence. SIGMA is a randomized, controlled, open-label, single-centre superiority trial with two parallel arms. A total of 100 non-adherent (Morisky Medication Adherence Scale ≤6) glaucoma patients from the Singapore National Eye Centre are block-randomized (blocking factor: single versus multiple medications users) into the VP and UC arms in a 1:1 ratio. The treatment received by VP patients will be strictly identical to that received by UC patients, with the only exception being that VP patients can earn either a 50 % or 25 % rebate on their glaucoma-related healthcare costs conditional on being adherent on at least 90 % or 75 % of days as measured by a medication event monitoring system. Masking the arm allocation will be precluded by the behavioural nature of the intervention but blocking size will not be disclosed to protect concealment. The primary outcome is the mean change from baseline in percentage of adherent days at month 6. A day will be counted as adherent when the patients take all their medication(s) within the appropriate dosing windows.Discussion: This trial will provide evidence on whether adherence-contingent rebates can improve medication adherence among non-adherent glaucoma patients, and more generally whether this approach represents a promising strategy to cost-effectively improve chronic disease management.Trial Registration: NCT02271269 . Registered on 19 October 2014.
Keywords: Motivation; Office Visits -- Economics; Health Care Costs; Glaucoma -- Drug Therapy; Insurance, Health, Reimbursement; Medication Compliance; Glaucoma -- Economics; Glaucoma -- Diagnosis; Risk Factors; Treatment Outcomes; Human; Singapore; Study Design; Aged; Attitude to Health; Risk Assessment; Middle Age; Male; Female; Time Factors; Young Adult; Adult; Aged, 80 and Over; Glaucoma -- Psychosocial Factors; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

A Worldwide Price Comparison of Glaucoma Medications, Laser Trabeculoplasty, and Trabeculectomy Surgery. - Zhao, Peter Y.; Rahmathullah, Raheem; Stagg, Brian C.; Almobarak, Faisal; Edward, Deepak P.; Robin, Alan L.; Stein, Joshua D. (JAMA Ophthalmology, 2018)
Importance: Medical and surgical interventions for glaucoma are effective only if they are affordable to patients. Little is known about how affordable glaucoma interventions are in developing and developed countries.Objective: To compare the prices of topical glaucoma medications, laser trabeculoplasty, and trabeculectomy relative with median annual household income (MA-HHI) for countries worldwide.Design, Setting and Participants: Cross-sectional observational study. For each country, we obtained prices for glaucoma medications, laser trabeculoplasty, and trabeculectomy using government pricing data, drug databases, physician fee schedules, academic publications, and communications with local ophthalmologists. Prices were adjusted for purchasing power parity and inflation to 2016 US dollars, and annual therapy prices were examined relative to the MA-HHI. Interventions costing less than 2.5% of the MA-HHI were considered affordable.Main Outcomes and Measures: Daily cost for topical glaucoma medications, cost of annual therapy with glaucoma medications, laser trabeculoplasty, and trabeculectomy relative to MA-HHI in each country.Results: Data were obtained from 38 countries, including 17 developed countries and 21 developing countries, as classified by the World Economic Outlook. We observed considerable variability in intervention prices compared with MA-HHI across the countries and across interventions, ranging from 0.1% to 5% of MA-HHI for timolol, 0.1% to 27% for latanoprost, 0.2% to 17% for laser trabeculoplasty, and 0.3% to 42% for trabeculectomy. Timolol was the most affordable medication in all countries studied and was 2.5% or more of MA-HHI in only 2 countries (5%). The annual cost of latanoprost was 2.5% or more of MA-HHI in 15 countries (41%) (15 developing countries [75%] and no developed countries). The cost of laser trabeculoplasty was 2.5% or more of the MA-HHI in 15 countries (44%) (11 developing countries [65%] and 4 developed countries [24%]). The cost of trabeculectomy was 2.5% or more of the MA-HHI in 28 countries (78%) (18 developing countries [95%] and 10 developed countries [59%]). In 18 countries (53%), laser trabeculoplasty cost less than a 3-year latanoprost supply.Conclusions and Relevance: For many patients worldwide, the costs of medical, laser, and incisional surgical interventions were 2.5% or more of the MA-HHI. Successfully reducing global blindness from glaucoma requires addressing multiple contributing factors, including making glaucoma interventions more affordable.
Keywords: Antihypertensive Agents -- Economics; Laser Therapy -- Economics; Glaucoma -- Economics; Glaucoma -- Therapy; Trabeculectomy -- Economics; Glaucoma -- Surgery; Health Services Accessibility -- Economics; Health Care Costs; Human; Male; Administration, Intraocular; Costs and Cost Analysis; Cross Sectional Studies; Intraocular Pressure; Income; Female; Glaucoma -- Drug Therapy; Middle Age; World Health; Timolol -- Economics; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Funding Source

Effectiveness of multiple therapeutic strategies in neovascular glaucoma patients: A PRISMA-compliant network meta-analysis. - Zixian Dong; Jianyang Gong; Rongfeng Liao; Shaojun Xu; Dong, Zixian; Gong, Jianyang; Liao, Rongfeng; Xu, Shaojun (Medicine, 2018)
Purpose: Neovascular glaucoma (NVG) is a severe secondary glaucoma with uncontrolled intraocular pressure that leads to serious eye pain and vision loss. Presently, the therapeutic strategies for NVG are diverse, but the therapeutic effects are still not ideal. We performed a network analysis to assess the effect of multiple therapeutic strategies on the treatment of NVG patients.Methods: We searched public electronic databases through April 2017 using the following keywords "neovascular glaucoma," "iris neovascularization," "hemorrhagic glaucoma," and "random" without language restrictions. The outcome considered in the present analysis was treatment success rate. A network meta-analysis and multilevel mixed-effects logistic regression were used to compare regimens.Results: We included 27 articles assessing a total of 1884 NVG patients in our analysis. According to the network analysis, interferon and mitomycin plus trabeculectomy (94.9%), glaucoma valve implantation (86.9%), and iris photocoagulation plus trabeculectomy (81.9%) were the most likely to improve treatment success rate in NVG patients. The multilevel logistic regression analysis showed that glaucoma valve, bevacizumab, interferon, cyclophotocoagulation, trabeculectomy, iris photocoagulation, ranibizumab, and mitomycin had advantages in terms of improving treatment success rate in NVG patients. However, the application of retinal photocoagulation and vitrectomy reduced patient treatment success rate.Conclusion: The regimen including mitomycin, interferon, and trabeculectomy was the most likely to improve the treatment success rate in NVG patients. The application of glaucoma valve and bevacizumab were more beneficial for improving patient treatment success rate as a surgery and as an agent, respectively.
Keywords: Glaucoma -- Therapy; Angiogenesis Inhibitors -- Therapeutic Use; Trabeculectomy -- Methods; Antiinfective Agents -- Therapeutic Use; Eye Surgery -- Methods; Human; Combined Modality Therapy -- Methods; Iris -- Surgery; Retina -- Surgery; Mitomycins -- Therapeutic Use; Treatment Outcomes; Interferons -- Therapeutic Use; Meta Analysis; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

Barriers to glaucoma case finding as perceived by optometrists in Ireland. - Barrett, Catriona; O'Brien, Colm; Butler, John S.; Loughman, James (Clinical & Experimental Optometry, 2018)
Background: This research was designed to provide an in-depth exploration of the perceptions of optometrists relating to the challenges of glaucoma case finding in the Irish health-care system.Methods: A survey was developed, piloted and distributed for anonymous completion by optometrists registered to practise in Ireland. The survey included 10 five-level Likert items exploring potential barriers to glaucoma detection and a free-text box for participants to comment more broadly.Results: One hundred and ninety-nine optometrists (27 per cent of registrants) responded to the survey. Among the barriers identified, there was notable agreement (71 per cent) with the need for extra training on glaucoma detection. Logistic regression showed that optometrists without postgraduate qualifications were more likely to agree with the need for extra training (OR 3.2, 95 per cent CI 1.3-8.1). Respondents largely agreed (61 per cent) that patient unwillingness to pay additional fees for supplementary glaucoma-specific tests was also a barrier. Appointment times of less than 30 minutes were significantly associated with six of the 10 proposed barriers to glaucoma detection. A logistic regression analysis (n = 179) confirmed that the time allotted per appointment was a significant predictor of the agreement time of optometrists as a barrier (χ2 [1] = 13.52, p < 0.001). Multiple linear regression showed that optometrists with less experience, charging lower fees, and working in large multiples or franchised practices have the shortest appointment times.Conclusion: The strong link found between postgraduate education and the confidence of optometrists in detecting glaucoma indicates that optometrists wishing to increase their scope of practice in the new legislative environment in Ireland may more actively seek training in areas of interest. The responses also indicate a lack of funding for the level of diagnostic testing required for accurate glaucoma diagnosis. Recent increases in the state's eye examination fees look likely to address the identified time and financial barriers to glaucoma detection in Ireland. Future work should look to analyse the effects of increased funding on optometric case finding for glaucoma.
Keywords: Attitude to Health; Glaucoma -- Diagnosis; Optometry -- Manpower; Health Care Delivery -- Administration; Diagnosis, Eye -- Statistics and Numerical Data; Glaucoma -- Epidemiology; Retrospective Design; Ireland; Morbidity -- Trends; Human; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

A Rare Case of KID Syndrome: The Use of Hydrosurgery and Strategies for Antiseptic Wound Care. - Kapila, Ayush K. MBBS, MD, MRCS; De Baerdemaeker, Randy MD; Bakal, Fadi MD; Hanssens, Valerie MSc; Spinnael, Jeannine MSc; Hendrickx, Benoit MD, PhD; Zeltzer, Assaf MD, PhD; Hamdi, Moustapha MD, PhD (Advances in Skin & Wound Care, 2019)
A 14-year-old girl with a history of keratitis-ichthyosis-deafness (KID) syndrome, a rare autosomal dominant condition, was referred to the Department of Plastic Surgery at Brussels University Hospital in June 2016 for progressively worsening inguinoperineal ulceration exacerbated by overapplication of combination drug treclinax (tretinoin and erythromycin). On assessment, a large area of purulent papillomatous hyperkeratosis with follicular plugging, likely superimposed bacterial colonization, and deep ulceration were noted requiring thorough debridement. A first procedure was performed in June 2016 with hydrosurgical debridement (Versajet IITM; Smith & Nephew, Forth Worth, Texas). During the procedure, significant blood loss was noted, and topical adrenaline, blood transfusion, and a short ICU stay were required for monitoring during which the patient remained hemodynamically stable. The wound was primarily dressed with an antimicrobial barrier silver dressing; meropenem, ceftazidime, and fluconazole were started to treat for Gram-negative, Gram-positive, and anaerobic bacilli, as well as Pseudomonas aeruginosa and fungal infections in situ. A further three debridements were required 6, 12, and 26 days after the initial procedure. The patient was discharged 36 days after admission without any antibiotics and with an outpatient wound care plan. Not only was this case rare, but it also reflected the importance of a careful approach when tackling KID syndrome's cutaneous manifestations. Multiple debridements, thorough wound care, and appropriate antibiotic therapy may be required to achieve local healing and a satisfactory result. Hydrosurgical debridement offered a precise and well-controlled method for treating a large ulcerating hyperkeratotic urogenital lesion in this pediatric patient.
Keywords: Keratitis -- Drug Therapy; Deafness -- Drug Therapy; Ichthyosis -- Drug Therapy; Ulcer -- Diagnosis; Groin -- Pathology; Perineum -- Pathology; Ulcer -- Therapy; Hydrotherapy; Wound Care; Female; Adolescence; Antimicrobial Dressings; Debridement

Attributes Associated with Adherence to Glaucoma Medical Therapy and its Effects on Glaucoma Outcomes: An Evidence-Based Review and Potential Strategies to Improve Adherence. - Joseph, Arun; Pasquale, Louis R. (Seminars in Ophthalmology, 2017)
The treatment paradigm in glaucoma classically starts with exhausting all medical therapy prior to proceeding with laser or incisional surgery, although laser-first and surgery-first strategies have been explored in randomized clinical trials. Although glaucoma drops are proven to work well to lower intraocular pressure, slow the conversion from ocular hypertension, and slow the progression of disease in early open angle glaucoma, adherence to treatment is likely optimum in the randomized clinical trials that support these claims. In real-world scenarios, medical therapy often fails and practitioners are forced to proceed with more invasive treatment modalities to slow the progression of this blinding disease. This review aims to take an evidence-based approach to study the risk factors for poor adherence in glaucoma patients, to determine whether poor adherence is, in fact, associated with worse outcomes, and to seek potential strategies to improve adherence in these patients.
Keywords: Intraocular Pressure -- Drug Effects; Medication Compliance; Antihypertensive Agents -- Therapeutic Use; Glaucoma -- Drug Therapy; Tonometry; Patient Education; Human; Medical Practice, Evidence-Based; Risk Factors; Treatment Outcomes; Reminder Systems; Arthritis Impact Measurement Scales; Clinical Assessment Tools; Scales

Laser as first line therapy could change paradigm of treatment for glaucoma. - Cimberle, Michela (Ocular Surgery News, 2019)
Keywords: Laser Therapy -- Methods; Trabeculectomy -- Methods; Glaucoma -- Surgery; Glaucoma -- Diagnosis; Ocular Hypertension -- Diagnosis; Ocular Hypertension -- Prevention and Control; Health Care Costs; Trabeculectomy -- Adverse Effects; Laser Therapy -- Adverse Effects; Health Services Accessibility; Ophthalmic Solutions -- Therapeutic Use; Treatment Outcomes; Severity of Illness; Medical Practice; Paradigms

Newly developed tool can identify factors that affect glaucoma medication adherence. - Linnehan, Robert (Ocular Surgery News, 2020)
Keywords: Clinical Assessment Tools; Glaucoma -- Drug Therapy; Medication Compliance; Health Behavior; Questionnaires

Level of adherence to ocular hypotensive agents and its determinant factors among glaucoma patients in Menelik II Referral Hospital, Ethiopia. - Mehari, Tesfay; Giorgis, Abeba T.; Shibeshi, Workineh (BMC Ophthalmology, 2016)
Background: Good adherence to ocular hypotensive agents is important to control intraocular pressure and hence to prevent progressive glaucomatous optic nerve head damage. Periodic investigation of adherence is crucial in glaucoma treatment. The purpose of this study was to assess level of adherence to ocular hypotensive agents and to identify factors affecting adherence among glaucoma patients at a tertiary public eye care center.Methods: The study was a hospital-based cross-sectional study that was conducted in Menelik II Referral Hospital from June 1, 2015 to July 31, 2015. A systematic random sampling technique was used to select 359 study participants from the source population. The study patients were interviewed and their medical charts were reviewed using a pretested structured questionnaire. Adherence was assessed using Morisky Medication Adherence Scale - 8 and adherence determinant factors were identified using multivariate binary logistic regression analysis. The association was declared statistically significant at p < 0.05.Results: Among the 359 study glaucoma patients, 42.6 % were adherent to their prescribed hypotensive agents. Higher educational level (AOR = 4.60, 95 % CI: 1.01-21.03, p < 0.049), being self - employed (AOR = 6.14, 95 % CI: 1.37-27.50, p < 0.018) and taking lesser frequency of drops (AOR = 2.89, 95 % CI: 1.25-6.66, p < 0.013) were significantly associated with adherence, whereas being a farmer (AOR = 0.07, 95 % CI: 0.01-0.75, p < 0.028), having very low monthly family income (AOR = 0.22, 95 % CI: 0.06-0.77, p < 0.019) and self - purchasing of medications (AOR = 0.30, 95 % CI: 0.10-0.93, p < 0.036) were significantly associated with non-adherence.Conclusions: The study has identified the adherence level to the prescribed ocular hypotensive agents to be sub-optimal and is influenced by different factors among glaucoma patients of the public tertiary center. We recommend glaucoma care providers to pay due attention on the importance of adherence.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Antihypertensive Agents -- Therapeutic Use; Intraocular Pressure; Aged; Employment; Middle Age; Educational Status; Adult; Cross Sectional Studies; Ophthalmic Solutions -- Therapeutic Use; Aged, 80 and Over; Socioeconomic Factors; Risk Factors; Ethiopia; Female; Young Adult; Multivariate Analysis; Male; Attitude to Health; Human

Utilization of Outpatient Eye Care Services in Taiwan: A Nationwide Population Study. - Hsu, Chia-An; Hsiao, Sheng-Huang; Hsu, Min-Huei; Yen, Ju-Chuan (Journal of Ophthalmology, 2020)
Introduction. A study based on the Taiwanese National Health Insurance Research Database (NHIRD) to reveal the ocular diseases landscape. Materials and Methods. This study comprised all ophthalmological outpatient patient visits (n = 6,341,266) in the Taiwanese longitudinal NHIRD 2000. Descriptive analytics based on 15 disease categories of ICD-9-CM and 10 tiers of age categories was performed with SAS for Windows 9.3 (SAS Institute, Inc., Cary, NC, U.S.A.). Results. The average frequency of visits was 0.7 visits per year. The mean age was 36.2 years old. Bimodal peak of visits in the first, second, and eighth decade of life was revealed. Conjunctiva is the most dominant disease category throughout life while different categories play major roles in each decade of life. The most frequent disease code of each category was listed. Discussion. The bimodal peak of visits revealed the age group of the most prominent ocular disease burden. Peak in school age population can be partially explained by the nationwide vision screening program, while aging accounts for the lens disorder and glaucoma of the senile peak. The disease category frequency variation among age categories reflects the development and aging of the eye. The most frequent disease codes of each category highlight disease of importance for primary practitioners and ophthalmologists. Conclusion. Taiwanese longitudinal NHIRD was used to reveal the ophthalmological disease landscape. The epidemiological insight, while limited in clinical presentation and economic impact, enables physicians and policy makers to improve the overall vision health of the population.
Keywords: Outpatient Service -- Utilization -- In Adulthood; Eye Care -- Utilization -- In Adulthood; Health Resource Utilization -- Taiwan; Human; Taiwan; Office Visits; Prospective Studies; Descriptive Research; International Classification of Diseases; Adult; Conjunctival Diseases -- Therapy; Diagnosis, Eye; Aging; Glaucoma; Ophthalmologists

Systematic Review of Knowledge Assessments for Glaucoma Patients. - Peralta, Esteban; Muir, Kelly W.; Rosdahl, Jullia A. (Seminars in Ophthalmology, 2018)
Glaucoma is a chronic eye disease affecting millions of people worldwide; it is frequently treated with daily eyedrop medications when patients are asymptomatic. Patient education is an essential feature for adherence to treatments. Developing useful patient education interventions is predicated on understanding what glaucoma patients know about their disease and identifying gaps in their knowledge. Thirteen studies that have measured and described glaucoma patient knowledge using questionnaires were identified from the literature, including cross-sectional studies of disease knowledge and studies evaluating the efficacy of an educational intervention, both randomized controlled and observational. All studies found significant knowledge gaps in glaucoma patients. Both the controlled studies and the observational studies supported the efficacy of various educational interventions for improving glaucoma knowledge.
Keywords: Glaucoma -- Etiology; Medication Compliance; Glaucoma -- Drug Therapy; Attitude to Health; Human; Cross Sectional Studies; Quality of Life; Patient Satisfaction; Patient Education -- Methods; Systematic Review

Patient attitudes toward novel glaucoma drug delivery approaches. - Wang, Benjamin B.; Lin, Michael M.; Nguyen, Thuan; Turalba, Angela V. (Digital Journal of Ophthalmology, 2018)
Purpose--Understanding patients' attitudes toward novel therapeutic options can help guide providers in personalizing treatment regimens for glaucoma patients. This study aimed to determine factors associated with acceptance of new drug delivery options among glaucoma patients. Methods--A total of 199 patient volunteers participated in an interviewer-administered survey from June to August 2016 at the Glaucoma Service of Massachusetts Eye and Ear. The questionnaire was designed to determine acceptance of 6 drug delivery approaches: (1) triple combination eye drop, (2) microdose eye spray, (3) drug-eluting contact lens, (4) drug-eluting periocular ring insert, (5) injectable subconjunctival drug insert, and (6) injectable anterior chamber implant. Other factors analyzed included self-reported demographics, disease severity, and prior ocular history. Results--The average respondent age was 63.2 ± 15.1 years; 48% were female. For approaches 1-6 listed above, overall acceptance rates were, respectively, 85%, 54%, 31%, 43%, 32%, and 30%. Patients with greater disease severity and prior incisional glaucoma surgery were more likely to pursue alternatives to traditional eye drops. Conclusions--There is limited acceptance of alternatives to traditional eye drop medications among glaucoma patients. Understanding motivating factors and potential barriers to patient acceptance of novel drug delivery approaches is important in how providers will incorporate these glaucoma treatment options into practice.
Keywords: Glaucoma -- Therapy; Patient Attitudes; Drug Delivery Systems; Human; Surveys; Questionnaires; Ophthalmic Solutions; Drug Combinations; Contact Lenses; Self Report; Severity of Illness; Male; Female; Middle Age; Aged; Eye, Artificial; Glaucoma -- Surgery

THE MAGNIFICENT 7: How many glaucoma medications are too many? Patient tolerance of and compliance with complex regimens are key. - Charters, Lynda; Serle, Janet B. (Ophthalmology Times, 2019)
The article offers guides to optimal, most effective and reasonable intraocular pressure (IOP) lowering glaucoma medications. Topics include insight from Dr. Janet Serle of the Icahn School of Medicine on finding the right balance surrounding the number of anti-glaucoma medications that take into considerations various factors including regimen complexity, cost, side effects, physical and mental status of patient. Also discussed are past treatment practices by ophthalmologists for glaucoma.
Keywords: Glaucoma -- Drug Therapy; Antihypertensive Agents -- Administration and Dosage; Polypharmacy; Drug Tolerance; Medication Compliance; Intraocular Pressure -- Drug Effects; Treatment Outcomes; Drug Therapy, Combination; Prescribing Patterns; Individualized Medicine

Prescribing Trends in a Glaucoma Clinic and Adherence to EGS Guidelines: A Retrospective, Non-Interventional, Single-Center UK Study. - Fajgenbaum, Mark; Ansari, Ejaz (Advances in Therapy, 2017)
Introduction: The purpose of this study was to determine prescribing trends in a specialist glaucoma clinic in the UK. Specifically, the aims were to determine which drugs were prescribed as first-, second-, and third-line treatment, the persistence of first-, second-, and third-line treatment regimens, and the proportion of treatment decisions conforming to the European Glaucoma Society (EGS) guidelines.Methods: A retrospective, non-interventional, single-center, case-note review was performed on a cohort of consecutive patients presenting to a specialist glaucoma clinic for follow-up. Inclusion criteria for the study were (1) a diagnosis of primary open-angle glaucoma or ocular hypertension, (2) glaucoma management entirely within the unit, and (3) minimum of 2 years of follow-up.Results: A total of 114 case notes met the inclusion criteria. Mean age was 71 years (range 40-95 years). Mean length of follow-up was 56 months (range 24-180 months). Prostaglandin analogues (PGA) were the most popular first-line treatment in 73% of patients. As second-line treatment, PGA were again the predominant class, prescribed in 87% of cases, whereas beta-blockers (BB) were prescribed in 70% of cases. Carbonic anhydrase inhibitors (CAI) and alpha-2 agonists (AA) were more popular in third-line regimens. Second-line treatment was introduced at a mean of 28.0 months after first-line treatment (range 1-120 months, 95% CI 22.1-33.9 months). Third-line treatment was introduced at a mean of 22.9 months after second-line treatment (range 1-96 months, 95% CI 17.1-28.8 months). Breaches to EGS guidelines were most common for third-line treatment and included duplication of drug classes.Discussion: There was a clear hierarchy of PGA as first-line, BB as second-line, while CAI and AA were considered third-line choices. First-line choices were generally in line with EGS guidelines. There was a tendency to breach guidelines by escalating treatment in dual steps rather than single steps (especially in third-line treatment). Combination drops were popular. In third-line treatment there was an increased incidence of prescribing errors. This data is important in terms of informing patients of the expected treatment course, to remind clinicians about best practice, and also to guide comparisons of cost-effectiveness with other treatment modalities.
Keywords: Prescriptions, Drug -- Statistics and Numerical Data; Antihypertensive Agents -- Therapeutic Use; Glaucoma -- Drug Therapy; Practice Guidelines; Prostaglandins, Synthetic -- Therapeutic Use; Human

The Impact of Adherence and Instillation Proficiency of Topical Glaucoma Medications on Intraocular Pressure. - Atey, Tesfay Mehari; Shibeshi, Workineh; T. Giorgis, Abeba; Asgedom, Solomon Weldegebreal (Journal of Ophthalmology, 2017)
Background. The possible sequel of poorly controlled intraocular pressure (IOP) includes treatment failure, unnecessary medication use, and economic burden on patients with glaucoma. Objective. To assess the impact of adherence and instillation technique on IOP control. Methods. A cross-sectional study was conducted on 359 glaucoma patients in Menelik II Hospital from June 1 to July 31, 2015. After conducting a Q-Q analysis, multiple binary logistic analyses, linear regression analyses, and two-tailed paired t-test were conducted to compare IOP in the baseline versus current measurements. Results. Intraocular pressure was controlled in 59.6% of the patients and was relatively well controlled during the study period (mean (M) = 17.911 mmHg, standard deviation (S) = 0.323) compared to the baseline (M=20.866 mmHg, S=0.383, t (358) = −6.70, p<0.0001). A unit increase in the administration technique score resulted in a 0.272 mmHg decrease in IOP (p=0.03). Moreover, primary angle-closure glaucoma (adjusted odds ratio (AOR) = 0.347, 95% confidence interval (CI): 0.144–0.836) and two medications (AOR = 1.869, 95% CI: 1.259–9.379) were factors affecting IOP. Conclusion. Good instillation technique of the medications was correlated with a reduction in IOP. Consequently, regular assessment of the instillation technique and IOP should be done for better management of the disease.
Keywords: Medication Compliance; Instillation, Drug; Administration, Topical; Glaucoma -- Drug Therapy; Intraocular Pressure; Antihypertensive Agents -- Therapeutic Use; Human; Cross Sectional Studies; Multiple Logistic Regression; Linear Regression; Paired T-Tests; Glaucoma, Angle-Closure -- Drug Therapy; Odds Ratio; Confidence Intervals; Antihypertensive Agents -- Administration and Dosage

Patient-Physician Communication on Medication Cost during Glaucoma Visits. - Slota, Catherine; Davis, Scott A.; Blalock, Susan J.; Carpenter, Delesha M.; Muir, Kelly W.; Robin, Alan L.; Sleath, Betsy (Optometry & Vision Science, 2017)
Significance: This article is the first to investigate the nature of medication cost discussions between ophthalmologists and glaucoma patients. Only 87 of the 275 office visits analyzed had a discussion of medication cost. Providers should consider discussing medication cost with patients to identify potential cost-related barriers to medication use.Purpose: Glaucoma is an incurable chronic eye disease affecting a growing portion of the aging population. Some of the most commonly utilized treatments require lifelong use, requiring high patient adherence to ensure effectiveness. There are numerous barriers to glaucoma treatment adherence in the literature, including cost. The aim of this secondary analysis was to describe the frequency and nature of patient-physician communication regarding medication cost during glaucoma office visits.Methods: This was a mixed-methods secondary analysis of video-recorded participant office visits (n = 275) from a larger observational study of glaucoma communication. We analyzed medical information, demographic characteristics, and interviewer-administrated questionnaires, as well as verbatim transcripts of interviews.Results: Only 87 participants discussed medication cost during their glaucoma office visit. The majority of the subjects who discussed cost had mild disease severity (51%), took one glaucoma medication (63%), and had Medicare (49%) as well as a form of prescription insurance (78%). The majority of glaucoma office visits did not discuss medication cost, and providers often did not ask about cost problems. Of the few conversations related to cost, most focused on providers offering potential solutions (n = 50), medical and prescription service coverage (n = 41), and brand or generic medication choices (n = 41).Conclusions: Our findings are similar to previous studies showing few patients have conversations with providers about the cost of glaucoma medications. Providers should consider bringing up medication cost during glaucoma office visits to prompt a discussion of potential cost-related barriers to medication use.
Keywords: Antihypertensive Agents -- Economics; Communication; Consumer Participation -- Statistics and Numerical Data; Glaucoma -- Economics; Health Care Costs; Physician-Patient Relations; Glaucoma -- Drug Therapy; Female; Aged; Aged, 80 and Over; Office Visits; Adult; Male; Patient Compliance; Middle Age; Funding Source; Human

Influence of Cost of Care and Adherence in Glaucoma Management: An Update. - Meier-Gibbons, Frances; Töteberg-Harms, Marc (Journal of Ophthalmology, 2020)
The costs for glaucoma care are rising worldwide. The main reason is the increase of life expectancy and the increasing variety of diagnostic tests and therapeutically options by implants and devices. How can we influence the increase in costs? Does a relationship exist between the rising costs and the behavior of patients especially in regard to adherence of patients to the prescribed therapy? Are there ways to improve adherence? The costs of a disease can be estimated by adding the direct costs and the indirect costs deriving from the disease. Many studies have been looking at the direct costs, for example, the costs of diagnostic tests and treatment modalities. Unfortunately, not many studies investigated the indirect costs, i.e., costs related to the need of a person to accompany the patient during his or her outpatient visits or the costs deriving from loss of work capacity because of the disease itself or the outpatient visits. Adherence or the synonym compliance has been discussed since many years, and it seems that it remains a major problem in the management of many chronic diseases. Despite all efforts to improve adherence, the adherence rate in chronic diseases such as glaucoma or arterial hypertension remains considerably low. One of the main factors in improving adherence is raising patient's awareness of the disease by providing general understanding of their disease. Other important factors are simplified therapeutic regimens, e.g., fixed combination drops, sustained drug release techniques, or new glaucoma surgical procedures with a more favorable risk profile.
Keywords: Glaucoma -- Economics; Glaucoma -- Diagnosis; Glaucoma -- Therapy; Health Care Costs; Patient Compliance; Economic Aspects of Illness; Disease Management; Life Expectancy; Outpatient Service -- Economics; Chronic Disease -- Economics; Delayed-Action Preparations; Ophthalmic Solutions -- Therapeutic Use; Eye Surgery -- Methods; Risk Assessment

Medication adherence in patients with ocular hypertension or glaucoma. - Robin, Alan L.; Muir, Kelly W. (Expert Review of Ophthalmology, 2019)
Introduction: Nonadherence to medication is a challenge to effective treatment of many chronic diseases, including glaucoma, and persists even with interventions aimed at improving adherence. The reported rates of nonadherence to topical glaucoma medication vary widely from 16% to 67%, and it is estimated that less than a third of patients remained on their initial therapy after 12 months. Nonadherence can lead to disease progression and increased economic burden. Areas covered: This review examines factors that contribute to nonadherence in patients with glaucoma, including the severity of the disease, complexity of treatment, lack of knowledge in patients, poor communications between physician and patient, difficulty with self-administration of drops, side-effects, and medication costs. We discuss the unique challenges in identifying nonadherence in glaucoma patients and investigate the current approaches to improving adherence. Expert opinion: Strategies for improving adherence should combine new treatment methods with enhanced patient education. New pharmaceuticals may comprise multiple medications in a single bottle, making dosing regimens simpler. Novel drug delivery systems are in development, such as injectable products and implants releasing IOP-lowering medication without the need for self-administration. A comprehensive approach involving these new methods and more effective patient-physician communication may lead to improved adherence.
Keywords: Medication Compliance; Ocular Hypertension -- Drug Therapy; Glaucoma -- Drug Therapy; Disease Progression; Health Care Costs; Severity of Illness; Health Knowledge; Physician-Patient Relations; Patient Education; Infusion Pumps, Implantable; Drug Delivery Systems

INPATIENT CARE: STICKING TO GLAUCOMA THERAPY REGIMENS KEY: Study finds medication rates increase when insurance providers are educated about importance. - Charters, Lynda; Mammo, Danny A. (Ophthalmology Times, 2020)
The article discusses a nonrandomized comparative retrospective study which showed an increase in the topical glaucoma medication adherence rate among inpatients who have been educated about the importance of continuous glaucoma treatment. Topics covered are the educational interventions provided to patients, association of adherence with other factors including length of the hospital stay and numbers and types of medications and outpatient medication regimen and correct admission prescribing.
Keywords: Glaucoma; Eye Care; Medication Compliance; Treatment Outcomes; Inpatients; Ophthalmologists -- Psychosocial Factors; Attitude of Health Personnel; Reminder Systems; Patient Compliance

Compliance of Glaucoma Patients to Ocular Hypotensive Medications Among the Saudi Population. - Osman, Essam A.; Alqarni, Bader Ahmed Mousa; AlHasani, Sara Salem Humaid; Al Harbi, Shatha Saleh Suliman; Gikandi, Priscilla Wairimu; Mousa, Ahmed (Journal of Ocular Pharmacology & Therapeutics, 2016)
Purpose: To evaluate the compliance of glaucoma patients to medical treatment and its impact on the intraocular pressure (IOP) and to verify the associated risk factors for noncompliance.Methods: All recruited patients were examined at the ophthalmology clinics of King Abdulaziz University Hospital, Riyadh, Saudi Arabia between May and August 2012. Patients were interviewed and subjected to answer a questionnaire that was developed based on a pilot test. Collected data included age, gender, number of prescribed drugs, and different reasons for noncompliance to the prescribed drugs.Results: Noncompliance was detected in 18 (19.4%) of the recruited patients. Factors associated with noncompliance demonstrated a trend toward older patients, males, patients with lower IOP at presentation, higher cup to disc ratio, and drug self-administering patients. However, the only statistically significant characteristic was being under lifelong medications (P = 0.005).Conclusion: Noncompliance was detected in around one-fifth of our glaucoma patients, particularly, the older group. Awareness programs, maintaining good patient-physician relationship, and personalizing treatment can lead to better adherence to treatment.
Keywords: Patient Compliance; Antihypertensive Agents -- Therapeutic Use; Glaucoma -- Drug Therapy; Ocular Hypertension -- Drug Therapy; Adult; Adolescence; Risk Factors; Intraocular Pressure -- Drug Effects; Cross Sectional Studies; Antihypertensive Agents -- Pharmacodynamics; Male; Aged, 80 and Over; Saudi Arabia; Aged; Young Adult; Antihypertensive Agents -- Administration and Dosage; Female; Middle Age; Impact of Events Scale; Interview Guides

Cysteamine eye drops in the treatment of cystinosis - an Australian perspective. - Radojkovic, Branko (Journal of Pharmacy Practice & Research, 2015)
Cystinosis is a rare but very serious genetic disorder. Advancements in medical science, in the past few decades, have transformed this previously terminal condition into a manageable disease. Ophthalmic sequelae of cystinosis are caused by accumulation of cystine crystals in ocular tissues and are very troublesome for most cystinosis patients. Accumulation of crystals in the cornea causes debilitating photophobia and pain that does not respond to systemic cysteamine therapy. If left untreated, this can lead to structural damage (corneal ulcers, scarring and band keratopathy) and eventually result in corneal blindness requiring corneal transplant. Topical ophthalmic application of cysteamine can alleviate the symptoms and, if instituted early, may prevent the damage. There is no commercially manufactured ophthalmic cysteamine product available in Australia and patients who receive treatment are usually supplied with extemporaneously prepared cysteamine eye drops or ointment. Stability issues, various factors influencing product effectiveness and patient adherence are only few of the problems that make formulation and compounding of cysteamine ophthalmic products a complex task.
Keywords: Metabolism, Inborn Errors -- Complications; Corneal Diseases -- Drug Therapy; Amines -- Administration and Dosage; Ophthalmic Solutions; Ointments; Drug Compounding; Patient Safety; Medication Compliance; Corneal Diseases -- Symptoms; Photophobia; Eye Pain

Komplians styrket efter deltagelse i glaukomskole. - Larsen, Anghelina; Solbæk Nielsen, Ulla; Frølund, Jannie Christina (Sygeplejersken / Danish Journal of Nursing, 2015)
Glaucoma is the second leading cause of blindness worldwide. Approx. 30-50,000 Danes have glaucoma, and almost as many are presumed to have the disease unawares. Low compliance is more prevalent than commonly assumed and carries an increased risk of blindness. In 2008, the Ophthalmology Department, Vejle Hospital and Vejle Local Authority established a group-based glaucoma training programme to inform patients about the disease, its consequences and compliance. In the interests of optimising the glaucoma training programme, a qualitative study was conducted based on 12 interviews with three women and three men. The interviews were analysed by applying S. Kvale's interpretative method. The study indicates that the training programme was well-designed, that it provides information and practical skills in coping with the disease and in communicating with the patient's own ophthalmologist. The study also reveals that the programme strengthens participant awareness of the importance of compliance immediately after the programme and six months later. Education in glaucoma can be conducted within a local authority or hospital setting, the latter providing the option of a combined intervention targeting detection of low compliance and education in glaucoma at a nurse-led glaucoma clinic.

Analysing barriers to service improvement using a multi‐level theory of innovation: the case of glaucoma outpatient clinics. - Turner, Simon; Vasilakis, Christos; Utley, Martin; Foster, Paul; Kotecha, Aachal; Fulop, Naomi J. (Sociology of Health & Illness, 2018)
Abstract: The development and implementation of innovation by healthcare providers is understood as a multi‐determinant and multi‐level process. Theories at different analytical levels (i.e. micro and organisational) are needed to capture the processes that influence innovation by providers. This article combines a micro theory of innovation, actor‐network theory, with organisational level processes using the ‘resource based view of the firm’. It examines the influence of, and interplay between, innovation‐seeking teams (micro) and underlying organisational capabilities (meso) during innovation processes. We used ethnographic methods to study service innovations in relation to ophthalmology services run by a specialist English NHS Trust at multiple locations. Operational research techniques were used to support the ethnographic methods by mapping the care process in the existing and redesigned clinics. Deficiencies in organisational capabilities for supporting innovation were identified, including manager‐clinician relations and organisation‐wide resources. The article concludes that actor‐network theory can be combined with the resource‐based view to highlight the influence of organisational capabilities on the management of innovation. Equally, actor‐network theory helps to address the lack of theory in the resource‐based view on the micro practices of implementing change.
Keywords: Health Services Accessibility; Glaucoma -- Therapy; Technology, Medical; Human; Outpatient Service; Ethnographic Research; Interpersonal Relations

Latanoprost, a balanced prostaglandin. - Martinez-de-la-Casa, Jose M; Donde, Shaantanu; Wierzbowska, Joanna (Expert Review of Ophthalmology, 2019)
Introduction: Glaucoma is a leading cause of blindness and represents a significant global health and economic concern. Prostaglandin analogs such as latanoprost - which act to reduce intraocular pressure by enhancing uveoscleral flow and slow the development and progression of glaucoma - are recommended as a first-line monotherapy. Areas covered: We review recent efficacy and safety data for latanoprost, both alone and in combination therapy, and vs. other prostaglandin analogs, focusing on the tolerability and adherence to the drug and the subsequent impact on patient-perceived quality of life. Relevant studies were identified by an electronic literature search using MEDLINE PubMed, and current global glaucoma guidelines were reviewed. Expert commentary: Prostaglandin analogs represent the cornerstone in glaucoma therapy. Individual studies demonstrate differences in efficacy between prostaglandin analogs, but within-class differences are generally small - and, on balance, latanoprost presents a good efficacy-safety profile. Low adverse event rates result in greater persistence and improved quality of life for patients. Further, a latanoprost/β-blocker combination represents an efficacious therapeutic alternative where monotherapy does not sufficiently reduce intraocular pressure. However, high-quality randomized controlled trials are required to provide further information regarding fixed-dose combination vs. unfixed combination treatment regimens.
Keywords: Latanoprost -- Administration and Dosage; Prostaglandins -- Analogs and Derivatives; Human; Systematic Review; Medline; PubMed; Intraocular Pressure -- Drug Effects; Glaucoma -- Drug Therapy; Quality of Life

Automated patient reminder system could boost patient compliance: EHR-linked system explored as strategy for improving glaucoma medication adherence. - Guttman Krader, Cheryl (Ophthalmology Times, 2019)
The article discusses a 2019 study which shows the feasibility of using electronic health records (EHR) in building an automated reminder system for glaucoma patients on their medications. Topics covered include the problem of poor adherence with glaucoma medications, and an automated reminder system's possible boosting of patient compliance rates. Also noted is the EHR's advantage of allowing clinician oversight to ensure taking of current medications.
Keywords: Automation; Reminder Systems; Patient Compliance; Glaucoma -- Drug Therapy; Electronic Health Records; Medication Compliance; Quality Improvement

New classes of glaucoma medications. - Schehlein, Emily M.; Novack, Gary D.; Robin, Alan L. (Current Opinion in Ophthalmology, 2017)
Purpose Of Review: To discuss recent advances in the medical management of glaucoma and to highlight future medical therapies currently in development.Recent Findings: In 1996, latanoprost (Xalatan) was approved in the United States as a new chemical entity and new class (prostaglandin analogs) for the topical treatment of ocular hypertension and glaucoma. In the period from the late 1990s-2010s, while there were additional new chemical entities, fixed dose combinations, and formulation improvements, there were no new classes of ocular hypotensive medications approved worldwide. We summarize new pharmacological treatments that are currently in clinical trials - new classes, new molecules and new delivery systems.Summary: Although challenges in medical treatment of glaucoma exist, particularly in patient adherence, medical therapy remains the first line treatment for almost all glaucoma patients. Few new medications for glaucoma therapy are currently available for our patients, but multiple drugs with novel mechanisms of action, new formulations, and new delivery mechanisms are currently in development.
Keywords: Glaucoma -- Drug Therapy; Antihypertensive Agents -- Therapeutic Use; Intraocular Pressure -- Drug Effects; Drug Combinations; Neurotransmitter Agents -- Therapeutic Use; Human; Receptors, Cell Surface; Drug Delivery Systems; RNA -- Therapeutic Use; Phosphotransferases -- Antagonists and Inhibitors; Prostaglandins F, Synthetic -- Therapeutic Use; Scales

Systematic review of educational interventions to improve glaucoma medication adherence: an update in 2015. - Newman-Casey, Paula Anne; Dayno, Megan; Robin, Alan L. (Expert Review of Ophthalmology, 2016)
Purpose: To evaluate the current state of the research on educational interventions whose aim is to improve glaucoma medication adherence. Methods: A systematic review of Pubmed, Embase and CINAHL was conducted to identify research studies evaluating educational interventions to improve glaucoma medication adherence. Studies were included if the intervention was described, the outcomes assessed glaucoma medication adherence and the focus of the research was on adults with glaucoma. The search was conducted on June 2, 2015. Results: Seventeen studies were identified that met the inclusion criteria. These included nine randomized controlled trials and eight observational studies. Eight of the studies demonstrated an impact on glaucoma medication adherence, though their outcome measures were too heterogeneous to estimate a pooled effect size. Conclusion: The interventions that successfully improved glaucoma medication adherence used an adequate dose of face-to-face counseling to overcome barriers to health behavior change alongside education about glaucoma.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance -- Education; Patient Education -- Evaluation; Systematic Review; Human; PubMed; Embase; CINAHL Database; Randomized Controlled Trials; Nonexperimental Studies; Effect Size; Health Belief Model; Quality Assessment; Outcome Assessment; Patient Education -- Methods; Patient Education -- Trends; Counseling; Glaucoma -- Education; Funding Source

Changing Initial Glaucoma Medical Therapy Increases Healthcare Resource Utilization. - Trese, Matthew G.J.; Lewis, Andrew W.; Blachley, Taylor S.; Stein, Joshua D.; Moroi, Sayoko E. (Journal of Ocular Pharmacology & Therapeutics, 2017)
Purpose: To determine the frequency and economic impact of changing initial glaucoma therapy for patients with newly diagnosed open-angle glaucoma (OAG) or ocular hypertension (OHT).Methods: This retrospective longitudinal cohort study identified individuals within a large managed care network in the United States, who were newly diagnosed with OAG or OHT from 2001 to 2012 and were prescribed either a topical beta blocker (BB) or a prostaglandin analog (PGA). Claims data were analyzed over the 12-month period following their index prescription to determine physician prescribing habits, healthcare resource utilization patterns, and sociodemographic factors which may have contributed to changing the initial treatment strategy.Results: A total of 15,019 beneficiaries were identified with newly diagnosed OAG or OHT and whose index therapy was either a topical BB or PGA. Among these enrollees 80.9% were started on PGAs, while 19.1% were started on BBs. Of these beneficiaries, 29.2% of those started on PGAs and 39.5% of those started on BBs underwent a change in therapy within 12 months of their index prescription. Those in the topical BB treatment group had a 38% increased odds of changing glaucoma therapy relative to those started on PGAs (odds ratio [OR] 0.61, 95% CI:0.56-0.68). Patients who changed therapy required more frequent office visits (P < 0.0001) and incurred higher median eye care related charges (P < 0.0001) compared to those who remained on the index therapy unchanged.Conclusions: Changing initial ocular hypotensive therapy is common. Individuals who undergo a change in therapy required more frequent face-to-face monitoring and incurred higher healthcare related costs. Identifying strategies capable of optimizing the process of initiating ocular hypotensive therapy are appealing and possess the potential to improve patient outcomes and reduce healthcare costs.
Keywords: Adrenergic Beta-Antagonists -- Administration and Dosage; Glaucoma -- Drug Therapy; Ocular Hypertension -- Drug Therapy; Prostaglandins, Synthetic -- Administration and Dosage; Female; Office Visits -- Statistics and Numerical Data; Aged; Health Care Costs -- Statistics and Numerical Data; Prospective Studies; Managed Care Programs -- Statistics and Numerical Data; Adrenergic Beta-Antagonists -- Economics; Retrospective Design; Managed Care Programs -- Economics; Prescriptions, Drug -- Statistics and Numerical Data; Administration, Topical; Glaucoma -- Economics; United States; Ocular Hypertension -- Economics; Human; Male; Time Factors; Prescriptions, Drug -- Economics; Middle Age; Prostaglandins, Synthetic -- Economics; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Impact of Events Scale; Scales

Eye Care Quality and Accessibility Improvement in the Community (EQUALITY) for adults at risk for glaucoma: study rationale and design. - Owsley, Cynthia; Rhodes, Lindsay A.; McGwin Jr., Gerald; Mennemeyer, Stephen T.; Bregantini, Mary; Patel, Nita; Wiley, Demond M.; LaRussa, Frank; Box, Dan; Saaddine, Jinan; Crews, John E.; Girkin, Christopher A. (International Journal for Equity in Health, 2015)
Background: Primary open angle glaucoma is a chronic, progressive eye disease that is the leading cause of blindness among African Americans. Glaucoma progresses more rapidly and appears about 10 years earlier in African Americans as compared to whites. African Americans are also less likely to receive comprehensive eye care when glaucoma could be detected before irreversible blindness. Screening and follow-up protocols for managing glaucoma recommended by eye-care professional organizations are often not followed by primary eye-care providers, both ophthalmologists and optometrists. There is a pressing need to improve both the accessibility and quality of glaucoma care for African Americans. Telemedicine may be an effective solution for improving management and diagnosis of glaucoma because it depends on ocular imaging and tests that can be electronically transmitted to remote reading centers where tertiary care specialists can examine the results. We describe the Eye Care Quality and Accessibility Improvement in the Community project (EQUALITY), set to evaluate a teleglaucoma program deployed in retail-based primary eye care practices serving communities with a large percentage of African Americans. Methods/Design: We conducted an observational, 1-year prospective study based in two Walmart Vision Centers in Alabama staffed by primary care optometrists. EQUALITY focuses on new or existing adult patients who are at-risk for glaucoma or already diagnosed with glaucoma. Patients receive dilated comprehensive examinations and diagnostic testing for glaucoma, followed by the optometrist's diagnosis and a preliminary management plan. Results are transmitted to a glaucoma reading center where ophthalmologists who completed fellowship training in glaucoma review results and provide feedback to the optometrist, who manages the care of the patient. Patients also receive eye health education about glaucoma and comprehensive eye care. Research questions include diagnostic and management agreement between providers, the impact of eye health education on patients' knowledge and adherence to follow-up and medication, patient satisfaction, program cost-effectiveness, and EQUALITY's impact on Walmart pharmacy prescription rates. Discussion: As eye-care delivery systems in the US strive to improve quality while reducing costs, telemedicine programs including teleglaucoma initiatives such as EQUALITY could contribute toward reaching this goal, particularly among underserved populations at-risk for chronic blinding diseases.
Keywords: Intraocular Pressure; Glaucoma -- Drug Therapy; Eye Care; Tertiary Health Care; Glaucoma -- Diagnosis; Black Persons; Primary Health Care; Human; Nonexperimental Studies; Prospective Studies; Alabama; Quality Improvement; Telemedicine

Microinvasive glaucoma surgery: an evidence-based assessment. - Schehlein, Emily M.; Kaleem, Mona A.; Swamy, Ramya; Saeedi, Osamah J. (Expert Review of Ophthalmology, 2017)
Introduction: The advent of Microinvasive Glaucoma Surgery (MIGS) offers a novel approach in the treatment of glaucoma with the number of procedures developing at an exciting pace. MIGS procedures aim to lower intraocular pressure (IOP) via: (1) increasing trabecular outflow, (2) increasing outflow via suprachoroidal shunts, (3) reducing aqueous production, and (4) subconjunctival filtration. Areas covered: A comprehensive search for published studies for Microinvasive Glaucoma Surgery (MIGS) devices or procedure was undertaken using PubMed. Search terms included ‘minimally invasive glaucoma surgery’, ‘microincisional glaucoma surgery’, and ‘microinvasive glaucoma surgery’. A manual search for each device or procedure was also performed. After review, randomized control trials and prospective studies were preferentially included. Expert commentary: These procedures offer several benefits: an improved safety profile allowing for intervention in earlier stages of glaucoma, combination with cataract surgery, and decreased dependence on patient compliance with topical agents. Established MIGS procedures have proven efficacy and more recent devices and procedures show promising results. Despite this, further study is needed to assess the long term IOP-lowering effectiveness of these procedures. Particularly, rigorous study with more randomized control trials and head-to-head comparisons would allow for better informed clinical and surgical decision-making. MIGS offers new solutions for glaucoma treatment.
Keywords: Intraocular Pressure; Glaucoma -- Surgery; Glaucoma -- Drug Therapy; Minimally Invasive Procedures; Decision Making, Clinical; Cataract Extraction; Patient Compliance; Systematic Review; Human; PubMed

Reshaping medical treatment of glaucoma management: Future therapies require problem-solving strategies to achieve efficiency. - Charters, Lynda; Baudouin, Christophe (Ophthalmology Times, 2019)
The article discusses the evolution of glaucoma treatment specifically the introduction of new routes and delivery systems. Topics covered include the delivery challenges in glaucoma management, how the introduction of internal and external drug delivery systems will help ensure patient compliance for long periods, and the development of the use of gold nanoparticles aimed to increase drug penetration and reduce the amount of drug to reduce side effects.
Keywords: Glaucoma -- Drug Therapy; Problem Solving; Disease Progression; Patient Education; Drug Delivery Systems; Patient Compliance; Nanotechnology; Anterior Chamber; Conjunctiva; Regeneration

Glaucoma patient expression of medication problems and nonadherence. - Slota, Catherine; Sayner, Robyn; Vitko, Michelle; Carpenter, Delesha M; Blalock, Susan J; Robin, Alan L; Muir, Kelly W; Hartnett, Mary Elizabeth; Sleath, Betsy (Optometry & Vision Science, 2015)
Purpose: The purpose of this study was to examine if patient demographic factors influenced self-reporting of medication side effects, difficulty with drop instillation, and nonadherence to glaucoma therapy.Methods: English-speaking adult glaucoma patients (n = 279) from six ophthalmology clinics were enrolled. Patients' medical visits were videotaped and patients were interviewed immediately afterward by research assistants. The videotapes were transcribed verbatim and coded to identify patients who expressed problems with medication side effects, eye drop administration, and nonadherence during the glaucoma office visits. Generalized estimating equations were performed to identify whether patient characteristics were associated with expression of problems with glaucoma medication and medication nonadherence during the office visit.Results: Patients with lower health literacy were significantly less likely to express problems with side effects (odds ratio [OR], 0.47; 95% confidence interval [CI], 0.25 to 0.88) and eye drop administration (OR, 0.26; 95% CI, 0.11 to 0.63) during the visit. Patients who reported eye drop administration and side effect problems during the interview were significantly more likely to express these problems to their ophthalmologist (OR, 3.13; 95% CI, 1.82 to 5.37 and OR, 1.86; 95% CI, 1.12 to 3.08, respectively). Patients who expressed a problem with eye drop administration and with side effects were significantly more likely to express medication nonadherence to their ophthalmologist (OR, 2.89; 95% CI, 1.44 to 5.80 and OR, 2.03; 95% CI, 1.16 to 3.54, respectively). Patients who reported greater than 80% medication adherence during the interview were significantly less likely to express nonadherence to their ophthalmologist (OR, 0.22; 95% CI, 0.12 to 0.40).Conclusions: Eye care providers should be aware that glaucoma patients with lower health literacy are less likely to express problems with side effects and eye drop administration. Providers should work with patients to assess medication-related problems to mitigate potential barriers to medication adherence because patients who expressed medication problems were also more likely to express nonadherence.
Keywords: Antihypertensive Agents -- Adverse Effects; Glaucoma -- Drug Therapy; Information Literacy; Medication Compliance; Patients -- Psychosocial Factors; Adult; Black Persons; Aged; Aged, 80 and Over; Antihypertensive Agents -- Administration and Dosage; White Persons; Female; Glaucoma -- Ethnology; Human; Intraocular Pressure -- Drug Effects; Male; Middle Age; Ophthalmic Solutions -- Administration and Dosage; Ophthalmic Solutions -- Adverse Effects; Questionnaires; Young Adult

Reliability of the Evidence Addressing Treatment of Corneal Diseases: A Summary of Systematic Reviews. - Saldanha, Ian J.; Lindsley, Kristina B.; Lum, Flora; Dickersin, Kay; Li, Tianjing (JAMA Ophthalmology, 2019)
Importance: Patient care should be informed by clinical practice guidelines, which in turn should be informed by evidence from reliable systematic reviews. The American Academy of Ophthalmology is updating its Preferred Practice Patterns (PPPs) for the management of the following 6 corneal diseases: bacterial keratitis, blepharitis, conjunctivitis, corneal ectasia, corneal edema and opacification, and dry eye syndrome.Objective: To summarize the reliability of the existing systematic reviews addressing interventions for corneal diseases.Data Source: The Cochrane Eyes and Vision US Satellite database.Study Selection: In this study of published systematic reviews from 1997 to 2017 (median, 2014), the Cochrane Eyes and Vision US Satellite database was searched for systematic reviews evaluating interventions for the management of any corneal disease, combining eyes and vision keywords and controlled vocabulary terms with a validated search filter.Data Extraction and Synthesis: The study classified systematic reviews as reliable when each of the following 5 criteria were met: the systematic review specified eligibility criteria for inclusion of studies, conducted a comprehensive literature search for studies, assessed risk of bias of the individual included studies, used appropriate methods for quantitative syntheses (meta-analysis) (only assessed if meta-analysis was performed), and had conclusions that were supported by the results of the systematic review. They were classified as unreliable if at least 1 criterion was not met.Main Outcomes and Measures: The proportion of systematic reviews that were reliable and the reasons for unreliability.Results: This study identified 98 systematic reviews that addressed interventions for 15 corneal diseases. Thirty-three of 98 systematic reviews (34%) were classified as unreliable. The most frequent reasons for unreliability were that the systematic review did not conduct a comprehensive literature search for studies (22 of 33 [67%]), did not assess risk of bias of the individual included studies (13 of 33 [39%]), and did not use appropriate methods for quantitative syntheses (meta-analysis) (12 of 17 systematic reviews that conducted a quantitative synthesis [71%]). Sixty-five of 98 systematic reviews (66%) were classified as reliable. Forty-two of the 65 reliable systematic reviews (65%) addressed corneal diseases relevant to the 2018 American Academy of Ophthalmology PPPs; 33 of these 42 systematic reviews (79%) are cited in the 2018 PPPs.Conclusions and Relevance: One in 3 systematic reviews addressing interventions for corneal diseases are unreliable and thus were not used to inform PPP recommendations. Careful adherence by systematic reviewers and journal editors to well-established best practices regarding systematic review conduct and reporting might help make future systematic reviews in eyes and vision more reliable.
Keywords: Corneal Diseases -- Therapy; Resource Databases; Practice Guidelines -- Standards; Human; Reproducibility of Results; Meta Analysis; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Scales

Determinants of Self-Reported Barriers to Glaucoma Medicine Administration and Adherence: A Multisite Study. - Sleath, Betsy L.; Blalock, Susan J.; Muir, Kelly W.; Carpenter, Delesha M.; Lawrence, Scott D.; Giangiacomo, Annette L.; Goldsmith, Jason A.; Hartnett, Mary Elizabeth; Slota, Catherine; Robin, Alan L. (Annals of Pharmacotherapy, 2014)
Background: Many factors influence glaucoma medication adherence. A better understanding of the relationships between health literacy, depressive symptoms, and patient-reported problems in using glaucoma medications may reveal opportunities for intervention that could improve patients' clinical outcomes.Objective: To examine the relationship between patient characteristics (demographics, health literacy, and depressive symptoms) and patient-reported problems in using glaucoma medications and to assess factors related to patients' self-reported adherence to glaucoma medications.Methods: Patients diagnosed with primary open-angle glaucoma (n = 228) currently taking intraocular pressure-lowering medications were recruited at 6 ophthalmology clinics. Patients were interviewed to identify problems using glaucoma medications, and self-reported medication adherence was determined using a Visual Analog Scale. Questionnaires were administered to assess health literacy, depressive symptoms, outcome expectations, and medication self-efficacy.Results: Younger patients (P = 0.03), patients with depressive symptoms (P = 0.02), and patients who reported more medication problems (P = 0.005) were significantly less adherent to their glaucoma medications. Patients with higher glaucoma medication self-efficacy adherence scores (P = 0.003) and higher outcome expectations (P = 0.03) were significantly more adherent.Conclusions: Providers should consider using tools to screen glaucoma patients for depressive symptoms and for problems in using medications to identify patients who are at higher risk of nonadherence to treatment and who might benefit from follow-up with primary care providers.

Cost-Related Medication Nonadherence and Cost-Saving Behaviors Among Patients With Glaucoma Before and After the Implementation of Medicare Part D. - Blumberg, Dana M; Prager, Alisa J; Liebmann, Jeffrey M; Cioffi, George A; De Moraes, C Gustavo (JAMA Ophthalmology, 2015)
Importance: Understanding factors that lead to nonadherence to glaucoma treatment is important to diminish glaucoma-related disability.Objectives: To determine whether the implementation of the Medicare Part D prescription drug benefit affected rates of cost-related nonadherence and cost-reduction strategies in Medicare beneficiaries with and without glaucoma and to evaluate associated risk factors for such nonadherence.Design, Setting, and Participants: Serial cross-sectional study using 2004 to 2009 Medicare Current Beneficiary Survey data linked with Medicare claims. Coding to extract data started in January 2014 and analyses were performed between September and November of 2014. Participants were all Medicare beneficiaries, including those with a glaucoma-related diagnosis in the year prior to the collection of the survey data, those with a nonglaucomatous ophthalmic diagnosis in the year prior to the collection of the survey data, and those without a recent eye care professional claim.Intervention: Effect of the implementation of the Medicare Part D drug benefit.Main Outcomes and Measures: The change in cost-related nonadherence and the change in cost-reduction strategies.Results: Between 2004 and 2009, the number of Medicare beneficiaries with glaucoma who reported taking smaller doses and skipping doses owing to cost dropped from 9.4% and 8.2% to 2.7% (P < .001) and 2.8%, respectively (P = .001). However, reports of failure to obtain prescriptions owing to cost did not improve in the same period (3.4% in 2004 and 2.1% in 2009; P = .12). After Part D, patients with glaucoma had a decrease in several cost-reduction strategies, namely price shopping (26.2%-15.2%; P < .001), purchasing outside the United States (6.9%-1.3%; P < .001), and spending less money to save for medications (8.0% to 3.5%; P < .001). Using a multivariate analysis, the main independent risk factors common to all cost-related nonadherence measures were female sex, younger age, lower income (<$30 000), self-reported visual disability, and a smaller Lawton index.Conclusions and Relevance: After the implementation of Part D, there was a decrease in the rate that beneficiaries with glaucoma reported engaging in cost-saving measures. Although there was a decline in the rate of several cost-related nonadherence behaviors, patients reporting failure to fill prescriptions owing to cost remained stable. This suggests that efforts to improve cost-related nonadherence should focus both on financial hardship and medical therapy prioritization, particularly in certain high-risk sociodemographic groups.

Increasing healthcare costs: can we influence the costs of glaucoma care? - Töteberg-Harms, Marc; Berlin, Michael S.; Meier-Gibbons, Frances (Current Opinion in Ophthalmology, 2017)
Purpose Of Review: Despite a decrease in real average growth rates per capita since 2009, healthcare costs continue to rise worldwide. Numerous patient-related and doctor-related factors have contributed to this rise. Glaucoma is the leading cause of irreversible blindness and requires chronic, usually lifelong treatment. As with other chronic diseases, the adherence to prescribed treatment is often low and maybe influenced by the cost of the therapy. The purpose of this review is to seek potential solutions to best control the escalating costs of glaucoma care.Recent Findings: The studies we selected for this review can be divided into four different categories: costs of diagnostic tests; costs of direct comparisons between drugs or laser and conventional surgery; patient-related factors (such as adherence); and general aspects regarding costs: theoretical models and calculations.Summary: It is challenging to find reliable studies concerning this subject matter. As patients are under the umbrellas of variously organized healthcare systems which span different cultures, the costs between countries are difficult to compare. However, one common aspect to lower costs in glaucoma care is to improve patient adherence. Theoretical models with actual patient studies could enable cost reductions by comparing multiple diagnostic and therapeutic scenarios. VIDEO ABSTRACT: http://links.lww.com/COOP/A22.
Keywords: Health Care Costs; Glaucoma -- Economics; Economics, Pharmaceutical; Health Care Delivery; Antihypertensive Agents -- Economics; Models, Theoretical; Eye Surgery -- Economics; Diagnosis, Eye -- Economics; Patient Compliance

Demodex: Easy to find, not so easy to kill. - Farid, Marjan (Ocular Surgery News, 2021)
Keywords: Mite Infestations -- Diagnosis; Eye Infections, Parasitic -- Diagnosis; Blepharitis -- Diagnosis; Mite Infestations -- Therapy; Eye Infections, Parasitic -- Therapy; Blepharitis -- Therapy; Aged; Male; Vision Disorders; Diagnosis, Eye; Cataract -- Diagnosis; Sclerosis -- Diagnosis; Keratitis; Meibomian Gland Dysfunction; Tea Tree Oil; Compression Therapy; Ophthalmic Solutions; Cataract Extraction; Patient Compliance; Postoperative Care

Quantifying Glaucoma Medication Adherence: The Relationship Between Self-Report, Electronic Monitoring, and Pharmacy Refill. - Kumar, Jaya B.; Bosworth, Hayden B.; Sleath, Betsy; Woolson, Sandra; Olsen, Maren; Danus, Susanne; Muir, Kelly W. (Journal of Ocular Pharmacology & Therapeutics, 2016)
Purpose: Glaucoma medications reduce the risk of progressive visual field loss, but adherence to these medications is often poor. A better understanding of the appropriate metrics for quantifying glaucoma medication adherence is needed. We describe and compare different means of quantifying glaucoma medication adherence.Methods: Adults with glaucoma were enrolled in a prospective 2-site study. Participants completed a self-report instrument and received electronic medication monitors to use for ∼3 months. Pharmacy records were queried regarding requested refills over the monitoring period; medication possession ratio (MPR) was calculated.Results: Of the 137 total participants, those who answered "Very confident" to the question, "How confident are you that you always remember to use your glaucoma medications?" and "No" to the question, "In the past 4 weeks, did you ever forget to take your medicine?" were more likely [odds ratio (OR) 2.78, 95% confidence interval (CI) 1.19-6.52] to take ≥80% of the prescribed doses according to electronic medication monitors. Mean MPR was 1.49, standard deviation (SD) 0.82, range 0.1-5.31. The proportion of participants taking greater than or equal to 80% of the prescribed doses according to the electronic monitors was 59% for participants with MPR <1.2 (n = 27), 63% for participants with MPR 1.2-1.8 (n = 27), and 88% for MPR >1.8 (n = 25).Conclusions: Asking about confidence may be a good method of screening for poor adherence for glaucoma medication. MPR may be an inadequate representation of glaucoma medication adherence.
Keywords: Pharmacy Service -- Statistics and Numerical Data; Self Report; Medication Compliance; Glaucoma -- Drug Therapy; Prescriptions, Drug -- Statistics and Numerical Data; Aged; Aged, 80 and Over; Middle Age; Adult; Drug Monitoring; Male; Female; Human

When Is Evidence Enough Evidence? A Systematic Review and Meta-Analysis of the Trabectome as a Solo Procedure in Patients with Primary Open-Angle Glaucoma. - Chow, Jeffrey T. Y.; Hutnik, Cindy M. L.; Solo, Karla; Malvankar-Mehta, Monali S. (Journal of Ophthalmology, 2017)
The purpose of this systematic review and meta-analysis was to examine the availability of evidence for one of the earliest available minimally invasive glaucoma surgery (MIGS) procedures, the Trabectome. Various databases were searched up to December 20, 2016, for any published studies assessing the use of the Trabectome as a solo procedure in patients with primary open-angle glaucoma (POAG). The standardized mean differences (SMD) were calculated for the change in intraocular pressure (IOP) and number of glaucoma mediations used at 1-month, 6-month, and 12-month follow-up. After screening, three studies and one abstract with analyzable data were included. The meta-analysis showed statistically significant reductions in IOP and number of glaucoma medications used at all time points. Though the Trabectome as a solo procedure appears to lower IOP and reduces the number of glaucoma medications, more high-quality studies are required to make definitive conclusions. The difficulty of obtaining evidence may be one of the many obstacles that limit a full understanding of the potential safety and/or efficacy benefits compared to standard treatments. The time has come for a thoughtful and integrated approach with stakeholders to determine optimal access to care strategies for our patients.
Keywords: Intraocular Pressure; Glaucoma -- Drug Therapy; Glaucoma -- Surgery; Minimally Invasive Procedures; Glaucoma; Computerized Literature Searching; Health Screening; Systematic Review; Randomized Controlled Trials; Confidence Intervals; Descriptive Statistics; Clinical Trials; Nonexperimental Studies; Case Studies; Study Design; Literature Review; Prospective Studies; Checklists

Standard medication regimens hard to define for treatment of glaucoma. - DuBosar, Ryan (Ocular Surgery News, 2010)
The article reveals that there is no standard regimen for treating glaucoma. Ophthalmologist Louis B. Cantor claims that glaucoma patients faced different situations, so it is not possible to have a standard approach to glaucoma care management. The use of prostaglandin analogue is advised for primary-open glaucoma at an early disease stage. It describes the second-line therapies for the disease such as beta-blockers and carbonic anhydrase. The cost and compliance in the treatment of glaucoma are also noted.
Keywords: Glaucoma -- Drug Therapy; Patient Selection; Decision Making, Clinical; Prostaglandins -- Therapeutic Use; Glaucoma -- Complications; Severity of Illness; Prostaglandins -- Adverse Effects; Patient Attitudes; Adrenergic Beta-Antagonists; Adrenergic Alpha-Antagonists; Carbonic Anhydrase Inhibitors; Costs and Cost Analysis; Medication Compliance; Treatment Failure; Glaucoma -- Surgery

Ocular Antihypertensive Medication Use After iStent Implantation Concurrent With Cataract Surgery vs Cataract Surgery Alone in a Large US Health Care Claims Database. - Wang, Sophia Y.; Singh, Kuldev; Stein, Joshua D.; Chang, Robert T. (JAMA Ophthalmology, 2019)
Importance: The iStent Trabecular Micro-Bypass (Glaukos Corporation) is a minimally invasive glaucoma implant used in conjunction with cataract surgery to lower intraocular pressure.Objective: To determine whether implantation of the iStent concurrent with cataract surgery is associated with reduced use of ocular antihypertensive medications in a US health care claims database.Design, Setting, and Participants: Retrospective, observational longitudinal cohort study of individuals enrolled in a US managed care network who underwent iStent implantation with cataract surgery (iStent/CEIOL) from 2012 to 2016 (n = 1509 bilateral and n = 1462 unilateral surgery). A control group of individuals who underwent bilateral cataract surgery only (CEIOL) were matched 1:1 to patients undergoing bilateral iStent/CEIOL on baseline demographic and clinical factors. Data were analyzed between November 1, 2017, and January 31, 2018.Main Outcomes and Measures: The number of topical ocular antihypertensive agents used postoperatively by patients undergoing iStent/CEIOL compared with baseline and with matched CEIOL control individuals, and hazard ratios with 95% confidence intervals for sustained reduced use of at least 1 topical ocular antihypertensive agent postoperatively.Results: Of the 2971 eligible enrollees, mean age at first surgery was 74.3 years, and 1659 (55.8%) were women. Patients undergoing iStent/CEIOL had diagnoses that included primary open-angle glaucoma (n = 2329; 78.4%), narrow angles (n = 381; 12.8%), and secondary glaucomas (n = 261; 8.8%). At baseline, 1223 (41.2%) were receiving no topical glaucoma agents; 876 (29.5%), 437 (14.7%), and 435 (14.6%) were receiving 1, 2, or at least 3 agents, respectively. Although only 678 persons (22.8%) completed at least 2 years of postoperative follow-up, the proportion of patients receiving no drops increased postoperatively (64.7%, 20-24 months, P < .001, χ2). Patients receiving at least 1 topical agent at baseline had mean reduction of 1.01 and 0.61 medications used at 20 to 24 months with bilateral or unilateral surgery, respectively (both P < .001, paired t). Sustained reduction in glaucoma medication use was more likely in patients receiving at least 3 vs 1 medication at baseline (hazard ratio, 1.68; 95% CI, 1.36-2.09). Compared with matched control individuals undergoing CEIOL, patients undergoing bilateral iStent/CEIOL had a greater mean reduction in drops used (0.99 vs 0.49; postoperative month 20-24; P < .001; paired t) and a higher proportion receiving no drops postoperatively (73.5% vs 55.3%, postoperative month 20-24; P < .001; χ2).Conclusions and Relevance: Implantation of the iStent trabecular micro-bypass stent concurrent with cataract surgery was associated with moderately reduced use of topical ocular antihypertensive medication. Reduction in the use of glaucoma medications may lessen the burden of medication adverse effects and promote better adherence.
Keywords: Stents; Antihypertensive Agents -- Administration and Dosage; Prostheses and Implants -- Methods; Prostheses and Implants; Cataract Extraction -- Methods; Glaucoma -- Drug Therapy; Aged, 80 and Over; Lenses, Intraocular; Visual Acuity -- Physiology; Male; Retrospective Design; Aged; Female; United States; Administration, Intraocular; Glaucoma -- Physiopathology; Insurance, Health -- Statistics and Numerical Data; Human; Prospective Studies; Resource Databases; Ophthalmic Solutions; Tonometry; Intraocular Pressure -- Physiology; Glaucoma -- Surgery; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Scales

Can glaucoma patients benefit from cell therapy approach? Sustained delivery, other treatment options may change landscape. - Gagnon, Louise (Ophthalmology Times, 2019)
The article discusses glaucoma patients' need for treatment options other than daily administration of eye drops in 2019. Topics covered include such innovations as a sustained delivery of intraocular pressure (IOP) drugs, the use of the Kali Drop wireless adherence monitoring device, and the identification of patients who will experience worsening. Also noted is the examination of the biomechanics of the lamina cribosa to help uncover such patients.
Keywords: Glaucoma -- Therapy; Cell Therapy -- Methods; Health Care Delivery; Decision Making, Clinical; Treatment Outcomes; Ophthalmic Solutions -- Therapeutic Use; Patient Compliance; Disease Progression; Diagnosis, Eye -- Methods; Biological Markers; Glaucoma -- Diagnosis; Intraocular Pressure -- Evaluation; Glaucoma -- Pathology; Quality of Life

Predicted patient demand for a new delivery system for glaucoma medicine. - Ozdemir, Semra; Wong, Tina T.; Allingham, Robert Rand; Finkelstein, Eric A. (Medicine, 2017)
Sustained-release drug delivery systems that replace the need for daily glaucoma medications will improve outcomes for those who are nonadherent and reduce the inconvenience of having to take medications on a recurring basis.The objective is to estimate uptake (i.e., demand) for a new technology that delivers sustained-release glaucoma medication and to investigate how uptake varies by product attributes, physician recommendations, peer adoption (i.e., percentage of patients seen in a clinic using the new technology), and patient characteristics.In a web-enabled discrete-choice experiment survey, glaucoma patients in the United States were asked to choose between continuing eye drop use or purchasing the new delivery system. In a cross-sectional web-enabled survey, ophthalmologists were asked their likelihood of recommending the new technology based on product and patient characteristics.Study participants were 500 glaucoma patients who were on topical administration of daily eye drops and 155 ophthalmologists who practice in the US.Main outcomes were predicted uptake for patients and likelihood of recommending a new drug delivery system for ophthalmologists. Logistic models were used to analyze the choice data.Uptake was estimated to be 18% at an annual cost of $1000 and to be 24% when the cost was $500. A physician's recommendation increased uptake by 6% to 12%, whereas an increase in peer adoption from 5% to 50% increased uptake by 3% to 7%. Patients aged ≥ 65 and those with lower income were more likely to remain on eye drops. Physicians were more likely to recommend a product if the interval between administrations is 6 months or longer and when long-term safety and efficacy data are available. They were less likely to recommend it to patients with lower income and no adherence problems.Results suggest a significant interest in an injectable solution or other sustained-release alternatives to daily eye drops. However, in this survey, patient uptake was greatly influenced by out-of-pocket cost and the interval between treatment administrations. Few physicians were willing to recommend sustained-release technology if the treatment interval was less than 3 months.
Keywords: Patient Satisfaction -- Statistics and Numerical Data; Forecasting; Health Services Needs and Demand -- Trends; Ophthalmic Solutions -- Administration and Dosage; Glaucoma -- Psychosocial Factors; Human; Male; Female; Drug Delivery Systems; Administration, Topical; Logistic Regression; Aged; Medication Compliance; Adult; Delayed-Action Preparations; United States; Cross Sectional Studies; Glaucoma -- Drug Therapy; Middle Age

Adaptive optics optical coherence tomography in glaucoma. - Dong, Zachary M.; Wollstein, Gadi; Wang, Bo; Schuman, Joel S. (Progress in Retinal & Eye Research, 2017)
Since the introduction of commercial optical coherence tomography (OCT) systems, the ophthalmic imaging modality has rapidly expanded and it has since changed the paradigm of visualization of the retina and revolutionized the management and diagnosis of neuro-retinal diseases, including glaucoma. OCT remains a dynamic and evolving imaging modality, growing from time-domain OCT to the improved spectral-domain OCT, adapting novel image analysis and processing methods, and onto the newer swept-source OCT and the implementation of adaptive optics (AO) into OCT. The incorporation of AO into ophthalmic imaging modalities has enhanced OCT by improving image resolution and quality, particularly in the posterior segment of the eye. Although OCT previously captured in-vivo cross-sectional images with unparalleled high resolution in the axial direction, monochromatic aberrations of the eye limit transverse or lateral resolution to about 15-20 μm and reduce overall image quality. In pairing AO technology with OCT, it is now possible to obtain diffraction-limited resolution images of the optic nerve head and retina in three-dimensions, increasing resolution down to a theoretical 3 μm3. It is now possible to visualize discrete structures within the posterior eye, such as photoreceptors, retinal nerve fiber layer bundles, the lamina cribrosa, and other structures relevant to glaucoma. Despite its limitations and barriers to widespread commercialization, the expanding role of AO in OCT is propelling this technology into clinical trials and onto becoming an invaluable modality in the clinician's arsenal.
Keywords: Tomography, Optical Coherence -- Equipment and Supplies; Lenses; Glaucoma -- Diagnosis; Equipment Design; Human; Funding Source

Cost-effectiveness and cost utility of community screening for glaucoma in urban India. - John, Denny; Parikh, Rajul (Public Health (Elsevier), 2017)
Objectives: Population-based screening for glaucoma has been demonstrated to be cost-effective if targeted at high-risk groups such as older adults and those with a family history of glaucoma, and through use of a technician for conducting initial assessment rather than a medical specialist. This study attempts to investigate the cost-effectiveness of a hypothetical community screening and subsequent treatment programme for glaucoma in comparison with current practice (i.e. with no screening programme but with some opportunistic case finding) in the urban areas of India. Study design: A hypothetical screening programme for both primary open-angle glaucoma and angle-closure disease was built for a population aged between 40 and 69 years in the urban areas of India. Methods: Screening and treatment costs were obtained from an administrator of a tertiary eye hospital in India. The probabilities for the screening pathway were derived from published literature and expert opinion. The glaucoma prevalence rates for urban areas were adapted from the Chennai Glaucoma Study findings. A decision-analytical model using TreeAge Pro 2015 was built to model events, costs and treatment pathways. One-way sensitivity analyses were conducted. Results: The introduction of a community screening programme for glaucoma is likely to be cost-effective, the estimated incremental cost-effectiveness ratio (ICER) values being Image 1 10,668.68 when compared with no screening programme and would treat an additional 4443 cases and prevent 1790 person-years of blindness over a 10-year period in the urban areas of India. Sensitivity analyses revealed that glaucoma prevalence rates across various age groups, screening uptake rate, follow-up compliance after screening, treatment costs and utility values of health states associated with medical and surgical treatment of glaucoma had an impact on the ICER values of the screening programme. Conclusions: In comparison with current practice (i.e. without a screening programme but with some opportunistic case finding), the introduction of a community screening programme for glaucoma for the 40-69 years age group is likely to be relatively cost-effective if implemented in the urban areas of India.
Keywords: Cost Benefit Analysis; Urban Areas; Glaucoma, Angle-Closure; Health Care Costs; Health Screening; Intraocular Pressure; India; Adult; Middle Age

Treat primary open-angle glaucoma based on needs of the individual, taking potential adherence problems into account. (Drugs & Therapy Perspectives, 2016)
Glaucoma is a leading cause of visual morbidity and blindness and the incidence increases with advancing age. Topical therapies that reduce intraocular pressure are commonly used as first-line agents to treat primary open-angle glaucoma, with the choice of treatment based on the need of the individual. Agents that are administered once daily with favourable tolerability profiles may lead to high levels of adherence and good treatment outcomes.
Keywords: Glaucoma -- Therapy; Intraocular Pressure; Administration, Topical; Individualized Medicine; Medication Compliance; Age Factors

Seeking the goal line for patients' glaucoma medication compliance: More than a third of patients do not receive anti-glaucoma drugs, study shows. - Charters, Lynda (Ophthalmology Times, 2019)
The article discusses a study by Tavish Nanda of Columbia University that investigated the rate of intra-ocular pressure (IOP) medication noncompliance among aging glaucoma patients. The study found that glaucoma treatment incurs a high rate of medication noncompliance in the elderly that occurs mostly during transition of care from hospital to nursing home or assisted living facilities. It suggest that emphasis on appropriate medical reconciliation will improve rates of noncompliance.
Keywords: Ophthalmic Solutions -- Therapeutic Use; Glaucoma -- Drug Therapy; Medication Compliance -- Evaluation; Eye Care; Medication Reconciliation; Disease Progression; Glaucoma -- Diagnosis; Treatment Outcomes; Ophthalmic Solutions -- Administration and Dosage; Glaucoma -- Rehabilitation; Transfer, Discharge; Age Factors; Aging

Case Reports: The Use of Sector Fresnel Prism for Increased Peripheral Visual Field Awareness for Patients with End-Stage Retinitis Pigmentosa and Glaucoma. - Chea, Christine; Marinoff, Rebecca (Optometry & Visual Performance, 2015)
Background: Peripheral field loss from conditions such as retinitis pigmentosa and glaucoma can cause significant disabilities by limiting activities of daily living. Severe peripheral field loss causes mobility difficulties with activities such as identifying and adapting to obstacles in the environment. It can also cause emotional strain and impair quality of life. Because this visual field loss is often slow and progressive, patients may be unaware of these functional implications. In addition to orientation and mobility training, sector Fresnel prism therapy is a complementary visual field awareness technique to help the patients obtain information from the missing field. Case Reports: Two cases are presented with the characteristic functional impairments of severe overall visual field constriction. The first case involves a 58-year-old male with advanced retinitis pigmentosa. The second case is of a 52-yearold male with advanced primary open-angle glaucoma. Conclusion: The use of sector Fresnel prism to improve mobility and spatial awareness has long been a clinically accepted tool for rehabilitating patients with overall constricted peripheral visual fields. The prism reduces the degree of eye movement needed to detect peripheral objects in the environment. With in-office training and mobility training, sector Fresnel prism can be successful in helping the patients increase their peripheral awareness of objects, improve their navigational ability, and improve their quality of life.
Keywords: Intraocular Pressure; Visual Fields; Rehabilitation of Vision Impaired; Activities of Daily Living; Retinitis Pigmentosa; Eye Movements; Cognition; Male; Middle Age

Study targets topical medication adherence, visual field progression. - Lenier, Steve; Fong, Donald S. (Ophthalmology Times, 2020)
The article discusses a study conducted by Donald S. Fong of Kaiser Permanente Southern California regarding the impact of topical medication adherence on visual field progression in the treatment of patients with open-angle glaucoma. Topics discussed include the association of poor medication adherence with a faster rate of visual field decline, the risk of damage from glaucoma due to low medication adherence according to Fong, and the importance of follow-up and tracking patient refills.
Keywords: Glaucoma -- Drug Therapy; Administration, Topical; Medication Compliance; Disease Progression -- Prevention and Control

Contemporary management of refractory pediatric glaucoma. - Malik, Rizwan; AlDarrab, Abdulrahman; Edward, Deepak P. (Current Opinion in Ophthalmology, 2020)
Purpose Of Review: The management of pediatric glaucoma poses a unique challenge in terms of maintaining lifelong vision and combating an aggressive scarring response from surgery. Contemporary literature regarding the surgical management of children with pediatric glaucoma who fail, or are at a high risk of failure, from conventional surgery is limited. The aim of this review is to highlight recent developments in relation to the current opinion regarding the management of children with refractory pediatric glaucoma.Recent Findings: Some studies have reported impressive success rates with circumferential trabeculotomy, even in eyes with previous failed surgery. Early results of deep sclerectomy in populations which may not respond well to conventional angle surgery are encouraging but data is limited for the pediatric age group. In compliant patients in whom multiple postoperative examinations under anesthesia are possible, trabeculectomy remains an effective procedure. Multiple recent studies have demonstrated that glaucoma drainage device (GDD) surgery is associated with 5-year success rates of over 70% in primary childhood glaucomas.Summary: Glaucoma drainage device surgery is likely to remain a mainstay of surgical management for refractory glaucoma in older children. More prospective data are needed on the success of circumferential trabeculotomy, deep sclerectomy and micropulse laser in pediatric eyes with previous failed surgery. VIDEO ABSTRACT: http://links.lww.com/COOP/A34.
Keywords: Trabeculectomy -- Methods; Prostheses and Implants; Child; Intraocular Pressure -- Physiology

Smartphones, tablets stepping up as diagnostic technology options: Portable devices can diagnose glaucoma, evaluate optic nerve. - Charters, Lynda (Ophthalmology Times, 2020)
The article examines the use of smartphone-based fundus photography and tablet-based visual field testing with fundus photography in evaluating the optic nerve and diagnosing glaucoma. It describes the results of a study conducted by Patricia Anne Santos Tecson from The Medical Center in the Philippines to determine whether the alternative technologies are as effective as standard fundus photographs and visual field tests. It describes the impact of accessibility and affordability on diagnosis.
Keywords: Technology, Medical; Smartphone; Computers, Portable; Telehealth; Optic Nerve -- Analysis; Visual Fields -- Evaluation; Glaucoma -- Diagnosis; Diagnosis, Eye -- Methods; Photography -- Methods; Nerve Fibers -- Analysis; Sensitivity and Specificity; Predictive Value of Tests

Rejuvenation of outflow system: The time has come for procedure. - Charters, Lynda (Ophthalmology Times, 2020)
The article discusses an innovative technique's effective rejuvenation of the outflow system which increases the number of eyes that will not need anti-glaucoma medications in 2020. It states that a hybrid minimally invasive glaucoma surgery, dual-blade goniotomy and direct viscodilation of the collector channels with cataract surgery allows access to diseased tissue by removing the trabecular meshwork. Also noted is the procedure's financial burden reduction and compliance improvement.
Keywords: Rejuvenation; Trabeculectomy; Cataract Extraction -- Methods; Intraocular Pressure; Glaucoma -- Surgery; Minimally Invasive Procedures

Advances in glaucoma management blur the barriers between subspecialties. - Cimberle, Michela (Ocular Surgery News, 2017)
Keywords: Glaucoma -- Surgery; Glaucoma; Retinal Ganglion Cells; Pediatric Surgery; Cataract Extraction

Patterns of adherence behaviour for patients with glaucoma. - Cate, H; Bhattacharya, D; Clark, A; Holland, R; Broadway, D C (Eye, 2013)
Aims and Purpose: Adherence to long-term treatment regimens for primary open-angle glaucoma holds a challenge for both clinicians and patients. The study aims were to (i) establish the magnitude of travoprost non-adherence using an Electronic Adherence Monitor (EAM), (ii) compare electronic with patient self-reported adherence, and (iii) explore the application of a previously reported method of graphically presenting adherence data to a larger cohort over a longer monitoring period.Methods: A cohort study of patients using travoprost for glaucoma or ocular hypertension was conducted. All participants used an EAM and adherence data were collected prospectively for 2 months. Self-reported adherence was obtained using the Morisky Medication Adherence Scale (MMAS); patients also reported frequency of missed doses. Potential predictors of adherence were collected via a structured interview. EAM-recorded interdose intervals were plotted graphically.Results: Of 100 patients invited to participate, 98 consented and EAM data were collected successfully from 88 participants. The median EAM adherence score for the cohort was 88.9% (interquartile range: 71.2, 92.2). When dichotomised (≥80%: adherent; <80%: non-adherent), EAM identified 36.7% as non-adherent and MMAS 12.2%. EAM data were used to classify five types of adherence behaviour including a category representing levels of ≥97% maintained by 21% of participants.Conclusion: EAM revealed good adherence to glaucoma monotherapy but poor agreement with patient self-reported adherence. An adherence category of persistent and exceptionally high adherence to travoprost over a 2-month period was identified.
Keywords: Antihypertensive Agents -- Therapeutic Use; Prostaglandins, Synthetic -- Analogs and Derivatives; Glaucoma -- Drug Therapy; Medication Compliance; Aged; Aged, 80 and Over; Prostaglandins, Synthetic -- Therapeutic Use; Prospective Studies; Female; Human; Logistic Regression; Male; Middle Age; Self Report

Glaucoma patient-provider communication about vision quality-of-life. - Sleath, Betsy; Sayner, Robyn; Vitko, Michelle; Carpenter, Delesha M.; Blalock, Susan J.; Muir, Kelly W.; Giangiacomo, Annette L.; Hartnett, Mary Elizabeth; Robin, Alan L. (Patient Education & Counseling, 2017)
Objective: The purpose of this study was to: (a) describe the extent to which ophthalmologists and glaucoma patients discuss vision quality-of-life during office visits, and (b) examine the association between patient and ophthalmologist characteristics and provider-patient communication about vision quality-of-life.Methods: Patients with glaucoma who were newly prescribed or on glaucoma medications were recruited at six ophthalmology clinics. Patients' visits were video-tape recorded and quality-of-life communication variables were coded. Generalized estimating equations were used to analyze the data.Results: Two hundred and seventy-nine patients participated. Specific glaucoma quality-of-life domains were discussed during only 13% of visits. Older patients were significantly more likely to discuss one or more vision quality-of-life domains than younger patients. African American patients were significantly less likely to make statements about their vision quality-of-life and providers were less likely to ask them one or more vision quality-of-life questions than non-African American patients.Conclusion: Eye care providers and patients infrequently discussed the patient's vision quality-of-life during glaucoma visits. African American patients were less likely to communicate about vision quality-of-life than non-African American patients.Practice Implications: Eye care providers should make sure to discuss vision quality-of-life with glaucoma patients.
Keywords: Patient Centered Care -- Methods; Quality of Life; Communication; Glaucoma -- Psychosocial Factors; Aged; Aged, 80 and Over; Middle Age; Socioeconomic Factors; Young Adult; Office Visits; Physician-Patient Relations; Videorecording; Glaucoma -- Drug Therapy; Adult; Funding Source; Human

Influence of new treatment modalities on adherence in glaucoma. - Meier-Gibbons, Frances; Berlin, Michael S.; Töteberg-Harms, Marc (Current Opinion in Ophthalmology, 2019)
Purpose Of Review: It is well known that glaucoma patients are not adherent to their therapeutic regimens. The issue of nonadherence is multifactorial and includes inadequate communication between doctors and patients, resulting in significant costs associated with enhanced disease progression. Therapeutic regimens are risk factors which often influences adherence rates. Thus, alternative treatment modalities, especially those risk factors that do not rely on patients' cooperation, may enable improvements in long-term outcomes of glaucoma in patient.Recent Findings: The studies selected for this review were divided into new medications, especially advancements in pharmaceutical approaches to treat glaucoma and new ways of delivering the medication, new surgical methods, especially minimally invasive surgery methods for glaucoma, and new studies about adherence in glaucoma.Summary: Surprisingly, a very few studies on glaucoma medication or surgery addressed the concept of adherence. However, adherence is discussed in studies which consider psychological aspects of patients or communication issues between doctors and patients. Although these studies were performed in clinical settings, the issue of adherence is not addressed; despite it has significant effect on long-term outpatient care. A combination of both aspects, adherence and miscommunication, should be considered in studies.
Keywords: Glaucoma -- Therapy; Drugs; Patient Compliance; Drug Delivery Systems; Antihypertensive Agents -- Therapeutic Use; Glaucoma -- Diagnosis; Minimally Invasive Procedures

Glaucoma course for beginners and experienced. - Andersen C; Sloth L; Solbæk U; Spøer K (Sygeplejersken / Danish Journal of Nursing, 2010)
The article describes establishment of a glaucoma course for patients with recently developed or long-term glaucoma. The course is being run in cooperation between the opthalmology unit at Vejle Hospital and Vejle Municipality, The aim of the course is to improve compliance and enhance exchange of experience between participants. The training includes anatomy, disease pathology and instruction in correct instillation of eye drops, based on the unit's concept: 'Self-administration of eye drops: Getting it right.' In the long term the aim is to evaluate the efficacy of the course by using a questionnaire.
Keywords: Glaucoma -- Prevention and Control; Patient Education -- Methods; Ophthalmic Solutions -- Administration and Dosage; Seminars and Workshops

Drug delivery removes adherence from equation, but raises new issues: Concerns exist over how reliable is duration of action; when to renew therapy. - Gebhart, Fred (Ophthalmology Times, 2018)
The article explores various innovations in the delivery of therapeutics for the treatment of glaucoma. Topics mentioned include the Eyenovia micro-dosing device based on piezoelectric technology, Glaukos' iDose sustained release drug delivery device, and Graybug Vision's injectable intracameral drug depot.
Keywords: Drug Delivery Systems; Glaucoma -- Drug Therapy; Medication Compliance; Ophthalmic Solutions -- Therapeutic Use; Travoprost -- Administration and Dosage; Intraocular Pressure

Web-based intervention for improving adherence of people with glaucoma. - Lunnela, Jaana; Kääriäinen, Maria; Kyngäs, Helvi (Journal of Nursing & Healthcare of Chronic Illnesses, 2011)
Keywords: Medication Compliance; Glaucoma -- Drug Therapy; Patient Education -- Methods; World Wide Web -- Utilization; Patient Centered Care; Support, Psychosocial; Human; Finland; Experimental Studies; Control Group; Medication Compliance -- Evaluation; Convenience Sample; Outcomes of Education -- Evaluation; Self Report; Descriptive Statistics; Male; Female; Adult; Middle Age; Aged; Aged, 80 and Over; Summated Rating Scaling; Questionnaires; Pretest-Posttest Design; Chi Square Test; Mann-Whitney U Test; T-Tests; Nonparametric Statistics; Funding Source

Effect of benzalkonium chloride-free travoprost on intraocular pressure and ocular surface symptoms in patients with glaucoma previously on latanoprost: an open-label study. - Lopes, Joao F.; Hubatsch, Douglas A.; Amaris, Patricia (BMC Ophthalmology, 2015)
Background: Prostaglandin analogs reduce intraocular pressure (IOP) in patients with open-angle glaucoma or ocular hypertension; however, these medications may affect the ocular surface and elicit ocular discomfort when preserved with benzalkonium chloride (BAK).Methods: This was an open-label, single-arm study conducted in Latin America from February 2012 to May 2013. Patients with open-angle glaucoma or ocular hypertension who were intolerant of latanoprost 0.005 % were transitioned to receive once-daily BAK-free travoprost 0.004 % containing polyquaternium-1 (Travatan® preserved with POLYQUAD® [PQ], Alcon Laboratories, Inc; Fort Worth, TX) for 12 weeks. Mean change in IOP from baseline (primary efficacy endpoint) and the percentage of patients who achieved a target IOP of ≤18 mmHg were evaluated at all on-therapy visits. Ocular hyperemia, patient preference, and self-projected adherence were assessed at week 12. Adverse events (AEs) were monitored throughout the study.Results: All enrolled patients were included in the analysis (n = 191); the majority of patients (90.6 %, n = 173/191) completed the study. Mean (SD) patient age was 67.5 (11.3) years, and mean baseline IOP was 14.8 mmHg. Mean IOP was reduced by 0.94 mmHg at week 6 and by 1.09 mmHg at week 12 (P < 0.001 for both). A greater percentage of patients achieved a target IOP of ≤18 mmHg at week 6 (93.1 %; n = 163/175) and week 12 (93.3 %; n = 166/178) compared with baseline (89.5 %; n = 171/191). There was a 10.5 % increase in the percentage of patients with "none/trace" amounts of hyperemia. Most patients preferred the study medication (81.5 %; n = 141/173) and were confident that they would adhere to their preferred medication (90.8 %; n = 157/173). No serious AEs were reported, and eye irritation (3.7 %; n = 7/191) was the most common treatment-related AE.Conclusions: Transitioning from BAK-containing latanoprost 0.005 % to BAK-free travoprost 0.004 % preserved with PQ reduced IOP in patients with open-angle glaucoma or ocular hypertension who were intolerant of latanoprost. BAK-free travoprost 0.004 % is a viable alternative for patients who require switching their IOP-lowering medications because of tolerability issues.Trial Registration: ClinicalTrials.gov identifier, NCT01510145.
Keywords: Intraocular Pressure -- Drug Effects; Pharmaceutical Additives; Glaucoma -- Drug Therapy; Antihypertensive Agents -- Therapeutic Use; Prostaglandins F, Synthetic -- Therapeutic Use; Benzalkonium Compounds; Male; Adult; Prescriptions, Drug; Middle Age; Hyperemia -- Chemically Induced; Antihypertensive Agents -- Adverse Effects; Tonometry; Female; Corneal Diseases -- Chemically Induced; Human; Young Adult; Ocular Hypertension -- Drug Therapy; Aged; Conjunctival Diseases -- Chemically Induced; Aged, 80 and Over; Clinical Trials; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

Efficacy and tolerability of fixed-combination brinzolamide/timolol in Latin American patients with open-angle glaucoma or ocular hypertension previously on brimonidine/timolol fixed combination. - Alezzandrini, Arturo; Hubatsch, Douglas; Alfaro, Rene (Advances in Therapy, 2014)
Introduction: Fixed-combination glaucoma medications are commonly used to achieve target intraocular pressure (IOP) reduction in patients uncontrolled with monotherapy; however, ocular discomfort associated with eye drops can decrease adherence. This study assessed the efficacy and tolerability of twice-daily fixed-combination brinzolamide 1%/timolol 0.5% (BRINZ/TIM-FC) in Latin American patients transitioned from fixed-combination brimonidine 0.2%/timolol 0.5% (BRIM/TIM-FC) because of insufficient IOP control or treatment intolerance.Methods: This 8-week, open-label, prospective study was conducted at six sites in Argentina, Chile, and Mexico. Enrolled patients were aged ≥18 years with open-angle glaucoma (including primary, exfoliative, or pigment-dispersion glaucoma) or ocular hypertension with IOP of 19-35 mmHg in ≥1 eye at baseline (on BRIM/TIM-FC). Patients self-administered BRINZ/TIM-FC to both eyes at 8 a.m. and 8 p.m. daily for 8 weeks. The primary and secondary efficacy endpoints were mean IOP change from baseline at week 8 and percentage of patients achieving target IOP (≤18 mmHg) at week 8, respectively. Exploratory endpoints included patient and investigator preference for treatment at week 8. Adverse events (AEs) were assessed as the safety endpoint.Results: Fifty patients (mean ± SD age, 66.7 ± 11.5 years) received BRINZ/TIM-FC, and 49 were included in the intent-to-treat population. Mean ± SD IOP was significantly reduced from baseline after 8 weeks of treatment with BRINZ/TIM-FC (-3.6 ± 3.0 mmHg; P < 0.0001, Wilcoxon signed-rank test; 17.1% reduction). Overall, 55.3% of patients achieved IOP ≤18 mmHg at week 8. Significantly more patients (89.4%) and investigators (95.7%) preferred BRINZ/TIM-FC to BRIM/TIM-FC (both P < 0.0001, exact binomial test). Of the 13 AEs observed, 8 were related to BRINZ/TIM-FC; the most common treatment-related AEs were eye irritation (n = 4) and abnormal sensation in the eye (n = 2).Conclusion: BRINZ/TIM-FC provides an effective and well-tolerated treatment option for patients transitioned from BRIM/TIM-FC.

Setting expectations for glaucoma patients having cataract surgery: Pearls can ensure physicians get best outcomes, help patients set realistic goals. - Caceres, Vanessa (Ophthalmology Times, 2019)
The article presents a discussion of the steps that ophthalmologists must take before cataract surgery in advanced glaucoma patients, designed to lower the chance for vision loss, adapted from Dr. Yvonne Ou's presentation at the American Glaucoma Society annual meeting. It includes setting expectations for patients and physicians before the surgery, the use of careful surgical planning, and using all methods to minimize inflammation.
Keywords: Motivation; Goal-Setting; Physician-Patient Relations; Preoperative Period; Attitude to Medical Treatment; Cataract Extraction -- Psychosocial Factors; Glaucoma -- Surgery; Strategic Planning; Ophthalmologists -- Psychosocial Factors; Treatment Outcomes; Inflammation -- Prevention and Control; Fluorouracil -- Administration and Dosage; Postoperative Care; Office Visits; Risk Assessment; Steroids -- Therapeutic Use; After Care

New therapies may prompt proactive approach to glaucoma care. - Linnehan, Robert (Ocular Surgery News, 2018)
Keywords: Glaucoma -- Therapy; Intraocular Pressure; Ophthalmic Solutions -- Therapeutic Use; United States Food and Drug Administration; Patient Compliance; Ophthalmic Solutions -- Administration and Dosage; Protein Kinases; Ocular Hypertension; Prostaglandins -- Analogs and Derivatives; Anterior Eye Segment -- Physiology; Drug Delivery Systems; Optic Nerve -- Physiology; Regeneration; Glaucoma -- Diagnosis

Drug delivery systems could improve poor adherence in glaucoma care: Agents gradually dissolve or elute medication; reduce treatment burden for patients. - Harrison, Laird; Myers, Jonathan S. (Ophthalmology Times, 2018)
The article presents a discussion of drug delivery systems that could improve poor adherence in patients taking glaucoma medications, adapted from Dr. Jonathan S. Myers' presentation during Glaucoma Subspecialty Day at the 2017 meeting of the American Academy of Ophthalmology. Topics covered include how intraocular drug delivery can help solve poor compliance, its ability to reduce treatment burden for patients, and descriptions of three intraocular devices now in clinical trials.
Keywords: Glaucoma; Drug Delivery Systems; Medication Compliance; Administration, Intraocular; Drug Implants

The Role of Pneumococcal Virulence Factors in Ocular Infectious Diseases. - Benton, Angela H.; Marquart, Mary E. (Interdisciplinary Perspectives on Infectious Diseases, 2018)
Streptococcus pneumoniae is a gram-positive, facultatively anaerobic pathogen that can cause severe infections such as pneumonia, meningitis, septicemia, and middle ear infections. It is also one of the top pathogens contributing to bacterial keratitis and conjunctivitis. Though two pneumococcal vaccines exist for the prevention of nonocular diseases, they do little to fully prevent ocular infections. This pathogen has several virulence factors that wreak havoc on the conjunctiva, cornea, and intraocular system. Polysaccharide capsule aids in the evasion of host complement system. Pneumolysin (PLY) is a cholesterol-dependent cytolysin that acts as pore-forming toxin. Neuraminidases assist in adherence and colonization by exposing cell surface receptors to the pneumococcus. Zinc metalloproteinases contribute to evasion of the immune system and disease severity. The main purpose of this review is to consolidate the multiple studies that have been conducted on several pneumococcal virulence factors and the role each plays in conjunctivitis, keratitis, and endophthalmitis.

Cannabis in End-of-Life Care: Examining Attitudes and Practices of Palliative Care Providers. - Luba, Rachel; Earleywine, Mitch; Farmer, Stacey; Slavin, Melissa (Journal of Psychoactive Drugs, 2018)
Medical cannabis research has become quite extensive, with indications ranging from glaucoma to chemotherapy-induced nausea. Despite increased interest in cannabis' potential medical uses, research barriers, cannabis legislation, stigma, and lack of dissemination of data contribute to low adoption for some medical populations. Of interest, cannabis use appears low in palliative care settings, with few guidelines available to palliative care providers. The present study sought to examine the attitudes, beliefs, and practices of palliative care providers regarding the use of cannabis for terminally ill patients. Palliative care providers (N = 426) completed a one-time online survey assessing these attitudes, beliefs, and practices. Results demonstrated that palliative care providers endorse cannabis for a wide range of palliative care symptoms, end-of-life care generally, and as an adjuvant medication. Nevertheless, the gap between these beliefs and actual recommendation or prescription appears vast. Many who support the use of cannabis in palliative care do not recommend it as a treatment. These data suggest recommendations for healthcare providers and palliative care organizations.
Keywords: Health Personnel -- Statistics and Numerical Data; Medical Marijuana -- Therapeutic Use; Palliative Care -- Methods; Terminal Care -- Methods; Middle Age; Attitude of Health Personnel; Female; Surveys; Male; Attitude to Health; Adult

Zika and the Eye: Pieces of a Puzzle. - de Oliveira Dias, João Rafael; Ventura, Camila V.; de Paula Freitas, Bruno; Prazeres, Juliana; Ventura, Liana O.; Bravo-Filho, Vasco; Aleman, Tomas; Ko, Albert Icksang; Zin, Andréa; Belfort, Rubens; Maia, Mauricio; de Oliveira Dias, João Rafael; et al. (Progress in Retinal & Eye Research, 2018)
Zika virus (ZIKV) is an arbovirus mainly transmitted to humans by mosquitoes from Aedes genus. Other ways of transmission include the perinatal and sexual routes, blood transfusion, and laboratory exposure. Although the first human cases were registered in 1952 in African countries, outbreaks were only reported since 2007, when entire Pacific islands were affected. In March 2015, the first cases of ZIKV acute infection were notified in Brazil and, to date, 48 countries and territories in the Americas have confirmed local mosquito-borne transmission of ZIKV. Until 2015, ZIKV infection was thought to only cause asymptomatic or mild exanthematous febrile infections. However, after explosive ZIKV outbreaks in Polynesia and Latin American countries, it was confirmed that ZIKV could also lead to Guillain-Barré syndrome and congenital birth abnormalities. These abnormalities, which can include neurologic, ophthalmologic, audiologic, and skeletal findings, are now considered congenital Zika syndrome (CZS). Brain abnormalities in CZS include cerebral calcifications, malformations of cortical development, ventriculomegaly, lissencephaly, hypoplasia of the cerebellum and brainstem. The ocular findings, which are present in up to 70% of infants with CZS, include iris coloboma, lens subluxation, cataract, congenital glaucoma, and especially posterior segment findings. Loss of retinal pigment epithelium, the presence of a thin choroid, a perivascular choroidal inflammatory infiltrate, and atrophic changes within the optic nerve were seen in histologic analyses of eyes from deceased fetuses. To date, there is no ZIKV licensed vaccines or antiviral therapies are available for treatment. Preventive measures include individual protection from mosquito bites, control of mosquito populations and the use of barriers measures such as condoms during sexual intercourse or sexual abstinence for couples either at risk or after confirmed infection. A literature review based on studies that analyzed ocular findings in mothers and infants with CZS, with or without microcephaly, was conducted and a theoretical pathophysiologic explanation for ZIKV-ocular abnormalities was formulated.
Keywords: Pregnancy Complications, Infectious; Eye Infections, Viral; Craniofacial Abnormalities; Pregnancy; Female; Eye Infections, Viral -- Complications; Eye Infections, Viral -- Transmission; Human; Craniofacial Abnormalities -- Complications; Ways of Coping Questionnaire

Irritation in a bottle: Glaucoma and OSD. - Mukkamala, Lekha; Khouri, Albert S. (Ophthalmology Times, 2017)
A 72-YEAR-OLD MALE with primary open-angle glaucoma (POAG) on three topical medications complained of foreign body sensation in both eyes. Pinhole vision was 20/40 OD and 20/50 OS. He was found to have moderate ocular surface disease (OSD) bilaterally, as well as uncontrolled IOP with progression of a visual field defect in the left eye. The patient was recommended to undergo trabeculectomy with mitomycin C (MMC) in the left eye. His ocular surface disease index (OSDI) score was high, congruent with the signs noted on exam. Three months after surgery, the patient had well-controlled IOP with no topical medications in the left eye and continued maximal medical therapy in the right, with persistent complaint of irritation. Vision was 20/60 OD and 20/25 OS. Examination noted persistent punctate epithelial erosions OD, with significant improvement in OSD OS. The recovery in vision was attributed to the improvement in OSD from the elimination of topical medical therapy. Aggressive treatment of OSD was initiated by prescribing cyclosporine 0.05% (Restasis, Allergan) and decreasing the frequency of topical therapy. Four months later, the patient's vision was 20/25 OU with significant improvement of OSD OD. OSD was attributed to the high burden of topical glaucoma therapy. The frequency and duration of topical medications have also been found to affect OSD development. This has been quantified by the intensity index (calculated as the number of drops/week multiplied by the duration of therapy in years), which was shown to be correlated to a higher OSDI, and may help predict the patients with greater propensity to develop OSD. Strategies to decrease the intensity index (such as fixed-combination medications) as well as pharmacologic therapies such as preservative-free artificial tears (as 0.3% hydroxypropyl methylcellulose/dextran), or sodium hyaluronate 0.18% are very effective in treating OSD and improving patient satisfaction.
Keywords: Glaucoma -- Drug Therapy; Glaucoma -- Surgery; Eye Surgery; Cyclosporins -- Administration and Dosage; Patient Compliance; Administration, Topical; Trabeculectomy -- Methods; Visual Acuity; Intraocular Pressure; Aged; Male

Extraocular, periocular, and intraocular routes for sustained drug delivery for glaucoma. - Kompella, Uday B.; Hartman, Rachel R.; Patil, Madhoosudan A. (Progress in Retinal & Eye Research, 2021)
Although once daily anti-glaucoma drug therapy is a current clinical reality, most therapies require multiple dosing and there is an unmet need to develop convenient, safe, and effective sustained release drug delivery systems for long-term treatment to improve patient adherence and outcomes. One of the first sustained release drug delivery systems was approved for the reduction of intraocular pressure in glaucoma patients. It is a polymeric reservoir-type insert delivery system, Ocusert™, placed under the eyelid and on the ocular surface for zero-order drug release over one week. The insert, marketed in two strengths, released pilocarpine on the eye surface. While many clinicians appreciated this drug product, it was eventually discontinued. No similar sustained release non-invasive drug delivery system has made it to the market to date for treating glaucoma. Drug delivery systems under development include punctal plugs, ring-type systems, contact lenses, implants, microspheres, nanospheres, gels, and other depot systems placed in the extraocular, periocular, or intraocular regions including intracameral, supraciliary, and intravitreal spaces. This article discusses the advantages and disadvantages of the various routes of administration and delivery systems for sustained glaucoma therapy. It also provides the reader with some examples and discussion of drug delivery systems that could potentially be applied for glaucoma treatment. Interestingly, one intracamerally injected implant, Durysta™, was approved recently for sustained intraocular pressure reduction. However, long-term acceptance of such devices has yet to be established. The ultimate success of the delivery system will depend on efficacy relative to eye drop dosing, safety, reimbursement options, and patient acceptance. Cautious development efforts are warranted considering prior failed approaches for sustained glaucoma drug delivery. Neuroprotective approaches for glaucoma therapy including cell, gene, protein, and drug-combination therapies, mostly administered intravitreally, are also rapidly progressing towards assessment in humans.

EDUCATE ON DED THERAPEUTICS: Provide the why, how to use and what to expect to increase the likelihood of patient compliance to the prescription. - KOETTING, CECELIA (Optometric Management, 2020)
Keywords: Dry Eye Syndromes -- Drug Therapy; Dry Eye Syndromes -- Etiology; Dry Eye Syndromes -- Complications; Patient Education; Optometrists; Patient Compliance; Amnion; Lacrimal Apparatus -- Pathology; Blood Transfusion, Autologous; Keratitis -- Drug Therapy; Inflammation -- Drug Therapy; Inflammation -- Complications; Prescriptions, Drug; Eye Protective Devices; Dietary Supplements; Ophthalmic Solutions; Contact Lenses; Antibiotics; Adrenal Cortex Hormones; Administration, Topical

Nanotechnology for Medical and Surgical Glaucoma Therapy-A Review. - Occhiutto, Marcelo Luís; Maranhão, Raul C.; Costa, Vital Paulino; Konstas, Anastasios G. (Advances in Therapy, 2020)
Glaucoma is the second leading cause of blindness worldwide. Even though significant advances have been made in its management, currently available antiglaucoma therapies suffer from considerable drawbacks. Typically, the success and efficacy of glaucoma medications are undermined by their limited bioavailability to target tissues and the inadequate adherence demonstrated by patients with glaucoma. The latter is due to a gradual decrease in tolerability of lifelong topical therapies and the significant burden to patients of prescribed stepwise antiglaucoma regimens with frequent dosing which impact quality of life. On the other hand, glaucoma surgery is restricted by the inability of antifibrotic agents to efficiently control the wound healing process without causing severe collateral damage and long-term complications. Evolution of the treatment paradigm for patients with glaucoma will ideally include prevention of retinal ganglion cell degeneration by the successful delivery of neurotrophic factors, anti-inflammatory drugs, and gene therapies. Nanotechnology-based treatments may surpass the limitations of currently available glaucoma therapies through optimized targeted drug delivery, increased bioavailability, and controlled release. This review addresses the recent advances in glaucoma treatment strategies employing nanotechnology, including medical and surgical management, neuroregeneration, and neuroprotection.
Keywords: Nanotechnology -- Methods; Glaucoma -- Drug Therapy; Nanoparticles; Nanomedicine -- Methods; Biological Availability; Glaucoma -- Therapy; Nanomedicine -- Trends; Quality of Life; Ferrans and Powers Quality of Life Index; Impact of Events Scale

Glaucoma, "the silent thief of sight": patients' perspectives and health seeking behaviour in Bauchi, northern Nigeria. - Abdull, Mohammed Mahdi; Chandler, Clare; Gilbert, Clare (BMC Ophthalmology, 2016)
Background: In Nigeria, glaucoma has a high prevalence and is the second cause of blindness among adults after cataract. People with glaucoma frequently present very late with advanced disease, and acceptance of and adherence to treatment is low. The purpose of the study was to explore how patients' understand and respond to glaucoma in order develop an intervention to improve adherence to treatment.Method: Hospital based qualitative study. Six focus group discussions were held with patients with advanced disease and who had either undergone glaucoma surgery, were receiving medical treatment, or had neither surgery nor medical treatment. Two traditional healers who treat eye conditions were interviewed. Audio files were transcribed, translated into English and recurring themes coded and categorized as the impact of vision loss, and understandings of the disease and its management.Results: Visual loss impacted significantly on the lives of people with glaucoma in many ways. Many heard the term "glaucoma" for the first time during the study. Local terms to describe the symptoms included Hawan jinin ido ("hypertension of the eye"). Patients sought treatment in pharmacies, or with traditional healers who had different interpretations of glaucoma and its treatment to biomedical understandings. Cost and forgetfulness were the main reasons for low adherence to treatment while fear was a reason for not accepting surgery. Lack of money and negative staff attitudes were reasons for low follow up.Conclusion: Halting the progression of glaucoma is possible with treatment but the condition will remain a "silent thief of sight" in West Africa unless awareness, uptake of services and adherence to treatment improve. Understanding how glaucoma is locally conceptualised, lived with and responded to by patients is essential to aid the design of interventions to prevent glaucoma blindness in Africa. Findings have been used to adapt a motivational interviewing intervention, which is being evaluated in a clinical trial.
Keywords: Patients -- Psychosocial Factors; Glaucoma -- Psychosocial Factors; Patient Attitudes; Attitude to Health; Health Behavior; Glaucoma -- Therapy; Filtering Surgery; Intraocular Pressure; Antihypertensive Agents -- Therapeutic Use; Male; Female; Rural Population; Health Services Accessibility; Nigeria; Patient Compliance; Glaucoma -- Epidemiology; Visual Acuity; Human

Topical Dorzolamide 2%/Timolol 0.5%: A Review of its Use in the Treatment of Open-Angle Glaucoma. - Ormrod D; Mcclellan K (Drugs & Aging, 2000)
The nonselective [beta]-blocker timolol and the carbonic anhydrase inhibitor dorzolamide both lower intraocular pressure (IOP). Timolol and dorzolamide have different mechanisms of action and their effects are additive when administered together. Therefore, the 2 drugs are frequently used concomitantly to treat patients with open-angle glaucoma who have not adequately responded to first-line therapy. A barrier to good compliance with concomitant therapy is the need to administer 5 or 6 drops of medication on 2 or 4 occasions during the day. Timolol 0.5% and dorzolamide 2.0% have therefore been combined in a single formulation, reducing the number of administrations required to 2 per day. Clinical trials in patients with glaucoma have demonstrated that dorzolamide 2%/timolol 0.5% (dorzolamide/timolol) is superior to monotherapy with the individual components. When dorzolamide/timolol administered twice daily was compared with concomitant treatment with dorzolamide 2% and timolol 0.5%, each administered twice daily for 90 days, both regimens resulted in marked lowering of trough IOP (measured just before the morning dose) compared with baseline (reduction in IOP = 4.2mm Hg). The effect of the 2 regimens on IOP at all time points, both before treatment and at peak effect (2 hours after treatment), were virtually indistinguishable. When the combined formulation was compared with a concomitant regimen that included dorzolamide 2% 3 times daily and timolol 0.5% twice daily the concomitant regimen was slightly more efficacious than the combined regimen at trough after 90 days: IOP was lowered by 3.6mm Hg in the combined group versus 4.1mm Hg in the concomitant group. Dorzolamide/timolol has been compared with concomitant administration of timolol 0.5% and the IOP lowering miotic drug, pilocarpine 2.0%. This non-blind patient-preference study found that both regimens reduced IOP. However, the dorzolamide/timolol combination was preferred by the patients because of reduced frequency and severity of adverse effects and less frequent administration. Dorzolamide/timolol was well tolerated in clinical trials, the adverse effects reflected those of the individual components, and no additional tolerability issues were identified. However, the potential for timolol to cause cardiorespiratory effects must be considered when prescribing this combination. Furthermore, dorzolamide is a sulfonamide and can cause allergic reactions in those who are hypersensitive to this class of drug. Conclusions: Dorzolamide/timolol is a well tolerated and effective fixed combination for lowering IOP in the treatment of open-angle glaucoma and is likely to be useful in those patients who do not respond adequately to first-line monotherapy. Compared with concomitant therapy with the same 2 drugs the primary advantage is convenience, which may lead to improved compliance. Studies of compliance and comparisons with other currently available combination therapies would be useful to fully define the value of the formulation. Nonetheless, dorzolamide combined with timolol in a single applicator system will be a useful addition to the treatment options for glaucoma, a leading cause of preventable blindness.
Keywords: Adrenergic Beta-Antagonists -- Therapeutic Use; Carbonic Anhydrase Inhibitors -- Therapeutic Use; Glaucoma -- Drug Therapy; Sulfonamides -- Therapeutic Use; Sulfur Compounds -- Therapeutic Use; Timolol -- Therapeutic Use; Adrenergic Beta-Antagonists -- Pharmacokinetics; Carbonic Anhydrase Inhibitors -- Pharmacokinetics; Drug Combinations; Drug Therapy, Combination; Female; Glaucoma -- Metabolism; Intraocular Pressure -- Drug Effects; Intraocular Pressure -- Physiology; Male; Sulfonamides -- Pharmacokinetics; Sulfur Compounds -- Pharmacokinetics; Timolol -- Pharmacokinetics

Exploring the influence of patient-provider communication on intraocular pressure in glaucoma patients. - Carpenter, Delesha M.; Tudor, Gail E.; Sayner, Robyn; Muir, Kelly W.; Robin, Alan L.; Blalock, Susan J.; Hartnett, Mary Elizabeth; Giangiacomo, Annette L.; Sleath, Betsy L. (Patient Education & Counseling, 2015)
Objective: We examined whether six patient-provider communication behaviors directly affected the intraocular pressure (IOP) of glaucoma patients or whether patient medication adherence and eye drop technique mediated the relationship between self-efficacy, communication, and IOP.Methods: During an 8-month, longitudinal study of 279 glaucoma patients and 15 providers, two office visits were videotape-recorded, transcribed, and coded for six patient-provider communication behaviors. Medication adherence was measured electronically and IOP was extracted from medical records. We ran generalized estimating equations to examine the direct effects of communication on IOP and used bootstrapping to test whether medication adherence and eye drop technique mediated the effect of communication on IOP.Results: Provider education about medication adherence (B=-0.50, p<0.05) and inclusion of patient input into the treatment plan (B=-0.35, p<0.05) predicted improved IOP. There was no evidence of significant mediation.Conclusion: The positive effects of provider education and provider inclusion of patient input in the treatment plan were not mediated by adherence and eye drop technique.Practice Implications: Providers should educate glaucoma patients about the importance of medication adherence and include patient input into their treatment plan.
Keywords: Physician-Patient Relations; Patient Education; Intraocular Pressure -- Evaluation; Glaucoma; Human; Videorecording; Communication; Medication Compliance; Prospective Studies; Ophthalmic Solutions; Funding Source

BLOG: Charting a new course for glaucoma care through COVID-19. - Teymoorian, Savak "Sev" (Ocular Surgery News, 2020)
Keywords: Glaucoma; COVID-19; Appointments and Schedules

The impact of a glaucoma nurse specialist role on glaucoma waiting lists. - Slight C; Marsden J; Raynel S (Nursing Praxis in New Zealand, 2009)
Over the last two decades there has been an increasing demand on health care services. This has led to increased waiting lists and waiting times to access public hospital services. In ophthalmic practice an aging population and technological advances have been major contributors to this situation. The challenge for health care providers is how to manage waiting lists within the resources provided and targets set by Elective Services, a department of the Ministry of Health (MoH). The Ministerial Taskforce on Nursing (1998) highlighted that nurses are an underutilised resource. Subsequent to the Ministerial Taskforce, the availability of interim funding from Elective Services and a skilled speciality nursing workforce the Ophthalmology Department at a large metropolitan hospital was able to implement an advanced nursing role with respect to glaucoma management. Early diagnosis is important in reducing the risk of permanent visual impairment from primary open angle glaucoma; therefore the length of time to diagnosis can have long term implications for the patient. Patients for the 'nurse-led' glaucoma clinic were recruited from specific categories of glaucoma patients on the waiting list. An audit of the impact on the waiting list was undertaken periodically over a two year first specialist assessment for glaucoma. The implementation of this role proved to be successful and has subsequently become a permanent nurse specialist position in the ophthalmology department.
Keywords: Clinical Nurse Specialists; Glaucoma -- Diagnosis; Ophthalmic Nursing; Waiting Lists; Audit; Clinical Competence; New Zealand; Nurse-Managed Centers; Nursing Role; Outcomes (Health Care); Patient Selection; Prospective Studies; Referral and Consultation; Triage; Human

Cost of the medical management and prescription pattern for primary open angle glaucoma (POAG) in Ghana-a retrospective cross-sectional study from three referral facilities. - Ocansey, Stephen; Kyei, Samuel; Diafo, Ama; Nkansah Darfor, Kwabena; Boadi-Kusi, Samuel Bert; Aglobitse, Peter B.; Darfor, Kwabena Nkansah (BMC Health Services Research, 2016)
Background: Glaucoma is the leading cause of irreversible blindness globally, and treatment involves considerable cost to stakeholders in healthcare. However, there is infrequent availability of cost information and patterns of management, especially in developing countries. This study determined the cost of the medical management of POAG, adherence, and pattern of medication prescription in Ghana.Methods: A retrospective cross-sectional study involving 891 Primary Open Angle Glaucoma (POAG) cases seen in the year 2012 at three referral facilities. Demographics, ocular history, resource consumption, medication, test, surgery and other related cost were extracted from 84 patients who had fully complied with their treatment to calculate total cost (TC) based on 2012 estimates. Glaucoma drugs prescribed to patients who had adhered to all their review visits within the period evident from case folders were recorded and analysed for the prescription pattern.Results: Out of 891 POAG cases seen in 2012, 351(39.4 %) attended all the required review visits, but only 84 (9.4) had fully and continually adhered to all their treatment regimes. They comprised 41(48.8 %) males and 43(51.2 %) females with a mean age of 65 ± 14.8. Majority of the respondents were elderly above 60 year of age (65.5 %). The total estimated cost for the 84 cases in the year was GH¢ 81,237 ($40,619), comprising GH¢ 72,193 ($36,097) direct medication cost and GH¢9,045 ($4,523) direct non-medication cost (surgery and test cost), and an average of GH¢ 967 ($484) for a mean visit of 5.6 ± 1.1 in the year. A total of 673 glaucoma medications had been prescribed for 351 patients for the year, with timolol being the most prescribed (64.19 %) and monotherapy as the most adopted form of therapy (61.06 %). Age and income showed concurrent increase with cost (P ≤ 0.05).Conclusions: Cost of managing glaucoma constitutes a substantial financial burden and influenced the pattern of medication prescription.
Keywords: Health Care Costs; Glaucoma -- Drug Therapy; Middle Age; Intraocular Pressure; Referral and Consultation; Costs and Cost Analysis; Health Resource Utilization -- Utilization; Blindness -- Prevention and Control; Cross Sectional Studies; Aged; Female; Ghana; Retrospective Design; Male; Human

Optometry-facilitated teleophthalmology: an audit of the first year in Western Australia. - Bartnik, Stephen E.; Copeland, Stephen P.; Aicken, Angela J.; Turner, Angus W. (Clinical & Experimental Optometry, 2018)
Background: Lions Outback Vision has run a state-wide teleophthalmology service since 2011. In September 2015 the Australian federal government introduced a Medicare reimbursement for optometry-facilitated teleophthalmology consultations under specific circumstances. This audit demonstrates the first 12 months experience with this scheme. We aim to provide practical insights for others looking to embed a telemedicine program as part of delivering outreach clinical services.Methods: A 12-month retrospective audit was performed between September 2015 and August 2016, inclusive. A research officer used a specifically designed data extraction tool to record information from all teleophthalmology consultations performed in the time period. The primary outcome was the diagnosis at the end of the teleophthalmology consultation. Secondary outcome measures included the number of teleconsultations, cataract surgery rate, remoteness area of patients referred and imaging accompanying the referral.Results: In the 12-month period, 709 patients were referred resulting in 683 teleophthalmology teleconsultations. Cataract was the most frequent diagnosis (n = 287, 42.7 per cent), followed by glaucoma (n = 77, 11 per cent), age-related macular degeneration (n = 30, 4.4 per cent) and diabetic retinopathy (n = 26, 3.8 per cent). Of those who had teleconsultations, 98.6 per cent were from Outer Regional, Remote or Very Remote Australia. One or more accompanying images or investigations were part of 349 (49 per cent) teleconsultations, most commonly optical coherence tomography (215, 30 per cent) and fundus photography (148, 21 per cent). Face-to-face consultations were undertaken at an outreach clinic in 23 (3.4 per cent) cases, to determine the diagnosis. There were no statistically significant factors associated with attendance at teleophthalmology consultation, or for successfully undergoing cataract surgery.Conclusion: Teleophthalmology is a valuable adjunct to regional outreach ophthalmology services, providing patients with increased access to specialist care for a wide range of ophthalmic conditions, and more efficient access to surgical care.
Keywords: Optometry -- Statistics and Numerical Data; Health Care Delivery -- Statistics and Numerical Data; Audit; Ophthalmology -- Statistics and Numerical Data; Telemedicine -- Statistics and Numerical Data; Health Services Accessibility; Eye Diseases -- Diagnosis; Middle Age; Aged; Female; Referral and Consultation; Adult; Child, Preschool; Eye Diseases -- Therapy; Retrospective Design; Male; Rural Population; Western Australia; Child; Aged, 80 and Over; Adolescence; Human

Comparing the effectiveness of selective laser trabeculoplasty with topical medication as initial treatment (the Glaucoma Initial Treatment Study): study protocol for a randomised controlled trial. - Lamoureux, Ecosse L.; Mcintosh, Rachel; Constantinou, Marios; Fenwick, Eva K.; Jing Xie; Casson, Robert; Finkelstein, Eric; Goldberg, Ivan; Healey, Paul; Thomas, Ravi; Ghee Soon Ang; Pesudovs, Konrad; et al. (Trials, 2015)
Background: Glaucoma is the leading cause of irreversible blindness in the world. Estimated to affect 60 million people worldwide, this figure is expected to rise to 80 million by 2020. Untreated, glaucoma leads to visual decay and eventually to blindness, and can significantly reduce quality of life. First-line treatment in patients with primary open-angle glaucoma and exfoliative glaucoma is topical medical therapy with ocular hypotensives as eye drops. However, eye drops have several disadvantages including cost, possible local and systemic side effects, and adherence and perseverance issues. Randomised controlled trials have demonstrated that selective laser trabeculoplasty is equally as effective in lowering intraocular pressure as eye drops. However, the impact of these two treatment modalities from the patient and economic perspectives has not been adequately determined. Thus, it remains unclear whether topical medical therapy or selective laser trabeculoplasty should be recommended as first-line treatment for glaucoma.Methods/design: This protocol describes an international, multi-centre, randomised controlled trial to determine the optimum first-line therapy for people with primary open-angle glaucoma and exfoliative glaucoma. This study will compare the effect of selective laser trabeculoplasty and topical medication with respect to patients' generic and glaucoma-specific quality of life. The trial will also provide a detailed cost-effectiveness analysis and compare the clinical effectiveness with respect to the degree of intraocular pressure lowering and rates of treatment failure. Research coordinators in each centre will identify and recruit previously untreated patients with primary open-angle glaucoma and exfoliative glaucoma. Those who meet the eligibility criteria will be invited to enter a randomised controlled trial with either selective laser trabeculoplasty or topical ocular hypotensive therapy, according to a stepped regimen. Outcome assessment will be measured at 6 weeks and at 6, 12, and 24 months post-treatment. Regular clinic follow-ups will continue as clinically indicated between study outcome visits.Discussion: The Glaucoma Initial Treatment Study is the first multi-centred RCT to determine the optimum first-line therapy for people with glaucoma. Our trial will have an unprecedented capacity to meaningfully transform the treatment and management of glaucoma in Australia and overseas.Trial Registration: ACTRN12611000720910; Date registered: 11 July 2011.
Keywords: Intraocular Pressure -- Drug Effects; Glaucoma -- Surgery; Laser Therapy -- Methods; Glaucoma -- Drug Therapy; Trabeculectomy -- Methods; Antihypertensive Agents -- Administration and Dosage; Vision -- Drug Effects; Laser Therapy -- Economics; Glaucoma -- Diagnosis; Time Factors; Administration, Intraocular; Trabeculectomy -- Adverse Effects; Study Design; Laser Therapy -- Adverse Effects; Laser Therapy -- Equipment and Supplies; Human; Ophthalmic Solutions; Trabeculectomy -- Economics; Antihypertensive Agents -- Economics; Cost Benefit Analysis; Trabeculectomy -- Equipment and Supplies; Antihypertensive Agents -- Adverse Effects; Health Care Costs; Glaucoma -- Physiopathology; Treatment Outcomes; Glaucoma -- Economics; Protocols; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Randomized Controlled Trials; Random Assignment

The temperament and character personality profile of the glaucoma patient. - Çakmak, Harun; Altinyazar, Vesile; Yilmaz, Suzan Güven; Ömürlü, İmran Kurt; Kocatürk, Tolga; Yazici, Alper; Değirmenci, Cumali; Dündar, Sema Oruç; Ates, Halil (BMC Ophthalmology, 2015)
Background: To determine the temperament and character profile of glaucoma patients.Methods: A total of 234 patients (104 with primary open angle glaucoma, and 130 control subjects without any ocular disease) were selected for this prospective, cross-sectional study. All the participants underwent a comprehensive ophthalmological examination, including the best corrected visual acuity, intraocular pressure measurement, gonioscopy, and visual field analysis. All the participants were given the Turkish version of the Temperament and Character Inventory (TCI). The TCI is a self-reported evaluate, with 240 true/false items measuring four domains of temperament; harm avoidance (HA), persistence (PS), novelty seeking (NS), reward dependence (RD), and three domains of character; self-transcendence (ST), cooperativeness (C), self-directedness (SD).Results: The glaucoma patients achieved the higher scores than the controls for the HA and SD dimensions (p < 0.001 and p = 0.033). The glaucoma patients scored lower than the controls for the NS, P and ST dimensions (p < 0.001, p < 0.001 and p = 0.002). There were no differences in the RD and C scores between the patients and the controls (p = 0.944 and p = 0.343). There was no correlation between the duration of illness and the TCI dimensions. Disease severity was positively associated with HA (r = 0,220, p = 0,025) and the anticipatory worry (r = 0.227, p = 0.021) dimension.Conclusions: Glaucoma patients had a different personality profile to healthy individuals. This may affect treatment compliance and is also important when coping with maladaptive patient attitudes.
Keywords: Personality Assessment; Glaucoma -- Psychosocial Factors; Character; Temperament; Visual Acuity; Male; Prospective Studies; Medication Compliance; Female; Aged; Middle Age; Cross Sectional Studies; Intraocular Pressure; Human; Psychological Tests

Predictors of adherence to glaucoma treatment in a multisite study. - Cook, Paul F; Schmiege, Sarah J; Mansberger, Steven L; Kammer, Jeffrey; Fitzgerald, Timothy; Kahook, Malik Y (Annals of Behavioral Medicine, 2015)
Background: Poor adherence hinders glaucoma treatment. Studies have identified demographic and clinical predictors of adherence but fewer psychological variables.Purpose: We examined predictors from four health behavior theories and past research.Methods: In the baseline phase of a three-site adherence study, before any intervention, 201 participants used electronic Medication Event Monitoring System (MEMS) bottles to monitor eyedrop use for 2 months, and completed questionnaires including self-reported adherence.Results: MEMS showed 79% adherence and self-report 94% (0.5-1.5 missed weekly doses), but they correlated only r(s) = 0.31. Self-efficacy, motivation, dose frequency, and nonminority race/ethnicity predicted 35% of variance in MEMS. Cues to action, self-efficacy, and intention predicted 20% of variance in self-reported adherence.Conclusions: Self-efficacy, motivation, intention, cues to action, dose frequency, and race/ethnicity each independently predicted adherence. Predictors from all theories were supported in bivariate analyses, but additional study is needed. Researchers and clinicians should consider psychological predictors of adherence. (ClinicalTrials.gov ID# NCT01409421.).

A Combination of Intrastromal and Intracameral Injections of Amphotericin B in the Treatment of Severe Fungal Keratitis. - Hu, Jianzhang; Zhang, Jingjin; Li, Yanling; Han, Xiaoli; Zheng, Weidong; Yang, Juan; Xu, Guoxing (Journal of Ophthalmology, 2016)
Purpose. To evaluate the efficacy of a combination of intrastromal and intracameral injections of amphotericin B in the treatment of severe recalcitrant fungal keratitis. Methods. Patients with severe fungal keratitis who were resistant to conventional antifungal medical treatments and needed potential surgical intervention were recruited at the First Affiliated Hospital of Fujian Medical University between January 2012 and July 2013. The patients were treated with a combination of intrastromal and intracameral injections of amphotericin B (25 μg/mL and 50 μg/mL, resp.). Selectively repeated injections were performed as necessary. The efficacy, complications, and outcome were evaluated. Results. Nine patients (9 eyes) were involved in this study. All 9 cases responded favorably, and the clinical appearance of serious corneal damage and intraocular extension was resolved after the treatment. Four eyes required only 1 injection, and 5 eyes required repeated injections. Seven corneal ulcers healed with leucoma, and 2 healed with adherent leucoma. All of our cases had a marked increase in the anterior chamber reaction and pain immediately after the injection. There was no obvious clinical evidence of corneal or lenticular toxicity in any patient. Conclusions. A combination of intrastromal and intracameral injections of amphotericin B may be safe and effective for the treatment of severe fungal keratitis that is resistant to conventional therapy.
Keywords: Amphotericin B; Keratitis, Fungal; Corneal Transplantation; Corneal Injuries; Anterior Chamber; Corneal Ulcer; Case Studies

Glaucoma medication adherence among African Americans: program development. - Dreer, Laura E; Girkin, Christopher A; Campbell, Lisa; Wood, Andy; Gao, Liyan; Owsley, Cynthia (Optometry & Vision Science, 2013)
Purpose: To elucidate barriers and facilitators related to glaucoma medication adherence among African Americans (AA) with glaucoma and to elicit input from a community-based participatory research team to guide the development of a culturally informed health promotion program for improving glaucoma medication adherence among AAs.Methods: The nominal group technique (NGT), a highly structured focus group methodology, was implemented with 12 separate groups of AA patients with glaucoma (N = 89) to identify barriers and facilitators related to glaucoma medication usage. Participant rank-ordering votes were summed across groups and categorized into themes. Next, an individually and culturally targeted health promotion program promoting appropriate medication adherence was developed based on focus group results and input from a community-based participatory research team.Results: The top five barriers included problems with forgetfulness, side effects, cost/affordability, eyedrop administration, and the eyedrop schedule. The most salient top five facilitators were fear or thoughts about the consequences of not taking eyedrops; use of memory aids, cues, or strategies; maintaining a regular routine or schedule for eyedrop administration; ability to afford eyedrops; and keeping eyedrops in the same area. The resulting health promotion program was based on a multicomponent empowerment framework that included glaucoma education, motivational interviewing, and problem-solving training to improve glaucoma medication adherence.Conclusions: Barriers and facilitators related to glaucoma medication adherence among AAs are multifactorial. Based on the NGT themes and input from the community-based participatory research team, a culturally informed health promotion program was designed and holds great promise for improving medication adherence among this vulnerable population.
Keywords: Black Persons -- Statistics and Numerical Data; Antihypertensive Agents -- Therapeutic Use; Glaucoma -- Drug Therapy; Medication Compliance; Program Development; Adult; Aged; Aged, 80 and Over; Female; Focus Groups; Glaucoma -- Ethnology; Health Promotion; Human; Male; Middle Age

Antimicrobial efficacy of a novel povidone iodine contact lens disinfection system. - Yamasaki, Katsuhide; Saito, Fumio; Ota, Ritsue; Kilvington, Simon (Contact Lens & Anterior Eye, 2018)
Purpose: Contact lens (CL) wear is a risk factor for the acquisition of microbial keratitis. Accordingly, compliance to manufacturers' recommended hygiene and disinfection procedures are vital to safe (CL) use. In this study we evaluated a novel povidone-iodine (PI) (CL) disinfection system (cleadew, Ophtecs Corporation, Japan) against a range of bacterial, fungal and Acanthamoeba.Methods: Antimicrobial assays were conducted according to ISO 14729 using the recommended strains of bacteria and fungi, with and without the presence of organic soil. Regrowth of bacteria and fungi in the disinfection system was also examined. The activity on biofilms formed from Stenotrophomonas maltophilia and Achromobacter sp. was evaluated. Efficacy against A. castellanii trophozoites and cysts was also investigated.Results: The PI system gave >4 log10 kill of all bacteria and fungi following the manufacturer's recommended disinfection and cleaning time of 4h, with or without the presence of organic soil. No regrowth of organisms was found after 14days in the neutralized solution. In the biofilm studies the system resulted in at least a 7 log10 reduction in viability of bacteria. For Acanthamoeba, >3 log10 kill of trophozoites and 1.1-2.8 log10 kill for the cyst stage was obtained.Conclusions: The PI system effective against a variety of pathogenic microorganisms under a range of test conditions. Strict compliance to recommended CL hygiene procedures is essential for safe CL wear. The use of care systems such as PI, with broad spectrum antimicrobial activity, may aid in the prevention of potentially sight threatening microbial keratitis.
Keywords: Ophthalmic Solutions -- Pharmacodynamics; Sterilization and Disinfection -- Methods; Povidone-Iodine -- Pharmacodynamics; Bacteria; Contact Lenses; Eye Infections, Bacterial -- Prevention and Control; Keratitis -- Prevention and Control; Antiinfective Agents, Local -- Pharmacodynamics; Bacteria -- Drug Effects; Eye Infections, Bacterial -- Microbiology; Keratitis -- Microbiology; Biofilms

Prospective Evaluation of Acupuncture as Treatment for Glaucoma. - Law, Simon K; Lowe, Starrie; Law, Samuel M; Giaconi, JoAnn A; Coleman, Anne L; Caprioli, Joseph (American Journal of Ophthalmology, 2015)
Purpose: To evaluate acupuncture as treatment for glaucoma.Design: Prospective double-masked randomized crossover study.Methods: setting: Clinical practice.Population: One eye per patient with primary open-angle glaucoma and stable intraocular pressure (IOP).Intervention: Patients were randomized to receive 1 acupuncture series (12 sessions with either eye-related [eye-points] or non-eye-related [non-eye-points] acupoints) and then crossed over to receive the other series.Outcome Measures: IOP, blood pressure (BP), heart rate (HR), best-corrected visual acuity (BCVA), visual field (VF), optic disc and peripapillary retinal nerve fiber layer (RNFL) measurements, compliance, and adverse reactions. Probability to detect 3 mm Hg IOP difference between series was 90%.Results: Twenty-two patients volunteered and 11 (50.0%) completed the study; 8 (36.4%) did not complete treatment owing to changes of health, moving away, lack of transportation, or family crisis; and 3(13.6%) were withdrawn owing to needle sensitivity or IOP elevation (8 mm Hg) in the contralateral eye. After an acupuncture session, mean IOP increased slightly with both eye-points (from 12.9 ± 1.8 mm Hg to 13.6 ± 2.0 mm Hg, P = .019) and non-eye-points (from 13.0 ± 1.5 mm Hg to 13.5 ± 1.7 mm Hg, P = .073) series. HR, diurnal IOP, and BCVA showed no statistically significant changes after 12 sessions of either series. Systolic and diastolic BP were reduced after 12 sessions of non-eye-points series (P = .040, P = .002, respectively). Optic disc, RNFL, and VF showed no statistically significant changes.Conclusions: Acupuncture has no overall effect on diurnal IOP or BCVA but may temporally increase the IOP immediately after a treatment session. BP is lowered by acupuncture with non-eye-points, but not with eye-points. Compliance and adverse event rates were low.

Limbal stem cell deficiency secondary to systemic paclitaxel (Taxol) for breast cancer: a case report. - Sekhon, Amardeep; Wang, Jeff Y. F.; Tan, Johnson C. H.; Holland, Simon P.; Yeung, Sonia N. (BMC Ophthalmology, 2020)
Background: Paclitaxel (PTX) is an antineoplastic drug widely used in treatments for ovarian, breast, and small-cell lung cancer. Although ocular effects associated with PTX have been previously described, very few studies have specifically reported systemic PTX as a contributing factor for limbal stem cell deficiency (LSCD), which is characterized by the loss of stem cell and barrier function of the limbus leading to progressive pain and reduction in visual acuity. Described here is a unique case where a patient was diagnosed with LSCD secondary to PTX use for the treatment of breast cancer, at doses of PTX far lower than what is reported in current literature.Case Presentation: A 73-year-old woman with a previous diagnosis of breast cancer with liver metastasis presented with a complaint of increasing pain in the left eye more than the right, along with decreasing visual acuity in both eyes following 3 months of PTX therapy for recurrent liver metastases. Upon examination, best-corrected visual acuity was 20/100 in the right eye and counting fingers on the left. Peripheral neovascularization, stromal scarring, and features of limbal stem cell deficiency (LSCD) were noted on the right cornea. A central neurotrophic ulcer with thinning to 50% and 360 degrees of conjunctivalization were noted on the left. After the discontinuation PTX with doxorubicin as the substitute, there was no further progression of her LSCD, and stabilization of her ocular surface was achieved.Conclusion: Although chemotherapy induced LSCD is a relatively rare adverse event, it is essential for clinicians starting new chemotherapy agents to consider the potential ocular toxicities that may result in their use. Ophthalmology review is recommended for patients after starting PTX therapy to assess for signs of LSCD, particularly in patients where drug toxicity can be aggravated due to impaired hepatic function.
Keywords: Epithelium; Corneal Diseases -- Diagnosis; Corneal Diseases -- Chemically Induced; Breast Neoplasms -- Drug Therapy; Cornea; Aged; Paclitaxel -- Adverse Effects; Female; Stem Cells

Glaucoma awareness and access to healthcare: perceptions among glaucoma patients in Tanzania. - Gilmour-White, Jeremy A; Shah, Peter; Cross, Vinette; Makupa, William; Philippin, Heiko (Postgraduate Medical Journal, 2015)
Objective: To investigate the barriers to access to eye health services for patients with glaucoma in Tanzania with the aim of identifying key areas for improvement and further research.Design: Qualitative investigation using face-to-face semi-structured interviews with patients recruited from the Kilimanjaro Christian Medical Centre (KCMC) outpatient eye clinic. This project is part of the international strategy of the Research into Glaucoma and Ethnicity (ReGAE) programme.Methods: Interviews were conducted with the help of a translator; all data were transcribed in Swahili and then translated into English. Manual coding and qualitative analysis was used to identify major themes and relevant concepts. Data were collected during May and June 2013.Main Outcome Measures: Qualitative data on glaucoma awareness and access to healthcare.Results: 12 patients (7 men, 5 women) of mean age 67.5 years (range 53-86 years) were interviewed. All participants had a previous diagnosis of glaucoma and no other eye conditions. The understanding of glaucoma was limited and the capacity for healthcare providers to improve glaucoma knowledge seemed underused. Participants had particular difficulty in understanding the aetiology and chronicity of the disease. Socioeconomic factors also posed significant barriers to service usage.Conclusions: Among many barriers to access to health services for patients with glaucoma, knowledge of the condition was identified as a key issue. Enhancing the understanding of glaucoma may improve access by triggering earlier presentation, informing those at risk and improving adherence to treatment. This is an area for further research with potential for improving service provision.

Use of Guidelines in the Management of Patients With Glaucoma. - Lee P (Disease Management & Health Outcomes, 1999)
Glaucoma is a leading cause of vision loss and blindness worldwide, especially among the elderly. While there are many forms of glaucoma, there are 2 major groups: 'open-angle' (OAG) and 'angle closure'. The latter is now successfully treated by laser iridotomy. The former, OAG, is a chronic condition that accounts for the majority of glaucomas in developed countries. For both major groups of glaucoma, different management guidelines exist. Both the American Academy of Ophthalmology (AAO) and the American Optometric Association (AOA) have guidelines which cover both groups of glaucoma. Comparison of these guidelines reveals striking similarity, suggesting relative uniformity of professional opinion regarding 'best practice' care of patients with glaucoma. However, there are a few important differences between the 2 guidelines promulgated by the 2 organisations. For OAG, the most important and striking difference is in the criteria for case identification and case severity classification. The AAO uses, essentially, an optic nerve head criteria for case identification and then classifies severity according to visual field criteria only. In contrast, the AOA uses both optic nerve and visual field criterion to both make a diagnosis and to classify the severity of disease. Related to this, early glaucoma in the AAO classification is explicitly glaucoma without any visual field loss, whereas the AOA classification of early glaucoma is already equivalent to at least moderate glaucoma in the AAO scheme. Additional differences between both guidelines centre mostly on more intensive use of services and testing in the optometric guidelines. Little data have been published to date on whether or not care provided to patients conforms to these guidelines. What has been described indicates relatively good compliance with most elements of care, but with major deficiencies in some important aspects of care i.e. the content of care and the follow-up nature of care. As such, significantly more work needs to be undertaken to better provide care to patients with glaucoma.

A comparative study of glaucoma referrals in Southeast Scotland: effect of the new general ophthalmic service contract, Eyecare integration pilot programme and NICE guidelines. - El-Assal, Karim; Foulds, Jonathan; Dobson, Stuart; Sanders, Roshini (BMC Ophthalmology, 2015)
Background: Glaucoma is a progressive disease responsible for the second commonest cause of blindness in the UK. Identifying appropriate patients for hospital care remains an ongoing challenge for all UK hospital glaucoma services. The purpose of our study is to evaluate accuracy and outcome of community optometry referrals before and after implementation of the new general ophthalmic service contract in 2006, the Eyecare Integration Programme pilot in 2008 and the effect of NICE guidelines in glaucoma in 2009, over a 12-year periodMethods: A retrospective case analysis using a glaucoma electronic patient record was performed encompassing two six-year periods, 2000-2006 (Group A), and 2007-2012 (Group B).Results: One thousand six hundred twenty-two new patients' records were analysed. Waiting times reduced from 12.3 to 9.4 weeks. Significantly more patients kept first appointment (p = 0.0002) in group B. Glaucoma symptoms were significantly more in group A (p <0.0001) and only three patients lost Snellen' visual acuity before appointment in group B compared to 12 in group A. Documentation of intraocular pressure was made in 74.1% of Group A and 75.9% of Group B, optic disc appearance in 85.4% of Group A, and 93% of Group B and visual fields in 84.4% of Group A and 81.3% of Group B. Significantly less normal (p < 0,0001), more glaucoma suspects (p < 0.0001), more open angle glaucoma (p = 0.0006) and fewer other conditions (p = 0.0024) were present in group B, compared to group A.Conclusion: Patients were referred earlier with shorter waiting times for hospital appointments with the new Scottish general ophthalmic service and Eyecare Integration Programme. Additionally there were fewer false positive referrals with more diagnosis of glaucomatous disease. We discuss the benefits of these national screening and referral pathways together with their limitations and further refinements.
Keywords: Health Care Delivery, Integrated -- Administration; Optometry -- Standards; Referral and Consultation -- Standards; Practice Guidelines -- Standards; Glaucoma -- Diagnosis; National Health Programs -- Standards; Health Facility Departments -- Standards; Contracts; Aged; Ophthalmoscopy; Glaucoma -- Epidemiology; Scotland; Adult; Human; Visual Fields; Waiting Lists; National Health Programs -- Administration; Guideline Adherence; Male; Documentation -- Statistics and Numerical Data; Female; Tonometry; Pilot Studies; Retrospective Design; Intraocular Pressure -- Physiology; Middle Age; Referral and Consultation -- Administration; Perimetry; Aged, 80 and Over; Ophthalmology -- Standards; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

Socioeconomics of long-term glaucoma therapy in India. - Nayak, Bhagabat; Gupta, Shikha; Kumar, Guresh; Dada, Tanuj; Gupta, Viney; Sihota, Ramanjit (Indian Journal of Ophthalmology, 2015)
Purpose: To determine the socioeconomic impact of long-term glaucoma therapy.Materials and Methods: One hundred and fifty consecutive glaucoma patients on medical therapy, following up at our glaucoma service for at least 6 months were recruited. A questionnaire regarding monthly income, cost of glaucoma medications prescribed, availability of medications, travel time, time spent in review clinics, compliance, education status, medical insurance and systemic or local side-effects was administered.Results: The patients seen at the tertiary government hospital had an average monthly income of Rs. 10,912/- (range: Rs. 500/- to Rs. 50,000/-) with approximately 56% of the patients having an income of less than Rs. 5000/month. The expenditure on anti-glaucoma medications ranged from 0.3% in high income group to 123% of their monthly gross income in low income group (P < 0.0001). The total expenditure including travel, stay, and loss of wages of patients and accompanying persons ranged from 1.6% in high income group to 137% of the monthly income in low income group (P < 0.0001). Mean time required for a glaucoma clinic visit was 15.66 h, (range: 6-96 h/month). About 2.7% experienced systemic side-effects and 21.3% had complaints of ocular adverse effects. About 90% of the patients were compliant. 92% were not covered by any insurance plan/government reimbursement for their treatment.Conclusions: Medical therapy for glaucoma is an economic burden to many patients and should be individualized, according to the socioeconomic status, availability of drugs and the required distance to travel to reach the specialist clinics.

Herpetic eye disease study: lessons learned. - Kalezic, Tanja; Mazen, Mostafa; Kuklinski, Eric; Asbell, Penny (Current Opinion in Ophthalmology, 2018)
Purpose Of Review: Ophthalmic herpes simplex virus (HSV) of the anterior segment is responsible for a range of corneal complications such as scarring, thinning, neovascularization, and severe loss of vision. This review provides current guidelines for treating anterior segment disease related to HSV.Recent Findings: We first review findings from the Herpetic Eye Disease Study (HEDS) clinical trials, and then review new topical and antiviral therapies developed since the HEDS studies. The development of vaccines to prevent recurrent episodes of herpetic infection is briefly reviewed. New corneal surgical procedures, developed since HEDS, may put patients at risk for ocular HSV disease: cross-linking and excimer refractive surgery.Summary: HEDS established the standard of HSV ocular therapy and is still valid today. However, newer antivirals may provide easier compliance with improved bioavailability, efficacy, dosage, and tolerability. Further research is needed to prevent latency of HSV, decrease recurrences, and more effectively treat necrotizing keratitis associated with HSV.
Keywords: Eye Infections, Viral -- Drug Therapy; Antiviral Agents -- Therapeutic Use; Keratitis, Herpetic -- Drug Therapy; Eye Infections, Viral -- Prevention and Control; Viral Vaccines -- Administration and Dosage; Human; Recurrence; Herpesviruses; Keratitis, Herpetic -- Prevention and Control

A Rho-Associated Kinase Inhibitor Protects Permeability in a Cell Culture Model of Ocular Disease, and Reduces Aqueous Flare in Anterior Uveitis. - Yamada, Hiroshi; Yoneda, Masahiko; Inaguma, Shingo; Gosho, Masahiko; Murasawa, Yusuke; Isogai, Zenzo; Zako, Masahiro (Journal of Ocular Pharmacology & Therapeutics, 2017)
Purpose: Recent clinical and experimental studies have reported favorable results when using Rho-associated kinase (ROCK) inhibitors for ocular disease, and in cell culture. Disruption of the human, nonpigmented ciliary epithelial cells (HNPCECs) that comprise the blood-aqueous barrier (BAB) induces anterior uveitis; these cells therefore provide a useful cell model of ocular disease. In this study, we examined the effects of ROCK inhibitors in anterior uveitis and in HNPCECs.Methods: Aqueous flare values and intraocular pressures (IOPs) were determined in patients with anterior uveitis, 2 weeks after administration of ripasudil hydrochloride hydrate, a commercial ROCK inhibitor used to treat glaucoma or ocular hypertension. We also investigated the effects of Y-27632, a second ROCK inhibitor, in HNPCECs following exposure to matrix metalloproteinases (MMPs) and human tumor necrosis factor-alpha (TNF-α).Results: Patients with anterior uveitis, glaucoma, or ocular hypertension, referred to the Aichi Medical University from February to July 2015, were enrolled. Thirty eyes from 25 outpatients were studied. Aqueous flare values and IOPs were significantly decreased 2 weeks after ripasudil hydrochloride hydrate treatment, with no adverse events. In a cultured HNPCEC monolayer, permeability was markedly increased following exposure to MMPs-1, 3, 9, and TNF-α, with these effects attenuated by exposure to Y-27632. In cultured HNPCECs, Y-27632 provoked a marked alteration in cytoskeletal morphology without a significant change in expression levels of claudin-1 and occludin.Conclusion: ROCK inhibitors may confer favorable effects in anterior uveitis, possibly due to a reorganized BAB, although the relevant mechanisms remain unclear.
Keywords: Ophthalmic Solutions -- Pharmacodynamics; Betamethasone -- Analogs and Derivatives; Sulfonamides -- Pharmacodynamics; Protein Kinase Inhibitors -- Pharmacodynamics; Uveitis, Anterior -- Drug Therapy; Isoquinolines -- Pharmacodynamics; Aqueous Humor -- Drug Effects; Glaucoma -- Pathology; Ocular Hypertension -- Pathology; Cell Physiology -- Drug Effects; Betamethasone -- Pharmacodynamics; Betamethasone -- Administration and Dosage; Female; Middle Age; Ophthalmic Solutions -- Administration and Dosage; Glaucoma -- Drug Therapy; Cell Culture Techniques; Phosphotransferases -- Metabolism; Male; Ocular Hypertension -- Drug Therapy; Adult; Isoquinolines -- Administration and Dosage; Phosphotransferases -- Antagonists and Inhibitors; Retrospective Design; Sulfonamides -- Administration and Dosage; Aged; Cells, Cultured; Uveitis, Anterior -- Pathology; Human

A Metric to Consider on the Global Accessibility of Glaucoma Surgery. - Mansouri, Kaweh; Gillmann, Kevin; Bravetti, Giorgio Enrico (JAMA Ophthalmology, 2019)

Response to comments on: A comparative study of tarsorrhaphy and amniotic membrane transplantation in the healing of persistent corneal epithelial defects. - Dhillon, Hennaav; Raj, Anuradha; Bahadur, Harsh; Dhillon, Hennaav Kaur (Indian Journal of Ophthalmology, 2020)
Patients non responsive to the treatment of AMT or tarsorrhaphy were post penetrating keratoplasty patients with large PED's. Indication for penetrating keratoplasty in all these patients was deep corneal opacities with adherent leucoma (healed corneal ulcers). REFERENCES 1 Srirampur A, Kola P, Mansoori T, Vemuganti S. Comments on: A comparative study of tarsorrhaphy and amniotic membrane transplantation in the healing of persistent corneal epithelial defects.
Keywords: Amnion -- Transplantation; Epithelium -- Surgery; Wound Healing; Eyelids; Psychological Tests

Glaucoma treatments abound but patients lax in adherence. - Gebhart, Fred (Ophthalmology Times, 2018)
The article discusses devices and platforms that can address multiple potential problems with glaucoma treatments. Topics mentioned include an injectable intracameral drug depot developed by Graybug, a proprietary hydrogel platform used by Ocular Therapeutix to deliver drugs through intracanalicular inserts, and the potential of thin film polymers being explored by researchers at the University of California, San Francisco for extended drug delivery.
Keywords: Glaucoma -- Therapy; Patient Compliance; Ophthalmic Solutions; Audiovisuals; Product Evaluation

Konzerválószer-mentes krónikus kezelés glaucomában: a cseppkezelés okozta szemfelszínbetegség elkerülése. - Gábor, HOLLÓ (LAM (Lege Artis Medicine), 2018)
Ocular surface disease is a frequently seen condition in the elderly in the general population. In glaucoma patients the glaucoma- therapy related ocular surface disease is a particularly serious and common condition with complex pathogenenesis. Preservatives, most commonly benzalkonium chloride, employed in intraocular pressure lowering eye drops frequently cause or worsen ocular surface disease in glaucoma. The symptoms frequently undermine both the adherence to the prescribed intraocular pressure lowering drops and the vision related quality of life. Therefore the success of long-term glaucoma care in glaucoma-therapy related ocular surface disease is reduced. The current article summarizes the main pathogenetic aspects of glaucoma-therapy related ocular surface disease, and presents how to eliminate the main causative factor and normalize the ocular surface by using completely preservative free topical medication in glaucoma.
Keywords: Glaucoma -- Drug Therapy; Ophthalmic Solutions -- Therapeutic Use; Ophthalmic Solutions -- Adverse Effects; Eye Diseases -- Chemically Induced; Eye Diseases -- Prevention and Control; Administration, Topical

Strategies to estimate the characteristics of 24-hour IOP curves of treated glaucoma patients during office hours. - Colombo, Leonardo; Fogagnolo, Paolo; Montesano, Giovanni; De Cillà, Stefano; Orzalesi, Nicola; Rossetti, Luca (BMC Ophthalmology, 2016)
Background: It is known that office-hour measurements might not adequately estimate IOP mean, peaks and fluctuations in healthy subjects. The purpose of the present study is to verify whether office-hour measurements in patients in different body positions can estimate the characteristics of 24-hour intraocular pressure (IOP) in treated POAG patients.Methods: The 24-hour IOP curves of 70 eyes of 70 caucasian patients with treated glaucoma were analyzed. Measurements were taken at 9 AM; 12, 3, 6, and 9 PM; and 12, 3, and 6 AM, both in the supine (TonoPen XL) and sitting (Goldmann tonometer) positions. The ability of five strategies to estimate IOP mean, peak and fluctuation was evaluated. Each method was analyzed both with regression of the estimate error on the real value and with "hit or miss" analysis.Results: The least biased estimate of the Peak IOP was obtained using measurements from both supine and sitting positions, also yielding the highest rate of correct predictions (which was significantly different from 3 of the remaining 4 strategies proposed, p < 0.05). Strategies obtained from the combination of supine, sitting and peak measurements resulted to be least biased for the Mean IOP and the IOP Fluctuation estimate, but all strategies were not found significantly different in terms of correct prediction rate (the only significant difference being between the two strategies based on sitting or supine measurements only, with the former being the one with the highest correct prediction rate).Conclusions: The results of this study remark the concept that IOP is a dynamic parameter and that intensive measurement is helpful in determining its characteristics. All office-hour strategies showed a very poor performance of in correctly predicting the considered parameters within the thresholds used in this paper, all scoring a correct prediction rate below 52%.
Keywords: Antihypertensive Agents -- Therapeutic Use; Glaucoma -- Drug Therapy; Circadian Rhythm -- Physiology; Glaucoma -- Physiopathology; Intraocular Pressure -- Physiology; Office Visits; Tonometry; Male; Timolol -- Therapeutic Use; Posture; Practitioner's Office; Drug Combinations; Intraocular Pressure -- Drug Effects; Prostaglandins F, Synthetic -- Therapeutic Use; Aged, 80 and Over; Female; Middle Age; Aged; Human

Ethnic variation in prevalence, self-reported barriers and outcome of cataract surgery in a rural population in southwestern China: the Yunnan minority eye study. - Shen, Wei; Cun, Qing; Zhong, Hua; Pan, Chen-Wei; Li, Jun; Chen, Qin (BMC Public Health, 2020)
Background: As a part of the Yunnan Minority Eye Studies, the purpose of this study was to determine the prevalence, barriers and visual acuity outcomes of cataract surgery in a multiethnic adult population in rural areas of southwestern China.Methods: A population-based cross-sectional survey was conducted with participants of Bai, Yi, and Han ethnicity aged ≥50 years in Yunnan. A detailed eye examination was performed. Information on the date, setting, type, and complications of cataract surgery were recorded in the examination of cataract-operated eyes.Results: Of 6546 subjects (2133 Bai ethnicity, 2208 Yi ethnicity and 2205 Han ethnicity), the prevalence of cataract surgery was 6.0%, with 4.6% in Bai, 7.0% in Yi, and 6.4% in Han ethnicity. Cataract Surgical coverage (CSC) among those with presenting visual acuity (PVA) < 20/200 in both eyes because of cataract was 53.3%, with 52.8% in Bai, 64.4% in Yi, and 45.3% in Han ethnicity. CSC was associated with Yi ethnicity, younger age, and higher education level, while unoperated cataract was associated with Han ethnicity, older age, and illiterate. The main barrier to cataract surgery was lack of awareness and knowledge, cost, and fear. Among the 525 cataract-operated eyes, PVA and best-corrected visual acuity (BCVA) of 20/63 or better was 44.5 and 67.2%, respectively, with 48.1 and 65.9% in Bai, 47.8 and 75.4% in Yi, 39.1 and 59.9% in Han ethnicity. Han ethnicity, aphakia, earlier year of surgery, lower-level surgical hospital and illiterate were associated with postoperative visual impairment defined by PVA, while Han ethnicity, aphakia, and illiterate were associated with that defined by BCVA. The principal causes of postoperative visual impairment were retinal disorders (26.8%), posterior capsule opacification (25.1%), refractive error(22.7%), and glaucoma (9.3%).Conclusions: Han ethnicity had a lower CSC and relatively poor visual outcomes compared with ethnic minorities. Further effective effort to remove barriers and provide sight restoration is warranted.
Keywords: Rural Population; Cataract Extraction -- Statistics and Numerical Data; Cataract -- Therapy; Visual Acuity; Healthcare Disparities; Minority Groups -- Statistics and Numerical Data; Ethnic Groups -- Statistics and Numerical Data; Vision Disorders -- Etiology; Aged, 80 and Over; Cataract -- Epidemiology; Cross Sectional Studies; Refractive Errors -- Epidemiology; Male; China; Treatment Outcomes; Aged; Prevalence; Cataract -- Ethnology; Postoperative Period; Female; Self Report; Middle Age; Eye Diseases -- Epidemiology; Psychological Tests

Sustained Delivery of Timolol Maleate for Over 90 Days by Subconjunctival Injection. - Lavik, Erin; Kuehn, Markus H.; Shoffstall, Andrew J.; Atkins, Kristyn; Dumitrescu, Alina V.; Kwon, Young H. (Journal of Ocular Pharmacology & Therapeutics, 2016)
Purpose: Medical treatment of glaucoma relies on intraocular pressure (IOP)-lowering medications, typically administered daily by the patient. While these medications are effective when applied correctly, patient adherence is a major obstacle in glaucoma treatment. We have developed a sustained-release formulation of timolol maleate that can be injected subconjunctivally to avoid patient noncompliance.Methods: A biodegradable microsphere formulation for timolol maleate was injected subconjunctivally in normal rabbits. We measured timolol levels in tears, aqueous humor, vitreous humor, and serum of study rabbits. Furthermore, IOP profiles were recorded longitudinally. Tissue compatibility and side effects were evaluated using histochemistry.Results: The microsphere formulation led to measureable amounts of timolol in the aqueous humor and the tear film for up to 90 days. Timolol was not detectable in the serum at any time. A significant reduction of IOP was observed in treated eyes. Clinically, the subconjunctival administration of the microspheres was well tolerated with no signs of inflammation or infection. The absence of local inflammation was confirmed by histology.Conclusions: A single subconjunctival administration of timolol microspheres achieved delivery and IOP reduction in rabbits for up to 90 days without local or systemic inflammation or toxicity. This approach has the potential to improve the management of glaucoma in patient populations, who are challenged to adhere to a regimen of daily eye drops.
Keywords: Delayed-Action Preparations; Timolol -- Administration and Dosage; Rabbits; Latex; Injections; Animal Studies; Funding Source

Accuracy of Patient-reported Adherence to Glaucoma Medications on a Visual Analog Scale Compared With Electronic Monitors. - Sayner, Robyn; Carpenter, Delesha M.; Blalock, Susan J.; Robin, Alan L.; Muir, Kelly W.; Hartnett, Mary Elizabeth; Giangiacomo, Annette L.; Tudor, Gail; Sleath, Betsy (Clinical Therapeutics, 2015)

MASTER GLAUCOMA SERVICES: Learn how to schedule these patients and code appropriately. - CLERMONT, JOSHUA M. (Optometric Management, 2020)
Keywords: Glaucoma; Private Practice Management; Appointments and Schedules -- Education; Coding -- Education; Optometrists -- Education; Referral and Consultation; Decision Making; Diagnosis, Eye; Insurance, Health, Reimbursement; Billing and Claims

Management of Corneal Bee Sting Injuries. - Rai, Ruju R.; Gonzalez-Gonzalez, Luis A.; Papakostas, Thanos D.; Siracuse-Lee, Donna; Dunphy, Robert; Fanciullo, Lisa; Cakiner-Egilmez, Tulay; Daly, Mary K. (Seminars in Ophthalmology, 2017)
Purpose: To review the management of keratitis after corneal bee stings and to report a case of deep stromal corneal infiltrate secondary to a retained bee stinger managed conservatively in a patient who presented three days after unsanitary manipulation of the stinger apparatus.Methods: Case report and review of literature.Results: A 57-year-old male beekeeper was evaluated for pain, blurry vision, and photosensitivity after a corneal bee sting. Of note, the venom sac had been removed with dirty tweezers three days prior to his visit. On exam, a focal infiltrate with diffuse edema was seen surrounding a retained bee stinger in the peripheral cornea. Trace cells in the anterior chamber were also noted. Based on a high suspicion for infectious keratitis, a conservative treatment strategy was elected. Administration of broad-spectrum topical antibiotics with concomitant abstention of corticosteroids led to rapid resolution of the symptoms. Over 16 months of follow-up, the stinger has remained in situ without migration and the patient has maintained 20/20 visual acuity without complications. There is debate on the preferred method for the management of corneal injury secondary to bee stings, especially when it is associated with a retained stinger. We herein present our findings in our appraisal of reported cases.Conclusion: In the aftermath of an ocular bee sting, close surveillance for inflammation and infection is essential. Individual manifestations of these injuries vary in timing, type, and severity; therefore, the accessibility of the stinger and the evolving clinical picture should guide therapeutic decisions.
Keywords: Corneal Injuries -- Therapy; Cornea; Insect Bites and Stings -- Therapy; Eye Foreign Bodies -- Therapy; Glucocorticoids -- Administration and Dosage; Antibiotics -- Administration and Dosage; Insect Bites and Stings -- Diagnosis; Corneal Injuries -- Diagnosis; Diagnosis, Eye; Prospective Studies; Visual Acuity; Tomography, Optical Coherence; Eye Foreign Bodies -- Diagnosis; Drug Therapy, Combination; Middle Age; Male; Administration, Topical; Scales

A Novel Approach to Helping People with Glaucoma Use Their Drops Routinely. - McDonald, John E.; Dickinson, Jane K. (Optometry & Vision Science, 2019)
Pharmacy data reveal that 70% of patients were missing one or more days worth of drops out of five. Adopting approaches to behavior change and management skills used for people with diabetes may provide insight to improve self-management of glaucoma. Every person who is diagnosed with a chronic health condition such as glaucoma has unique life circumstances that may present barriers to behavior change. An accurate diagnosis and a treatment plan are useless if patients do not use their prescribed eye drops. Active listening and effective communication can result in persons who are more engaged in their self-care behaviors. Collaborative communication using person-centered and strengths-based messages could help eye care providers identify challenges and concerns for people with glaucoma who are experiencing inconsistencies with their eye drops. In an atmosphere where patients can discuss their challenges with treatment recommendations without judgment or fear, they are more likely to trust their provider and therefore share their situation openly and honestly. This is accomplished by choosing language that communicates mutually-agreed-upon self-management goals and addresses and strengthens individual and clinical outcomes. The eye care professional is then seen by the patient as a resource who can empathize when setbacks occur and reinforce the patient's self-management goals. Open-ended questions and tell-ask-tell approaches for identifying barriers to care are keys to more effective communication and trusting relationships. This includes recognizing that glaucoma is associated with increased rates of anxiety or depression that may be an overlooked barrier to self-management. By adopting language recommendations from diabetes care and education, eye care practitioners may be better equipped to help people with glaucoma improve their self-care.
Keywords: Antihypertensive Agents -- Administration and Dosage; Ophthalmic Solutions -- Administration and Dosage; Communication; Glaucoma -- Drug Therapy; Language; Patient Education -- Methods; Self Administration; Medication Compliance; Physician-Patient Relations; Administration, Intraocular; Patient Centered Care; Scales

Managing cataracts in glaucoma patients: A rock-hard case: Challenging procedures often require a deft approach by surgeons. - Caceres, Vanessa (Ophthalmology Times, 2019)
The article offers tips in managing rock-hard cataract in glaucoma patients. Topics discussed include insight from Dr. Garry P. Condon, Ophthalmology associate at Allegheny Ophthalmic on the use of a divide-and-conquer approach in phaco energy being expended in the capsular bag, and taking advantage of an adherent dispersive viscoelastic material to protect the endothelium. Also mentioned are postoperative use of intra-ocular pressure (IOP) lowering medication.
Keywords: Cataract Extraction -- Methods; Glaucoma; Intraocular Pressure

Current opinion in ophthalmology: novel glaucoma devices in the pipeline. - Ittoop, Sabita M.; Seibold, Leonard K.; Kahook, Malik Y. (Current Opinion in Ophthalmology, 2019)
Purpose Of Review: Adherence to chronic use of topical intraocular pressure (IOP) lowering medications is a fundamental barrier to successful, long-term control in patients suffering from glaucoma. This has fueled innovation to create new vehicles for drug administration, new drug formulations with enhanced bioavailability, and minimally invasive glaucoma surgeries (MIGS) with improved risk-benefit profiles to enhance sustained IOP control. The present article is an overview of novel devices in the pipeline.Recent Findings: Several new devices that promise to deliver sustained drug therapy and reduce dependence on daily patient adherence are currently being vetted through clinical trials. In addition, the pipeline for new MIGS devices that target sustained IOP control continues to grow.Summary: Alternative drug delivery approaches and novel MIGS devices broaden the treatment options for patients with glaucoma. This will allow the clinician to customize treatment by selecting specific approaches based on each patient's individual needs and coexisting ocular pathologies. Additional comprehensive, large-scale, clinical studies will help define the role that these options hold in a constantly evolving treatment paradigm.
Keywords: Drug Delivery Systems; Glaucoma -- Therapy; Minimally Invasive Procedures; Drugs; Intraocular Pressure -- Drug Effects; Glaucoma -- Drug Therapy; Ophthalmology; Tonometry; Glaucoma -- Surgery

Trends in Glaucoma Medication Expenditures under Universal Health Coverage: A National Population-Based Longitudinal Survey in Taiwan. - Chiu, Shin-Lin; Chu, Chiao-Lee; Muo, Chih-Hsin; Chen, Chiu-Liang; Lan, Shou-Jen (Journal of Ophthalmology, 2015)
Medical care in Taiwan is well known for its low cost, high efficiency, high quality, excellent medical accessibility, and high equity. We investigate the trends in medication expenditures for glaucoma from 1997 to 2010. The results show that higher medical expenditures were incurred by patients who were aged ≥40 years, male patients, and patients in the highest salary population whereas lower medical expenditures were incurred by blue-collar workers. The medications with the most significant increases in expenditure were prostaglandin analogs (PGAs), α-agonists, and fixed combinations, whereas the medications with the most significant decreases in expenditure were β-blockers and cholinergic agonists. The number of trabeculectomies shows two downward break points in 1999 and 2000 when PGAs were listed and were reimbursed. These results suggest socioeconomic disparities in glaucoma care, as well as understanding of the changes in the expenditure of glaucoma medications under such universal health insurance coverage system.
Keywords: Glaucoma -- Drug Therapy; Drugs, Prescription -- Economics; Health Care Costs -- Taiwan; Insurance Coverage; Government Programs; Taiwan; Human; Prospective Studies; Adult; Costs and Cost Analysis; Linear Regression; Pearson's Correlation Coefficient; Models, Statistical; Data Analysis Software; Male; Middle Age; Aged; Female

Changes in Ocular Surface Characteristics after Switching from Benzalkonium Chloride-Preserved Latanoprost to Preservative-Free Tafluprost or Benzalkonium Chloride-Preserved Tafluprost. - Tokuda, Naoto; Kitaoka, Yasushi; Matsuzawa, Akiko; Tsukamoto, Ayaka; Sase, Kana; Sakae, Shinsuke; Takagi, Hitoshi (Journal of Ophthalmology, 2017)
Purpose. The aim of the present study was to examine the effects of switching from Latanoprost ophthalmic solution containing a preservative to preservative-free Tafluprost ophthalmic solution or Tafluprost containing a preservative on ocular surfaces. Materials and Methods. Forty patients (40 eyes) with glaucoma (mean age: 62.0 ± 10.9 years) using Latanoprost with preservative for six months or longer were assigned either to a Tafluprost-containing-preservative group (20 eyes) or preservative-free-Tafluprost group (20 eyes). The intraocular pressure, corneal epithelial barrier function (fluorescein uptake concentration with fluorophotometer FL-500), superficial punctate keratopathy (AD classification), and tear film breakup time (TBUT) were assessed before switching and at 12 weeks after switching. Results. No significant differences in intraocular pressure were noted after switching in either group. Corneal epithelial barrier function was improved significantly after switching in both the Tafluprost-containing-preservative and the preservative-free-Tafluprost groups. There were no significant differences in AD scores after switching in the Tafluprost-containing-preservative group, but significant improvements were noted in the preservative-free-Tafluprost group. No significant differences in TBUT were noted in the Tafluprost-containing-preservative or preservative-free-Tafluprost groups after switching. Conclusion. After switching from preservative Latanoprost to Tafluprost containing-preservative or preservative-free Tafluprost, corneal epithelial barrier function was improved while the intraocular pressure reduction was retained.
Keywords: Intraocular Pressure; Glaucoma -- Drug Therapy; Dry Eye Syndromes -- Drug Therapy; Latanoprost; Ophthalmic Solutions; Chlorides; Eye; Descriptive Statistics; Paired T-Tests; Sensitivity and Specificity

Effects of Common Topical Antiglaucoma Medications on the Ocular Surface, Eyelids and Periorbital Tissue. - Servat, J. Javier; Bernardino, C. Robert (Drugs & Aging, 2011)
Glaucoma affects millions of people around the world. With the baby boom generation aging, the number of people affected by primary open-angle glaucoma in the US is expected to reach 3.3 million by 2020, and about half may not know they have the disease. The treatment of most forms of glaucoma includes the use of topical agents that enhance aqueous humour outflow, reduce aqueous production, or both. Topical intraocular pressure-lowering drugs must penetrate across the tissues of the eye to reach their therapeutic targets. Often, these tissues show the first signs and symptoms of drug toxicity and adverse effects. These include eyelid dermatitis, malpositions, lacrimal system scarring, ocular discomfort upon instillation, tear film instability, conjunctival inflammation, subconjunctival fibrosis, conjunctival epithelium changes, and corneal surface and endothelial impairment. For these reasons, ophthalmologists should evaluate the risks and benefits of ophthalmic medications before initiating therapy, identify the minimum dosages necessary to achieve a therapeutic benefit, and monitor patients for local and systemic adverse effects. Adverse events may be reduced by changing to a different class of topical medication, using corticosteroids, lubricating the eyes frequently, and reducing exposure to preservatives. This in turn can lead to higher levels of adherence to antiglaucoma therapy, improved outcomes and a reduction in the costs associated with long-term glaucoma complications. This article reviews the ocular adverse effects associated with the various classes of topical antiglaucoma drugs, with a particular focus on the ocular surface, eyelids and periorbital tissue.
Keywords: Administration, Topical; Glaucoma -- Drug Therapy; Eyelids -- Drug Effects; Eye -- Anatomy and Histology; Human; PubMed; Medline; Receptors, Adrenergic, Beta -- Antagonists and Inhibitors; Lacrimal Apparatus -- Drug Effects; Receptors, Adrenergic, Alpha

Sustained-release delivery systems on horizon of glaucoma care: Novel platforms address adherence; clinicians look to efficacy, treatment duration. - Charters, Lynda (Ophthalmology Times, 2019)
The article reports on how sustained-release delivery systems will help address compliance in patients with glaucoma. The challenges of developing sustained-release platforms are also discussed. The risk-to-benefit ratio for patients with advanced disease can change if better efficacy and treatment duration can be achieved. It is noteworthy that intraocular pressure increases are asymptomatic when considering any sustained-release platform.
Keywords: Delayed-Action Preparations; Glaucoma -- Drug Therapy; Treatment Duration; Patient Compliance; Treatment Outcomes; Drug Design; Patient Safety; Ocular Hypertension; Risk Assessment; Anterior Eye Segment; Infusion Pumps, Implantable; Patient Attitudes

Reconsidering the Postoperative Day 0 Visit for Retina Surgery. - Ringeisen, Alexander L.; Parke III, David Wilkin; Parke, David Wilkin 3rd (Ophthalmic Surgery, Lasers & Imaging Retina, 2018)
Background and Objective: This study compares outcomes of patients who were examined on postoperative (PO) day 0 and PO day 1 following retina surgery.Patients and Methods: A nonrandomized, comparative, retrospective series of one vitreoretinal surgeon was conducted on 166 patients with a PO day 0 visit (approximately 5 hours following surgery) and 428 patients with a PO day 1 visit.Results: Among patients examined at PO day 0, 4.6% had hypotony (intraocular pressure [IOP] ≤ 5 mm Hg) and 1.8% needed intervention for elevated IOP (IOP ≥ 30 mm Hg) compared with 1.6% and 4.0% of patients, respectively, examined on PO day 1.Conclusion: Following retina surgery, there is a similar percentage of patients with abnormal IOP when patients are examined on PO day 0 when compared with PO day 1. However, the rate of hypotony was statistically higher on PO day 0, and there was a trend toward more elevated IOP on PO day 1. [Ophthalmic Surg Lasers Imaging Retina. 2018;49:e52-e56.].
Keywords: Retinal Diseases -- Surgery; Ocular Hypertension -- Diagnosis; Office Visits -- Statistics and Numerical Data; Eye Diseases -- Diagnosis; Postoperative Complications; Male; United States; Eye Diseases -- Epidemiology; Time Factors; Prospective Studies; Middle Age; Ocular Hypertension -- Epidemiology; Eye Diseases -- Physiopathology; Ocular Hypertension -- Physiopathology; Retrospective Design; Postoperative Period; Human; Intraocular Pressure -- Physiology; Female; Incidence; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

Awareness and practices regarding eye diseases among patients with diabetes: a cross sectional analysis of the CoDiab-VD cohort. - Konstantinidis, Lazaros; Carron, Tania; de Ancos, Eva; Chinet, Léonie; Hagon-Traub, Isabelle; Zuercher, Emilie; Peytremann-Bridevaux, Isabelle (BMC Endocrine Disorders, 2017)
Background: The increasing prevalence of diabetes is leading to a rise of eye diseases, augmenting the risk of sight-threatening complications. The aim of this study was to evaluate prevalence, awareness and practices regarding eye diseases among patients with diabetes in the canton of Vaud, Switzerland. Methods: A cohort of 323 patients with diabetes completed a self-administered questionnaire assessing prevalence, awareness and practices regarding eye diseases, besides health status and quality of care measures. Descriptive analyses followed by exploratory subgroup analyses and linear regressions were performed to investigate factors associated with awareness and practices. Results: While diabetic retinopathy was reported by 40.9% of patients with type 1 diabetes and 9.8% of patients with type 2 diabetes, 35.8% and 12.6% of all participants reported cataract and glaucoma, respectively. Awareness that diabetes could damage the eyes was reported by almost all participants; the majority was also aware of the importance of glycemic control and regular eye examination in preventing eye diseases. In contrast, only 70.5% of participants underwent an eye examination by an ophthalmologist during the past year. Eye examination was associated with better patients' awareness. Barriers mentioned by patients revealed a lack of knowledge about screening guidelines, in particular regarding the preventive nature of eye examinations. Conclusions: Despite high levels of awareness regarding diabetic eye diseases, a significant proportion of patients with diabetes did not report annual eye examination. Both healthcare strategic efforts targeting the promotion of regular eye examination and initiatives aiming at improving knowledge of screening guidelines should be encouraged. Trial registration: ClinicalTrials.gov on 9th July 2013, identifier (retrospectively registered).
Keywords: Diabetes Mellitus -- Complications; Eye Diseases -- Prevention and Control; Prevalence -- Evaluation; Cognition -- Evaluation; Health Knowledge; Attitude to Health -- Evaluation; Human; Cross Sectional Studies; Prospective Studies; Switzerland; Self Report; Questionnaires; Health Status; Quality of Health Care; Exploratory Research; Linear Regression; Descriptive Statistics; Cataract; Glaucoma; Diagnosis, Eye; Health Services Accessibility

Patterns of adherence to NICE glaucoma guidance in two different service delivery models. - Chawla A; Patel I; Yuen C; Fenerty C; Chawla, A; Patel, I; Yuen, C; Fenerty, C (Eye, 2012)
Purpose: To assess adherence patterns to the UK National Institute of Health and Clinical Excellence (NICE) guidelines on glaucoma management (2009) in a tertiary referral centre shared care setting and in a district general hospital (DGH) setting. Method: We performed a retrospective case note analysis of 200 patients from two centres between January and June 2010. The two centres involved were a consultant-guided teaching hospital optometry-led shared care setting (setting 1) and a consultant-led DGH clinic setting (setting 2). The main outcome measures were compliance with eight of the main NICE guidelines on glaucoma diagnosis and management (2009). Results: Both centres showed good adherence to the guidelines regarding the choice of initial treatment (96% vs 100%, settings 1 and 2, respectively) and arranging appropriate monitoring intervals (92% vs 86%). However, significant differences were seen when assessing whether an optic disc image was obtained at the initial visit (74% vs 10%), whether an appropriate initial assessment was performed (96% vs 58%), whether patients' review interval complied with the NICE guidance regardless of hospital cancellations (92% vs 66%), and whether concordance with medication was checked (88% vs 24%) (settings 1 and 2, respectively, P<0.01-Fisher's exact test). Conclusion: Our study provides evidence to suggest that a hospital-based shared care service with trained optometrists using assessment sheets compares favourably to non-specialist glaucoma care delivered by ophthalmologists.
Keywords: Glaucoma -- Diagnosis; Guideline Adherence -- Standards; Intraocular Pressure; Ophthalmology -- Standards; Optometry -- Standards; Multidisciplinary Care Team -- Standards; Practice Guidelines -- Standards; Aged; Health Care Delivery -- Standards; Female; Diagnosis, Eye; Great Britain; Hospitals, Public -- Standards; Academic Medical Centers -- Standards; Human; Male; Middle Age; National Health Programs -- Standards; Retrospective Design; Tonometry; Perimetry; Visual Fields

Analysis of Factors Affecting Patients’ Compliance to Topical Antiglaucoma Medications in Egypt as a Developing Country Model. - Abu Hussein, Nahla B.; Eissa, Iman M.; Abdel-Kader, Ahmed A. (Journal of Ophthalmology, 2015)
Purpose. To study factors affecting patients’ compliance to antiglaucoma medications in Egypt where there are unique factors as a developing country. Patients and Methods. A cross-sectional descriptive study on 440 Egyptian patients with open angle glaucoma (OAG) recruited for over two years. The patients were thoroughly interviewed about their age, education level, duration of glaucoma, difficulty in instilling the drops, medication regimens, a family history of glaucoma, knowledge of the disease, and the presence of medical insurance. Results. 236 (53.6%) were noncompliant compared to 204 (46.4%) who were compliant. Females had a tendency for higher compliance (p=0.061). Patient age above 50 years and low level of education and negative family history of glaucoma were factors significantly associated with poor compliance (p<0.0001). Polytherapy and lack of medical insurance could be contributing factors. Conclusion. Egyptian patients have a high rate of noncompliance compared to the average in literature. Great effort is needed in educating patients about the importance of medications and the risk and the prognosis of this disease. Economic factors must also be taken into consideration in developing countries with large number of poor patients. We recommend simplifying drug regimens, incorporating electronic dose monitors, and creating reminders for follow-up visits of glaucoma patients.
Keywords: Intraocular Pressure; Patient Compliance; Medication Compliance; Descriptive Research; Family -- Education; Family History; Developing Countries; Egypt; Factor Analysis; Logistic Regression; Female; Multivariate Analysis; Univariate Statistics; Middle Age; Chi Square Test; Descriptive Statistics; Clinical Trials; Regression; Case Studies; Qualitative Studies; Data Collection; Cross Sectional Studies; Interviews; Questionnaires; Surveys

Cataract surgeons adopting interventional glaucoma treatments: Tips for working the latest MIGS and other procedures into your practice. - Tyson, Farrell "Toby" (Ophthalmology Times, 2018)
The article offers tips for adopting micro-invasive glaucoma surgery (MIGS) and other procedures into the practice of cataract surgery. It recognizes these procedures for having much lower risks of complications compared with older procedures. Cataract surgeons are advised to consider integrating standalone procedures into their practice and to use a gonio lens in implanting a stent in the eye.
Keywords: Glaucoma -- Surgery; Surgeons; Cataract Extraction; Microsurgery -- Methods; Surgical Technology; Intraocular Pressure; Perioperative Care; Postoperative Period; Severity of Illness; Disease Progression; Insurance Coverage; Needs Assessment; Patient Compliance; Decision Making, Clinical

Consecutive bilateral decompression retinopathy after mitomycin C trabeculectomy: a case report. - Marcos Figueiredo, Ana Raquel; Coutinho Sampaio, Isabel; dos Santos Menéres, Maria João Fernandes; Spaeth, George L.; Figueiredo, Ana Raquel Marcos; Sampaio, Isabel Coutinho; Menéres, Maria João Fernandes Dos Santos; Fernandes dos Santos Menéres, Maria João (Journal of Medical Case Reports, 2016)
Background: After a successful trabeculectomy, a sudden intraocular pressure decrease may alter the intracranial to intraocular pressure ratio and cause decompression retinopathy. Frequent Valsalva maneuvers may also play a role in its pathogenesis. This condition may manifest as multiple retinal hemorrhages, edema of the optic disc, macular edema, or a sudden decrease in visual acuity postoperatively. Outcomes for patients are usually good, with spontaneous resolution occurring within a matter of weeks. It has been rarely reported in the literature as a bilateral condition.Case Presentation: We present a case of consecutive bilateral decompression retinopathy in a 54-year-old severely obese Caucasian woman (body mass index 37 kg/m(2)) with open angle glaucoma and a poor history of medical therapeutic compliance, who chose surgical treatment based on her inability to consistently use ocular drops. Our patient underwent a trabeculectomy with mitomycin C in both eyes, with surgeries taking place 3 months apart. After the first surgery, 2 weeks postoperatively, she complained of decreased visual acuity. Examination of her right eye fundus revealed multiple retinal hemorrhages and disc edema. There was a similar pattern in her left eye, this time including maculopathy. Her visual acuity and fundoscopic changes resolved spontaneously over a period of a month in both cases. Currently, our patient has well-controlled bilateral intraocular pressure, ranging between 14 and 16 mmHg, without hypotensive medication.Conclusions: Decompression retinopathy is a potential complication after glaucoma surgery, but has rarely been described as a bilateral consecutive condition. A comprehensive approach could help to anticipate its occurrence and manage it.
Keywords: Retinal Diseases -- Etiology; Trabeculectomy -- Adverse Effects; Middle Age; Mitomycins -- Therapeutic Use; Indicators and Reagents -- Therapeutic Use; Decompression Sickness -- Prevention and Control; Eye Hemorrhage -- Etiology; Female; Glaucoma -- Surgery; Optic Nerve Diseases -- Etiology; Interview Guides

Patient Question-Asking About Glaucoma and Glaucoma Medications During Videotaped Medical Visits. - Sleath, Betsy; Sayner, Robyn; Blalock, Susan J.; Carpenter, Delesha M.; Muir, Kelly W.; Hartnett, Mary E.; Tudor, Gail; Lawrence, Scott; Giangiacomo, Annette L.; Robin, Alan L. (Health Communication, 2015)
We applied the ecologic model of communication in medical consultations to examine how patient, physician, and situational/contextual factors are associated with whether patients ask one or more questions about glaucoma and glaucoma medications during visits to ophthalmologists. Patients with glaucoma who were newly prescribed or already on glaucoma medications were recruited at six ophthalmology clinics. Patients’ visits with their doctors were video-recorded and patients were interviewed after visits. Generalized estimating equations were used to analyze the data. Two hundred and seventy-nine patients participated. Patients asked one or more questions about glaucoma during 59% of visits and about glaucoma medications during 48% of visits. Patients who were newly prescribed glaucoma medications were significantly more likely to ask one or more questions about glaucoma and glaucoma medications. Whether providers asked patients if they had questions was not significantly associated with patient question-asking. Patients were significantly more likely to ask older providers questions about glaucoma medications and female providers questions about glaucoma. Eye care providers should encourage glaucoma patients to ask questions during their medical visits.
Keywords: Physician-Patient Relations; Glaucoma; Patient Education; Office Visits; Communication; Information Seeking Behavior; Human; Videorecording; United States; Multicenter Studies; Scales; Communication -- Evaluation; Literacy -- Evaluation; Kappa Statistic; T-Tests; Chi Square Test; Male; Female; Adult; Middle Age; Odds Ratio; Confidence Intervals; Descriptive Statistics; Qualitative Studies; Descriptive Research; Age Factors; Sex Factors; Funding Source

Electronic monitoring to assess adherence with once-daily glaucoma medications and risk factors for nonadherence: the automated dosing reminder study. - Boland, Michael V; Chang, Dolly S; Frazier, Travis; Plyler, Ryan; Friedman, David S (JAMA Ophthalmology, 2014)
Keywords: Antihypertensive Agents -- Administration and Dosage; Drug Monitoring -- Methods; Glaucoma -- Drug Therapy; Medication Compliance; Prostaglandins F, Synthetic -- Administration and Dosage; Reminder Systems -- Equipment and Supplies; Aged; Antihypertensive Agents -- Therapeutic Use; Prospective Studies; Drug Monitoring -- Equipment and Supplies; Female; Health Behavior; Attitude to Health; Human; Intraocular Pressure -- Drug Effects; Male; Ophthalmic Solutions; Prostaglandins F, Synthetic -- Therapeutic Use; Questionnaires; Risk Factors

Glaucoma: a prescriber's guide. - Price, Liam D; Shweikh, Yusrah; Siriwardena, Dilani (Journal of Prescribing Practice, 2019)
Glaucoma is a common eye condition that features progressive optic nerve damage with corresponding visual field loss. According to The Royal College of Ophthalmologists' The Way Forward: Glaucoma Report, it is destined to become an escalating problem due to an increasingly elderly population expected in the next 2 decades. In order to cope with the anticipated demand, hospital eye services are required to re-think the way care is delivered, and it is likely that more multidisciplinary clinical staff will be needed to manage glaucoma patients. Medical treatment with eye drops is sufficient for most patients, with surgery offered to those with worsening glaucoma despite medical and/or laser treatment, or patients who are intolerant to such treatment. This article aims to provide an overview of glaucoma with a focus on the prescribing options available and the associated challenges of the medical treatment of glaucoma.
Keywords: Glaucoma -- Physiopathology; Glaucoma -- Drug Therapy; Glaucoma -- Surgery; Ophthalmic Solutions; Glaucoma -- Risk Factors; Quality of Life; Prostaglandins -- Analogs and Derivatives; Glaucoma -- Classification; Adrenergic Beta-Antagonists; Carbonic Anhydrase Inhibitors; Parasympathomimetics; Pregnancy; Female; Breast Feeding; Pharmaceutical Additives; Patient Compliance; Ocular Hypertension

Lessons learned from the development and implementation of a patient-reported outcome and experience measure (POEM) in an Australian glaucoma practice. - Fraenkel, Alison; Lee, Graham A.; Vincent, Stephen J; Vincent, Roslyn A.; Bourne, Rupert R. A.; Shah, Peter (BMC Ophthalmology, 2019)
Background: A patient's perception of how their glaucoma is managed will influence both adherence to their medication and outcome measures such as quality of life.Methods: Prospective consecutive study using a Glaucoma Patient-reported Outcome and Experience Measure (POEM) modified for an Australian ophthalmic private clinical practice setting. The Australian Glaucoma POEM consists of eight items related to the patient's understanding of the diagnosis and management, acceptability of the treatment, whether they feel their glaucoma is getting worse, interfering with their daily life and concerns regarding loss of vision as well as addressing whether they feel safe under the care of their glaucoma team and how well their care is organised.Results: Two hundred and two patients (M:F 91:111) participated in the study. Mean ± standard deviation for subject age was 69 ± 13 years. Patient's overall perception of their treatment and outcome was favourable. Younger patients felt their glaucoma interfered more with their daily lives and were more worried about losing vision from glaucoma. The greater the number of medications in use, the more they felt their glaucoma was getting worse and that glaucoma interfered with their daily lives. With all other variables accounted for by the multivariate linear model, female patients more strongly agreed that they understood their glaucoma diagnosis and glaucoma management. The patients with a severe visual defect in their worse eye, reported a greater perceived understanding of their glaucoma diagnosis and management and that they felt that glaucoma had a greater interference on their daily life. They were also more concerned about losing vision from glaucoma than their fellow glaucoma patients with less severe or no visual field deficit in the worse eye.Conclusions: The modified POEM demonstrates potential to capture the concerns of a practice's glaucoma cohort with a view to enhancing the quality of glaucoma care delivered.
Keywords: Visual Fields -- Physiology; Intraocular Pressure -- Physiology; Quality of Health Care; Visual Acuity; Glaucoma -- Therapy; Quality of Life; Glaucoma -- Physiopathology; Glaucoma -- Epidemiology; Female; Prospective Studies; Aged; Morbidity -- Trends; Young Adult; Aged, 80 and Over; Middle Age; Male; Activities of Daily Living; Cross Sectional Studies; Adult; Queensland; Ferrans and Powers Quality of Life Index; Scales

Current management of glaucoma. - Lusthaus, Jed; Goldberg, Ivan (Medical Journal of Australia, 2019)
Glaucoma is an irreversible progressive optic neuropathy, for which the major proven treatment is to lower the intraocular pressure (IOP). Five groups of IOP-lowering eye drops have varying mechanisms of action. Some drops, such as β-blockers and α-2 agonists, have potentially serious systemic side effects. Acetazolamide is the only available oral agent; it is effective at lowering IOP, but significant side effects relegate its use usually to refractory glaucoma. Two new eye drops, netarsudil and latanoprostene bunod, have recently been approved by the United States Food and Drug Administration. Both have novel IOP-lowering mechanisms and target the conventional aqueous outflow system. Selective laser trabeculoplasty is a gentle treatment that enhances conventional aqueous outflow. It may be used as an initial treatment, as a substitute for eye drops, or to delay glaucoma drainage surgery. Recent advancements in glaucoma surgery have seen an influx of minimally invasive glaucoma surgery devices, which are being used more frequently and earlier on in the treatment paradigm. As limited long term data are available, trabeculectomy remains the gold standard IOP-lowering procedure. Improvements in drug delivery are on the horizon. Drug-eluting devices and implants are able to deliver the drug closer to the receptors for an extended period of time. This will improve treatment adherence and efficacy, which are major limitations with current medical therapy.
Keywords: Drug Delivery Systems -- Trends; Glaucoma -- Therapy; Laser Therapy -- Trends; Trabeculectomy -- Trends; Ophthalmic Solutions -- Therapeutic Use

Evolution of the treatment paradigm for maximum medical therapy in glaucoma. - Costa, Vital Paulino; Aung, Tin; Konstas, Anastasios G. (Expert Review of Ophthalmology, 2019)
Introduction: Glaucoma therapy is typically started with a single drug that is considered most effective for IOP control and is relatively safe. Several classes of agents are available, including prostaglandin analogs (PGAs), β-blockers, carbonic anhydrase inhibitors (CAIs), cholinergic agonists, and α2-agonists. Most patients will require combined therapy to achieve predetermined target intraocular pressure (IOP), which can be difficult to sustain over time. Currently, maximum medical therapy (MMT) in glaucoma refers to ≤3 classes of medications combined to substantially lower IOP. MMT can be achieved using multiple single agents, double, or triple fixed-dose combinations. Areas covered: Several randomized controlled clinical trials demonstrated that 3-drug combination regimens are superior to 2-drug regimens for lowering 24-hour IOP, which may prevent glaucoma progression. However, long-term clinical evidence with 3- or 4-drug MMT regimens is scarce. Expert commentary: The next logical step in evolution of effective MMT may be the use of 4 classes of medications, adding triple fixed-combination to single agent or combining fixed-dose combinations of CAI plus α2-agonist and fixed-dose β-blocker plus PGA. Availability of novel fixed-dose combinations may optimize efficacy, tolerability, adherence, and improve long-term outcomes. Further controlled evidence is required to accurately delineate the value of current and future MMT regimens.
Keywords: Evolution -- Evaluation; Paradigms -- Utilization; Glaucoma -- Drug Therapy; Intraocular Pressure -- Drug Effects; Drug Therapy, Combination; Glaucoma -- Prevention and Control

Systematic review of educational interventions to improve glaucoma medication adherence. - Newman-Casey, Paula Anne; Weizer, Jennifer S; Heisler, Michele; Lee, Paul P; Stein, Joshua D (Seminars in Ophthalmology, 2013)
Adherence to prescribed glaucoma medications is often poor, and proper adherence can be challenging for patients. We systematically reviewed the literature and identified eight studies using educational interventions to improve glaucoma medication adherence. Overall, five of the eight studies found that educational interventions lead to a significant improvement in medication adherence, and two additional studies found a trend towards improvement. Using information from this systematic review and Health Behavior Theory, we constructed a conceptual framework to illustrate how counseling and education can improve glaucoma medication adherence. More rigorous studies grounded in Health Behavior Theory with adequately powered samples and longer follow-up are needed.
Keywords: Antihypertensive Agents -- Therapeutic Use; Glaucoma -- Drug Therapy; Medication Compliance; Patient Education; Human; Patient Attitudes; Scales; Systematic Review

Early surgical intervention with stent advantageous for certain glaucomas: Approach may help physicians, patients avoid compliance, other medical therapy issues. - Vold, Steven D. (Ophthalmology Times, 2017)
This article focuses on early surgical intervention with stent for patients with glaucoma. It discusses the use of micro-invasive glaucoma surgery in controlling intraocular pressure, the trabecular meshwork in patients with glaucoma for a sustained period, and merits of early stent intervention in the glaucomatous-disease process.
Keywords: Glaucoma -- Surgery; Stents; Treatment Outcomes; Early Intervention; Minimally Invasive Procedures; Intraocular Pressure; Medication Compliance

Preliminary Steps to Address Glaucoma Medication Adherence: Beginning to Tackle the Elephant in the Room. - Newman-Casey, Paula Anne; Myers, Jonathan S. (JAMA Ophthalmology, 2019)
Keywords: Medication Compliance; Glaucoma; Antihypertensive Agents; Patient Satisfaction

Accessibility of ophthalmic healthcare for residents of an offshore island-an example of integrated delivery system. - Li-Ju Chen; Yun-Jau Chang; Chun-Fu Shieh; Jy-Haw Yu; Ming-Chin Yang; Chen, Li-Ju; Chang, Yun-Jau; Shieh, Chun-Fu; Yu, Jy-Haw; Yang, Ming-Chin (BMC Health Services Research, 2016)
Background: To assess the utilization of and satisfaction with ophthalmic healthcare provided by integrated delivery system (IDS) since 2000 and vision-related quality of life (VRQoL) for residents of an offshore island of Taiwan.Methods: Facilitators interviewed residents (age ≥ 50 years) with the 25-item National Eye Institute Visual Function Questionnaire (NEI-VFQ-25) for VRQoL and a questionnaire on clinical information, ophthalmic care utilization and satisfaction.Results: A total of 841 participants (response rate 93.4 %, 841/900) completed the questionnaire survey. Mean age was 63.7 (±10. 7) years. The common eye diseases were cataract (44.7 %), dry eye (15.5 %), and glaucoma (8.7 %). Among the participants, 61.0 % sought ophthalmic care under the IDS in the past year and 17.6 % experienced unmet ophthalmic needs in the past 6 months. Satisfaction with ophthalmic care under the IDS was 88.1 %. Determinants of dissatisfaction under the IDS were distance to healthcare facility and VRQoL. Predictors of VRQoL included age, residential area, marital status, occupation, comorbid condition, commercial insurance, household income, cataracts and glaucoma.Conclusions: The implementation of IDS improves accessibility of ophthalmic care for residents of an offshore island. Geographic proximity to avail healthcare facility and VRQoL affect satisfaction with the IDS.
Keywords: Patient Satisfaction; Vision; Health Services Accessibility -- Statistics and Numerical Data; Quality of Life; National Health Programs; Ophthalmology; Aged, 80 and Over; Eye Diseases -- Therapy; Aged; Female; Male; Diagnosis, Eye; Health Care Delivery, Integrated -- Utilization; Middle Age; Taiwan; Regression

Newer brands, compounded drugs improve efficacy, compliance: Compounded drops save time, money. - Wörtz, Gary (Ocular Surgery News, 2020)
Keywords: Chemistry, Pharmaceutical; Ophthalmic Solutions -- Therapeutic Use; Cost Savings; Ophthalmic Solutions -- Economics; Medication Compliance; Treatment Outcomes; Health Care Costs; Drugs, Generic -- Therapeutic Use; Prednisolone -- Therapeutic Use; Quinolines -- Therapeutic Use; Myopia -- Prevention and Control; Glaucoma -- Prevention and Control; Postoperative Period

Community-based screening programs promising for glaucoma: Early disease detection could reduce vision loss, especially in underserved populations. - Harrison, Laird (Ophthalmology Times, 2019)
The article discusses the potential of U.S. community-based mobile screening programs in reducing vision-loss linked to glaucoma in 2019. Topics covered include their identification of patients with glaucoma and other sight-threatening diseases, especially in underserved populations, and their transport of equipment in a van, and presentation of material on, and diagnosis of glaucoma. Also noted are their recommended therapies for the condition.
Keywords: Glaucoma -- Diagnosis; Diagnosis, Eye -- Methods; Early Diagnosis; Community Health Services; Blindness -- Prevention and Control; Centers for Disease Control and Prevention (U.S.); Telemedicine; Eye Care; Intraocular Pressure; Glaucoma -- Therapy; Ophthalmic Solutions; Laser Therapy; Appointments and Schedules

Patient-reported barriers to glaucoma medication access, use, and adherence in southern India. - Sleath BL; Krishnadas R; Cho M; Robin AL; Mehta R; Covert D; Tudor G; Sleath, Betsy L; Krishnadas, R; Cho, Minhee; Robin, Alan L; Mehta, Rakhi; et al. (Indian Journal of Ophthalmology, 2009)
The objectives of the study were to (a) describe the different types of problems that patients in southern India reported having when taking their glaucoma medications and (b) examine the relationship between patient reported-problems in taking their glaucoma medications and the self-reported patient adherence. A survey was conducted by clinical staff on 243 glaucoma patients who were on at least one glaucoma medication in an eye clinic in southern India. We found that 42% of patients reported one or more problems in using their glaucoma medications. Approximately 6% of patients reported being less than 100% adherent in the past week. Unmarried patients and patients who reported difficulty squeezing the bottle and difficulty opening the bottle were significantly more likely to report nonadherence.
Keywords: Antihypertensive Agents -- Therapeutic Use; Attitude to Health; Drug Utilization -- Statistics and Numerical Data; Glaucoma -- Drug Therapy; Health Services Accessibility -- Statistics and Numerical Data; Medication Errors -- Statistics and Numerical Data; Patient Compliance; Female; Health Services Research; India; Male; Questionnaires; Urban Population; Human

Factors associated with adherence to glaucoma pharmacotherapy in the primary care setting. - Cohen Castel, Orit; Keinan-Boker, Lital; Geyer, Orna; Milman, Uzi; Karkabi, Khaled (Family Practice, 2014)
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Physician's Role; Primary Health Care; Aged; Aged, 80 and Over; Antihypertensive Agents -- Therapeutic Use; Cross Sectional Studies; Female; Human; Israel; Male; Ophthalmology; Physicians, Family; Questionnaires

The pathophysiology and treatment of glaucoma: a review. - Weinreb, Robert N; Aung, Tin; Medeiros, Felipe A (JAMA: Journal of the American Medical Association, 2014)
Importance: Glaucoma is a worldwide leading cause of irreversible vision loss. Because it may be asymptomatic until a relatively late stage, diagnosis is frequently delayed. A general understanding of the disease pathophysiology, diagnosis, and treatment may assist primary care physicians in referring high-risk patients for comprehensive ophthalmologic examination and in more actively participating in the care of patients affected by this condition.Objective: To describe current evidence regarding the pathophysiology and treatment of open-angle glaucoma and angle-closure glaucoma.Evidence Review: A literature search was conducted using MEDLINE, the Cochrane Library, and manuscript references for studies published in English between January 2000 and September 2013 on the topics open-angle glaucoma and angle-closure glaucoma. From the 4334 abstracts screened, 210 articles were selected that contained information on pathophysiology and treatment with relevance to primary care physicians.Findings: The glaucomas are a group of progressive optic neuropathies characterized by degeneration of retinal ganglion cells and resulting changes in the optic nerve head. Loss of ganglion cells is related to the level of intraocular pressure, but other factors may also play a role. Reduction of intraocular pressure is the only proven method to treat the disease. Although treatment is usually initiated with ocular hypotensive drops, laser trabeculoplasty and surgery may also be used to slow disease progression.Conclusions and Relevance: Primary care physicians can play an important role in the diagnosis of glaucoma by referring patients with positive family history or with suspicious optic nerve head findings for complete ophthalmologic examination. They can improve treatment outcomes by reinforcing the importance of medication adherence and persistence and by recognizing adverse reactions from glaucoma medications and surgeries.
Keywords: Glaucoma -- Complications; Glaucoma -- Diagnosis; Glaucoma -- Pathology; Glaucoma -- Therapy; Human; Primary Health Care

Sustained drug delivery in glaucoma. - Knight, O'Rese J; Lawrence, Scott D (Current Opinion in Ophthalmology, 2014)
PURPOSE OF REVIEW: This article reviews recently published studies and important clinical trials of novel drug delivery systems for glaucoma and evaluates the potential of these systems to provide sustained therapeutic benefits. RECENT FINDINGS: The efficacy of topical medications to lower intraocular pressure (IOP) is limited by poor patient adherence, low bioavailability of drug and the potential for local and systemic side effects. Recent studies highlight the potential for sustained drug delivery through innovative delivery platforms. Nanoparticle-based formulations, drug-eluting contact lenses, punctum inserts and bioadhesive matrices placed in the conjunctival sac can enhance drug delivery by increasing precorneal residence time, enhancing corneal permeation and lowering the systemic absorption of drug. Periocular injections and surgically implanted drug reservoirs could offer even greater duration of drug delivery, particularly when the drug is packaged within stable vehicles. SUMMARY: Novel platforms for providing sustained drug delivery in glaucoma continue to evolve. The ability to incorporate effective commercially available drugs into more stable compounds is an important element. Although more research is needed to establish their clinical efficacy, novel delivery systems will allow for more targeted medical therapy and for the opportunity to further explore neuroprotective and gene-based therapies.
Keywords: Antihypertensive Agents -- Administration and Dosage; Delayed-Action Preparations -- Administration and Dosage; Drug Delivery Systems; Glaucoma -- Drug Therapy; Intraocular Pressure -- Drug Effects; Biological Availability

Supporting patients with using eye drops. - Thomas, Sarah; Chiu, Fiona; Kitney, Cathy (Guidelines in Practice, 2018)
Keywords: Ophthalmic Solutions; Patient Care; Health Promotion; Patient Compliance; Program Evaluation; Practice Guidelines; National Institute for Health and Care Excellence; Treatment Outcomes; Health Services Accessibility; Medication Compliance; Support, Psychosocial; Feedback; Glaucoma -- Therapy

Visual health awareness, the Scottish community optometry service and Eyecare Integration Project: Breaking barriers in preventing visual impairment. - Cheng, Mei-Ling; Henderson, Clair; Sinclair, Anne; Sanders, Roshini (British Journal of Visual Impairment, 2015)
There are 34,492 registered with severe or partial sight impairment in Scotland, with 75% aged over 65. With the ageing population, the proportion of those who will develop sight impairing disease will only increase. Therefore, early presentation and treatment are important. Recently, new sight saving treatments and community screening programmes for sight impairing disease have been introduced with concomitant advance in ophthalmic digital imaging.In order to assess older patients’ attendance of free eye tests, awareness of different sight impairing disease and treatments. We describe the first electronic visual healthcare system within any global public healthcare service – ‘The Scottish Eyecare Integration Project’ – and potential improvements along with the General Ophthalmic Service (GOS) contract.A 14-point questionnaire was devised to assess 100 patients’ awareness of free annual eye tests, and the three most common causes and treatment for severe sight impairment: age-related macular degeneration (ARMD), glaucoma, and diabetic retinopathy (DR).In all, 82% of patients were aware of the free annual eye tests; however, 31% had not attended community optometrist for over 2 years. There was good awareness of glaucoma (77%), but poor understanding of glaucoma treatment (24%), ARMD (43%) and ARMD treatment (17%). Only 39% of patients had heard of free annual DR screening, but there was a significant difference between the two groups (p = .0263), with increased awareness in the middle-aged group.More education is required to encourage the older population to use existing and new eye services. The Scottish Eyecare Integration Project along with the GOS contract is a significant step of change towards meeting the demand for a multidisciplinary approach, bringing ophthalmic care closer to home and into the community.
Keywords: Vision; Health Knowledge -- Scotland; Optometry; Community Programs; Health Services Accessibility; Vision Disorders -- Prevention and Control; Scotland; Human; Early Intervention; Questionnaires; Patient Attitudes; Health Screening -- Methods; Data Analysis Software; T-Tests; Middle Age; Aged; Aged, 80 and Over; Descriptive Statistics; Adult

Adherence and Persistence of Bimatoprost in Prior Latanoprost Users. - Patel, Vaishali; Schwartz, Gail F.; Landsman-Blumberg, Pamela B.; Lunacsek, Orsolya E.; Wong, William (American Journal of Pharmacy Benefits, 2016)
Keywords: Bimatoprost -- Administration and Dosage; Latanoprost -- Administration and Dosage; Medication Compliance; Glaucoma -- Drug Therapy; Human; Retrospective Design; Nonexperimental Studies; Prospective Studies

Overcoming hurdles when branded drugs are what physicians ordered: While complexity of insurers, pharmacies is daunting, physicians can succeed. - Vosoghi, Houman (Ophthalmology Times, 2020)
The author offers tips to physicians on overcoming obstacles when prescribing a brand-name glaucoma medication over a generic. Topics discussed include seeking prior authorization when a medication is not covered by insurance, connecting patients to pharmacies that respect the preferences of physicians, drug companies' offering of discount programs and rebates for patients with commercial insurance and educating patients about why their physicians want them to use certain medications.
Keywords: Prescribing Patterns; Drugs, Prescription; Insurance Carriers; Physicians; Drugs, Generic

The Role of Minimally Invasive Glaucoma Surgery Devices in the Management of Glaucoma. - Fingeret, Murray; Dickerson, Jaime E.; Dickerson, Jaime E Jr (Optometry & Vision Science, 2018)
Significance: Noncompliance is a problem affecting glaucoma patients. Approaches to improve adherence include the use of drug-delivery systems and safer forms of surgery. Minimally invasive glaucoma surgery (MIGS) has reduced complications, particularly in combination with cataract surgery, and with its good intraocular pressure (IOP) reduction may reduce or eliminate glaucoma medications.Glaucoma is a progressive disease and a leading cause of irreversible blindness. Elevated IOP is the most important risk factor, but effective medical management is dependent on patient adherence. This review summarizes the adherence problem in glaucoma and the efforts, including MIGS, to provide effective IOP control that is not dependent on patient compliance.The current understanding of patient adherence to pharmacological treatment of glaucoma is discussed including the challenges facing glaucoma patients. Historical approaches to providing IOP control in a sustained and reliable way are presented culminating in a review of the burgeoning use of MIGS devices.It is estimated that, in the United States, 27% of prescriptions written, across all medications, are not filled or are filled but not taken. For ocular hypotensive medications, even when filled, a large percentage (which varies widely by study) are not instilled as prescribed. To address this problem, methods for sustained drug delivery have been and continue to be developed, as well as surgical and laser approaches. Most recently, MIGS devices have gained popularity because of the ease of implantation during cataract surgery, favorable safety profile, and the possibility for effective and long-lasting IOP lowering, as well as the reduction or elimination of need for IOP-lowering medication.Poor adherence to treatment is relatively common among glaucoma patients and is associated with progression of disease. Recommending MIGS implantation during cataract surgery may offer optometrists a valuable treatment option in managing glaucoma patients, particularly where good adherence is in doubt.
Keywords: Intraocular Pressure -- Physiology; Minimally Invasive Procedures; Glaucoma -- Surgery; Prostheses and Implants; Cataract Extraction; Patient Compliance; Glaucoma -- Physiopathology

The association between compliance with recommended follow-up and glaucomatous disease severity in a county hospital population. - Ung, Cindy; Murakami, Yohko; Zhang, Elisa; Alfaro, Tatyana; Zhang, Monica; Seider, Michael I; Singh, Kuldev; Lin, Shan C (American Journal of Ophthalmology, 2013)
Purpose: To assess the association between insufficient follow-up and clinical parameters such as disease severity and medication use among glaucoma patients at a metropolitan county hospital.Design: Cross-sectional study.Methods: Two-hundred and six patients with established glaucoma were recruited from San Francisco General Hospital. Subjects were classified based on compliance with recommended follow-up examination intervals over the year preceding commencement of the study, as determined by patient medical records. Glaucoma severity was determined based on the American Academy of Ophthalmology Preferred Practice Patterns guidelines. Multivariate logistic regression analysis was used to assess the relationship between adherence with follow-up visits and disease severity.Results: After adjustment for the impact of potential confounding variables, subjects with severe glaucomatous disease were found to have been less adherent to their recommended follow-up than those patients with mild or moderate glaucomatous disease (adjusted OR 1.89, 95% CI 1.21-2.94; P = .01). Subjects who were on glaucoma medications were found to be less adherent to follow-up recommendations (adjusted OR 3.29, 95% CI 1.41-7.65, P = .01).Conclusion: Subjects with poor follow-up adherence were significantly more likely to have severe glaucomatous disease, suggesting that poor follow-up may contribute to disease worsening or, alternatively, those with more severe disease are less inclined to follow up at appropriate intervals.
Keywords: Continuity of Patient Care -- Statistics and Numerical Data; Glaucoma -- Diagnosis; Glaucoma -- Physiopathology; Hospitals, Public -- Statistics and Numerical Data; Patient Compliance; Antihypertensive Agents -- Therapeutic Use; Cross Sectional Studies; Health Care Delivery; Female; Prospective Studies; Glaucoma -- Drug Therapy; Guideline Adherence; Human; Intraocular Pressure -- Drug Effects; Intraocular Pressure -- Physiology; Male; Medication Compliance; Middle Age; Office Visits; Questionnaires; Severity of Illness Indices

TELEPHONE TRIAGE: Recognize potential visual disturbance emergencies. - Johnson, Rebecca L. (Ophthalmology Times, 2019)
The article discusses the concept of triage and some important issues to put in mind when it comes to recognizing potential visual disturbance emergencies. Topics mentioned include proper documentation of telephone conversation with a patient, the impact of acute angle-closure glaucoma on vision, and the phenomena of flashes of light and floaters as a sign of retinal detachment.
Keywords: Vision Disorders -- Symptoms; Eye Care; Telehealth; Triage; Conversation; Professional-Patient Relations; Appointments and Schedules; Vision Disorders -- Therapy; Physician-Patient Relations; Age of Onset; Disease Duration; Severity of Illness; Eye Pain -- Etiology; Retinal Artery Occlusion -- Risk Factors; Glaucoma, Angle-Closure -- Risk Factors; Retinal Detachment -- Risk Factors; Eye Surgery -- Methods; Patient Safety; Migraine -- Symptoms; Diplopia -- Risk Factors; Empathy; Documentation; Emergencies; Ambulatory Care

The Effect of Rebamipide on Ocular Surface Disorders Induced by Latanoprost and Timolol in Glaucoma Patients. - Tokuda, Naoto; Kitaoka, Yasushi; Matsuzawa, Akiko; Miyamoto, Junsuke; Sakae, Shinsuke; Munemasa, Yasunari; Takagi, Hitoshi (Journal of Ophthalmology, 2015)
Purpose. To examine the efficacy of ophthalmic rebamipide suspensions on ocular surface disorders induced by antiglaucoma eye drops. Patients and Methods. Forty eyes of 40 patients receiving latanoprost (0.005%) and timolol (0.5%) were included in this randomized prospective study. The patients were randomly divided into two groups (n = 20): the rebamipide-treated group and control group. Changes in intraocular pressure, tear film break-up time (TBUT), and corneal epithelial barrier function were evaluated at baseline, 4 weeks, and 8 weeks after rebamipide administration. Furthermore, superficial punctate keratopathy severity was evaluated by scoring the lesion area and density. Results. There was no significant difference in intraocular pressure before and after rebamipide treatment. However, corneal epithelial barrier function improved significantly 4 and 8 weeks after rebamipide treatment. TBUT was partially, but significantly, increased (P = 0.02) 8 weeks after rebamipide treatment, whereas no significant change was observed at 4 weeks. Additionally, a significant decrease in area and density of keratopathy was observed 8 weeks after rebamipide treatment but not at 4 weeks. The control group showed no significant difference compared to baseline. Conclusions. Our data suggests that rebamipide treatment may reduce the occurrence of drug-induced ocular surface disorder.
Keywords: Glaucoma -- Drug Therapy; Intraocular Pressure; Control Group; Ophthalmic Solutions; Dry Eye Syndromes -- Drug Therapy; Eye Diseases -- Drug Therapy; Timolol; Latanoprost; Prospective Studies; Clinical Trials; Sensitivity and Specificity; Human; Randomized Controlled Trials; Random Assignment

CO2 LASER SURGERY a new option fo glaucoma. - Melamed, Shlomo (Ophthalmology Times, 2014)
The article examines the efficacy of CO2 laser-assisted sclerectomy surgery (CLASS) in treating glaucoma. Topics discussed include the common use of carbon dioxide laser in skin resurfacing treatments, the impact of patient compliance as a critical factor in the effectiveness of hypotensive topical medication for glaucoma, and the success rate of CLASS procedure in reducing elevated intraocular pressure (IOP) by thinning the sclera and restore aqueous flow of the eye.
Keywords: Glaucoma -- Surgery; Laser Therapy; Treatment Outcomes; Lasers; Carbon Dioxide; Intraocular Pressure

PROVIDE TAKE-HOME TOOLS FOR COMPLIANCE: Suss out the barriers to medication consistency that aid glaucoma, and provide strategies to overcome them. - REYNOLDS, SHERROL A.; KUBAL, AARUP (Optometric Management, 2020)
Keywords: Glaucoma -- Drug Therapy; Medication Compliance -- Education; Patient Education -- Methods; Home Health Care -- Methods; After Care; Disease Progression -- Prevention and Control; Health Knowledge; Mobile Applications; Text Messaging; Tonometry -- Equipment and Supplies; Drugs, Prescription -- Administration and Dosage; Ophthalmic Solutions -- Administration and Dosage; Equipment Alarm Systems; Optometrists -- Education

Provider Education about Glaucoma and Glaucoma Medications during Videotaped Medical Visits. - Sleath, Betsy; Blalock, Susan J.; Carpenter, Delesha M.; Muir, Kelly W.; Sayner, Robyn; Lawrence, Scott; Giangiacomo, Annette L.; Hartnett, Mary Elizabeth; Tudor, Gail; Goldsmith, Jason; Robin, Alan L. (Journal of Ophthalmology, 2014)
Objective. The purpose of this study was to examine how patient, physician, and situational factors are associated with the extent to which providers educate patients about glaucoma and glaucoma medications, and which patient and provider characteristics are associated with whether providers educate patients about glaucoma and glaucoma medications. Methods. Patients with glaucoma who were newly prescribed or on glaucoma medications were recruited and a cross-sectional study was conducted at six ophthalmology clinics. Patients' visits were videotape recorded and patients were interviewed after visits. Generalized estimating equations were used to analyze the data. Results. Two hundred and seventy-nine patients participated. Providers were significantly more likely to educate patients about glaucoma and glaucoma medications if they were newly prescribed glaucoma medications. Providers were significantly less likely to educate African American patients about glaucoma. Providers were significantly less likely to educate patients of lower health literacy about glaucoma medications. Conclusion. Eye care providers did not always educate patients about glaucoma or glaucoma medications. Practice Implications. Providers should consider educating more patients about what glaucoma is and how it is treated so that glaucoma patients can better understand their disease. Even if a patient has already been educated once, it is important to reinforce what has been taught before.
Keywords: Glaucoma -- Drug Therapy; Physician-Patient Relations; Patient Education; Physicians; Patients; Glaucoma -- Education; Office Visits; Cross Sectional Studies; United States; Questionnaires; Videorecording; Interviews; Clinical Assessment Tools; Interrater Reliability; Descriptive Statistics; Bivariate Statistics; Pearson's Correlation Coefficient; Chi Square Test; T-Tests; Human; Male; Female; Aged; Middle Age; Multivariate Analysis; Adult; Odds Ratio; Confidence Intervals; Funding Source

Patients' and physicians' perceptions of the travoprost dosing aid: an open-label, multicenter study of adherence with prostaglandin analogue therapy for open-angle glaucoma or ocular hypertension. - Flowers B; Wand M; Piltz-Seymour J; Berke SJ; Day D; Teague J; Smoot TM; Landry TA; Bergamini MV; Mallick S (Clinical Therapeutics, 2006)
OBJECTIVE: This study describes patients' and physicians' perceptions of issues related to dosing adherence with topical therapies for lowering intraocular pressure before and after use of the travoprost dosing aid (Travatan Dosing Aid, Alcon Research Ltd., Fort Worth, Texas). METHODS: The study had an open-label, multicenter, single-treatment-arm design that included sequential patients with open-angle glaucoma (with or without pigment dispersion or pseudoexfoliation component) or ocular hypertension who were taking any prostaglandin analogue monotherapy. Ten participating physicians were chosen on the basis of factors such as their experience, qualifications, and previous clinical study participation. The study consisted of 2 visits: screening and week 4. Patients were asked to complete a survey about their medication adherence before study entry at the screening visit and at study exit during the week-4 visit. In addition, each physician was asked to complete an entry and exit survey on each patient as well as a survey to provide feedback on the travoprost dosing aid. RESULTS: Of the 87 enrolled patients, 6 did not complete the exit survey; therefore, 81 patients were included in the intent-to-treat analysis. Mean (SD) age at enrollment was 65.4 (11.6) years; 61.7% (50/81) of the patients were women and 60.5% (49/81) were white. Most patients (96.3% [78/81]) had open-angle glaucoma. Participating physicians perceived that problems involving dosing and adherence were reduced after patients used the dosing aid. Physicians indicated that they would recommend continued use of the travoprost dosing aid for 91.3% (73/80) of patients. All 10 participating physicians said that they would recommend the dosing aid to patients in the future. Of the 81 patients, the majority (68.8% [55/80]) indicated that they would like to continue using the travoprost dosing aid. For 67.5% (54/80) of patients, dosing adherence as recorded by the travoprost dosing aid was >70%. The dosing lever (39.7% [31/78]) and the visual alarm (29.5% [23/78]) were the 2 most favored features of the dosing aid reported by all evaluable patients. The majority of patients (58.8% [47/80]) indicated that they were 'relieved' or 'very relieved' that the doctor was able to monitor when they dosed their medication; few (7.5% [6/80]) were 'concerned' or 'very concerned' that the doctor was able to monitor their dosing. CONCLUSIONS: The travoprost dosing aid was perceived to be effective in reminding this group of patients to take their medication as prescribed. In this study, the device was well accepted by both patients and physicians.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Ocular Hypertension -- Drug Therapy; Travoprost -- Administration and Dosage; Blindness -- Prevention and Control; Clinical Trials; Funding Source; Human; Multicenter Studies; Self Report

Self-reported prevalence and factors associated with nonadherence with glaucoma medications in veteran outpatients. - Sleath B; Ballinger R; Covert D; Robin AL; Byrd JE; Tudor G (American Journal of Geriatric Pharmacotherapy, 2009)
Objective: The purpose of the current study was to determine the self-reported prevalence of and factors associated with nonadherence with glaucoma medications in veteran outpatients. Methods: This survey study was conducted at a Veterans Affairs (VA) clinic. A survey was administered to patients with glaucoma. We calculated the percentage of self-reported adherence with glaucoma medications in each patient. Logistic regression was used to assess whether patient characteristics and difficulties with using glaucoma medications were related to patients' reporting that they were <100% adherent with their glaucoma medications in the previous week. Results: The survey was completed by 141 patients (men, 91.5%; mean [SD] age, 70.22 [11.60] years [range, 37-93 years]; black race, 45.4%; white race, 44.0%; 'other' or data unavailable, 10.6%). Nonwhite patients were significantly less adherent in the previous week than were white patients (27.0% vs 11.3%; P < 0.05). A total of 67.4% patients reported >/=1 difficulty in using their glaucoma medications. The 3 most commonly reported difficulties were 'drops fall on cheek' (29.1%), 'too many drops come out' (20.6%), and 'hard to read print' (17.0%). A total of 19.1% of patients self-reported using <100% of their glaucoma medications in the previous week. The number of difficulties reported was significantly associated with reporting being <100% adherent in the previous week (P<0.05). Conclusion: In this small sample of VA patients with glaucoma, adherence to glaucoma medications could be improved, especially among those who reported difficulties using their medications and those who were nonwhite.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Outpatients -- Statistics and Numerical Data; Veterans -- Statistics and Numerical Data; Aged; Aged, 80 and Over; Black Persons -- Statistics and Numerical Data; Female; Glaucoma -- Ethnology; Logistic Regression; Male; Middle Age; Odds Ratio; Questionnaires; Risk Assessment; Risk Factors; Surveys; United States; White Persons -- Statistics and Numerical Data; Human

ROCK inhibitor represents 'breakthrough' treatment with disease-modifying potential. - Cimberle, Michela (Ocular Surgery News, 2018)
Keywords: Protein Kinases -- Antagonists and Inhibitors; Enzyme Inhibitors -- Therapeutic Use; Anterior Eye Segment -- Physiology; Glaucoma -- Therapy; Enzyme Inhibitors -- Administration and Dosage; Ocular Hypertension -- Prevention and Control; Disease Resistance; Minimally Invasive Procedures -- Methods; Prostaglandins -- Therapeutic Use; Patient Compliance; Anterior Eye Segment -- Surgery

WHAT'S ON MY CONTACT LENS WISH LIST. - MORGAN, PHILIP B. (Contact Lens Spectrum, 2019)
Keywords: Contact Lenses -- Evaluation; Contact Lenses -- Trends; Technology, Medical; Patient Compliance; Dendritic Cells; Keratitis; Child; Adolescence; Quality of Life; Myopia -- Therapy; Presbyopia -- Therapy; Business

Glaucoma: the patient's perspective. - Imrie, Claire; Tatham, Andrew J. (British Journal of General Practice, 2016)
The article presents questions and answers related to the concerns of patients with glaucoma and how can they be addressed in general practice.
Keywords: Ophthalmic Solutions -- Therapeutic Use; Glaucoma -- Diagnosis; Antihypertensive Agents -- Therapeutic Use; Age Factors; Patient Compliance; Referral and Consultation; Health Behavior; Patient Education; Glaucoma -- Physiopathology; Glaucoma -- Therapy; Questionnaires

Use optic stereo-photography in conjunction with OCT: New device appears to overcome obstacles of image acquisition in traditional photography. - Oddone, Francesco (Ophthalmology Times, 2018)
The article discusses the diagnostic test for glaucoma, a degenerative disease characterized by typical morphological changes in the optic nerve head (ONH) and the retinal nerve fiber layer (RNFL), followed by a corresponding loss of the visual field. Topics include the detection of structural damage to the ONH, the use of stereoscopic photograph, and the guidelines for treating diabetic retinopathy.
Keywords: Photography -- Methods; Tomography, Optical Coherence -- Methods; Glaucoma -- Diagnosis; Visual Fields; Quality of Life; Optic Nerve -- Pathology; Intraocular Pressure -- Evaluation; Nerve Fibers; Eye Hemorrhage -- Diagnosis

Automated telecommunication-based reminders and adherence with once-daily glaucoma medication dosing: the automated dosing reminder study. - Boland, Michael V; Chang, Dolly S; Frazier, Travis; Plyler, Ryan; Jefferys, Joan L; Friedman, David S (JAMA Ophthalmology, 2014)
Keywords: Antihypertensive Agents -- Administration and Dosage; Drug Monitoring; Glaucoma -- Drug Therapy; Medication Compliance; Reminder Systems -- Equipment and Supplies; Telecommunications -- Equipment and Supplies; Administration, Topical; Aged; Prospective Studies; Female; Human; Intraocular Pressure -- Drug Effects; Male; Medical Record Linkage; Middle Age; Ophthalmic Solutions

Determinants of medication adherence to topical ocular hypotensives and application of health belief model among glaucoma patients visiting a tertiary care hospital in coastal Karnataka, India. - Kaup, Soujanya; Oomman, Sithara Sara; Shivalli, Siddharudha (Indian Journal of Ophthalmology, 2018)
Keywords: Hospitals, Special; Intraocular Pressure; Antihypertensive Agents -- Therapeutic Use; Glaucoma -- Drug Therapy; Medication Compliance; India; Glaucoma -- Physiopathology

Incidence and clinical features of contact lens related microbial keratitis. - Wajin WAS; Qader AMA; Shaharuddin B; Hitam WHW (International Medical Journal, 2008)
Purpose: To determine the incidence, clinical features and outcome of contact lens related corneal ulcer.Design: Retrospective cross sectional study, conducted in Hospital Unversiti Sains Malaysia (HUSM).Methods: A five-year review of contact lens related Microbial keratitis admitted to a tertiary government referral centre at the north-eastern part of Malaysia.Results: 132 cases of corneal ulcer were reviewed from 1 January 2000 to 30 April 2005, from which 20 patients (14.9%) were diagnosed with contact lens related microbial keratitis. Eleven were females and 9 males, with mean age of 25 +/- 6.81 years. All of them were soft contact lens wearers. Most patients presented with eye pain (75%), conjunctival congestion (65%) and blurred vision (60%). Majority of cases (55%) presented with hypopyon and one corneal perforation. In 65% corneal scraping culture isolated Pseudomonas aeruginosa. In 30%, cleaning and storage solutions also isolated Pseudomonas aeruginosa. Eleven cases (55%) showed microbial resistance to chloramphenicol.Conclusion: Contact lens wear remains a major risk factor for ocular morbidity due to microbial keratitis, especially involving the young population, even in the present advances in technology. Stricter contact lens prescription guideline and emphasis on compliance to hygienic regime are mandatory to prevent this complication. The routine use of chloramphenicol as topical use of choice is not recommended.
Keywords: Contact Lenses -- Adverse Effects; Keratitis -- Epidemiology; Adult; Antibiotics -- Therapeutic Use; Child; Chloramphenicol -- Adverse Effects; Cross Sectional Studies; Descriptive Statistics; Drug Resistance, Microbial; Female; Incidence; Malaysia; Male; Middle Age; Pseudomonas Infections -- Complications; Record Review; Retrospective Design; Treatment Outcomes; Human

Eye-care utilization among women aged greater than or equal to 40 years with eye diseases -- 19 states, 2006-2008. (MMWR: Morbidity & Mortality Weekly Report, 2010)
Diabetic retinopathy (DR), glaucoma, and age-related macular degeneration (ARMD) are major causes of vision loss and blindness. Women have been found to have a higher prevalence of vision loss than men. Early detection and timely treatment by eye-care providers are necessary to delay disease progression and prevent vision loss. To assess the use of professional eye care among women aged >/=40 years, CDC analyzed data from the Behavioral Risk Factor Surveillance System (BRFSS) for 19 U.S. states for the period 2006--2008. This report summarizes the results of that analysis, which indicated that 21% of women with self-reported DR, 12% of women with self-reported glaucoma, and 8% of women with self-reported ARMD did not visit an eye-care provider in the recommended follow-up period. Women who did not have insurance coverage for eye care or who did not receive routine medical check-ups were more likely to report not having the recommended follow-up eye care. The two most commonly cited reasons for not having an eye-care visit were cost or not having insurance (range across diseases: 40%--46%) and having no reason to go for follow-up (range: 20%--29%). Compliance with obtaining eye examinations at recommended intervals among women aged >/=40 years with eye diseases might be enhanced by improving access to health care and implementing and expanding existing educational programs to raise awareness regarding the importance of routine follow-up eye examinations.
Keywords: Diabetic Retinopathy -- Diagnosis; Glaucoma -- Diagnosis; Health Services -- Utilization; Macular Degeneration -- Diagnosis; Vision Screening -- Utilization; Adult; Aged; Female; Health Services Accessibility; Insurance Coverage; Medically Uninsured; Middle Age; Patient Compliance; Risk Assessment; United States

Nanotechnology and glaucoma: little particles for a big disease. - Pita-Thomas, Daniel W; Goldberg, Jeffrey L (Current Opinion in Ophthalmology, 2013)
PURPOSE OF REVIEW: Current medical treatments designed to halt the progressive loss of retinal ganglion cells (RGCs) in glaucoma are limited by low bioavailability to target tissues and lack of patient adherence to frequent dosing regimens. For a certain percentage of patients with glaucoma, reducing intraocular pressure (IOP) does not stop disease progression, motivating the search for new therapeutic targets and delivery systems. RECENT FINDINGS: The emerging science of nanoparticles has the potential to address the current limitations of glaucoma therapy by improving drug bioavailability, exploiting IOP-independent targets such as RGC neuroprotection, and optimizing gene therapy as a more permanent treatment for glaucoma. SUMMARY: We review the recent advances in nanoparticle-based glaucoma therapy with a focus on drug delivery to the eye, as well as novel applications including gene therapy.
Keywords: Antihypertensive Agents; Drug Delivery Systems; Glaucoma -- Drug Therapy; Nanotechnology; Nanotechnology -- Methods; Intraocular Pressure

Stratification of antigen-presenting cells within the normal cornea. - Knickelbein JE; Watkins SC; McMenamin PG; Hendricks RL (Ophthalmology & Eye Diseases, 2009)
The composition and location of professional antigen presenting cells (APC) varies in different mucosal surfaces. The cornea, long considered an immune-privileged tissue devoid of APCs, is now known to host a heterogeneous network of bone marrow-derived cells. Here, we utilized transgenic mice that express enhanced green fluorescent protein (EGFP) from the CD11c promoter (pCD11c) in conjunction with immunohistochemical staining to demonstrate an interesting stratification of APCs within non-inflamed murine corneas. pCD11c+ dendritic cells (DCs) reside in the basal epithelium, seemingly embedded in the basement membrane. Most DCs express MHC class II on at least some dendrites, which extend up to 50 μm in length and traverse up 20 μm tangentially towards the apical surface of the epithelium. The DC density diminishes from peripheral to central cornea. Beneath the DCs and adjacent to the stromal side of the basement membrane reside pCD11c-CD11b+ putative macrophages that express low levels of MHC class II. Finally, MHC class II-pCD11c-CD11b+ cells form a network throughout the remainder of the stroma. This highly reproducible stratification of bone marrow-derived cells is suggestive of a progression from an APC function at the exposed corneal surface to an innate immune barrier function deeper in the stroma.
Keywords: Antigen-Presenting Cells -- Immunology; Cornea -- Physiology; Dendritic Cells -- Immunology; Analysis of Variance; Animal Studies; Data Analysis Software; Funding Source; Immunohistochemistry; Mice; Microscopy -- Methods; Phenotype; Post Hoc Analysis

Part II: identifying barriers to adherence. - Hahn SR; Budenz DL (Johns Hopkins Advanced Studies in Ophthalmology, 2008)
Keywords: Glaucoma -- Drug Therapy; Patient Compliance; Aged; Female; Glaucoma -- Complications; Male; Middle Age; Motivation; Patient Attitudes; Patient Education; Vision Disorders -- Risk Factors

The influence of health literacy level on an educational intervention to improve glaucoma medication adherence. - Muir KW; Ventura A; Stinnett SS; Enfiedjian A; Allingham RR; Lee PP; Muir, Kelly W; Ventura, Alice; Stinnett, Sandra S; Enfiedjian, Abraham; Allingham, R Rand; Lee, Paul P (Patient Education & Counseling, 2012)
Objective: To test an educational intervention targeted to health literacy level with the goal of improving glaucoma medication adherence.Methods: One hundred and twenty-seven veterans with glaucoma were randomized to glaucoma education or standard care. The intervention included a video scripted at a 4th, 7th, or 10th grade level, depending on the subject's literacy level. After six months, the number of days without glaucoma medicine (DWM) according to pharmacy records for the intervention and control groups was compared.Results: The number of DWM in the six months following enrollment was similar for control and intervention groups (intervention, n=67, DWM=63 ± 198; standard care, n=60, DWM=65 ± 198; p=0.708). For each subgroup of literacy (adequate, marginal, inadequate), subjects in the intervention group experienced less mean DWM than subjects in the control group and the effect size (ES) increased as literacy decreased: adequate literacy, ES 0.069; marginal, ES 0.183, inadequate, ES 0.363. Decreasing health literacy skills were associated with decreasing self-reported satisfaction with care (slope=0.017, SE=0.005, p=0.002).Conclusions: Patients with decreased health literacy skills may benefit from educational efforts tailored to address their health literacy level and learning style.Practice Implications: Providers should consider health literacy skills when engaging in glaucoma education.
Keywords: Drug Administration; Educational Status; Glaucoma -- Drug Therapy; Information Literacy; Medication Compliance; Patient Education -- Methods; Health Literacy; Adult; Aged; Aged, 80 and Over; Attitude to Health; Audiorecording; Female; Human; Male; Middle Age; North Carolina; Patient Satisfaction; Questionnaires; Randomized Controlled Trials; Veterans

Glaucoma compliance a complex issue with many contributing factors. - Boyle EL (Ocular Surgery News, 2010)
From drop amount permitted by insurance companies to glaucoma patients' difficulty, glaucoma medical therapy adherence is a challenge to maintain.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Insurance Coverage; Insurance, Health, Reimbursement; Ophthalmic Solutions -- Administration and Dosage

Novel drug delivery platforms: Filling a 'GAP' in glaucoma. - Guttman Krader, Cheryl (Ophthalmology Times, 2017)
Information on how to address glaucoma's need for Guided Administration of Pharmaceuticals (GAP) therapy according to ophthalmology professor Malik Y. Kahook, M.D. is presented. Topics covered include strategies introduced to address poor adherence with prescribed topical therapies, an unmeet need for some GAP therapy that would fit in a zone between topical medical therapy and laser or surgery, and concerns about the long-term safety of a punctal plug.
Keywords: Drug Delivery Systems; Glaucoma -- Drug Therapy; Patient Safety; Patient Attitudes; Risk Assessment; Invasive Procedures

Eye Care Disparities and Health-Related Consequences in Elderly Patients with Age-Related Eye Disease. - Umfress, Allison C.; Brantley, Milam A. (Seminars in Ophthalmology, 2016)
The elderly population in the United States (age 65 and older) is growing rapidly, estimated by the U.S. Census Department to reach 83.7 million by 2050.(1) Visual impairment increases with age among all racial and ethnic groups.(2) In the elderly, the most common culprits for vision loss are cataract, glaucoma, and age-related macular degeneration (AMD).(2) In the developed world, vision loss from cataract has been dramatically reduced by increased access to cataract surgery. However, AMD and glaucoma lead to irreversible vision loss without early diagnosis and intervention. In the U.S., cases of AMD are expected to double by 2050, reaching 17.8 million among patients age 50 or older.(3) Similarly, cases of glaucoma are expected to reach 5.5 million by 2050, an increase of over 90% from 2014.(3) The visually impaired elderly face disparities in access to eye care, and subsequent general medical and psychosocial complications.
Keywords: Eye Diseases -- Epidemiology; Aging; Vision Disorders -- Epidemiology; Health Status; Healthcare Disparities -- Statistics and Numerical Data; Aged; Aged, 80 and Over; Disabled -- Statistics and Numerical Data; Health Services Accessibility; Scales

Adherence may be most important factor for glaucoma treatment. - Linnehan, Robert (Ocular Surgery News, 2016)
The article discusses highlights of the presentation by physician Norbert Pfeiffer on the importance of patient's adherence to therapy as a factor for glaucoma treatment, at the 2016 European Glaucoma Society congress.
Keywords: Intraocular Pressure; Glaucoma -- Therapy; Glaucoma; Physicians; Organizations; Glaucoma -- Diagnosis; Europe

Balancing efficacy and tolerability of prostaglandin analogues and prostaglandin–timolol fixed combinations in primary open-angle glaucoma. - F. Aptel; P. Denis (Current Medical Research & Opinion, 2011)
Background:Lowering intraocular pressure (IOP) is currently the only therapeutic approach that preserves visual function in primary open-angle glaucoma. In making treatment decisions for first- and second-line therapy, the clinician needs to provide an appropriate balance of efficacy and tolerability. Prostaglandin analogues (PGAs) are frequently used as first-line monotherapy, because of their efficacy and low risk of systemic side effects. Similarly, PGA-based fixed combinations are frequently used in patients who progress or fail to achieve the target IOP.Scope:We have reviewed the literature on the management of primary open-angle glaucoma with PGAs, both as monotherapies and in fixed combinations.Findings:In the clinical trial and meta-analysis data identified, bimatoprost 0.03% seems to be associated with a greater overall ability to lower IOP compared with latanoprost, travoprost or tafluprost, at the cost of a slightly higher incidence of conjunctival hyperaemia. Studies indicate that patients’ adherence to treatment is generally better with PGAs than with many other monotherapies. In patients requiring more than one IOP-lowering agent, fixed combination treatments may provide improved adherence and tolerability benefits compared with concomitant use of individual treatments. Bimatoprost/timolol fixed combination appears to be slightly more efficacious than latanoprost/timolol or travoprost/timolol, and tolerability differences between the fixed combinations appear to be slight, probably because the addition of timolol to the PGA component lessens the associated hyperaemia. Surveys on EU physician attitudes appear largely in line with these clinical data.Conclusion:An appropriate balance between efficacy and tolerability ensures optimum IOP lowering and reduces the risk of non-adherence. PGAs largely fulfil this need as monotherapies and as components of combinations.
Keywords: Intraocular Pressure; Glaucoma -- Drug Therapy; Prostaglandins -- Administration and Dosage; Human; Timolol; Bimatoprost; Drug Therapy, Combination; Meta Analysis

Balancing efficacy and tolerability of prostaglandin analogues and prostaglandin–timolol fixed combinations in primary open-angle glaucoma. - F. Aptel; P. Denis (Current Medical Research & Opinion, 2011)
Background:Lowering intraocular pressure (IOP) is currently the only therapeutic approach that preserves visual function in primary open-angle glaucoma. In making treatment decisions for first- and second-line therapy, the clinician needs to provide an appropriate balance of efficacy and tolerability. Prostaglandin analogues (PGAs) are frequently used as first-line monotherapy, because of their efficacy and low risk of systemic side effects. Similarly, PGA-based fixed combinations are frequently used in patients who progress or fail to achieve the target IOP.Scope:We have reviewed the literature on the management of primary open-angle glaucoma with PGAs, both as monotherapies and in fixed combinations.Findings:In the clinical trial and meta-analysis data identified, bimatoprost 0.03% seems to be associated with a greater overall ability to lower IOP compared with latanoprost, travoprost or tafluprost, at the cost of a slightly higher incidence of conjunctival hyperaemia. Studies indicate that patients’ adherence to treatment is generally better with PGAs than with many other monotherapies. In patients requiring more than one IOP-lowering agent, fixed combination treatments may provide improved adherence and tolerability benefits compared with concomitant use of individual treatments. Bimatoprost/timolol fixed combination appears to be slightly more efficacious than latanoprost/timolol or travoprost/timolol, and tolerability differences between the fixed combinations appear to be slight, probably because the addition of timolol to the PGA component lessens the associated hyperaemia. Surveys on EU physician attitudes appear largely in line with these clinical data.Conclusion:An appropriate balance between efficacy and tolerability ensures optimum IOP lowering and reduces the risk of non-adherence. PGAs largely fulfil this need as monotherapies and as components of combinations.
Keywords: Intraocular Pressure; Glaucoma -- Drug Therapy; Prostaglandins -- Administration and Dosage; Human; Timolol; Bimatoprost; Drug Therapy, Combination; Meta Analysis

A Review of the Clinical Usefulness of Selective Laser Trabeculoplasty in Exfoliative Glaucoma. - Katsanos, Andreas; Konstas, Anastasios G.; Mikropoulos, Dimitrios G.; Quaranta, Luciano; Voudouragkaki, Irini C.; Athanasopoulos, Georgios P.; Asproudis, Ioannis; Teus, Miguel A. (Advances in Therapy, 2018)
In the last decade, selective laser trabeculoplasty (SLT) has been commonly used in the management of several different types of glaucoma, as either primary or adjunct therapy. The technique has an excellent safety profile and is at least as effective as argon laser trabeculoplasty. Although the actual mechanism of action of SLT remains unclear, evidence has shown that it does not induce morphologically evident trabecular meshwork alterations. SLT's non-disruptive mode of action offers the advantage of repeatability. Exfoliation glaucoma (XFG) is a secondary open-angle glaucoma with unfavorable intraocular pressure (IOP) characteristics, which typically carries a poorer long-term prognosis than primary open-angle glaucoma. Consequently, patients with XFG often need multiple medications to achieve IOP levels that prevent disease progression. Because complicated pharmacotherapy regimens undermine the long-term tolerability and compliance of patients with XFG, options such as SLT may decrease the burden of multiple therapies and ultimately improve prognosis. In fact, SLT may be a particularly attractive option in XFG because the pigment-laden trabecular tissue of these patients enhances the absorption of laser energy and thus augments the biologic effects induced by this treatment. The current article reviews the postulated mechanisms of action of SLT, discusses practical aspects of SLT therapy, and examines selected peer-reviewed literature pertaining to the clinical usefulness of this modality in XFG patients.
Keywords: Trabeculectomy -- Equipment and Supplies; Trabeculectomy -- Methods; Laser Therapy -- Methods; Trabeculectomy -- Adverse Effects; Exfoliation Syndrome -- Surgery; Treatment Outcomes; Clinical Assessment Tools; Scales

A CARE-compliant article: ipsilateral progressive idiopathic lipid keratopathy: A case report. - Pang, Yilin MD; Zhang, Qin MD; Bao, Yongzhen MD; Pang, Yilin; Zhang, Qin; Bao, Yongzhen (Medicine, 2019)
Rationale: Lipid deposition on the cornea without previous infection, inflammation, vascularization, or trauma is idiopathic lipid keratopathy. In vivo laser confocal microscopy (IVCM) and anterior segment optical coherence tomography (AS-OCT) are 2 noninvasive methods that can help identify the structures and morphological characteristics of the focus.Patient Concerns: A 63-year-old woman with ipsilateral corneal lipid deposits developing from a small white spot into a yellow-white superotemporal elliptic shape within a year. AS-OCT showed peripheral deep stromal deposits. IVCM showed hyper-reflective material with typical crystalline-like or needle-like structures in the superotemporal area.Diagnosis: Idiopathic lipid degeneration.Interventions: Topical steroids eye drops 3 times a day for a month and further consultation every 3 months.Outcomes: This patient of idiopathic lipid keratopathy was observed every 3 months and till now we have reviewed this patient twice. Topical steroids eye drops were only used during the first month. No further development was observed about the lesion and the patient's visual acuity remained good.Conclusion: IVCM and AS-OCT can help identify the characteristic crystalline-like or needle-like hyper-reflective material that could help diagnosis of idiopathic lipid degeneration.
Keywords: Cornea; Corneal Diseases -- Drug Therapy; Steroids -- Administration and Dosage; Lipid Metabolism, Inborn Errors; Microscopy; Tomography, Optical Coherence; Treatment Outcomes; Administration, Topical; Female; Corneal Diseases; Corneal Diseases -- Metabolism; Middle Age; Steroids -- Pharmacodynamics; Cornea -- Metabolism; Visual Acuity

How ocular surface disease impacts the glaucoma treatment outcome. - Kastelan, Snjezana; Tomic, Martina; Metez Soldo, Kata; Salopek-Rabatic, Jasminka (BioMed Research International, 2013)
The treatment goals for glaucoma are lowering the intraocular pressure and preservation of vision. Topical hypotensive drops are the standard form of therapy which is often associated with some symptoms of toxicity, ocular inflammation, allergy, or ocular surface disease (OSD). OSD is a common comorbidity in glaucoma patients, and its prevalence with glaucoma increases with age. Use of topical treatment could additionally increase symptoms of OSD mostly due to preservatives added to multidose medication bottles used to reduce the risk of microbial contamination. This toxicity has been particularly associated with BAK, the most commonly used preservative which damages conjunctival and corneal epithelial cells and significantly aggravates OSD symptoms. OSD adversely affects patients' quality of life causing discomfort and problems with vision which in turn may result in noncompliance, lack of adherence, and eventually visual impairment. In the management of glaucoma patients OSD symptoms should not be overlooked. If they are present, topical glaucoma treatment should be adapted by decreasing the amount of drops instilled daily, using BAK-free or preservative-free medication and lubricants if necessary. Awareness of the presence and importance of OSD will in turn improve patients' adherence and compliance and thus ultimately the preservation of long-term vision.
Keywords: Eye -- Drug Effects; Glaucoma -- Drug Therapy; Pharmaceutical Additives; Administration, Topical; Aged; Antihypertensive Agents -- Adverse Effects; Antihypertensive Agents -- Therapeutic Use; Eye -- Pathology; Glaucoma -- Complications; Glaucoma -- Pathology; Intraocular Pressure -- Drug Effects; Male; Pharmaceutical Additives -- Therapeutic Use; Treatment Outcomes

Retinal Macroglial Responses in Health and Disease. - de Hoz, Rosa; Rojas, Blanca; Ramírez, Ana I.; Salazar, Juan J.; Gallego, Beatriz I.; Triviño, Alberto; Ramírez, José M. (BioMed Research International, 2016)
Due to their permanent and close proximity to neurons, glial cells perform essential tasks for the normal physiology of the retina. Astrocytes and Müller cells (retinal macroglia) provide physical support to neurons and supplement them with several metabolites and growth factors. Macroglia are involved in maintaining the homeostasis of extracellular ions and neurotransmitters, are essential for information processing in neural circuits, participate in retinal glucose metabolism and in removing metabolic waste products, regulate local blood flow, induce the blood-retinal barrier (BRB), play fundamental roles in local immune response, and protect neurons from oxidative damage. In response to polyetiological insults, glia cells react with a process called reactive gliosis, seeking to maintain retinal homeostasis. When malfunctioning, macroglial cells can become primary pathogenic elements. A reactive gliosis has been described in different retinal pathologies, including age-related macular degeneration (AMD), diabetes, glaucoma, retinal detachment, or retinitis pigmentosa. A better understanding of the dual, neuroprotective, or cytotoxic effect of macroglial involvement in retinal pathologies would help in treating the physiopathology of these diseases. The extensive participation of the macroglia in retinal diseases points to these cells as innovative targets for new drug therapies.
Keywords: Retina -- Physiology; Health; Disease; Nervous System; Cells; Retinal Diseases -- Physiopathology; Homeostasis; Biological Transport; Neurotransmitters; Neural Pathways; Immune System; Inflammation; Cytokines; Neurons

The challenges of glaucoma management. - Katz LJ (Ocular Surgery News, 2008)
Keywords: Glaucoma -- Drug Therapy; Blindness; Disease Progression; Education, Continuing (Credit); Glaucoma -- Complications; Glaucoma -- Epidemiology; Health Services Accessibility; Intraocular Pressure; Medically Uninsured; Medication Compliance; Patient Compliance; Poverty; Prevalence

An adherence based cost-consequence model comparing bimatoprost 0.01% to bimatoprost 0.03%. - Wong, William B; Patel, Vaishali D; Kowalski, Jonathan W; Schwartz, Gail (Current Medical Research & Opinion, 2013)
Abstract Objectives: Estimate the long-term direct medical costs and clinical consequences of improved adherence with bimatoprost 0.01% compared to bimatoprost 0.03% in the treatment of glaucoma. Methods: A cost-consequence model was constructed from the perspective of a US healthcare payer. The model structure included three adherence levels (high, moderate, low) and four mean deviation (MD) defined health states (mild, moderate, severe glaucoma, blindness) for each adherence level. Clinical efficacy in terms of IOP reduction was obtained from the randomized controlled trial comparing bimatoprost 0.01% with bimatoprost 0.03%. Medication adherence was based on observed 12 month rates from an analysis of a nationally representative pharmacy claims database. Patients with high, moderate and low adherence were assumed to receive 100%, 50% and 0% of the IOP reduction observed in the clinical trial, respectively. Each 1 mmHg reduction in IOP was assumed to result in a 10% reduction in the risk of glaucoma progression. Worse glaucoma severity health states were associated with higher medical resource costs. Outcome measures were total costs, proportion of patients who progress and who become blind, and years of blindness. Deterministic sensitivity analyses were performed on uncertain model parameters. Results: The percentage of patients progressing, becoming blind, and the time spent blind slightly favored bimatoprost 0.01%. Improved adherence with bimatoprost 0.01% led to higher costs in the first 2 years; however, starting in year 3 bimatoprost 0.01% became less costly compared to bimatoprost 0.03% with a total reduction in costs reaching US$3433 over a lifetime time horizon. Deterministic sensitivity analyses demonstrated that results were robust, with the majority of analyses favoring bimatoprost 0.01%. Application of 1 year adherence and efficacy over the long term are limitations. Conclusions: Modeling the effect of greater medication adherence with bimatoprost 0.01% compared with bimatoprost 0.03% suggests that differences may result in improved economic and patient outcomes.
Keywords: Amides -- Administration and Dosage; Amides -- Economics; Bimatoprost -- Administration and Dosage; Bimatoprost -- Economics; Models, Biological; Ophthalmic Solutions -- Administration and Dosage; Ophthalmic Solutions -- Economics; Optic Nerve Diseases -- Drug Therapy; Optic Nerve Diseases -- Economics; Optic Nerve Diseases -- Physiopathology; Optic Nerve Diseases -- Therapy; Patient Compliance; Administration, Topical

Bimatoprost sustained-release device mitigates glaucoma adherence issue. - Charters, Lynda (Ophthalmology Times, 2016)
The article discusses the effectiveness of the bimatoprost sustained-release implant in improving patients' adherence to topical intraocular pressure (IOP)-lowering glaucoma drugs. Topics covered include Doctor Thomas R. Walters saying that the implant is a biodegradable device placed intracamerally in the eye, the results of a controlled clinical trial in open-angle glaucoma patients aimed at evaluating the safety and efficacy of the implant, and the IOP reduction linked with the implant.
Keywords: Glaucoma -- Drug Therapy; Bimatoprost -- Therapeutic Use; Intraocular Pressure -- Drug Effects

Hand hygiene is linked to microbial keratitis and corneal inflammatory events. - Fonn, Desmond; Jones, Lyndon (Contact Lens & Anterior Eye, 2019)
Lack of or inadequate hand washing is a risk factor in the development of contact lens related microbial keratitis and corneal inflammatory events. In the public health domain there is compelling evidence that proper hand washing with soap can save lives. The purpose of this review is to draw attention to some of the public health literature in support of hand washing and how education can influence patients' hand hygiene behavior. Contact lens wearers are also guilty of poor hand washing behavior but there is scant evidence that education of hand washing procedures of lens wearers alters patient non-compliance. It is well known that pathogenic microbial contamination of contact lenses, lens cases, care solutions and anterior ocular components have been found with contact lens wear. However while the originating source may be hands or water, it is most likely both of these. Besides proper hand washing this paper will include mitigating strategies for avoiding microbial contamination.
Keywords: Keratitis -- Microbiology; Eye Infections, Bacterial -- Microbiology; Handwashing; Contact Lenses; Equipment Contamination; Risk Factors; Patient Compliance; Inflammation -- Microbiology

The Effectiveness of Education Intervention on Glaucoma Patients for Improving Their Topical Medication (Eye Drop Therapy) Adherence and Outcomes: A Randomized Controlled Trial. - Suk Kwan Ho (Effectiveness of Education Intervention on Glaucoma Patients for Improving Their Topical Medication (Eye Drop Therapy) Adherence & Outcomes: A Randomized Controlled Trial, 2017)
Background: Globally, glaucoma is the leading cause of irreversible blindness and primary open-angle glaucoma (POAG) is a lifelong chronic eye disease. Although eye drop therapy (EDT) can prevent vision loss, patients do not adhere to the prescribed medication regimen that becomes a major clinical problem in glaucoma care. An evidence-based education intervention (EI) on promoting adherence to EDT was developed based on literature review and professional input to tackle the problem. A randomized controlled trial (RCT) was conducted to evaluate its effectiveness in Hong Kong. An Evidence Based EI: The content of education material aims to enhance patients' glaucoma knowledge and remove barriers to reinforce their treatment adherence. The EI consists of a one and a half hour structured education program, an information booklet, a telephone hotline, and five weekly follow up calls. Participants watched two self-developed videos which focused on information about the disease and selfinstillation of eye drop skills (SIEDS). During demonstration and return demonstration of the skills, reassurance, feedback, and encouragement were given to enhance participants' self-efficacy on the adherence. Research Aims: and Study Design The aim of this study was to evaluate the effectiveness of the EI as an adjunct to usual care, on adherence to eye drop therapy and outcomes. The study was a RCT with a pre-test-post-test study design. Participants: POAG outpatients were recruited from an ophthalmic centre in Hong Kong. Methods: Upon completing the face to face baseline interview, participants were randomly assigned to either intervention group or control group. Participants from intervention group received the EI while those from control group received an information leaflet on eye drop instillation. Two months later, both groups of participants were followed up by a trained research assistant who was blinded to conduct the telephone interview for data collection. Generalized estimating equations (GEE) were used to test the effectiveness of the EI. Outcome Measures: There were totally six major outcomes. (1) The primary outcome was eye drop adherence rate which was measured by self-report. Other outcomes were (2) glaucoma knowledge (33 items modified questionnaire from Hoevenaars' study) and (3) SIEDS (8 items self-developed checklist). (4) Psychological outcomes on depression and anxiety were measured by the Chinese version of the Hospital Anxiety and Depression Scale; and (5) Quality of life was measured by the Chinese version of Glaucoma Quality of Life-15 (GQL-15-CHI) questionnaire from Zhou, Zhou, Yao & Qian and (6) Physiological outcome on intraocular pressure was retrieved from medical record. Results: 128 eligible outpatients were participated with 75 males and 53 females. The mean age of them was 66.7. The average baseline adherence rate for all participants was 96.4 %. Their mean score of glaucoma knowledge and skills assessment were 19.93 (score ranged 0-33) and 3.86 (score ranged 0-8), respectively. For GQL-15- CHI, their mean score was 24.18 (score ranged 0-75). It correlated with degree of severity in the loss of visual field. Their average anxiety level and depression level were 3.73 and 4.23 (out of a range from 0 to 21), respectively. There were 54 (84.4%) participants received EI and most of them could not be contacted via weekly reminder calls. At T1, the attrition rates were calculated. It was 26.6% (n=17) in the control group and 9.4% (n=6) in the intervention group (p=0.011). For the effectiveness of the EI, the findings on hypothesis testing based on the GEE results showed that only the hypothesis regarding glaucoma knowledge was supported (p<0.001). A hypothesis on physiological change (IOP) was not tested because of a large volume of intraocular pressure readings was not available during this short term study. Conclusion: In the current study, the baseline glaucoma medication adherence rate was very high in compared with other studies. According to the skills assessment, participants had poor self-instillation of eye drop skills. This study showed that EI could improve participants' knowledge significantly but not the eye drop instillation skills nor the psychological outcomes and quality of life.
Keywords: Medication Compliance; Glaucoma -- Drug Therapy; Treatment Outcomes; Patient Education; Human; Male; Female; Randomized Controlled Trials; Health Knowledge; Outcomes of Education; Scales; Questionnaires; Aged

Cost may hinder use of new glaucoma drugs. - Lindstrom, may hinder use of new glaucoma drugs Richard L. (Ocular Surgery News, 2019)
Keywords: Glaucoma -- Drug Therapy; Antihypertensive Agents -- Economics; Latanoprost -- Economics; Health Care Costs; Latanoprost -- Administration and Dosage; Timolol -- Administration and Dosage; Timolol -- Economics; Brimonidine Tartrate-Timolol Maleate -- Economics; Patient Compliance; Protein Kinase Inhibitors -- Economics

Microbial Contamination of Periorbital Tissues and Accessories of Children. - Cheung, Sin Wan; Boost, Maureen; Shi, Guang Sen; Cho, Pauline (Optometry & Vision Science, 2016)
Purpose: To investigate normal flora of children with and without orthokeratology (ortho-k) treatment, and the associations between carriage of Staphylococcus aureus and Gram-negative rods with contamination of contact lenses and lens cases in ortho-k subjects and with spectacles of control subjects.Methods: Twenty-three ortho-k subjects (treatment >12 months) and 20 control myopic subjects aged 7-14 years were recruited. Samples were collected from four sites surrounding the left eye (lower conjunctiva, upper and lower eyelids, and eyelashes) for all subjects, spectacles for control subjects and contact lens accessories for ortho-k subjects. Samples were cultured, total numbers enumerated, and isolates identified using chromogenic agars.Results: Ortho-k subjects had significantly less total isolates in the conjunctiva than controls (p = 0.009). Otherwise, carriage rates in normal flora levels of the peri-orbital tissues were not significantly different between the two groups (p > 0.19). The total isolates and carriage rates of normal flora on spectacles, contact lenses, and lens cases were similar to those identified on the skin tissues. Small numbers of bacteria were identified from the multipurpose solution of two ortho-k subjects. Although the association between the carriage of S. aureus with contamination of accessories was statistically significant only in control subjects (p = 0.03), ortho-k subjects not yielding S. aureus and Gram-negative rods from samples of their peri-orbital tissues tended to be less likely to have these organisms in their accessories. No Pseudomonas was isolated from any of the sites sampled and no Acinetobacter was isolated from any of the accessories.Conclusions: Ortho-k may lower the total number of bacteria in conjunctiva due to the use of solution and lenses, but the physiologic effect of this treatment on the types of normal flora in children was minimal and should not increase the risk of microbial keratitis in children with good compliance.
Keywords: Staphylococcus Aureus; Conjunctiva -- Microbiology; Eyelids -- Microbiology; Equipment Contamination; Contact Lenses; Gram-Negative Bacteria; Refractive Errors -- Therapy; Myopia -- Therapy; Male; Child; Female; Adolescence; Human

Factors affecting compliance with eye drop therapy for glaucoma in a multicultural outpatient setting. - Curtis C; Lo E; Ooi L; Bennett L; Long J (Contemporary Nurse: A Journal for the Australian Nursing Profession, 2009)
Abstract Ophthalmic nurses at Sydney Hospital Sydney Eye Hospital aimed to assess and evaluate the knowledge and resulting behaviours of patients using eye drop therapy for glaucoma and the effect that using interpreters or English speaking family members had on patients' understanding and compliance. Non-compliance is known to lead to progression of the disease with resulting loss of vision. The study showed that patients undergoing long-term therapy for glaucoma have areas of non-compliance that may not be apparent to staff who see them in a clinic setting. It also showed that ineffectual use or missed doses of eye drops occur in both male and female groups, young and older groups and those from non-English and English speaking backgrounds. This is in spite of the same patients' assurances that they have received clear instructions. It has been shown that the use of interpreters or English speaking family members has not affected compliance. This study has shown that even patients who have been on therapy for over 12 months are likely to benefit from continuing education and reinforcement of good technique. Poor understanding of glaucoma in the over 65 age group was not associated with a higher rate of non-compliance. Acknowledgements The authors thank Nick Marosszeky for assistance with data analysis and staff of Sydney Hospital Sydney Eye Hospital Eye Outpatients Department for their comments.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Ophthalmic Solutions -- Administration and Dosage; Adolescence; Adult; Aged; Aged, 80 and Over; Chi Square Test; Communication Barriers; Convenience Sample; Female; Health Knowledge; Hospitals, Special; Male; Middle Age; New South Wales; Ophthalmic Nursing; Outpatient Service; Outpatients; Patient Education; Questionnaires; Human

Microshunt moves aqueous to ocular surface. - Cimberle, Michela (Ocular Surgery News, 2020)
Keywords: Glaucoma -- Surgery; Shunts, Surgical; Intraocular Pressure; Aqueous Humor; Patient Safety; Health Services Accessibility

A novel eye drop application monitor to assess patient compliance with a prescribed regimen: a pilot study. - Eaton, A M; Gordon, G M; Konowal, A; Allen, A; Allen, M; Sgarlata, A; Gao, G; Wafapoor, H; Avery, R L (Eye, 2015)
Purpose: To assess the ability of a novel imaging device to allow physicians to personalize therapeutic regimens based on objective patient drop administration data.Methods: A novel imaging system was used to record video of the drop technique of subjects in clinic (n=25) or at home (n=17) for 1 week. Video assessment by a reading center was compared with patient reporting and their prescribed regimen with respect to how many drops were applied and how many landed in the eye.Results: Reading center assessment of both drops dispensed and drops landing in the eye was significantly different from the prescribed regimen in the clinic (Pd=0.005, Pi<0.001, respectively) and at-home arms (Pd=0.003, Pi<0.001, respectively).Conclusions: This imaging system is a powerful tool to help physicians tailor patient therapy more accurately, to help researchers evaluate new drop therapies with objective rather than subjective data, and to potentially facilitate better patient training for improved drug delivery.
Keywords: Glaucoma -- Drug Therapy; Videorecording -- Equipment and Supplies; Antihypertensive Agents -- Administration and Dosage; Medication Compliance; Drug Delivery Systems -- Equipment and Supplies; Female; Adult; Prospective Studies; Male; Self Administration; Pilot Studies; Aged, 80 and Over; Middle Age; Monitoring, Physiologic; Young Adult; Aged; Ophthalmic Solutions; Human

Timolol 0.1% in Glaucomatous Patients: Efficacy, Tolerance, and Quality of Life. - Negri, Letizia; Ferreras, Antonio; Iester, Michele (Journal of Ophthalmology, 2019)
Glaucoma is a progressive, chronic optic neuropathy characterized by a typical visual field defects. Four main classes of topical medication are actually available on the market: beta-blockers, prostaglandins, alpha2-agonists, and topical carbonic anhydrase inhibitor to treat intraocular pressure (IOP). The aim of this review is to outline the efficacy of timolol and to evaluate the impact of this treatment on patients' quality of life. Among beta-blockers, timolol is most used at three different concentrations: 0.1%, 0.25%, and 0.5%. While the first one is a gel, the other two products are solution. Timolol has few topical side effects, while it has some important systemic side effects on the cardiac and respiratory systems. The balance between efficacy and safety is always the main aspect to care patients. Because of the less efficacy of timolol 0.1% solution, the possibility to use carbomers as vehicle in the gel drops helped timolol 0.1 to be used in clinics, extending the time contact between the active ingredient and the surface of the cornea. Using preservative-free timolol 0.1 for treatment, IOP was at the same level of the other beta-blockers at higher concentration, but it was better tolerated. Preservative-free treatment improved the quality of life reducing dry-eye like symptoms; furthermore, the presence of an artificial tear in the medication bottle could help adherence. The once daily dosing improves compliance.
Keywords: Glaucoma -- Drug Therapy; Timolol -- Therapeutic Use; Quality of Life -- Evaluation; Drug Tolerance -- Evaluation; Timolol -- Administration and Dosage; Patient Safety; Intraocular Pressure -- Evaluation; Medication Compliance

Reader Questions. (Ophthalmology Coding Alert, 2011)
Keywords: Ophthalmology; Coding; Cornea -- Surgery; Eye Foreign Bodies; Office Visits; Medicare; Current Procedural Terminology; Corneal Topography; Visual Fields; Glaucoma; Hospitalization; Lasers

Reader Questions. (Ophthalmology Coding Alert, 2011)
The article presents questions & answers related to coding for ophthalmological diseases including the code to be used for rust ring removal through slit lamp and a burr, whether 99215 is applicable for extended office visit, and the rules for coding corneal tophography.
Keywords: Ophthalmology; Coding; Cornea -- Surgery; Eye Foreign Bodies; Office Visits; Medicare; Current Procedural Terminology; Corneal Topography; Visual Fields; Glaucoma; Hospitalization; Lasers

Physicians can take steps to help improve patient adherence: Ask patients if they are experiencing problems; have them demonstrate how they take drops. - Groves, Nancy (Ophthalmology Times, 2017)
The article discusses how physicians can help improve patient adherence to glaucoma medication. Topics discussed include steps to help improve patient adherence including asking patients if they are experiencing problems and having them demonstrate how they take drops, and factors behind patients' difficulties with adherence including complicated regimen and financial issues.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance -- Evaluation

Noncompliance with Ocular Hypertensive Treatment in Patients with Primary Open Angle Glaucoma among the Arab Population in Israel: A Cross-Sectional Descriptive Study. - Masoud, Muhannad; Sharabi-Nov, Adi; Pikkel, Joseph (Journal of Ophthalmology, 2013)
Keywords: Glaucoma -- Drug Therapy -- Israel; Medication Compliance; Arabs; Antihypertensive Agents -- Therapeutic Use; Israel; Human; Cross Sectional Studies; Questionnaires; Interviews; Male; Female; Middle Age; Aged; Descriptive Statistics; Multiple Logistic Regression; T-Tests; Chi Square Test

How to Improve Compliance and Adherence. - Cakiner-Egilmez, Tulay (Insight: The Journal of the American Society of Ophthalmic Registered Nurses, 2015)
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Ophthalmic Solutions -- Therapeutic Use; Health Status; Age Factors; Comorbidity; Socioeconomic Factors; Physician-Patient Relations; Communication; Ophthalmic Solutions -- Economics; Reminder Systems; Teaching Materials; Patient Education; Patient Centered Care; Education, Continuing (Credit)

Teleglaucoma in the community: Taking it to the neighborhood. - Groves, Nancy (Ophthalmology Times, 2019)
The article discusses the initiatives of teleglaucoma screening in small U.S. communities to detect the condition early and check blindness as of July 2019. Topics covered include the approaches of isolating high-risk populations based on age, race, and family history of glaucoma to improve finding and treatment of glaucoma cases, and of tapping primary eye care providers like optometrists to perform comprehensive dilated eye exams on patients. Also noted are examples of these screening models.
Keywords: Glaucoma -- Prevention and Control; Telemedicine; Community Health Services; Health Services Accessibility; Quality of Health Care; Vision Screening; Glaucoma -- Diagnosis; Tomography, Optical Coherence

Impact of a health communication intervention to improve glaucoma treatment adherence. Results of the interactive study to increase glaucoma adherence to treatment trial. - Glanz, Karen; Beck, Allen D; Bundy, Lucja; Primo, Susan; Lynn, Michael J; Cleveland, Julia; Wold, Jessica A; Echt, Katharina V (Archives of Ophthalmology, 2012)
Keywords: Antihypertensive Agents -- Administration and Dosage; Communication -- Methods; Glaucoma -- Drug Therapy; Health Promotion -- Methods; Medication Compliance; Patient Education; Adolescence; Adult; Aged; Aged, 80 and Over; Appointments and Schedules; Female; Health Behavior; Human; Male; Middle Age; Ophthalmic Solutions; Patient Attitudes; Prescriptions, Drug -- Statistics and Numerical Data; Randomized Controlled Trials; Teaching Materials; Telephone -- Utilization; Young Adult

Usage of glaucoma-specific patient-reported outcome measures (PROMs) in the Singapore context: a qualitative scoping exercise. - Hee, Owen Kim; Thng, Zheng-Xian; Zhu, Hong-Yuan; Lamoureux, Ecosse Luc (BMC Ophthalmology, 2018)
Background: Despite the increasing emphasis on the role of glaucoma-specific patient-reported outcome measures (PROMs) as relevant outcome measures for the impact of glaucoma and its intervention on patients' daily lives, the feasibility of implementing PROMs in the routine clinical setting in Singapore remains undefined. We aim to evaluate the comprehensibility, acceptability, and relevance of four glaucoma-specific PROMs at healthcare professionals' and patients' level in a Singapore context.Methods: Sixteen ophthalmic healthcare professionals and 24 glaucoma patients, with average age 60 years (SD = 15), were invited from a tertiary hospital in Singapore. Semi-structured interviews were conducted to explore participants' perceptions on the content and administration of four glaucoma-specific PROMs - the Glaucoma Quality of Life-15, Glaucoma Symptom Identifier, Independent Mobility Questionnaire and Treatment Satisfaction Survey of Intra-ocular Pressure. Semi-structured interviews were hand transcribed, and analysed thematically. Each participant filled out a feasibility survey at the end of interview.Results: 79% of glaucoma patients and 94% of glaucoma healthcare professionals felt selected PROMs relevant to patients. 63% of glaucoma patients and 50% of healthcare professionals felt that selected PROMs were sufficiently comprehensive for clinical use. 46% of glaucoma patients and 56% of healthcare professionals felt selected PROMs were user-friendly.Conclusions: Using PROMs in the Singapore clinical setting receives promising support from both healthcare professionals and patients. The identified potential barriers tailored to Singapore clinical setting will help successful implementation of PROMs into routine clinical care.
Keywords: Glaucoma -- Therapy; Antihypertensive Agents -- Therapeutic Use; Pilot Studies; Glaucoma -- Physiopathology; Quality of Life; Male; Glaucoma -- Epidemiology; Female; Singapore; Middle Age; Exercise of Self-Care Agency Scale; Ferrans and Powers Quality of Life Index; Impact of Events Scale; Scales

Part I: detecting nonadherence. - Hahn SR; Budenz DL (Johns Hopkins Advanced Studies in Ophthalmology, 2008)
Keywords: Glaucoma -- Drug Therapy; Patient Compliance; Aged; Decision Making; Female; Male; Patient Education; Physician-Patient Relations; Psychology

Part III: addressing nonadherence. - Hahn SR; Schwartz GF (Johns Hopkins Advanced Studies in Ophthalmology, 2008)
Keywords: Glaucoma -- Drug Therapy; Patient Compliance; Patient Education; Behavioral Changes; Models, Psychological; Patient Centered Care

Interprofessional Problem-Based Learning Project Outcomes Between Prelicensure Baccalaureate of Science in Nursing and Doctor of Pharmacy Programs. - Hodges, Helen F.; Massey, Ann T. (Journal of Nursing Education, 2015)
Background: Persistently high medical error rates, caregiver dissatisfaction, and compromised patient safety often result from poorly coordinated, increasingly complex health care. Barriers to interprofessional health professions education persist despite the urgent calls for improved quality and safety. Investigators explored the effects of a problem-based learning (PBL) strategy between prelicensure doctorate of pharmacy (PharmD) and baccalaureate nursing (BSN) students. Method: A descriptive design was used to compare the learning gains and satisfaction with a PBL hybrid approach for BSN and PharmD prelicensure student groups over three academic terms. Results: Consistent with earlier works, content-based learning gains and student satisfaction were not significantly different between groups. Narrative data provide insight into perceived benefits, barriers, and perspectives of participating students and facilitators. Conclusion: Attributes of this pedagogical approach provide opportunity for prelicensure students to explore professional interdependence while adequately mastering fact-based content. [J Nurs Educ. 2015;54(4):201-206.]
Keywords: Problem-Based Learning; Education, Nursing, Baccalaureate; Education, Pharmacy; Human; Descriptive Research; Learning; Student Satisfaction; Pretest-Posttest Design; Summated Rating Scaling; Narratives; Perception; Student Attitudes; Funding Source; Female; Aged; Glaucoma -- Diagnosis; Glaucoma -- Drug Therapy; Patient Education; Teamwork; Interprofessional Relations

Turning to simplified regimen increases adherence, reduces drops: Bottle monotherapy may help to avoid possible added preservative-induced side effects. - Singh, Inder Paul (Ophthalmology Times, 2017)
The article reports on the potential for bottle monotherapy to avoid possible added preservative-induced side effects in glaucoma therapy. Topics discussed include the benefits of monotherapy, information on combination glaucoma drops, examples of compounded medications, and case studies involving glaucoma patients.
Keywords: Glaucoma -- Drug Therapy; Ophthalmic Solutions -- Administration and Dosage; Aged, 80 and Over; Male

Resource utilization and use of life-extending therapies and corticosteroids in prostate cancer patients with corticosteroid-sensitive comorbidities. - Bui, Cat N; Wang, Li; Baser, Onur (Current Medical Research & Opinion, 2014)
Abstract Objectives: Corticosteroids (CSs) are used concomitantly with life-extending therapies (LETs) in patients with castration-resistant prostate cancer (CRPC). This study examined time to LETs, LETs and concomitant CS adherence, and monthly all-cause healthcare utilization and costs in patients with CPRC with and without CS-sensitive comorbidities in the Veterans Health Administration population. METHODS: Patients had CRPC if records showed prostate cancer diagnosis, medical/surgical castration and >=2 prostate-specific antigen increases through 1 June 2007-31 May 2012. CS-sensitive comorbidities were assessed 6 months prior to the index date. Adherence, defined as medication possession ratio (MPR) >=0.8, among patients initiating LETs (cabazitaxel, docetaxel, or abiraterone acetate) before 30 November 2011, resource utilization and costs among patients with concomitant CS were assessed. Statistical analysis included descriptive, Cox proportional hazards, and logistic regression models. RESULTS: Common CS-sensitive conditions among 12,128 patients with CRPC included hypertension (75.74%) and hyperlipidemia (54.69%). Those with glaucoma (hazard ratio [HR] = 0.67), ischemic heart disease (HR = 0.78), and peripheral vascular disease (PVD) (HR = 0.78) were less likely to be prescribed LETs (all p < 0.01). Duration of LET was shorter among patients with CS-sensitive comorbidities (125.02 vs 133.08 days; p = 0.04) in the 6 month follow-up period. Among LET-treated patients with and without CS-sensitive comorbidities, less than half had MPR >= 0.8 (LET: 48.72% vs 54.05%; concomitant CS: 42.19% vs 40.54%, respectively). Cerebrovascular disease (odds ratio = 0.107; 95% confidence interval = 0.012 to 0.966) and PVD (odds ratio = 0.523; 95% confidence interval = 0.276 to 0.991) were associated with reduced CS adherence. Among patients with concomitant CS, those with CS-sensitive comorbidities had more inpatient stays than those without (20.45% vs 12.88%; p = 0.033), incurring higher monthly inpatient costs ($1157 vs $342; p < 0.0001) and total costs ($5725 vs $4772; p = 0.036). CONCLUSION: CS-sensitive conditions influence initiation and duration of LETs, concomitant CS adherence, inpatient stays, and total costs. Future efforts should focus on specific strategies for treating prostate cancer patients with CS-sensitive comorbidities to ensure that they have appropriate access to LETs and to reduce costs and inpatient stays. Study limitations include the use of retrospective claims data and the relatively restricted subpopulation of older North American males.
Keywords: Glucocorticoids -- Therapeutic Use; Health Care Costs; Health Services -- Utilization; Prostatic Neoplasms -- Complications; Prostatic Neoplasms -- Drug Therapy; Adult; Aged; Glucocorticoids -- Contraindications; Human; Logistic Regression; Male; Medication Compliance; Middle Age; Prostatic Neoplasms -- Pathology; Retrospective Design; United States

Glaucoma surveillance essential for optimizing patient outcomes. - Guttman Krader, Cheryl (Ophthalmology Times, 2016)
The article focuses on the message given by professor Kuldev Singh on glaucoma progression. Topics covered include the imperfect surveillance-related storm for developing severe visual disability from glaucoma, the failure of ophthalmologists to accurately predict which patients are going to demonstrate rapid- versus slow-disease progression and the results of a study investigating medication adherence based on prescription refill data.
Keywords: Glaucoma -- Therapy; Disease Progression; Outcomes (Health Care) -- Evaluation; Disease Surveillance

Global Survey of Corneal Transplantation and Eye Banking. - Gain, Philippe; Jullienne, Rémy; Zhiguo He; Aldossary, Mansour; Acquart, Sophie; Cognasse, Fabrice; Thuret, Gilles; He, Zhiguo (JAMA Ophthalmology, 2016)
Importance: Corneal transplantation restores visual function when visual impairment caused by a corneal disease becomes too severe. It is considered the world's most frequent type of transplantation, but, to our knowledge, there are no exhaustive data allowing measurement of supply and demand, although such data are essential in defining local, national, and global strategies to fight corneal blindness.Objective: To describe the worldwide situation of corneal transplantation supply and demand.Design, Setting, and Participants: Data were collected between August 2012 and August 2013 from a systematic review of published literature in parallel with national and international reports on corneal transplantation and eye banking. In a second step, eye bank staff and/or corneal surgeons were interviewed on their local activities. Interviews were performed during international ophthalmology or eye-banking congresses or by telephone or email. Countries' national supply/demand status was classified using a 7-grade system. Data were collected from 148 countries.Main Outcomes and Measures: Corneal transplantation and corneal procurements per capita in each country.Results: In 2012, we identified 184,576 corneal transplants performed in 116 countries. These were procured from 283,530 corneas and stored in 742 eye banks. The top indications were Fuchs dystrophy (39% of all corneal transplants performed), a primary corneal edema mostly affecting elderly individuals; keratoconus (27%), a corneal disease that slowly deforms the cornea in young people; and sequellae of infectious keratitis (20%). The United States, with 199.10-6 corneal transplants per capita, had the highest transplantation rate, followed by Lebanon (122.10-6) and Canada (117.10-6), while the median of the 116 transplanting countries was 19.10-6. Corneas were procured in only 82 countries. Only the United States and Sri Lanka exported large numbers of donor corneas. About 53% of the world's population had no access to corneal transplantation.Conclusions and Relevance: Our survey globally quantified the considerable shortage of corneal graft tissue, with only 1 cornea available for 70 needed. Efforts to encourage cornea donation must continue in all countries, but it is also essential to develop alternative and/or complementary solutions, such as corneal bioengineering.
Keywords: Corneal Transplantation -- Statistics and Numerical Data; Tissue Banks -- Statistics and Numerical Data; World Health; Organ Procurement -- Statistics and Numerical Data; Transplant Donors; Cornea; Organ Procurement -- Legislation and Jurisprudence; Surveys; Prayer; Corneal Diseases -- Rehabilitation; Waiting Lists; Systematic Review; Human

Provider Education about Glaucoma and Glaucoma Medications during Videotaped Medical Visits. - Sleath, Betsy; Blalock, Susan J.; Carpenter, Delesha M.; Muir, Kelly W.; Sayner, Robyn; Lawrence, Scott; Giangiacomo, Annette L.; Hartnett, Mary Elizabeth; Tudor, Gail; Goldsmith, Jason; Robin, Alan L. (Journal of Ophthalmology, 2014)
Keywords: Glaucoma -- Drug Therapy; Physician-Patient Relations; Patient Education; Physicians; Patients; Glaucoma -- Education; Office Visits; Cross Sectional Studies; United States; Questionnaires; Videorecording; Interviews; Clinical Assessment Tools; Interrater Reliability; Descriptive Statistics; Bivariate Statistics; Pearson's Correlation Coefficient; Chi Square Test; T-Tests; Human; Male; Female; Aged; Middle Age; Multivariate Analysis; Adult; Odds Ratio; Confidence Intervals; Funding Source

How to succeed in today's brave new world of glaucoma. - Guttman Krader, Chelyl (Ophthalmology Times, 2016)
The article focuses on the message given by Glaucoma Center of San Francisco executive director Andrew G. Iwach on the challenges posed by the changing health care delivery to ophthalmologists. Topics covered include the utilization of optical coherence tomography (OCT) and visual fields, the problems with medication compliance in glaucoma patient care and the impact of coding changes on ophthalmology practices.
Keywords: Glaucoma -- Therapy; Glaucoma -- Trends; Practice Patterns -- Trends

Diyabetli Olgularda Nd: YAG Lazer Kapsülotominin Görme Keskinliği, Maküler Kalınlık ve Göz İçi Basıncına Etkileri. - Türkoğlu, Elif Betül; Çelik, Erkan; Aksoy, Nilgün Özkan; Alagöz, Gürsoy (Turkish Journal of Ophthalmology / Turk Oftalmoloji Dergisi, 2015)
Objectives: To compare macular thickness, best-corrected visual acuity (BCVA), and intraocular pressure (IOP) changes after Nd: YAG laser capsulotomy for posterior capsule opacification (PCO) in diabetic and non-diabetic eyes. Materials and Methods: Thirty-six eyes of 25 diabetic patients and 40 eyes of 25 non-diabetic patients were included. All patients was treated with Nd: YAG laser capsulotomy. Macular thickness measured by optical coherence tomography (OCT), IOP, and BCVA were evaluated before and 1 week, 1 month, and 3 months after the procedure. Results: There was no difference between the two groups in age, gender, and applied laser technique. The time interval between cataract surgery and laser capsulotomy was shorter in the group of diabetic patients (p=0.009). In both groups, BCVA was significantly increased 1 week after laser capsulotomy (respectively, p = 0.023, p = 0.016). However, there was no statistically significant difference between the two groups. There was no significant difference in macular thickness before and after the procedure between the two groups (p>0.05). However, in group 1, cystoid macular edema was observed in 2 eyes during follow-up. Despite prophylactic treatment, IOP remained around 21-30 mmHg in 3 patients in group 1 and 4 patients in group 2 at first day and at the end of the 1st week. IOP was controlled except in one glaucoma patient. In the two groups, IOP values before and after laser capsulotomy were not statistically significantly different (p>0.05). At first day, +2 cells in the anterior chamber were detected in 3 patients in group 1 and in 2 patients in group 2; at 1 week after routine topical steroid treatment, anterior chamber reaction was not observed. Conclusion: It is known that there is a breakdown in the blood-aqueous and inner blood-retinal barriers in diabetes, however, no difference was determined in visual improvement, macular thickness, and IOP when comparing diabetic to non-diabetic eyes. We observed that Nd: YAG laser capsulotomy is a safe and effective method for posterior capsular opacification in diabetic and non-diabetic patients.

Occlusion of retinal capillaries caused by glial cell proliferation in chronic ocular inflammation. - Bianchi, E; Ripandelli, G; Feher, J; Plateroti, A M; Plateroti, R; Kovacs, I; Plateroti, P; Taurone, S; Artico, M (Folia Morphologica, 2015)
The inner blood-retinal barrier is a gliovascular unit in which glial cells surround capillary endothelial cells and regulate retinal capillaries by paracrine interactions. During chronic ocular inflammation, microvascular complications can give rise to vascular proliferative lesions, which compromise visual acuity. This pathologic remodelling caused by proliferating Müller cells determines occlusion of retinal capillaries. The aim of the present study was to identify qualitative and quantitative alterations in the retinal capillaries in patients with post-traumatic chronic ocular inflammation or post-thrombotic vascular glaucoma. Moreover, we investigated the potential role of vascular endothelial growth factor (VEGF) and pro-inflammatory cytokines in retinal inflammation. Our electron microscopy findings demonstrated that during chronic ocular inflammation, thickening of the basement membrane, loss of pericytes and endothelial cells and proliferation of Müller cells occur with irreversible occlusion of retinal capillaries. Angiogenesis takes place as part of a regenerative reaction that results in fibrosis. We believe that VEGF and pro-inflammatory cytokines may be potential therapeutic targets in the treatment of this disease although further studies are required to confirm these findings.

Switching from latanoprost to fixed-combination latanoprost-timolol: a 21-day, randomized, double-masked, active-control study in patients with glaucoma and ocular hypertension. - Olander K; Zimmerman TJ; Downes N; Schoenfelder J (Clinical Therapeutics, 2004)
BACKGROUND: Approximately 40% of patients with glaucoma are concomitantly prescribed >or=2 different intraocular pressure (IOP)-lowering medications. An effective and well-tolerated fixed combination of agents requiring once-daily instillation may improve patient compliance. OBJECTIVE: The purpose of this study was to compare the efficacy and safety profile of the fixed combination latanoprost 0.005% + timolol maleate 0.5% QD with those of latanoprost 0.005% monotherapy QD in patients whose elevated IOP (>or=21 mm Hg) was inadequately controlled by latanoprost. METHODS: This 21-day, randomized, double-masked, active-control study was conducted at 49 study sites in Argentina, Brazil, Colombia, Mexico, Peru, the United States, and Venezuela. Adults with glaucoma or ocular hypertension who had failed to reach an IOP of <21 mm Hg while receiving latanoprost for at least 28 days were enrolled. After an additional 28 days of latanoprost run-in, patients were randomly assigned to continue latanoprost monotherapy or to switch to the fixed combination for 21 days. The intent-to-treat (ITT) population included all patients who received at least 1 dose of double-masked study medication; the per-protocol (PP) analysis included patients who completed the study without a major protocol violation and who had IOP measurements both at baseline and at day 21. The primary end point was the proportion of patients whose IOP was decreased >or=2 mm Hg from the baseline level on day 21. Proportions of patients demonstrating IOP decreases >or=3, >or=4, or >or=5 mm Hg from the baseline level and of patients reaching an 10P <or=18 mm Hg were evaluated. Adverse events (AEs) were also assessed. RESULTS: A total of 350 patients were enrolled. In all, 348 patients were included in the ITT and tolerability analyses (fixed combination, n = 175; latanoprost, n = 173; mean [SD] age, 64.4 [13.2] and 63.2 [14.0] years, respectively; 103 women in each group). Baseline demographic and clinical characteristics were similar between groups. A higher percentage of patients receiving the fixed combination had IOP decreases of 2 mm Hg on day 21 relative to baseline compared with latanoprost-treated patients (79.4% vs 51.4%, respectively; P < 0.001). PP analyses found that more patients in the fixed-combination group had IOP decreases >or=3, >or=4, or >or=5 mm Hg (for each target level, P < 0.001 vs latanoprost group) or final IOP 18 mm Hg (fixed -combination, 35.1%; latanoprost, 17.8%; P < 0.001). Both treatments were well tolerated. Similar proportions of patients in the fixed-combination and latanoprost groups reported at least 1 treatment-emergent AE (10.9% and 12.1%, respectively). CONCLUSION: In this selected population of patients with an inadequate initial IOP response to latanoprost, switching to fixed-combination latanoprosttimolol resulted in a greater decrease in IOP and similar tolerability compared with continuing latanoprost therapy.
Keywords: Glaucoma -- Drug Therapy; Intraocular Pressure -- Drug Effects; Latanoprost -- Therapeutic Use; Ocular Hypertension -- Drug Therapy; Timolol -- Therapeutic Use; Aged; Data Analysis, Statistical; Descriptive Statistics; Double-Blind Studies; Female; Human; Male; Middle Age; Random Assignment; Tennessee; United Kingdom

Telemedicine, teleophthalmology programs in action at Johns Hopkins. - Lenier, Steve; Zimmer-Galler, Ingrid (Ophthalmology Times, 2019)
The article reports on the launch of 44 telemedicine programs at Johns Hopkins Medicine in Maryland in 31 specialties for over 16,700 patient encounters. Topics mentioned include the challenges in using telemedicine at Johns Hopkins, the effort of the Johns Hopkins Medicine Office of Telemedicine to coordinate all telemedicine efforts in the Hopkins healthcare enterprise, and the potential of teleophthalmology to be a radical transformer of care delivery.
Keywords: Program Implementation; Technology, Medical; Telemedicine; Ophthalmology; Patient Centered Care; Health Facilities -- Maryland; Health Care Costs; Diabetic Retinopathy -- Diagnosis; Glaucoma -- Diagnosis; Macular Degeneration -- Diagnosis; Maryland; Telecommunications; Reimbursement Mechanisms; Health Services Accessibility; Electronic Health Records; Quality of Health Care; Risk Management; Ophthalmologists; Emergency Service; Diagnosis, Eye -- Methods

Ocular carteolol: a review of its use in the management of glaucoma and ocular hypertension. - Henness S; Swainston Harrison T; Keating GM (Drugs & Aging, 2007)
Ocular carteolol (Mikelan((R)), Teoptic((R)), Ocupress((R))) is a nonselective beta-adrenoceptor antagonist with intrinsic sympathomimetic activity (ISA). Ocular carteolol effectively reduces intraocular pressure (IOP) in patients with open-angle glaucoma (OAG) or ocular hypertension (OH). Twice-daily administration of standard carteolol has generally similar IOP-lowering efficacy to other ocular beta-adrenoceptor antagonists such as timolol, betaxolol and metipranolol in patients with OAG or OH. In addition, long-term treatment with carteolol has similar efficacy to timolol and betaxolol in terms of reducing IOP and maintaining visual fields in patients with newly diagnosed primary OAG (POAG). The new long-acting formulation of once-daily carteolol has equivalent efficacy to the standard formulation of carteolol administered twice daily in patients with OAG or OH. Both the standard and long-acting formulations of ocular carteolol are generally well tolerated in terms of topical adverse effects involving the eyes or systemic adverse effects involving the cardiovascular system. Thus, twice-daily carteolol is a well established option in the treatment of glaucoma and OH, and the new once-daily formulation of long-acting carteolol offers similar efficacy and tolerability with a potential for improved patient adherence.
Keywords: Adrenergic Beta-Antagonists; Glaucoma -- Drug Therapy; Ocular Hypertension -- Drug Therapy; Adrenergic Beta-Antagonists -- Adverse Effects; Adrenergic Beta-Antagonists -- Therapeutic Use; Aged; Clinical Trials; Glaucoma -- Physiopathology; Instillation, Drug; Middle Age; Treatment Outcomes

Eye drop instillation technique in patients with glaucoma. - Tatham, A J; Sarodia, U; Gatrad, F; Awan, A (Eye, 2013)
Keywords: Antihypertensive Agents -- Administration and Dosage; Glaucoma -- Drug Therapy; Ophthalmic Solutions -- Administration and Dosage; Aged; Aged, 80 and Over; Analysis of Variance; Cross Sectional Studies; Female; Human; Logistic Regression; Male; Middle Age; Ocular Hypertension -- Drug Therapy; Patient Compliance; Patient Education -- Standards; Self Care

Cataract patients may benefit from new drug-delivery methods: Approaches aim to improve compliance for efficacy, while reducing medication burden. - Harrison, Laird (Ophthalmology Times, 2018)
The article presents a discussion of the benefits of new drug-delivery methods for cataract surgery, adapted from Dr. Francis S. Mahs' presentation at the 2017 meeting of the American Academy of Ophthalmology. Topics covered include the system's ability to improve compliance and reduce medication burden, how the devices might improve efficacy and reduce toxicity, and examples of delivering drugs in the anterior chamber or through intravitreal or transzonular injection.
Keywords: Cataract -- Drug Therapy; Drug Delivery Systems; Treatment Outcomes; Medication Compliance; Antibiotics -- Therapeutic Use; Antiinflammatory Agents -- Therapeutic Use; Ophthalmic Solutions -- Therapeutic Use; Patient Education; Glaucoma -- Drug Therapy; Retinal Diseases -- Drug Therapy; Miosis -- Prevention and Control; Phenylephrine -- Therapeutic Use; Ketorolac -- Therapeutic Use; Dexamethasone -- Therapeutic Use

How MIGS benefits those with the greatest of needs: Charitable missions provide long-lasting care to patients in underserved areas of the world. - Sondheimer, Stuart (Ophthalmology Times, 2018)
The article highlights the benefits of microinvasive glaucoma surgeries (MIGS) to treating glaucoma in developing countries that have limited access to ophthalmic care. Topics covered include how the technology in combination with charitable missions is transforming glaucoma care to disadvantaged individuals worldwide, the mission of nonprofit SEE International in Honduras performing cataract surgery and implanting iStents, and studies showing the customization of iStent implantation.
Keywords: Glaucoma -- Surgery; Eye Surgery -- Methods; Medically Underserved Area; Patient Care; Health Services Needs and Demand; Charities; Treatment Outcomes; Rural Areas; Technology, Medical; Cataract Extraction; Ophthalmologists; Missions and Missionaries; Phacoemulsification; Stents; Intraocular Pressure; Health Services Accessibility; Minimally Invasive Procedures; Glaucoma -- Prevention and Control

Patient noncompliance in the managed care setting. The case of medical therapy for glaucoma. - Gurwitz, J H; Yeomans, S M; Glynn, R J; Lewis, B E; Levin, R; Avorn, J (Medical Care, 1998)
Objectives: The authors identify demographic and clinical characteristics associated with noncompliance in patients beginning medical therapy for the treatment of glaucoma in a managed care setting.Methods: The authors describe a retrospective cohort study in a group-model health maintenance organization in Massachusetts. Patients were members of the health maintenance organization who were newly initiated on topical drug therapy to treat open-angle glaucoma during the period January 1, 1987 through December 31, 1990, who met eligibility requirements, and who had evidence of health services utilization for a 12-month follow-up period. For all study subjects, we determined the number of days without available therapy for glaucoma during the 12-month period. Study subjects who did not fill prescriptions adequate to provide medication to cover at least 80% of days during the study period were considered noncompliant. Logistic regression analysis was used to assess demographic and clinical factors independently associated with noncompliance among patients initiated on medical therapy for the treatment of glaucoma.Results: Of 616 subjects who met inclusion criteria, 152 (24.7%; 95% confidence interval, 21.3%-28.1%) met the study definition for noncompliance. These patients had an average number of days without therapy during the 12-month study period of 103.9 +/- 70.0 days compared with 6.8 +/- 19.5 days for those categorized as compliant. Of a variety of selected demographic and clinical characteristics, having fewer visits with an ophthalmologist during the study period (< 2) was most strongly related to noncompliance (odds ratio 2.99; 95% confidence interval 2.03, 4.40). There were no differences in average intraocular pressure between the compliant and noncompliant groups during the study period.Conclusions: Noncompliance with prescribed medical therapy for glaucoma was found to be common in a managed care setting characterized by essentially unrestricted access to health care and medications. It remains difficult to identify noncompliant patients based on demographic and clinical characteristics. The use of automated prescription data to identify noncompliant patients is feasible in large managed health care insurance programs where such data are collected routinely for administrative purposes.
Keywords: Glaucoma -- Drug Therapy; Treatment Refusal -- Statistics and Numerical Data; Health Maintenance Organizations -- Statistics and Numerical Data; Middle Age; Aged, 80 and Over; Massachusetts; Aged; Retrospective Design; Prospective Studies; Self Administration; Logistic Regression; Time Factors; Female; Human; Male; Adult; Prescriptions, Drug -- Statistics and Numerical Data; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Scales

The Effect of Latanaprost on Intraocular Inflammation and Macular Edema. - Razeghinejad, M. Reza (Ocular Immunology & Inflammation, 2019)
There is debate concerning whether the use of Latanoprost in early postoperative period of cataract surgery and in glaucoma patients with uveitis as it may aggravate the inflammation and results in macular edema (ME), because of blood-ocular barrier disruption. However, there is no solid evidence for disruption of blood-ocular barrier with Latanoprost and aggravation of uveitis or ME formation. Similar to pseudophakic ME, the imaging ME in cases claimed to be secondary to Latanoprost is greater than clinical ME, happens mostly in complicated surgeries, and the vast majority resolve within weeks to months with using a non-steroidal anti-inflammatory drug. The current literature suggests that Latanoprost can be used in patients with uveitis and early after cataract surgery with or without concomitant topical non-steroidal anti-inflammatory drugs that are currently used by many ophthalmologists as a preventive measure for ME even in non-glaucoma uncomplicated cataract surgeries.
Keywords: Uveitis -- Drug Therapy; Macular Degeneration -- Drug Therapy; Macular Degeneration -- Etiology; Uveitis -- Complications; Inflammation -- Drug Therapy; Antihypertensive Agents -- Therapeutic Use; Scales

Compliance of a patient with glaucoma and associated factors. - Lunnela J; Kyngäs H; Hupli M (Hoitotiede, 2006)
The purpose of this research was to study the compliance and associated factors of a patient with glaucoma. The data were collected from adult glaucomapatients by using a structured instrument modified to this study. The instrument was developed by Kyngas (1999a) to measure compliance and factors connected to it. The data were collected from glaucomapatients who used medication (n=97) and visited at out patient clinic. The data were collected in winter 2004 and were analysed with SPSS statistical programme. Descriptive statistics, i.e. frequenses and percentages were used to describe the data. The statistical tests used were cross-tables, Chi-Square, Fisher Exact test, Mann-Whitney U -test and Kruskall-Wallis test. The items that measure compliance and the factors associated to it were formatted sum variables.More than half (58%) of the glaucomapatients showed good compliance and 70% showed good compliance in medical care. The associated factors were motivation to take care of oneself and will-power and support from doctors, nurses, relatives and friends, sense of normality, good results of care and if the patient was not afraid of complications. Women showed better adherence than men. Also, satisfaction with patient education was clearly associated with compliance.As a conclusion it can be said that the compliance of glaucomapatients was similar than other patients with chronic disease. The patients had good motivation, had energy and will-power to take care of themselves and received support from relatives, nurses and physicians. The patients also received counselling and information from nurses and physicians.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance -- Evaluation; Chi Square Test; Descriptive Statistics; Fisher's Exact Test; Kruskal-Wallis Test; Mann-Whitney U Test; Outpatients; Self Care -- Evaluation; Structured Questionnaires; Human

Treatment of glaucoma patients with insufficient intraocular pressure control: a survey of German ophthalmologists in private practice. - Vorwerk C; Thelen U; Buchholz P; Kimmich F; Vorwerk, Christian; Thelen, Ulrich; Buchholz, Patricia; Kimmich, Friedemann (Current Medical Research & Opinion, 2008)
Objective: To assess the degree to which glaucoma treatment guidelines have been incorporated into daily practices and to describe the therapeutic practices chosen for patients with insufficient intraocular pressure (IOP) control.Methods: Ophthalmologists in private practice in Germany were surveyed to obtain information about patients who exhibited unsatisfactory progress with IOP-lowering pharmacotherapy. Using a questionnaire, physicians provided data concerning treatment difficulty, target IOP, number and type of medications used, two most recent IOP readings, and optic nerve head and visual field observations.Results: Of the 853 patients analyzed, primary open-angle glaucoma was the diagnosis for 67.1%, and other diagnoses included ocular hypertension, normal tension glaucoma, and pseudoexfoliation glaucoma. Target IOP levels had been determined for 95.5% of patients, and not achieving the target pressure was identified as a treatment difficulty for 81.0% of patients. Of patients on monotherapy, beta-blockers were prescribed most often (42.3%). Of all patients, 53.3% were treated with two or more agents as either fixed or non-fixed combinations. The non-fixed combination of a prostaglandin and carbonic anhydrase inhibitor was the most frequently prescribed dual therapy (19.2%). Non-fixed prostaglandin plus beta-blocker was used by 18.0% of dual therapy patients, whereas the available fixed combination was used by 10.5%. Non-compliance was identified as a cause of unsatisfactory IOP-lowering in 26.8% of all patients. This study is limited by its descriptive, non-interventional design.Conclusions: Treatment alterations are necessary to achieve sufficient IOP control in some patients. If these patients were to take advantage of more aggressive therapies as outlined by treatment guidelines, including newer formulations and fixed combination preparations, both efficacy and compliance may be improved.
Keywords: Adrenergic Beta-Antagonists -- Administration and Dosage; Glaucoma -- Diagnosis; Glaucoma -- Drug Therapy; Intraocular Pressure -- Drug Effects; Prostaglandins, Synthetic -- Administration and Dosage; Aged; Aged, 80 and Over; Dose-Response Relationship, Drug; Drug Therapy, Combination; Female; Germany; Intraocular Pressure -- Physiology; Male; Middle Age; Ophthalmology -- Methods; Patient Compliance; Practice Guidelines; Practice Patterns -- Standards; Private Practice; Prognosis; Questionnaires; Risk Assessment; Severity of Illness Indices; Surveys; Tonometry; Treatment Failure; Human

Surveillance for ocular hypertension: an evidence synthesis and economic evaluation. - Burr J; Botello-Pinzon P; Takwoingi Y; Hernández R; Vazquez-Montes M; Elders A; Asaoka R; Banister K; van der Schoot J; Fraser C; King A; Lemij H; et al. (Health Technology Assessment, 2012)
OBJECTIVES: To determine effective and efficient monitoring criteria for ocular hypertension [raised intraocular pressure (IOP)] through (i) identification and validation of glaucoma risk prediction models; and (ii) development of models to determine optimal surveillance pathways. DESIGN: A discrete event simulation economic modelling evaluation. Data from systematic reviews of risk prediction models and agreement between tonometers, secondary analyses of existing datasets (to validate identified risk models and determine optimal monitoring criteria) and public preferences were used to structure and populate the economic model. SETTING: Primary and secondary care. PARTICIPANTS: Adults with ocular hypertension (IOP > 21mmHg) and the public (surveillance preferences). INTERVENTIONS: We compared five pathways: two based on National Institute for Health and Clinical Excellence (NICE) guidelines with monitoring interval and treatment depending on initial risk stratification, 'NICE intensive' (4-monthly to annual monitoring) and 'NICE conservative' (6-monthly to biennial monitoring); two pathways, differing in location (hospital and community), with monitoring biennially and treatment initiated for a >= 6% 5-year glaucoma risk; and a 'treat all' pathway involving treatment with a prostaglandin analogue if IOP > 21 mmHg and IOP measured annually in the community. MAIN OUTCOME MEASURES: Glaucoma cases detected; tonometer agreement; public preferences; costs; willingness to pay and quality-adjusted life-years (QALYs). RESULTS: The best available glaucoma risk prediction model estimated the 5-year risk based on age and ocular predictors (IOP, central corneal thickness, optic nerve damage and index of visual field status). Taking the average of two IOP readings, by tonometry, true change was detected at two years. Sizeable measurement variability was noted between tonometers. There was a general public preference for monitoring; good communication and understanding of the process predicted service value. 'Treat all' was the least costly and 'NICE intensive' the most costly pathway. Biennial monitoring reduced the number of cases of glaucoma conversion compared with a 'treat all' pathway and provided more QALYs, but the incremental cost-effectiveness ratio (ICER) was considerably more than £30,000. The 'NICE intensive' pathway also avoided glaucoma conversion, but NICE-based pathways were either dominated (more costly and less effective) by biennial hospital monitoring or had a ICERs > £30,000. Results were not sensitive to the risk threshold for initiating surveillance but were sensitive to the risk threshold for initiating treatment, NHS costs and treatment adherence. LIMITATIONS: Optimal monitoring intervals were based on IOP data. There were insufficient data to determine the optimal frequency of measurement of the visual field or optic nerve head for identification of glaucoma. The economic modelling took a 20-year time horizon which may be insufficient to capture long-term benefits. Sensitivity analyses may not fully capture the uncertainty surrounding parameter estimates. CONCLUSIONS: For confirmed ocular hypertension, findings suggest that there is no clear benefit from intensive monitoring. Consideration of the patient experience is important. A cohort study is recommended to provide data to refine the glaucoma risk prediction model, determine the optimum type and frequency of serial glaucoma tests and estimate costs and patient preferences for monitoring and treatment. FUNDING: The National Institute for Health Research Health Technology Assessment Programme.
Keywords: Antihypertensive Agents -- Economics; Antihypertensive Agents -- Therapeutic Use; Glaucoma -- Prevention and Control; Ocular Hypertension -- Drug Therapy; Ocular Hypertension -- Economics; Age Factors; Antihypertensive Agents -- Administration and Dosage; Clinical Trials; Cost Benefit Analysis; Health Screening; Human; Intraocular Pressure; Models, Theoretical; Ocular Hypertension -- Epidemiology; Prospective Studies; Quality-Adjusted Life Years; Risk Assessment; Systematic Review

Big picture of glaucoma care presents with shades of gray. - Meszaros, Liz (Ophthalmology Times, 2014)
Keywords: Glaucoma -- Therapy; Eye Care; Patient Compliance

Many advances made with glaucoma drugs and delivery systems in 2015. - Harrison, Laird (Ophthalmology Times, 2015)
The article discusses advances in drugs and delivery systems for the treatment of glaucoma in 2015. Topics cited include the clinical trial of the Rhopressa drug as an alternative to prostaglandin analogues, the pairing of the prostaglandin analogue latanoprost acid with nitric oxide to create the eye drop latanoprostene bunod and drug makers' development of medications that improve patient adherence and convenience.
Keywords: Glaucoma -- Drug Therapy; Drug Delivery Systems -- Trends; Drugs, Investigational; Glaucoma -- Trends

Pharmacologic Interventions for Apathy in Patients with Alzheimer Disease. - Rey, Jeanmarie B.; Kalish, Virginia B. (American Family Physician, 2019)
The article discusses pharmacologic interventions for Apathy in Patients with Alzheimer Disease (AD) which involves use of methylphenidate. It mentions that Methylphenidate is more effective than placebo over AD. It presents information on use of nonpharmacologic therapies for behavioral and psychological symptoms of dementia. It also mentions information on risk of medication noncompliance which involves open-angle glaucoma, hypertension and related cardiovascular conditions.

Aging Eye. (Ophthalmology Times, 2013)
The article presents views of several eye experts including Stephen C. Pflugfelder, Steven L. Mansberger and Cindy M.L. Hutnik on aging eye problems. According to Pflugfelder, conjunctivochalasis increases with age and it results in pooling and stagnation of the central tear meniscus. Mansberger mentions that disc hemorrhages persist for six months in patients who are poorly adherent to their glaucoma medications and Hutnik discusses ocular surface disease in aged people.
Keywords: Aging; Diagnosis, Eye; Eye Diseases -- Therapy; Treatment Outcomes -- Evaluation; Eye Diseases -- Classification

To improve compliance in glaucoma patients, EyeMDs can keep it simple. - Groves, Nancy (Ophthalmology Times, 2015)
The article discusses ways that can help ophthalmologists ensure that their patients comply with their glaucoma medications. Topics covered include common reasons for non-compliance with glaucoma medications, the need to prescribe cheaper and more effective medicines to the patients, addition of laser therapy to the treatment regimen and the recommendation to use travoprost and bimatoprost, the two most effective prostaglandin analogs in the U.S.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance -- Evaluation

Influence of parental health literacy and dosing responsibility on pediatric glaucoma medication adherence. - Freedman RB; Jones SK; Lin A; Robin AL; Muir KW (Archives of Ophthalmology, 2012)
Keywords: Glaucoma -- Drug Therapy; Information Literacy; Medication Compliance; Ophthalmic Solutions -- Administration and Dosage; Parents -- Education; Health Literacy; Adolescence; Adult; Child; Child, Preschool; Clinical Assessment Tools; Drug Monitoring -- Statistics and Numerical Data; Female; Human; Male; Medication Errors -- Prevention and Control; Medication Errors -- Statistics and Numerical Data; Prospective Studies; Surveys

Innovative alternatives in the surgical management of glaucoma with cataract surgery. - Ianchulev, Tsontcho; Ahmed, Iqbal I. K.; Stamper, Robert L.; Chang, David F.; Samuelson, Thomas W.; Lindstrom, Richard L. (Expert Review of Ophthalmology, 2017)
Introduction: Glaucoma is the leading cause of irremediable blindness worldwide. The prevalence of glaucoma will continue to increase with the increased ageing of the global population. The only way to reduce the progression of vision loss due to glaucoma is to control the level of intraocular pressure (IOP). IOP control initially depends upon pharmaceutical interventions. The efficacy of IOP-lowering medications is limited by poor patient compliance, incorrect medication administration, ocular side effects and cost. When IOP-lowering medications fail to halt the progression of glaucoma, surgical intervention, such as trabeculectomy or glaucoma drainage device surgery, is indicated, but neither has been found completely satisfactory. Surgical interventions have a significant risk of complications that result in decreased vision. Areas covered:This article summarizes the design and function, as well as reviewing the efficacy, of various innovative, highly safe, surgical approaches to the treatment of glaucoma. Expert opinion:Recent treatment innovations have taken advantage of the fact that many patients with mild-to-moderate glaucoma also have cataracts. Devices and procedures have been developed that are no more invasive than cataract surgery and that can be performed concurrently with cataract surgery. These IOP-lowering treatments have an excellent safety profile and minimize ocular tissue trauma.
Keywords: Glaucoma -- Prevention and Control; Intraocular Pressure; Surgery, Operative -- Trends; Trabeculectomy; Medication Compliance; Medication Errors; Adverse Drug Event; Health Care Costs

Tracking treatment, adherence in cases of newly diagnosed OAG. - Charters, Lynda (Ophthalmology Times, 2017)
The article focuses on a retrospective claims analysis on the treatment and adherence in cases of open-angle glaucoma (OAG) diagnosis. It mentions findings of the study including 17% of patients who remain untreated four years following initial OAG diagnosis, the prescription of prostaglandin analogue and beta-blocker as common medical treatments and the performance of laser trabeculoplasty as first-line treatment.
Keywords: Glaucoma -- Drug Therapy; Intraocular Pressure -- Drug Effects; Medication Compliance; Guideline Adherence; Early Intervention -- Evaluation

Knowledge and Attitudes towards Eye Diseases in a Rural South-eastern Nigerian Population. - Onwubiko, S. N.; Eze, B. I.; Udeh, N. N.; Okoloagu, N. N.; Chuka-Okosa, C. M. (Journal of Health Care for the Poor & Underserved, 2015)
Background. Knowledge and attitudes concerning eye disorders are important socio-demographic parameters critical for eye care uptake and outcomes, especially in underserved populations. Objectives. To assess knowledge and attitudes concerning common eye disorders in a rural south-eastern Nigerian population. Methods. The study was a population-based survey of knowledge and attitudes concerning common eye diseases conducted in Abagana community in September 2011. Results. The participants comprised 263 males and 238 females. Their profile of good knowledge was eye infections: 38.9%; refractive error: 28.9%; cataracts: 18.0%; diabetic retinopathy: 8.0%; glaucoma: 5.8%; and overall good knowledge: 4.0%. Prevention and treatment of eye disorders were rated as first priorities over other major disabilities by 91.4% participants. Older age and formal education were the significant predictors of good knowledge. Conclusion. In Abagana, there is poor overall and disorder-specific knowledge of eye disorders. Socio-demographic factors are important determinants of knowledge. Community-based preventive eye health education is underscored.
Keywords: Eye Diseases; Health Knowledge; Attitude to Illness; Human; Rural Areas; Medically Underserved; Nigeria; Surveys; Female; Male; Adult; Middle Age; Aged; Age Factors; Health Education; Random Sample; Cluster Sample; Data Analysis Software; T-Tests; Odds Ratio; Confidence Intervals; Logistic Regression; Demography; Sex Factors; Health Services Accessibility; Perception; Self Report

Improving patient access to prevent sight loss: ophthalmic electronic referrals and communication (Scotland). - Khan, A. A.; Mustafa, M. Z.; Sanders, R. (Public Health (Elsevier), 2015)
Introduction: With the number of people with sight loss predicted to double to four million people in the UK by the year 2050, preventable visual loss is a significant public health issue. Sight loss is associated with an increased risk of falls, accidents and depression and evidence suggests that 50% of sight loss can be avoided. Timely diagnosis is central to the prevention of sight loss. Access to care can be a limiting factor in preventable cases. By improving referrals and access to hospital eye services it is possible to treat and minimise the number of patients with preventable sight loss and the impact this has on wider society. Clinical pilot study: In 2005, NHS Fife took part in a flagship pilot funded by the Scottish government e-health department to evaluate the feasibility, safety, clinical effectiveness, and cost of electronic referral with images of patients directly from community optometrists to Hospital Eye Service (HES). The pilot study showed that electronic referral was feasible, fast, safe, and obviated the need for outpatient appointments in 128 (37%) patients with a high patient satisfaction. Centralised ophthalmic electronic referral unit: The results of the pilot study were presented and in May 2007, the electronic referral system was rolled out regionally in southeast Scotland. Referrals were accepted at a single site with vetting by a trained team and appointments were allocated within 48 hours. Following the implementation of electronic referral, waiting times were reduced from a median of 14 to 4 weeks. Significantly fewer new patients were seen (7462 us 8714 [p < 0.001]). There were also fewer casualties (1984 us 2671 [p < 0.001]) and 'did not arrive1 (DNA) new patients (503 us 635 [p < 0.001]). Eye care integration project (Scotland): In 2010 the Scottish Government Health Department committed £6.6 million to community and hospital ophthalmic services forming the Eyecare Integration Project in 2011. The main aim of this project was to create electronic communication between community optometry practices and hospital eye departments. Five electronic forms were specifically designed for cataract, glaucoma, macula, paediatric and general ophthalmic disease. A Virtual Private Network was created which enabled optometrists to connect to the Scottish clinical information gateway system and send referrals to hospital and receive referral status feedback. Numerous hurdles have been encountered and overcome in order to deliver this project.
Keywords: Health Services Accessibility -- Evaluation; Patient Care; Blindness -- Prevention and Control; Ophthalmology; Referral and Consultation; Public Health; Human; Technology, Medical; Pilot Studies

A multicentre evaluation of the effect of patient education on acceptance of hyperaemia associated with bimatoprost therapy for glaucoma or ocular hypertension. - Trattler W; Noecker RJ; Earl ML (Advances in Therapy, 2008)
INTRODUCTION: The aim of this study was to evaluate the incidence of hyperaemia in patients using bimatoprost and to determine if simple interventions result in increased understanding of glaucoma and hyperaemia. METHODS: This was a multicentre, open-label, evaluator-masked clinical trial of 106 patients. Prior to enrolling in the trial, patients were washed out from any ocular hypotensive medications and prescribed bimatoprost daily in the evening for 6 weeks. Patients were randomised to one of two groups: intervention and no intervention. Patients in the intervention group (n=63) were given a fact sheet explaining the importance of reducing intraocular pressure (IOP) and the efficacy of bimatoprost, while patients in the no intervention group (n=43) were instructed only to instil bimatoprost daily and were given no additional instructions. RESULTS: As graded by the masked investigators, conjunctival hyperaemia peaked 1 day after commencing bimatoprost, with a mean of 1.2 (0=none, 0.5=trace, 1=mild, 2=moderate, 3=severe). By day 7, hyperaemia levels were approximately trace (0.79) and continued to decrease throughout the study. There were no significant differences between groups in mean conjunctival hyperaemia at any study visit (P> or =0.215). At every visit, patients in the intervention group were significantly more likely than patients in the no intervention group to report that lowering IOP was very important for preserving vision (P< or =0.001). At week 6, 98% of patients in the intervention group reported that IOP-lowering was very important for preserving vision, compared with 76% of patients who did not receive the intervention (P< or =0.001). Patients in the intervention group were more likely than patients in the no intervention group to be willing to continue to use bimatoprost, despite hyperaemia. This difference was statistically significant at day 1 (P=0.003). CONCLUSION: Patients were not bothered by the trace.mild hyperaemia associated with bimatoprost therapy. Patient education can improve patient acceptance of a prescribed regimen and potentially increase compliance.
Keywords: Bimatoprost -- Therapeutic Use; Hyperemia -- Chemically Induced; Ocular Hypertension -- Drug Therapy; Patient Education -- Methods; Aged; Bimatoprost -- Administration and Dosage; Bimatoprost -- Adverse Effects; Clinical Trials; Female; Glaucoma -- Drug Therapy; Human; Intraocular Pressure; Male; Patient Compliance

GLAUCOMA 2020: A CALL TO ARMS: The three reasons glaucoma should be on our radar. - BENCE, BRETT G. (Optometric Management, 2020)
Keywords: Glaucoma -- Diagnosis; Diagnosis, Eye; Optometrists; Glaucoma -- Therapy; Optometry -- Equipment and Supplies; Intraocular Pressure; Health Services Accessibility; Primary Health Care; Tomography, Optical -- Methods; Optometry -- Education

LOOK BEYOND IOP IN GLAUCOMA: It's important to also consider cost, availability, side effects and administration when determining treatment. - O'DONNELL JR., JOHN J. (Optometric Management, 2020)
Keywords: Glaucoma -- Drug Therapy; Intraocular Pressure; Health Care Costs; Health Services Accessibility; Adverse Drug Event; Drug Administration; Decision Making, Clinical; Adrenergic Alpha-Agonists -- Adverse Effects; Adrenergic Beta-Antagonists -- Adverse Effects; Carbonic Anhydrase Inhibitors -- Adverse Effects; Drug Combinations -- Adverse Effects; Prostaglandins -- Adverse Effects; Protein Kinase Inhibitors -- Adverse Effects

Vision loss: normal and not normal changes among older adults. - Stuen C; Faye EE (Generations, 2003)
Keywords: Vision Disorders -- In Old Age; Aging; Vision -- In Old Age; Aged; Gerontologic Care; Aging -- Physiology; Middle Age; Cataract; Diabetic Retinopathy; Macular Degeneration; Glaucoma; Functional Status -- In Old Age; Rehabilitation of Vision Impaired -- In Old Age; Rehabilitation Centers -- New York; New York; Health Services Accessibility

Influence of switching to travoprost on intraocular pressure of uncontrolled chronic open-angle glaucoma patients compliant to previously-used topical medication. - Holló G; Vargha P; Kóthy P (Current Medical Research & Opinion, 2005)
OBJECTIVE: To investigate the influence of switching to travoprost on intraocular pressure (IOP) of chronic open-angle glaucoma (COAG) patients. RESEARCH DESIGN AND METHODS: Multicentre, open-label, non-comparative, 12-week, phase IV study conducted at 10 academic and hospital centres in Hungary. Patients' compliance to use of the pre-study medication was confirmed at a visit 10 days before the baseline measurements, and compliance was monitored throughout the study period. RESULTS: Of the 203 COAG patients three (1.48%) ceased travoprost medication due to ocular hyperaemia, and one subject was lost from follow-up. Self-reported compliance was optimal except for two patients. For the per-protocol analysis 197 patients were evaluable. IOP of the 37 per-protocol patients receiving additional travoprost medication decreased from 23.1 +/- 3.2 mmHg (mean +/- SD) to 17.3 +/- 2.6 mmHg at week 12 (p < 0.001). Switching the 121 per-protocol patients from latanoprost to travoprost IOP decrease from 20.8 +/- 3.5 mmHg to 17.7 +/- 2.4 mmHg (p < 0.001). IOP of the 11 patients switched from topical nonselective beta-blockers to travoprost decreased from 20.1 +/- 2.1 mmHg to 15.7 +/- 1.5 mmHg (p < 0.001). For the whole per-protocol population (n = 197) IOP decreased from 21.0 +/- 3.4 mmHg to 17.4 +/- 2.4 mmHg (p < 0.001). Defining responders as having an IOP decrease > 2.0 mmHg or >or= 5 mmHg at week 12, the responder rate was respectively 62.9% or 31% for the total study population; 86.5% or 54.1% when travoprost was added to the established therapy; 54.5% or 24.0% if latanoprost was switched to travoprost; and 90.9% or 36.4% for those who switched from beta-blockers. CONCLUSION: Travoprost provided a clinically and statistically significant IOP decrease in uncontrolled COAG patients whose self-reported compliance to their previous topical medication was optimal. Our results suggest that the IOP reduction found after switching to travoprost is not explainable by improved compliance due to the clinical study situation.
Keywords: Glaucoma -- Drug Therapy; Intraocular Pressure -- Drug Effects; Travoprost -- Therapeutic Use; Adolescence; Adult; Aged; Aged, 80 and Over; Analysis of Covariance; Clinical Trials; Confidence Intervals; Data Analysis Software; Female; Funding Source; Human; Hungary; Male; Middle Age; Pearson's Correlation Coefficient

The Effect of Health Education Video on Ocular Massage After Trabeculectomy. - Liu Hua; Lv Yingjuan; Zhao Jingshu; Cao Wei (CIN: Computers, Informatics, Nursing, 2014)
The aim of this study was to investigate the effect of different ocular massage health education methods on ocular massage in glaucoma patients after trabeculectomy. Eighty-six patients with glaucoma after trabeculectomy (86 eyes) were randomly divided into two health education groups. One group was a watch video group (43 patients, 43 eyes), while the other was an orally taught health education group (43 patients, 43 eyes). Patients were followed up for 1 week, 1 month, and 3,6, and 12 months after discharge. Records of the patient responses after health education, compliance of patients with follow-up, and intraocular pressure were determined. Measurements included intraocular pressure and differences between the watch video and orally taught health education groups. The differences between the watch video group and orally taught health education group were not statistically significant at 1 week and 1 month, while the differences were statistically significant at 3, 6, and 12 months. The results indicated that health education videos can enable glaucoma patients to have a better mastery of ocular massage after trabeculectomy. According to the needs of patients, health education video use produced good results and should be promoted.
Keywords: Trabeculectomy; Health Education -- Methods; Eye Care; Massage -- Methods; Motion Pictures; Glaucoma -- Therapy; Human; Intraocular Pressure; After Care; Patient Compliance; Descriptive Statistics; Self Care; Male; Female; Middle Age; Aged; Chi Square Test; Data Analysis Software; T-Tests; Funding Source

Clinical. Preventing complications in people who wear contact lenses. - Martin S; Barr O (British Journal of Nursing, 1997)
The number of contact lens wearers has steadily increased over the past 10 years. Convenience, efficiency and availability of different types of lenses have made them popular. The rise in the use of contact lenses has increased the number of people at risk of contact lens-related complications. Studies have highlighted the consequences of poor contact lens care. Acanthamoeba keratitis is one of the most devastating complications of contact lens wear and can be avoided by adhering to the recommended contact lens regimen. This article reviews the literature on the complications of contact lens wear and stresses the need to educate the wearer. It examines the nurse's role in relation to health promotion and the basic principles for successful long-term contact lens wear. This information is relevant to all nurses caring for people with contact lenses and will be of particular interest to the nurse who wears contact lenses.
Keywords: Contact Lenses -- Adverse Effects; Eye Care; Eye Manifestations -- Prevention and Control; Patient Compliance; Ophthalmic Solutions; Health Education

Systematic review of the appropriateness of eye care delivery in eye care practice. - Ho, Kam Chun; Stapleton, Fiona; Wiles, Louise; Hibbert, Peter; Alkhawajah, Sally; White, Andrew; Jalbert, Isabelle (BMC Health Services Research, 2019)
Background: Health care systems are continually being reformed, however care improvement and intervention effectiveness are often assumed, not measured. This paper aimed to review findings from published studies about the appropriateness of eye care delivery, using existing published evidence and/or experts' practice and to describe the methods used to measure appropriateness of eye care.Methods: A systematic search was conducted using Medline, Embase and CINAHL (2006 to September 2016). Studies reporting the processes of eye care delivery against existing published evidence and/or experts' practice were selected. Data was extracted from published reports and the methodological quality using a modified critical appraisal tool. The primary outcomes were percentage of appropriateness of eye care delivery. This study was registered with PROSPERO, reference CRD42016049974.Results: Fifty-seven studies were included. Most studies assessed glaucoma and diabetic retinopathy and the overall methodological quality for most studies was moderate. The ranges of appropriateness of care delivery were 2-100% for glaucoma, 0-100% for diabetic retinopathy and 0-100% for other miscellaneous conditions. Published studies assessed a single ocular condition, a sample from a single centre or a single domain of care, but no study has attempted to measure the overall appropriateness of eye care delivery.Conclusions: These findings indicated a wide range of appropriateness of eye care delivery, for glaucoma and diabetic eye care. Future research would benefit from a comprehensive approach where appropriateness of eye care is measured across multiple conditions with a single methodology, to guide priorities within eye care delivery and monitor quality improvement initiatives.
Keywords: Quality of Health Care; Eye Diseases -- Therapy; Health Care Delivery -- Standards; Office Visits -- Statistics and Numerical Data; Health Care Delivery -- Statistics and Numerical Data; Female; Male; Human; Program Evaluation; Meta Analysis; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

Cost of illness of glaucoma: a critical and systematic review. - Fiscella RG; Lee J; Davis EJ; Walt J; Fiscella, Richard G; Lee, Jeff; Davis, Elizabeth J H; Walt, John (PharmacoEconomics, 2009)
Cost-of-illness studies determine the total financial burden of a disease by considering direct and indirect costs, including medication, diagnostics and surgery. Studies of resource use and costs associated with primary open-angle glaucoma have used varying methodologies. Most have focused on consumption of healthcare resources at various stages of disease to anticipate costs. The direct costs associated with the disease often continue to increase as glaucoma progresses from the earliest to most advanced stages. Determinations of the costs associated with glaucoma progression and prevention should also incorporate the chance of patient non-compliance with treatment. Since glaucoma severity most often correlates with increased costs, minimizing or halting visual field loss and increasing patient treatment compliance may all contribute to a reduction in the overall economic burden of glaucoma.
Keywords: Glaucoma -- Drug Therapy; Glaucoma -- Economics; Canada; Economic Aspects of Illness; Europe; United States; Human

Investigación original. Encuesta nacional de ceguera y deficiencia visual evitables en Honduras. - Alvarado, Doris; Rivera, Belinda; Lagos, Luis; Ochoa, Mayra; Starkman, Ivette; Castillo, Mariela; Flores, Eduardo; Lansingh, Van C.; Limburg, Hans; Silva, Juan Carlos (Revista Panamericana de Salud Pública, 2014)
Objectives. To determine the prevalence of blindness and visual impairment in Honduras, its causes and the response by the health services to growing demand. Methods. A cross-sectional population study was conducted between June and December 2013 using the standard methodology of the Rapid Assessment of Avoidable Blindness. A random sample survey was done in 63 clusters of 50 individuals aged ≥ 50, representative of the country as a whole. Visual acuity (VA) was assessed using a Snellen eye chart, and the condition of the lens and posterior pole was examined by direct ophthalmoscopy. Cataract surgical coverage was calculated and an assessment made of its quality, the causes of VA < 20/60 and the barriers to accessing surgical treatment. Results. A total of 2 999 people were examined (95.2% of the forecast total). Blindness prevalence was 1.9% (confidence interval of 95%: 1.4-2.4%) and 82.2% of these cases were avoidable. The main causes of blindness were unoperated cataracts (59.2%) and glaucoma (21.1%). Uncorrected refraction error was the main cause of severe (19.7%) and moderate (58.6%) visual impairment. Cataract surgical coverage was 75.2%. 62.5% of the eyes operated for cataracts achieved a VA > 20/60 with available correction. The main barriers against cataract surgery were cost (27.7%) and the lack of availability or difficulty of geographical access to the treatment (24.6%). Conclusions. The prevalence of blindness and visual impairment in Honduras is similar to that of other Latin American countries. 67% of cases of blindness could be resolved by improving the response capacity of the ophthalmological services, especially of cataract surgery, improving optician services and incorporating eye care in primary health care.
Keywords: Blindness -- Epidemiology -- Honduras; Vision Disorders -- Epidemiology -- Honduras; Prevalence; Human; Honduras; Descriptive Statistics; Cross Sectional Studies; Random Sample; Visual Acuity; Blindness -- Etiology -- Honduras; Cataract -- Complications -- Honduras; Glaucoma -- Complications -- Honduras; Cataract Extraction -- Economics -- Honduras; Health Services Accessibility; Male; Female

Investigación original. Prevalencia y causas de ceguera en Perú: encuesta nacional. - Campos, Betty; Cerrate, Amelia; Montjoy, Enrique; Dulanto Gomero, Víctor; Gonzales, César; Tecse, Aldo; Pariamachi, Andrés; Lansingh, Van C.; Dulanto Reinoso, Víctor; Minaya Barba, Jean; Carlos Silva, Juan; Limburg, Hans (Revista Panamericana de Salud Pública, 2014)
Objective. To estimate the prevalence of blindness and visual impairment among adults in Peru and to determine their causes, to evaluate the coverage and quality of the cataract surgical services and to investigate the barriers that inhibit access to these services. Methods. A cross-sectional population study with two-stage random cluster sampling of individuals of ≥ 50 years old, representative of the entire country, using the standard methodology of the Rapid Assessment of Avoidable Blindness. Visual acuity was assessed and the condition of the lens and posterior pole examined by direct ophthalmoscopy. Cataract surgical coverage was calculated. Its quality, as well as the causes of visual acuity < 20/60 and the barriers to accessing surgical treatment were assessed. Results. A total of 4 849 people were examined. Blindness prevalence was 2.0% (confidence interval of 95%: 1.5-2.5%). The main causes of blindness were cataract (58.0%), glaucoma (13.7%) and age-related macular degeneration (11.5%). Uncorrected refraction errors were the principal cause of moderate visual impairment (67.2%). Cataract surgical coverage was 66.9%. 60.5% of the eyes operated for cataracts achieved a visual acuity ≥ 20/60 with available correction. The main barriers to cataract surgery were the high cost (25.9%) and people being unaware that treatment was possible (23.8%). Conclusions. The prevalence of blindness and visual impairment in Peru is similar to that of other Latin American countries. Given the low cataract surgical coverage and the aging of the population, access to the services could be improved by increasing the population education on eye health and the response capacity of the ophthalmological and cataract surgical services, and by reducing the costs of the latter.
Keywords: Blindness -- Epidemiology -- Peru; Prevalence; Blindness -- Etiology -- Peru; Vision Disorders -- Epidemiology -- Peru; Human; Cross Sectional Studies; Descriptive Statistics; Peru; Confidence Intervals; Middle Age; Visual Acuity; Cataract Extraction -- Economics -- Peru; Male; Female; Aged; Aged, 80 and Over

Clinical efficacy analysis of Ahmed glaucoma valve implantation in neovascular glaucoma and influencing factors: A STROBE-compliant article. - He, Ye; Tian, Ying; Song, Weitao; Su, Ting; Jiang, Haibo; Xia, Xiaobo (Medicine, 2017)
This study aimed to evaluate the efficacy of Ahmed glaucoma valve (AGV) implantation in treating neovascular glaucoma (NVG) and to analyze the factors influencing the surgical success rate.This is a retrospective review of 40 eyes of 40 NVG patients who underwent AGV implantation at Xiangya Hospital of Central South University, China, between January 2014 and December 2016. Pre- and postoperative intraocular pressure (IOP), visual acuity, surgical success rate, medications, and complications were observed. Surgical success criteria were defined as IOP ≤21 and >6 mm Hg with or without additional medications. Kaplan-Meier survival curves and Multivariate cox regression analysis were used to examine success rates and risk factors for surgical outcomes.The mean follow-up period was 8.88 ± 3.12 months (range: 3-17). IOP declined at each visit postoperatively and it was statistically significant (P < .001). An average of 3.55 ± 0.86 drugs was applied preoperatively, while an average of 0.64 ± 0.90 drugs was used postoperatively, with the difference being of statistical significance (P < .05). The complete surgical success rate of 3, 6, and 12 months after the operation was 85%, 75%, and 65%, respectively. Meanwhile, the qualified success rate of 3, 6, and 12 months after the operation was 85%, 80%, and 77.5%, respectively. The multivariate cox regression analysis showed that age (hazard ratio: 3.717, 7.246; 95% confidence interval: 1.149-12.048, 1.349-38.461; P = .028, .021) was influencing factors for complete success rate and qualified success rate among all NVG patients. Gender, previous operation history, primary disease, and preoperative IOP were found to be not significant.AGV implantation is an effective and safe surgical method to treat NVG. Age is an important factor influencing the surgical success rate.
Keywords: Prostheses and Implants; Glaucoma -- Surgery; Female; Intraocular Pressure; Male; Adult; Sex Factors; Middle Age; Retrospective Design; Postoperative Complications -- Epidemiology; Visual Acuity; Aged; China; Age Factors; Kaplan-Meier Estimator; Scales

Improving care of chronic open angle glaucoma. - Watkinson S (Nursing Older People, 2010)
This article focuses on the nursing care and management of older people with chronic open angle glaucoma (COAG). It provides an overview of the condition, its pathogenesis, clinical features, aetiology, diagnosis and approaches to care and treatment. Patient education and promotion of adherence to medical therapy are paramount in establishing the confidence and independence required for the long-term self-management of COAG because the majority of older people with this condition are based in the community.
Keywords: Glaucoma -- Nursing; Gerontologic Nursing; Nursing Practice; Glaucoma; Chronic Disease; Glaucoma -- Etiology; Glaucoma -- Symptoms; Glaucoma -- Diagnosis; Glaucoma -- Drug Therapy; Glaucoma -- Physiopathology; Eye -- Anatomy and Histology; Glaucoma -- Complications; Intraocular Pressure -- Drug Effects; Glaucoma -- Risk Factors; Middle Age; Glaucoma -- Surgery; Medication Compliance; Laser Therapy; Patient Education; Aged; Ophthalmic Solutions -- Administration and Dosage; Timolol -- Administration and Dosage; Carbonic Anhydrase Inhibitors -- Administration and Dosage; Prostaglandins, Synthetic -- Administration and Dosage; Quality of Life; Glaucoma -- Psychosocial Factors; Nursing Assessment; Support, Psychosocial; Support Groups; Information Resources; World Wide Web; United Kingdom

Glaucoma expert patient programme and ocular hypotensive treatment. - Amro R; Cox CL; Waddington K; Siriwardena D (British Journal of Nursing, 2010)
Expert patient programmes (EPPs) are becoming an increasingly important aspect of chronic disease management, resulting in improved health outcomes for patients. Patients with chronic open angle glaucoma (COAG) require lifelong therapy. However, to date, no EPPs have been designed specifically for patients with chronic eye conditions like COAG. This article describes the development and implementation of the Glaucoma Expert Patient Programme (GEPP), a glaucoma-specific educational self-management programme which aims to improve glaucoma patients' knowledge, self-management skills, expectations and adherence to treatment. A review of theoretical frameworks and models which underpin the design, use and conduct of EPPs was undertaken, and the GEPP was designed based on the model by Kate Lorig (2003). The result is an educational programme which offers COAG patients a different perspective on their condition and supports them with knowledge, skills and strategies to better manage their condition on a daily basis.
Keywords: Glaucoma -- Therapy; Program Development; Self Care; Patient Education; Motivation; Health Behavior; Medication Compliance; Models, Theoretical; Health Knowledge; National Health Programs; Ophthalmic Solutions; Motivational Interviewing; Role Playing

CONTINUING PROFESSIONAL DEVELOPMENT. Management of patients with chronic open angle glaucoma. - Stainsby, Helen (Nursing Standard, 2016)
Glaucoma refers to a group of conditions that can cause sight loss as a result of damage to the optic nerve head. Glaucoma can affect a person's life in many ways. Healthcare professionals have an important role in educating and supporting patients to manage their condition and adhere to their glaucoma management regimens. Since patients with glaucoma may have additional health conditions, healthcare professionals should have an understanding of glaucoma and the importance of continuing treatment, so that they can facilitate care effectively.
Keywords: Glaucoma -- Therapy; Glaucoma -- Complications; Quality of Life; Patient Compliance; Glaucoma -- Drug Therapy; Patient Education; Glaucoma -- Epidemiology; Glaucoma -- Physiopathology; Ocular Hypertension; Glaucoma -- Classification; Glaucoma, Angle-Closure; Glaucoma -- Risk Factors; Glaucoma -- Symptoms; Glaucoma -- Surgery; Laser Therapy; Ophthalmic Solutions -- Therapeutic Use; Adult; Female; Blindness -- Risk Factors; Professional Development; Education, Continuing (Credit)

MANAGE NON-COMPLIANCE. - Appold, Karen (Optometric Management, 2017)
Keywords: Glaucoma -- Drug Therapy; Intraocular Pressure; Patient Compliance; Vision Disorders -- Risk Factors; Economic Aspects of Illness; Financial Support; Patient Education; After Care; Mindfulness; Physician-Patient Relations

Criteria for choosing clinically effective glaucoma treatment: a discussion panel consensus. - Thygesen J; Burk R; Carassa R; Crichton A; Goñi FJ; Menage M; Miglior S; Montgomery D; Nordmann J; Roberts T; Singh K (Current Therapeutic Research, 2007)
Background:In the clinical management of patients at risk for or diagnosed with primary open-angle glaucoma (POAG), the aim of medical treatment is to reduce intraocular pressure (IOP) and then maintain it over time at a level that preserves both the structure and function of the optic nerve.Objective:The objective of this report was to establish a consensus on the criteria that should be used to determine the characteristics of IOP-lowering medication.Methods:Discussion was held among a panel of 12 physicians considered to be experts in glaucoma to develop a consensus on the criteria used by them to determine the characteristics of the IOP-lowering medication chosen for initial monotherapy and adjunctive treatment of ocular hypertension (OHT) or POAG. Consensus development combined available evidence and the impressions of these physicians regarding the clinical effectiveness of IOP-lowering medication for OHT and POAG. Once the panel identified the criteria, the order of priority and the relative importance of these criteria were then established in the setting of 3 risk categories (low, medium, and high) for a patient to experience significant visual disability from glaucoma over their expected life span.Results:The panel identified 5 criteria to determine the characteristics of IOP-lowering medication for OHT and POAG: IOP-lowering effect, systemic adverse events (AEs), ocular tolerability, compliance/administration, and cost of treatment. IOP-lowering effect was consistently ranked as the highest priority and cost as the lowest. The priority of compliance/administration did not vary by clinical situation. Systemic AEs and ocular tolerability were ranked as higher priorities in initial monotherapy than in adjunctive treatment and ranked lower as the risk for visual disability increased. The priority given to the criteria used to determine clinical effectiveness varied both with the risk for functional vision loss from glaucoma and whether initial monotherapy or adjunctive treatment was being considered.Conclusion:Glaucoma treatment should be assessed with regard to the need not only to lower IOP but also to minimize systemic and ocular AEs, promote patient compliance, and minimize cost. The order of priority and relative importance given to these treatment criteria will vary as part of individualizing patient care.
Keywords: Decision Making, Clinical; Drug Therapy -- Standards; Glaucoma -- Drug Therapy; Delphi Technique; Drug Therapy, Combination -- Standards; Funding Source; Intraocular Pressure; Netherlands; Physician Attitudes; Human

Encuesta de ceguera y deficiencia visual evitable en Panamá. - López, Maritza; Brea, Ileana; Yee, Rita; Yi, Rodolfo; Carles, Víctor; Broce, Alberto; Limburg, Hans; Silva, Juan Carlos (Revista Panamericana de Salud Pública, 2014)
Objective. Determine prevalence of blindness and visual impairment in adults aged ≥ 50 years in Panama, identify their main causes, and characterize eye health services. Methods. Cross-sectional population study using standard Rapid Assessment of Avoidable Blindness methodology. Fifty people aged ≥ 50 years were selected from each of 84 clusters chosen through representative random sampling of the entire country . Visual acuity was assessed using a Snellen chart; lens and posterior pole status were assessed by direct ophthalmoscopy. Cataract surgery coverage was calculated and its quality assessed, along with causes of visual acuity < 20/60 and barriers to access to surgical treatment. Results. A total of 4 125 people were examined (98.2% of the calculated sample). Age- and sex-adjusted prevalence of blindness was 3.0% (95% CI: 2.3-3.6). The main cause of blindness was cataract (66.4%), followed by glaucoma (10.2%). Cataract (69.2%) was the main cause of severe visual impairment and uncorrected refractive errors were the main cause of moderate visual impairment (60.7%). Surgical cataract coverage in individuals was 76.3%. Of all eyes operated for cataract, 58.0% achieved visual acuity ≤ 20/60 with available correction. Conclusions. Prevalence of blindness in Panama is in line with average prevalence found in other countries of the Region. This problem can be reduced, since 76.2% of cases of blindness and 85.0% of cases of severe visual impairment result from avoidable causes.
Keywords: Blindness -- Epidemiology -- Panama; Eye Care -- Evaluation; Health Services -- Evaluation; Vision Disorders -- Epidemiology -- Panama; Panama; Blindness -- Etiology; Cross Sectional Studies; Random Sample; Confidence Intervals; Vision Disorders -- Etiology; Middle Age; Aged; Aged, 80 and Over; Human

Microinvasive medical therapies needed for glaucoma patients. - Lindstrom, Richard L. (Ocular Surgery News, 2018)
Keywords: Glaucoma -- Surgery; Eye Surgery -- Methods; Invasive Procedures; Glaucoma -- Diagnosis; Latanoprost -- Therapeutic Use; Latanoprost -- Economics; Dorzolamide Hydrochloride -- Economics; Ophthalmic Solutions -- Economics; Treatment Outcomes; Conjunctiva -- Pathology; Patient Compliance

STOP Glaucoma in Sub Saharan Africa: enhancing awareness, detection, management, and capacity for glaucoma care. - Damji, Karim F.; Nazarali, Samir; Giorgis, Abeba; Kiage, Dan; Marco, Sheila; Philippin, Heiko; Daniel, Neema; Amin, Samreen (Expert Review of Ophthalmology, 2017)
Introduction: Glaucoma in Sub Saharan Africa (SSA) poses a daunting challenge. Communities are often unaware of the serious implications of glaucoma and are faced with limited access to specialists, making early detection and management difficult. For those who have been diagnosed, socioeconomic barriers limit access to treatment. Since 2006, we have been involved in an innovative program we term ‘STOP Glaucoma in SSA’. The four main pillars of this program include building capacity, enhancing awareness, and improving glaucoma detection and management. The aim of this initiative is to train the first generation of highly qualified glaucoma subspecialist leaders and to develop centers of excellence for glaucoma care throughout SSA that are interconnected. Our ultimate aim is to reduce the burden of blindness from glaucoma in SSA. Areas covered: Our review addresses background context, provides learning from the first decade of this program, and offers solutions to help tackle the scourge of glaucoma in SSA. Expert commentary: Research in ocular genetics, primary congenital glaucoma, ophthalmic nanomedicine, and cost effective therapies will continue to improve our understanding of glaucoma as well as access to quality care for glaucoma in SSA.
Keywords: Glaucoma -- Prevention and Control -- Africa South of the Sahara; Program Development; Glaucoma -- Diagnosis; Glaucoma -- Therapy; Ophthalmologists -- Education; Glaucoma -- Education; Africa South of the Sahara; Blindness -- Prevention and Control; Glaucoma -- Psychosocial Factors; Community Health Services; Health Promotion; Quality of Health Care

Sustained benefit found in fixed-drug combination: Netarsudil/latanoprost duo safe, provided greater IOP lowering than either of components. - Guttman Krader, Cheryl; Brubaker, Jacob (Ophthalmology Times, 2018)
The article presents a discussion of the findings of a clinical trial on the safety and efficacy of fixed-dose combination (FDC) of netarsudil and latanoprost for glaucoma or ocular hypertension, adapted from a poster presented by Dr. Jacob Brubaker during the 2018 meeting of the American Glaucoma Society meeting. Topics covered include the intraocular pressure (IOP)-lowering effect of the FDC, dosing that would improve compliance, and the common adverse event reported by the study.
Keywords: Intraocular Pressure; Drug Combinations; Ophthalmic Solutions -- Administration and Dosage; Glaucoma -- Drug Therapy; Ocular Hypertension -- Drug Therapy

Pharmacotherapy compliance in patients with ocular hypertension or primary open-angle glaucoma. - Traverso CE; Walt JG; Stern LS; Dolgitser M (Journal of Ocular Pharmacology & Therapeutics, 2009)
Keywords: Antihypertensive Agents -- Therapeutic Use; Carbonic Anhydrase Inhibitors -- Therapeutic Use; Glaucoma -- Drug Therapy; Ocular Hypertension -- Drug Therapy; Patient Compliance; Aged; Aged, 80 and Over; Female; Glaucoma -- Epidemiology; Male; Ocular Hypertension -- Epidemiology; Prospective Studies; Retrospective Design; Human

Barriers to adherence with glaucoma medications: a qualitative research study. - Lacey J; Cate H; Broadway DC (Eye, 2009)
Keywords: Antihypertensive Agents -- Therapeutic Use; Glaucoma -- Drug Therapy; Attitude to Health; Medication Compliance; Aged; Blindness -- Prevention and Control; Female; Focus Groups; Human; Male; Middle Age; Motivation; Qualitative Studies; Questionnaires

Intraocular pressure regulation: findings of pulse-dependent trabecular meshwork motion lead to unifying concepts of intraocular pressure homeostasis. - Johnstone, Murray A (Journal of Ocular Pharmacology & Therapeutics, 2014)
Intraocular pressure (IOP) is the only treatable risk factor in glaucoma, one of the world's leading causes of blindness. Mechanisms that maintain IOP within a normal range have been poorly understood in contrast to intrinsic mechanisms that regulate systemic blood pressure. Vessel walls experience continuous pulse-induced cyclic pressure and flow. Pressure-dependent wall stress and flow-dependent shear stress provide sensory signals that initiate mechanotransduction responses. The responses optimize vessel wall elasticity, compliance and lumen size, providing a feedback loop to maintain intrinsic pressure homeostasis. Aqueous humor is part of a vascular circulatory loop, being secreted into the anterior chamber of the eye from the vasculature, then returning to the vasculature by passing through the trabecular meshwork (TM), a uniquely modified vessel wall interposed between the anterior chamber and a vascular sinus called Schlemm's canal (SC). Since pressure in circulatory loops elsewhere is modulated by cyclic stresses, one might predict similar pressure modulation in the aqueous outflow system. Recent laboratory evidence in fact demonstrates that cyclic IOP changes alter aqueous outflow while increasing cellularity and contractility of TM cells. Cyclic changes also lead to alterations in gene expression, changes in cytoskeletal networks and modulation of signal transduction. A new technology, phase-based optical coherence tomography, demonstrates in vivo pulse-dependent TM motion like that elsewhere in the vasculature. Recognition of pulse-dependent TM motion provides a linkage to well-characterized mechanisms that provide pressure homeostasis in the systemic vasculature. The linkage may permit unifying concepts of pressure control and provide new insights into IOP homeostatic mechanisms.
Keywords: Glaucoma -- Pathology; Intraocular Pressure -- Physiology; Anterior Eye Segment -- Pathology; Anterior Chamber -- Physiology; Aqueous Humor -- Physiology; Homeostasis; Signal Transduction; Risk Factors; Tomography, Optical Coherence -- Methods; Anterior Eye Segment -- Physiology

The effects of prostaglandin analogues on the blood aqueous barrier and corneal thickness of phakic patients with primary open-angle glaucoma and ocular hypertension. - Arcieri ES; Pierre Filho PT; Wakamatsu TH; Costa VP (Eye, 2008)
Keywords: Antihypertensive Agents -- Pharmacodynamics; Ocular Hypertension -- Physiopathology; Prostaglandins, Synthetic -- Pharmacodynamics; Uvea -- Drug Effects; Adult; Aged; Amides -- Adverse Effects; Amides -- Pharmacodynamics; Antihypertensive Agents -- Adverse Effects; Aqueous Humor -- Drug Effects; Clinical Trials; Epidemiological Research; Female; Glaucoma -- Drug Therapy; Glaucoma -- Pathology; Glaucoma -- Physiopathology; Intraocular Pressure -- Drug Effects; Male; Middle Age; Ocular Hypertension -- Drug Therapy; Ocular Hypertension -- Pathology; Prostaglandins, Synthetic -- Adverse Effects; Prostaglandins, Synthetic -- Analogs and Derivatives; Human

Correlation of visual function with health-related quality of life in glaucoma patients. - Lin J; Yang M (Journal of Evaluation in Clinical Practice, 2010)
Objectives The purpose of this study was to assess visual impairment and quality of life (QOL), the relationship between visual function and health-related and vision-related QOL, and to identify factors significantly impacting QOL for glaucoma patients. Methods One-on-one interviews of 280 glaucoma patients at a regional hospital in Taiwan from 1 April 2005 to 30 September 2005. Data collected included demographics, clinical examinations and treatment status. QOL data collected utilized the Chinese (Taiwanese) version of the Medical Outcomes Study Short-Form 36 Health Survey (SF-36) and the National Eye Institute Visual Function-25 (NEIVFQ-25). Results The majority of study participants had open-angle glaucoma (54.3%) and were classified as moderate stage (33.6%). The higher the health-related QOL scores for both questionnaires, the fewer difficulties experienced by the patients. Moderate correlation was found between the SF-36 and NEIVFQ-25 subscales and visual function. Significant predicting factors for the SF-36 were gender, age, employment status, presence of systemic disease, better-eye visual acuity and better-eye mean defect. For the NEIVFQ-25, these were general vision, near and distance activities, colour vision and peripheral vision scores. Conclusions A combination of demographic data, clinical examination and QOL questionnaires may help clinicians better ascertain the impact of disease severity on glaucoma patients' QOL. This information may help in patient education, treatment compliance and selection of treatment options.
Keywords: Glaucoma -- Psychosocial Factors; Glaucoma -- Symptoms; Quality of Life; Adult; Aged; Coefficient Alpha; Convenience Sample; Data Analysis Software; Descriptive Statistics; Female; Glaucoma -- Classification; Health Status; Hospitals; Human; Interviews; Male; Middle Age; One-Way Analysis of Variance; Pearson's Correlation Coefficient; Questionnaires; Severity of Illness; Severity of Illness Indices; Short Form-36 Health Survey (SF-36); Step-Wise Multiple Regression; Taiwan; Vision

National survey of blindness and avoidable visual impairment in Honduras. - Alvarado, Doris; Rivera, Belinda; Lagos, Luis; Ochoa, Mayra; Starkman, Ivette; Castillo, Mariela; Flores, Eduardo; Lansingh, Van C.; Limburg, Hans; Silva, Juan Carlos (Revista Panamericana de Salud Pública, 2014)
Objectives. To determine the prevalence of blindness and visual impairment in Honduras, its causes and the response by the health services to growing demand. Methods. A cross-sectional population study was conducted between June and December 2013 using the standard methodology of the Rapid Assessment of Avoidable Blindness. A random sample survey was done in 63 clusters of 50 individuals aged ≥ 50, representative of the country as a whole. Visual acuity (VA) was assessed using a Snellen eye chart, and the condition of the lens and posterior pole was examined by direct ophthalmoscopy. Cataract surgical coverage was calculated and an assessment made of its quality, the causes of VA < 20/60 and the barriers to accessing surgical treatment. Results. A total of 2 999 people were examined (95.2% of the forecast total). Blindness prevalence was 1.9% (confidence interval of 95%: 1.4-2.4%) and 82.2% of these cases were avoidable. The main causes of blindness were unoperated cataracts (59.2%) and glaucoma (21.1%). Uncorrected refraction error was the main cause of severe (19.7%) and moderate (58.6%) visual impairment. Cataract surgical coverage was 75.2%. 62.5% of the eyes operated for cataracts achieved a VA > 20/60 with available correction. The main barriers against cataract surgery were cost (27.7%) and the lack of availability or difficulty of geographical access to the treatment (24.6%). Conclusions. The prevalence of blindness and visual impairment in Honduras is similar to that of other Latin American countries. 67% of cases of blindness could be resolved by improving the response capacity of the ophthalmological services, especially of cataract surgery, improving optician services and incorporating eye care in primary health care.
Keywords: Blindness -- Epidemiology -- Honduras; Vision Disorders -- Epidemiology -- Honduras; Prevalence; Human; Honduras; Descriptive Statistics; Cross Sectional Studies; Random Sample; Visual Acuity; Blindness -- Etiology -- Honduras; Cataract -- Complications -- Honduras; Glaucoma -- Complications -- Honduras; Cataract Extraction -- Economics -- Honduras; Health Services Accessibility; Male; Female

National survey on the prevalence and causes of blindness in Peru. - Campos, Betty; Cerrate, Amelia; Montjoy, Enrique; Dulanto Gomero, Víctor; Gonzales, César; Tecse, Aldo; Pariamachi, Andrés; Lansingh, Van C.; Dulanto Reinoso, Víctor; Minaya Barba, Jean; Carlos Silva, Juan; Limburg, Hans (Revista Panamericana de Salud Pública, 2014)
Objective. To estimate the prevalence of blindness and visual impairment among adults in Peru and to determine their causes, to evaluate the coverage and quality of the cataract surgical services and to investigate the barriers that inhibit access to these services. Methods. A cross-sectional population study with two-stage random cluster sampling of individuals of ≥ 50 years old, representative of the entire country, using the standard methodology of the Rapid Assessment of Avoidable Blindness. Visual acuity was assessed and the condition of the lens and posterior pole examined by direct ophthalmoscopy. Cataract surgical coverage was calculated. Its quality, as well as the causes of visual acuity < 20/60 and the barriers to accessing surgical treatment were assessed. Results. A total of 4 849 people were examined. Blindness prevalence was 2.0% (confidence interval of 95%: 1.5-2.5%). The main causes of blindness were cataract (58.0%), glaucoma (13.7%) and age-related macular degeneration (11.5%). Uncorrected refraction errors were the principal cause of moderate visual impairment (67.2%). Cataract surgical coverage was 66.9%. 60.5% of the eyes operated for cataracts achieved a visual acuity ≥ 20/60 with available correction. The main barriers to cataract surgery were the high cost (25.9%) and people being unaware that treatment was possible (23.8%). Conclusions. The prevalence of blindness and visual impairment in Peru is similar to that of other Latin American countries. Given the low cataract surgical coverage and the aging of the population, access to the services could be improved by increasing the population education on eye health and the response capacity of the ophthalmological and cataract surgical services, and by reducing the costs of the latter.
Keywords: Blindness -- Epidemiology -- Peru; Prevalence; Blindness -- Etiology -- Peru; Vision Disorders -- Epidemiology -- Peru; Human; Cross Sectional Studies; Descriptive Statistics; Peru; Confidence Intervals; Middle Age; Visual Acuity; Cataract Extraction -- Economics -- Peru; Male; Female; Aged; Aged, 80 and Over

Setting goals effective way to start glaucoma support organizations. - Boyle EL (Ocular Surgery News, 2009)
Glaucoma support groups play an important role in the community, assisting in diagnosis and patient adherence.
Keywords: Glaucoma -- Psychosocial Factors; Goals and Objectives; Support Groups; Health Knowledge; Patient Education; Support, Psychosocial

Silicone oil-induced secondary glaucoma: a case study. - Orticio LP (Insight: The Journal of the American Society of Ophthalmic Registered Nurses, 2000)
Silicone oil intraocular tamponade is a widely accepted procedure in the management of complex retinal detachments caused by proliferative diabetic vitreoretinopathy. Silicone oil has a high surface tension that mechanically limits fibrovascular reproliferation resulting in successful retinal reattachments. However, postoperative secondary glaucoma is a relatively frequent complication that may require intensive nursing management focused at intraocular pressure monitoring, positioning compliance, pain management, fluid and electrolyte balance, and glucose control. This article presents the postoperative clinical course of a 51-year-old man with diabetes and recurrent proliferative diabetic vitreoretinopathy who developed secondary glaucoma after silicone oil injection with a dramatic rise in intraocular pressure on the first postoperative day. Nursing management concurrent with medical and surgical management is discussed and the necessary nursing plan of care is identified.
Keywords: Diabetic Retinopathy -- Surgery; Silicones -- Adverse Effects; Glaucoma -- Etiology; Eye Surgery -- Adverse Effects; Case Studies; Middle Age; Male; Oils -- Adverse Effects; Ophthalmic Nursing; Postoperative Complications

Effect of selected antihypertensives, antidiabetics, statins and diuretics on adjunctive medical treatment of glaucoma: a population based study. - Iskedjian M; Walker JH; Desjardins O; Robin AL; Covert DW; Bergamini MV; Einarson TR (Current Medical Research & Opinion, 2009)
BACKGROUND: The prevalence of open angle glaucoma increases with age, with many patients also receiving medications for non-ocular systemic diseases. Little is known about how systemic medications impact on the need for adjunctive therapy with prostaglandin analogues (PGA). OBJECTIVES: To evaluate whether systemic medications for hypertension, cholesterol, or glucose influence the need for adjunctive intraocular pressure (IOP) lowering medications in patients using PGAs. METHODS: Pharmaceutical records from the Québec prescription database provided a sample of patients receiving prescriptions for bimatoprost, latanoprost, or travoprost, from which subjects receiving > or =1 prescription for antihypertensives, antidiabetics. diuretics, and statins were identified. Chi-square tests compared proportions using PGAs to those using PGAs + adjunctive therapy, based on the use or non-use of systemic medications; a logistic regression was performed post hoc to adjust for gender and age. RESULTS: Of the 8548 evaluated patients (all using PGAs); 2934 (34.3%) took none of the studied systemic drugs. For the 5614 patients taking systemic medications, significantly fewer (p < 0.001) required an additional IOP lowering medication if taking a systemic antihypertensive medication. The use of a statin or a diabetic medication, alone or in combination, in addition to a PGA, made no significant difference in the need for adjunct glaucoma therapy. Individual drugs associated with significantly less utilization of adjunctive glaucoma medications were calcium-channel blockers, angiotensin-converting enzyme (ACE), and combination antihypertensive therapies. DISCUSSION: A profound association between systemic antihypertensive use and a reduced need for adjunct topical IOP lowering medications in patients using the same prostaglandin analogue for at least one year was found. LIMITATIONS: The use of a prescription claims database without patient compliance or patient outcomes may not reflect actual patient medication use. In addition, these findings may not be applicable to all patients initiating prostaglandin analogues. CONCLUSIONS: In this real-world population-based evaluation, a significant association exists between using systemic antihypertensive medications and reduced use of adjunctive IOP lowering therapies. These results confirm findings from previous studies suggesting an IOP lowering effect with systemic agents or some synergy with topical therapies.
Keywords: Antihypertensive Agents -- Pharmacodynamics; Antilipemic Agents -- Pharmacodynamics; Diuretics -- Pharmacodynamics; Glaucoma -- Drug Therapy; Hypoglycemic Agents -- Pharmacodynamics; Prostaglandins, Synthetic -- Therapeutic Use; Adult; Aged; Aged, 80 and Over; Antihypertensive Agents -- Administration and Dosage; Antihypertensive Agents -- Therapeutic Use; Antilipemic Agents -- Administration and Dosage; Antilipemic Agents -- Therapeutic Use; Databases; Diuretics -- Administration and Dosage; Diuretics -- Therapeutic Use; Female; Hypoglycemic Agents -- Administration and Dosage; Hypoglycemic Agents -- Therapeutic Use; Male; Middle Age; Quebec; Young Adult

Effect of health education on patients' beliefs about glaucoma and compliance. - Rendell J (Insight: The Journal of the American Society of Ophthalmic Registered Nurses, 2000)
A pretest-posttest control group experimental design (n = 100) was used to determine the effectiveness of an interactive patient education program compared with a didactic approach for persons with primary open angle glaucoma at a major specialist eye hospital in England. This study used a questionnaire with a knowledge test to explore patients' glaucoma knowledge, a series of vignettes to explore understanding of compliance and health motivation, and health locus of control scales to assess the effect of these variables. The improved posttest results (P = .000) suggest that patients benefit from education programs and that the ophthalmic nurse is an effective patient teacher. The interactive program had no statistically significant difference from the didactic presentation. Other types of interactive programs may prove to be more beneficial.
Keywords: Patient Education; Glaucoma -- Education; Patient Compliance; Pretest-Posttest Design; Experimental Studies; Comparative Studies; Lecture; Consumer Participation; Questionnaires; Descriptive Statistics; T-Tests; Chi Square Test; Health Beliefs; Teaching Methods; Human

Expert question and answer session. (Johns Hopkins Advanced Studies in Ophthalmology, 2008)
Keywords: Contact Lenses; Eye Care; Contact Lenses -- Utilization; Hydrogen Peroxide; Keratitis -- Prevention and Control; Ophthalmic Solutions; Patient Compliance; Silicones

When complications arise. - Joslin C (Johns Hopkins Advanced Studies in Ophthalmology, 2008)
Keywords: Contact Lenses -- Adverse Effects; Keratitis; Cornea -- Pathology; Eye Care; Hygiene; Keratitis -- Prevention and Control; Keratitis -- Risk Factors; Keratitis -- Therapy; Ophthalmic Solutions; Patient Compliance; Patient Education; Silicones; Staining and Labeling

Survey on avoidable blindness and visual impairment in Panama. - López, Maritza; Brea, Ileana; Yee, Rita; Yi, Rodolfo; Carles, Víctor; Broce, Alberto; Limburg, Hans; Silva, Juan Carlos (Revista Panamericana de Salud Pública, 2014)
Objective. Determine prevalence of blindness and visual impairment in adults aged ≥ 50 years in Panama, identify their main causes, and characterize eye health services. Methods. Cross-sectional population study using standard Rapid Assessment of Avoidable Blindness methodology. Fifty people aged ≥ 50 years were selected from each of 84 clusters chosen through representative random sampling of the entire country . Visual acuity was assessed using a Snellen chart; lens and posterior pole status were assessed by direct ophthalmoscopy. Cataract surgery coverage was calculated and its quality assessed, along with causes of visual acuity < 20/60 and barriers to access to surgical treatment. Results. A total of 4 125 people were examined (98.2% of the calculated sample). Age- and sex-adjusted prevalence of blindness was 3.0% (95% CI: 2.3-3.6). The main cause of blindness was cataract (66.4%), followed by glaucoma (10.2%). Cataract (69.2%) was the main cause of severe visual impairment and uncorrected refractive errors were the main cause of moderate visual impairment (60.7%). Surgical cataract coverage in individuals was 76.3%. Of all eyes operated for cataract, 58.0% achieved visual acuity ≤ 20/60 with available correction. Conclusions. Prevalence of blindness in Panama is in line with average prevalence found in other countries of the Region. This problem can be reduced, since 76.2% of cases of blindness and 85.0% of cases of severe visual impairment result from avoidable causes.
Keywords: Blindness -- Epidemiology -- Panama; Eye Care -- Evaluation; Health Services -- Evaluation; Vision Disorders -- Epidemiology -- Panama; Panama; Blindness -- Etiology; Cross Sectional Studies; Random Sample; Confidence Intervals; Vision Disorders -- Etiology; Middle Age; Aged; Aged, 80 and Over; Human

Glaucoma medication cost, compliance pose challenges in India. - Boyle, Erin L.; Mullin, David W. (Ocular Surgery News, 2010)
The article reports on the challenges posed by glaucoma medication cost and compliance in India, which was discussed by physician G. Chandra Sekhar during the Asia-Pacific Academy of Ophthalmology Congress held in Beijing, China on September 16-20, 2010.
Keywords: Glaucoma -- Drug Therapy -- India; Prostaglandins -- Economics; Costs and Cost Analysis; Medication Compliance; Patient Attitudes; India

Patterns and rate of adherence to glaucoma therapy using an electronic dosing aid. - Ajit RR; Fenerty CH; Henson DB (Eye, 2010)
Keywords: Antihypertensive Agents -- Administration and Dosage; Prostaglandins, Synthetic -- Analogs and Derivatives; Drug Monitoring -- Equipment and Supplies; Glaucoma -- Drug Therapy; Medication Compliance; Adult; Aged; Aged, 80 and Over; Prostaglandins, Synthetic -- Administration and Dosage; Prospective Studies; Female; Human; Male; Middle Age; Ophthalmic Solutions -- Administration and Dosage

Patient profile and management in advanced glaucoma. - Wallace EJ; Paterson H; Miller S; Sinclair A; Sanders R; Hinds A (British Journal of Visual Impairment, 2008)
Purpose: to study patient characteristics and management profile in advanced glaucoma. Method: A retrospective study of 87 case notes of patients registered blind due to glaucoma, and cross-sectional interview of 29 patients. Results: advanced glaucoma at presentation was documented in 43 cases (49%). Insufficient optometry assessment was significantly associated with advanced disease (p = 0.0339). Normal tension glaucoma patients were significantly more likely to present with advanced disease compared to other types of glaucoma (p = 0.0034). Poor compliance with medication was significantly higher in those with hearing loss (p = 0.0168). Patients with advanced field defect at presentation and those with poor compliance had significantly higher social deprivation scores compared to others on the blind register (p < 0.0001). Nine (10%) patients had partial registration before full registration and 29 (33%) patients had late registration. Of the 29 patients interviewed, 20 (69%) did not demonstrate basic knowledge regarding their disease or its management; nor had they received written information on glaucoma or instructions on drop technique. Conclusion: Special care pathways are required in advanced glaucoma taking into account co-existent morbidity, disease education and compliance. Copyright © 2008 SAGE Publications
Keywords: Glaucoma -- Therapy; Adult; Aged; Aged, 80 and Over; Blindness; Comorbidity; Cross Sectional Studies; Diagnostic Errors; Glaucoma -- Complications; Health Knowledge; Hearing Disorders -- Complications; Interviews; Intraocular Pressure; Medication Compliance; Middle Age; Prospective Studies; Questionnaires; Registries, Disease; Retrospective Design; Scales; Scotland; Human

Imagining eye care in India (2018 Lalit Prakash Agarwal lecture). - Das, Taraprasad; Panda, Lapam (Indian Journal of Ophthalmology, 2018)
India has done well in eye care delivery by recognizing visual impairment and blindness as a major medical challenge. Major contributions have come from ophthalmologists (mass cataract surgery in the early 1900s; major participation of non-government organizations), policy makers (National Program for Control of Blindness and Visual Impairment 1976; systematic development under the World Bank assisted India Cataract Project, 1995-2002), and the industry (manufacturing of affordable surgical instruments and medicines). Although the country could boast of higher cataract surgical coverage and near-total elimination of trachoma, there is increasing prevalence of diabetic retinopathy and undetected glaucoma. India is in the crossroad of adherence to old successful models of service delivery and adoption of new innovative methods of teaching and training, manpower development and skill-based training, relevant medical research and product development. In the absence of these new approaches, the initial gains in eye care could not be furthered in India. A new approach, that will combine the best of the "old" tradition of empathy and the "new" technology of analytics, is required to imagine the future of eye care in India.
Keywords: Diagnostic Imaging -- Methods; Eye Diseases -- Diagnosis; Diagnosis, Eye -- Trends; Diagnostic Imaging -- Trends; India

Allograft reaction after latanoprost use following penetrating keratoplasty for corneal scarring due to herpatic keratitis. - Bozkurt, Tahir Kansu; Bahadir, Ayse Ebru; Kutan, Selda Aktay; Acar, Suphi (Turkish Journal of Ophthalmology / Turk Oftalmoloji Dergisi, 2012)
A 27-year-old male patient with a corneal scar secondary to herpetic keraritis in the right eye underwent penetrating keraroplasty (PK). At the 14th month of follow-up, latanoprost was started to treat high intraocular pressure which was refracrory to trearment. On the 15th day of latanoprost use, allograft reaction (AR) developed. Insufficient clinical response despite incensive immunosuppressive therapy made us consider the possibility of recurrent herpetic kerarouveitis secondary co steroid trearment. The dramatic reduction in the number of keratic precipitates with oral valacydovir trearment confirmed this diagnosis. The graft remained dear 3 monchs after the AR trearment. Inflammation in eyes that had undergone PK jeopardizes the graft success by disrupting the immune privilege of anrerior chamber. Considering the effects of prostaglandin analogues on blood-aqueous barrier, laranoprost use might have been related co allograft reaction in this case. Another remarkable characteristics of this case was the herpes simplex virus (HSV) reactivation secondary co AR therapy. For this reason, oral acyclovir prophylaxis together with AR rherapy would improve grafi: success in cases with HSV history.
Keywords: Corneal Diseases -- Surgery; Corneal Transplantation -- Methods; Glaucoma -- Prevention and Control; Graft Rejection; Keratitis, Herpetic -- Complications; Latanoprost -- Adverse Effects; Adult; Male

Glaucoma. Consider a 'Stop- Go' Approach. - LIFFERTH, AUSTIN (Optometric Management, 2020)
Keywords: Glaucoma -- Drug Therapy; Patient Centered Care; Life Expectancy; Decision Making, Clinical; Patient Compliance; Health Knowledge; Anxiety; Prescriptions, Drug; Adverse Drug Event -- Risk Factors; Risk Assessment

Tafluprost for the Reduction of Interocular Pressure in Open Angle Glaucoma and Ocular Hypertension. - Schultz, Clyde (Ophthalmology & Eye Diseases, 2011)
Keywords: Prostaglandins -- Therapeutic Use; Ocular Hypertension -- Drug Therapy; Glaucoma -- Drug Therapy; Intraocular Pressure -- Drug Effects; Prostaglandins -- Pharmacodynamics; Models, Biological; Treatment Outcomes; Patient Compliance

Intravitreal bevacizumab for neovascular glaucoma. - Vasudev D; Blair MP; Galasso J; Kapur R; Vajaranant T; Vasudev, Deepta; Blair, Michael P; Galasso, John; Kapur, Rashmi; Vajaranant, Thasarat (Journal of Ocular Pharmacology & Therapeutics, 2009)
Purpose: To report 6-month and 1 year outcomes of eyes treated for neovascular glaucoma (NVG) with intravitreal bevacizumab injection and panretinal laser (PRP) compared to those receiving PRP alone.Design: retrospective, consecutive case series.Methods: Charts of patients with NVG from retinal ischemia and at least 6 months of follow-up were reviewed. Patients were treated with one injection of 1.25 mg intravitreal bevacizumab followed by PRP or with PRP alone. The primary outcome was the long-term angle anatomy. Secondary measures included intraocular pressure (IOP), visual acuity, patient compliance, and control of systemic diseases.Results: Fourteen eyes of 12 patients treated with bevacizumab and PRP and 15 eyes of 11 patients treated with PRP alone were included in the study. Mean sectors of open angle at baseline was 1.31 in the bevacizumab group and 1.47 in the retinal ablation group (P = 0.73). Mean sectors of open angle was 2.14 and 1.18 in the bevacizumab and retinal ablation groups, respectively (P < 0.05) at 6-month follow-up, and 2.27 and 1.18, respectively (P < 0.05) at 1-year follow-up. Mean baseline IOP was 32.3 mmHg (+/-14.8) in the bevacizumab group and 31.8 mmHg (+/-13) in the PRP group (P = 0.75). At 6-month follow-up, the mean IOP was 18.28 mmHg (+/-10) in the bevacizumab group and 23.33 mmHg (+/-14.6) in the PRP group (P = 0.05), and 19.12 mmHg (+/-6.8) and 26.2 mmHg (+/-18) (P = 0.1), respectively at 1-year follow-up. Nineteen patients were judged to be noncompliant, 10 had uncontrolled diabetes and 7 had uncontrolled hypertension.Conclusions: This study documents better long-term preservation of open angle and IOP control in eyes receiving bevacizumab along with PRP. We stress that NVG is still associated with poor visual acuity outcomes.
Keywords: Angiogenesis Inhibitors -- Therapeutic Use; Antibodies, Monoclonal -- Therapeutic Use; Glaucoma -- Drug Therapy; Angiogenesis Inhibitors -- Administration and Dosage; Antibodies, Monoclonal -- Administration and Dosage; Combined Modality Therapy; Glaucoma -- Surgery; Human; Injections; Intraocular Pressure; Laser Therapy -- Methods; Middle Age; Patient Compliance; Retina -- Surgery; Retrospective Design; Visual Acuity; Vitreous Body

Estimated first-year costs of prostaglandin analogs with/without adjunctive therapy for glaucoma management: a United States perspective. - Schmier JK; Covert DW; Robin AL; Schmier, Jordana K; Covert, David W; Robin, Alan L (Current Medical Research & Opinion, 2007)
Objective: To evaluate costs associated with prostaglandin analogs among newly-diagnosed glaucoma patients in a managed-care population.Research Design and Methods: A cost minimization model compared annual costs for patients initiating therapy with one of the three prostaglandin analogs (bimatoprost, latanoprost, travoprost). The study cohort was identified from pharmacy claims and eligibility files of patients who met study inclusion criteria. Annual costs were estimated for patients initiating therapy with each prostaglandin based on treatment patterns and medication use over the year. Costs for outpatient physician visits and medications were estimated from standard sources.Results: A total of 4444 patients met study criteria: 674 received travoprost, 729 received bimatoprost, and 3041 received latanoprost. More than 80% stayed on monotherapy for 1 year (82.9% of travoprost patients, 82.8% of bimatoprost patients, and 80.5% of latanoprost patients). Of those who required adjunctive therapy, the average number of days until starting adjunctive therapy was 130 days for travoprost patients, 94 days for bimatoprost patients, and 104 days for latanoprost patients. Average annual costs were $1198, $1290, and $1217 for patients treated with travoprost, bimatoprost, and latanoprost, respectively.Conclusions: The use of adjunctive therapy in glaucoma is an important driver of glaucoma management costs. This study demonstrates that the longer duration of monotherapy and the likelihood to use single rather than combination adjunctive agents contribute to lower annual costs among patients starting on travoprost compared with the other available prostaglandin analogs. Study limitations include the lack of clinical indicators in the study database; further, results may not be generalizable to patients who discontinue prostaglandin analogs or to the population of patients with glaucoma as a whole. Future studies with clinical and compliance indicators would further identify distinctions among treatment regimens.
Keywords: Glaucoma -- Drug Therapy; Health Care Costs; Prostaglandins -- Economics; Insurance; Prospective Studies; Prostaglandins -- Therapeutic Use; United States; Human

Glaucoma. - GUPTA, DIVAKAR; CHEN, PHILIP P. (American Family Physician, 2016)
Glaucoma is a set of irreversible, progressive optic neuropathies that can lead to severe visual field loss and blindness. The two most common forms of glaucoma, primary open-angle glaucoma and primary angle-closure glaucoma, affect more than 2 million Americans and are increasing in prevalence. Many patients with glaucoma are asymptomatic and do not know they have the disease. Risk factors for primary open-angle glaucoma include older age, black race, Hispanic origin, family history of glaucoma, and diabetes mellitus. Risk factors for primary angle-closure glaucoma include older age, Asian descent, and female sex. Advanced disease at initial presentation and treatment nonadherence put patients with glaucoma at risk of disease progression to blindness. The U.S. Preventive Services Task Force has concluded that the evidence is insufficient to assess the potential benefits and harms of screening for glaucoma in the primary care setting. Regular eye examinations for adults are recommended by the American Academy of Ophthalmology, with the interval depending on patient age and risk factors. Diagnosis of glaucoma requires careful optic nerve evaluation and functional studies assessing a patient's visual field. The goal of treatment with eye drops, laser therapy, or surgery is to slow visual field loss by lowering intraocular pressure. Family physicians can contribute to lowering morbidity from glaucoma through early identification of high-risk patients and by emphasizing treatment adherence in patients with glaucoma.
Keywords: Cholinergic Agonists -- Therapeutic Use; Adrenergic Beta-Antagonists -- Therapeutic Use; Prostaglandins, Synthetic -- Therapeutic Use; Glaucoma -- Drug Therapy; Glaucoma, Angle-Closure -- Drug Therapy; Adrenergic Alpha-Agonists -- Therapeutic Use; Carbonic Anhydrase Inhibitors -- Therapeutic Use; Health Screening; Age Factors; Practice Guidelines; Glaucoma -- Physiopathology; Glaucoma -- Epidemiology; Risk Factors; Glaucoma, Angle-Closure -- Physiopathology; Diabetes Mellitus -- Epidemiology; Risk Assessment; Glaucoma, Angle-Closure -- Epidemiology; Ethnic Groups -- Statistics and Numerical Data; Glaucoma, Angle-Closure -- Diagnosis; Glaucoma -- Diagnosis; Clinical Assessment Tools

Topical glaucoma medication: risks and treatment. - Diggory P; Spratt A; Ogunbowale L (Geriatric Medicine, 2006)
There are more treatment options for reducing intraocular pressure in glaucoma than ever before and currently ophthalmologists are combining eye drops to achieve lower therapeutic targets. However, often they forget the systemic side effects - and physicians are unaware of them. Drs Paul Diggory, Alexander Spratt and Lola Ogunbowale review the risks of, and barriers to, effective glaucoma therapy.
Keywords: Glaucoma -- Drug Therapy; Ophthalmic Solutions -- Therapeutic Use; Adrenergic Beta-Antagonists -- Adverse Effects; Adrenergic Beta-Antagonists -- Therapeutic Use; Aged; Medication Compliance; Ophthalmic Solutions -- Adverse Effects; Pilocarpine -- Adverse Effects; Pilocarpine -- Therapeutic Use; Prostaglandins -- Analogs and Derivatives

The British Asian community eye study: outline of results on the prevalence of eye disease in British Asians with origins from the Indian subcontinent. - Rauf, Abdul; Malik, Rizwan; Bunce, Catey; Wormald, Richard (Indian Journal of Ophthalmology, 2013)
Background: Asians from the Indian Subcontinent form the largest ethnic minority in the United Kingdom. Data on the prevalence of visually-impairing eye conditions in this population are vital for planning eye health care services. Materials and Methods: This survey was based in the two London boroughs with the largest Asian populations. Subjects originating from the Indian Subcontinent were identified from GP practice records. All subjects were asked about demographic details and were given a full ophthalmological examination. The severity of cataract, glaucoma, diabetic retinopathy, and age-related maculopathy was recorded. Blindness was defined as logMAR visual acuity of 0.99 (Snellen equivalence 20/200 in the better eye) or worse, 'low vision' was defined as Snellen equivalence of 20/63 or worse (logMAR 0.5 or higher), and visual impairment was defined as visual acuity worse than 20/40. Results: The median age was 56 years. Two hundred and eighty four subjects did not attend for eye examination. Of the 922 examined, 128 subjects (13.9%) were 'visually impaired,' 39 (4.2%) had 'low vision,' and 6 (0.7%) were bilaterally blind. The overall prevalence of cataract, open-angle glaucoma, age-related macular degeneration, and diabetic retinopathy were 77%, 1.0%, 8.7%, and 8.8%, respectively. Conclusion: Visual impairment rates amongst Asians seem to be similar to Caucasian populations in the UK. The prevalence of cataract and diabetic retinopathy is higher, while the risk of ARMD and OAG are comparable. In view of the high cataract prevalence, a more detailed assessment of the visual profile and factors limiting healthcare accessibility in this community are needed.
Keywords: Asians; White Persons; Eye Diseases -- Ethnology; Population Surveillance; Adult; Demography; Aged; Cross Sectional Studies; Female; Great Britain; Human; India -- Ethnology; Male; Middle Age; Prevalence

Attitudes of physicians, patients, and village health workers toward glaucoma and diabetic retinopathy in rural china: a focus group study. - Yan X; Liu T; Gruber L; He M; Congdon N (Archives of Ophthalmology, 2012)
Keywords: Community Health Workers -- Psychosocial Factors; Diabetic Retinopathy -- Psychosocial Factors; Glaucoma -- Psychosocial Factors; Attitude to Health; Patients -- Psychosocial Factors; Physicians -- Psychosocial Factors; Rural Population; Adult; Aged; Attitude of Health Personnel; China; Diabetic Retinopathy -- Diagnosis; Diabetic Retinopathy -- Therapy; Female; Focus Groups; Glaucoma -- Diagnosis; Glaucoma -- Therapy; Human; Male; Middle Age; Patient Attitudes; Patient Compliance

The effect of appointment rescheduling on monitoring interval and patient attendance in the glaucoma outpatient clinic. - Tatham A; Murdoch I (Eye, 2012)
Keywords: Appointments and Schedules; Continuity of Patient Care -- Statistics and Numerical Data; Glaucoma -- Physiopathology; Intraocular Pressure -- Physiology; Outpatient Service; Patient Compliance; Chronic Disease; Female; Human; Male; Monitoring, Physiologic; Practice Patterns; Practice Guidelines; Retrospective Design; Time Factors

Racial differences in primary open-angle glaucoma: more than meets the eye. - Racette, Lyne; Ozobu Jr., Lawrence (Expert Review of Ophthalmology, 2013)
The authors reflect on the prevalence of primary open-angle glaucoma (POAG) among people of African descent compared with people of European descent. They state that POAG could result in irreversible blindness which appears 10 years earlier in people of African descent. They relate that health disparities was defined by the U.S. National Institutes of Health (NIH) as the difference in the incidence, prevalence, mortality, and burden of diseases among specific population groups in the U.S.
Keywords: Glaucoma -- Ethnology; Health Status Disparities; Black Persons; Patient Protection and Affordable Care Act; Health Services Accessibility; Social Justice

Persistence with medications in glaucoma management, hypertension, and dyslipidemia. - Velentgas P; Sheffield R; Nordstrom BL; Johnson E; Do T; Mentor SM; Seeger JD (Journal of Pharmacy Technology, 2007)
OBJECTIVE: To summarize pharmacy database studies of persistence with ocular hypotensives and review the literature of adherence with 2 additional classes of medication--antihypertensives and antihyperlipidemics-- comparing methods used to analyze adherence in the 3 treatment areas. DATA SOURCES: A search of MEDLINE (1990DS2004) was conducted, using search terms designed to identify English-language articles describing adherence or persistence with any of the 3 drug classes of interest.. STUDY SELECTION AND DATA EXTRACTION: All articles identified through MEDLINE were reviewed and screened for use of an automated pharmacy database as an information source, quantitative results provided, and follow-up duration of at least 90 days. Details of methods used to estimate adherence or persistence and estimates of persistence with ocular hypotensive therapy, antihypertensives, and lipid-lowering agents were extracted. DATA SYNTHESIS: All studies describing the use of ocular hypotensives, and the majority of studies in the other treatment areas, identified inception cohorts of drug initiators. Use of survival analysis techniques to analyze adherence to medication therapy was less common in the hypertension and hyperlipidemia treatment adherence literature than in literature about glaucoma. In the treatment of hypertension, use of angiotensin II receptor antagonists or angiotensin-converting enzyme inhibitors was associated with higher levels of adherence. Statins in treatment of hyperlipidemia and topical prostaglandins as ocular hypotensive medications were also associated with higher levels of adherence. CONCLUSIONS: Findings regarding the relative superiority of specific drug classes were consistent within each therapeutic area, with less consistency in identifying other predictors of adherence. Increased use of survival analysis in future studies of persistence might improve comparability of results across studies.
Keywords: Glaucoma -- Drug Therapy; Hyperlipidemia -- Drug Therapy; Hypertension -- Drug Therapy; Medication Compliance; Canada; Databases; Education, Continuing (Credit); Europe; Funding Source; Medical Practice, Evidence-Based; Medline; Time Factors; Treatment Duration; United States; World Health Organization; World Wide Web; Human

WHY DAILY DISPOSABLES. - KADING, DAVID L.; FISCHER, ANDREW (Contact Lens Spectrum, 2019)
Keywords: Disposable Equipment; Contact Lenses; Patient Compliance; Comfort; Eye Care; Risk Assessment; Decision Making, Clinical; Ophthalmologists -- Psychosocial Factors; Contact Lens Fitting; Silicones; Keratitis -- Risk Factors; Sterilization and Disinfection; Patient Satisfaction; Diffusion of Innovation; Health Care Industry

An evaluation of the effectiveness of a nurse-led glaucoma monitoring clinic. - Sheppard J; Warner J; Kelley K (Ophthalmic Nursing: International Journal of Ophthalmic Nursing, 2003)
Background/aim: In 1999 a quarter of patients attending the general ophthalmic clinics at a local hospital had a diagnosis of chronic glaucoma. This led to the development of a nurse-led clinic specifically to manage patients with chronic glaucoma, the glaucoma monitoring clinic (GMC). The aim of this study was to compare the GMC clinic with the general ophthalmic clinics on patient understanding of the symptoms, management and treatment of glaucoma, patient adherence to eye drops and patient satisfaction. Method: The study was a randomised controlled trial with two groups. Participants were recruited from the general ophthalmic clinics and randomly allocated to return to either the GMC or a general ophthalmic clinic for their next outpatients appointment. The participants were followed up with a telephone questionnaire 12 weeks later. Results: At the 12 week follow-up, significantly fewer participants attending the GMC reported specific problems in adherence to their eye drops and significantly higher satisfaction with treatment, compared to those attending the general ophthalmic clinic. No differences were found between the two groups on the level of adherence to eye drops, or on the understanding of the symptoms, management and treatment of glaucoma. Conclusion: Nurse-led clinics can be as effective as general ophthalmic clinics in caring for patients with long term chronic stable glaucoma. To further support the advice and information patients are given in the GMC we aim to develop a personalised patient booklet that patients can refer to at home and update at every appointment.
Keywords: Glaucoma -- Therapy; Nurse-Managed Centers; Nursing Outcomes -- Evaluation; Analysis of Covariance; Clinical Trials; Convenience Sample; Descriptive Statistics; Evaluation Research; Health Knowledge -- Evaluation; Medication Compliance -- Evaluation; Nursing Assessment; Patient Education; Patient Satisfaction -- Evaluation; Physicians; Power Analysis; Questionnaires; Sample Size; Self Report; Telephone; Human

The experiences of adolescents with juvenile idiopathic arthritis with transition programs to adult services: A systematic review protocol. - Mäkeläinen, Paula; Korhonen, Anne (JBI Database of Systematic Reviews & Implementation Reports, 2013)
Background Juvenile idiopathic arthritis (JIA) is a heterogeneous group of diseases characterized by arthritis of unknown origin. JIA is a clinical diagnosis made at age less than 16 years with continued arthritis of at least six weeks duration and with other identifiable causes of arthritis excluded. JIA is the most common chronic rheumatic disease in children being a significant cause of short- and long-term disability1. Throughout the world, the incidence of JIA ranges from 1 to 22 new cases per 100,000 population per year with a prevalence of 8-400 per 100,000. In Europe and North America, the most common subtype of JIA is oligoarthritis (symptoms in one joint) accounting for approximately 50% of patients with JIA. In the Western world, girls are affected more often than boys2. In Finland, 0,2 % of children under 16 years suffer from JIA. The prognosis of the disease has been improved due to advances in medication 3, 4 however despite these advances, disease-related complications and side-effects of the medication occur. For example eye inflammation (uveitis) which may cause cataracts, glaucoma or blindness regardless of careful screening and care, occurs in approximately 10 % of all cases. Adverse side-effects of medication relate mainly to the use of corticosteroids, which may inhibit growth5. In addition, unsuccessful transition to adult services can result in poor health indicators and loss to follow-up 6. Adolescence as a phase of life interposes between childhood and adulthood from 12 to 22 years consisting of specific physical, psychological and social development7. Adolescents with chronic illness have special health needs, which are not fully recognized in health care 8. Chronic illness may impede the maturation process 9 10, which may impact on physiological, psychological and social maturation and vice versa 9, 11, 12. Understanding the complexity of the mutual relationship of the natural maturation process and chronic illness is urgent for health care professionals to contribute to both normal development task achievements and overall well-being for adolescents with JIA 13. For example, the experience of chronic illness can make adolescents feel uncomfortable in their body, or it disrupts their normal life10. Transition and transition care has been a research interest for over twenty years and practical models for organizing transition care have been developed 14. Regardless of this, local protocols and principles vary 15 often causing fragmented and disease-centered care 16. Transition has been recognized as a key component of care 6. The Transition phase is defined as the multifaceted, active phase in care aimed at ensuring a seamless transition from pediatric to adult services for an adolescent patient 17, 18, 19. It is a continuous process lasting from early preparation, which starts in pediatrics until the young person with a chronic illness is settled in the adult services 18, 20. Transition of care from pediatric to adult healthcare services is important and should be an age and developmentally appropriate process 21. The Transition phase is challenging for all involved, including the patient, the family and health care organizations in terms of fostering adherence so as to avoid long-term complications 21, 22. Success during this phase will be manifested as the patient's adherence to self-care as well as gaining positive skills in order to cope with challenges in adulthood, such as integration of physical, psychological and social maturation23. Different transition programs have been developed 6 19 24 with their goal being to ensure uninterrupted, comprehensive health care, which should be evaluated from the point of view of adolescents 24. According to the literature, the transition programs should be holistic by nature and address clinical, psychosocial and educational aspects as well as being simultaneously flexible and developmentally appropriate. It should not focus only on the young person but als It is important to collect all available evidence around JIA patients' experiences with transition programs and adherence levels to care as these may be disturbed by intrinsic factors of adolescents and also by organizational inabilities to meet the needs of this population. This systematic review will collect and synthesize findings of all relevant studies in order to give valuable information for health care professionals to develop transition programs based on evidence for JIA patients. A preliminary search for existing systematic reviews was performed in the following databases: Cochrane Library of systematic reviews, JBI Library of systematic reviews, Medline, CINAHL, and PROSPERO. No existing systematic reviews are available on the topic. Existing systematic reviews are focused on health outcomes of transitional programs among children with chronic illness, mental illness or disability 6.
Keywords: Transitional Programs; Family Health; Arthritis, Juvenile Rheumatoid; Chronic Disease; Systematic Review; Cochrane Library; Medline; CINAHL Database

Gold standard medical therapy for glaucoma: defining the criteria identifying measures for an evidence-based analysis. - Obstbaum SA; Cioffi GA; Krieglstein GK; Fennerty MB; Alm A; Araie M; Carassa RG; Greve EL; Hitchings RA; Kaufman PL; Kitazawa Y; Pongpun PR; et al. (Clinical Therapeutics, 2004)
BACKGROUND: Over the past decade, several new medical therapies have become available for the treatment of primary open-angle glaucoma (POAG). A systematic evidence-based approach for identifying an optimal therapeutic agent is lacking. OBJECTIVES: The aims of this review were to critically evaluate published treatment recommendations for POAG and, based on a systematic review of the literature, to develop criteria that would define a 'gold standard' medical therapy that reflects new treatment advances and established therapeutic goals. METHODS: A MEDLINE search spanning the years 1966 to 2002 and using the search terms gold standard, drug of choice, agent of choice, benchmark, ophthalmology, eye, and glaucoma was conducted and the results reviewed by a panel of 15 experts in the field of glaucoma. Published treatment recommendations for POAG were discussed. Criteria, anchored to medical evidence, for distinguishing a standard of medical therapy for POAG were defined. RESULTS: The terms connoting a gold standard therapy were found in only 258 of approximately 368,000 ophthalmology-related citations and 53 of almost 23,000 glaucoma citations, validating the need to define therapeutic standards. The lack of recommendations for the use of new classes of ocular hypotensive agents was acknowledged. Criteria identified to evaluate intraocular pressure (IOP)-lowering agents as gold standards included the following: efficacy in reducing IOP consistently over a 24-hour period to a level that will preserve the visual field and protect the optic nerve without inducing tachyphylaxis and tolerance, paucity of local and systemic adverse effects, promotion of patient compliance, and applicability in diverse patient populations. CONCLUSIONS: These criteria should be employed as measures for evidence-based analyses to evaluate available and future IOP-lowering medical therapies for POAG. The conceptual framework presented may be applicable to other therapeutic areas.
Keywords: Glaucoma -- Drug Therapy; Professional Practice, Evidence-Based; Descriptive Statistics; Drug Tolerance; Economics, Pharmaceutical; Medication Compliance; Quality of Life; Human

Novel drug delivery systems will target better glaucoma treatment. - Caceres, Vanessa (Ophthalmology Times, 2016)
The article suggests that until glaucoma drug delivery methods beyond eye drops are developed and made available, clinicians must coach patients on better drop use and teach healthcare payers about the importance of compliance. Topics include drawback of eye drops as well as novel drug delivery systems targeting better glaucoma systems. Also mentioned are a peer-reviewed paper from Singapore on a liposomal-sustained release of latanoprost as well as other delivery systems such as corneal rings.
Keywords: Glaucoma -- Drug Therapy; Drug Delivery Systems; Ophthalmic Solutions; Treatment Outcomes

Patient adherence, drug response keys to selecting glaucoma therapy. - Gagnon L (Ocular Surgery News, 2008)
An expert in the field reviews 'anchor' and 'adjunct' regimens and discusses the right time to switch therapies.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Decision Making, Clinical; Drug Therapy, Combination; Intraocular Pressure -- Drug Effects; Prostaglandins -- Administration and Dosage; Prostaglandins -- Therapeutic Use

Programs to optimize adherence in glaucoma. - Kowing D; Messer D; Slagle S; Wasik A (Optometry -- Journal of the American Optometric Association, 2010)
Keywords: Glaucoma -- Drug Therapy; Patient Compliance; Drug Delivery Systems; Equipment Design; Human; Internet; Ophthalmic Solutions -- Administration and Dosage; Optometry -- Equipment and Supplies; Optometry -- Methods; Patient Education -- Methods; Reminder Systems; Videorecording

Use of fixed-dose combination drugs for the treatment of glaucoma. - Khouri AS; Realini T; Fechtner RD (Drugs & Aging, 2007)
Glaucoma is a leading cause of irreversible visual loss. This potentially blinding disease is a progressive optic neuropathy associated with elevated intraocular pressure (IOP). Initial therapy for glaucoma typically consists of topical medications or laser treatment to lower IOP. Frequently, more than one medication is required to achieve adequate control of IOP. However, more medications means more bottles and greater complexity for the patient. There are several potential benefits of fixed combination medications compared with using the individual components separately. These include a reduction in the total number of drops and preservative instilled per day, cost savings, improved tolerability and compliance and avoiding the washout effect resulting from rapid-sequence instillation of multiple drops. Attempts to develop effective fixed combinations of glaucoma medications date back several decades. In recent years, fixed combinations of commonly paired drugs have been approved by various regulatory bodies in different countries and have gained wide acceptance. Current commercially available, fixed combination drugs include the topical beta-adrenoceptor antagonist timolol 0.5% combined with a prostaglandin, a topical carbonic anhydrase inhibitor or an alpha-adrenoceptor agonist. Although there is no uniformity among registration trial designs, most published literature compares the efficacy of the fixed combination to the individual components and to concomitant use of both components. Various factors inherent to study design such as medication run-in, washout periods and peak and trough effects have to be taken into consideration when analysing the demonstrated efficacy of fixed combinations. Fixed combination treatments offer effective IOP control while reducing the washout effect and exposure to preservatives. They are also convenient. However, fixed combinations also remove the possibility of titrating the individual components both in terms of concentration and timing of administration. In addition, fixed combinations might not always provide the same efficacy as proper use of the individual components. The clinician must make individualised assessments when weighing the convenience of these medications against their limitations for specific patients.
Keywords: Drug Combinations; Glaucoma; Glaucoma -- Drug Therapy; Drug Combinations -- Adverse Effects; Medication Compliance

Four simple rules to ensure more 'good days' at work. - Suter, Donna A. (Ophthalmology Times, 2019)
The article provides tips for how physicians and staff at ophthalmic practices can improve in four steps. Topics mentioned include the importance of proper charting documentation, development of a culture that allows employees to feel appreciated, and the book "Talk is Not Cheap, Saving the High Cost of Misunderstanding at Work and Home," by Beverly Inman-Ebel.
Keywords: Ophthalmology; Rules and Regulations; Physician Attitudes; Leadership; Organizational Culture; Interpersonal Relations; Work Environment; Patient Care; Emotions; Documentation; Office Visits; Diabetic Patients; Glaucoma; Wellness; Professional Boundaries; Leaders -- Psychosocial Factors; Communication; Multidisciplinary Care Team

Challenges of implementing adherence psychology in ophthalmology clinical practice. - Friedman DS (Johns Hopkins Advanced Studies in Ophthalmology, 2008)
Keywords: Ophthalmology; Patient Compliance; Physicians; Glaucoma -- Drug Therapy; Models, Psychological; Patient Education; Physician-Patient Relations

Brinzolamide 1%/timolol 0.5%: safety and efficacy of a new fixed-combination IOP-lowering product for glaucoma. - Januleviciene, Ingrida (Current Medical Research & Opinion, 2010)
OBJECTIVE: To provide a commentary on recent studies with the new IOP-lowering fixed-combination product brinzolamide 1%/timolol 0.5%. METHODS: Medline was searched for brinzolamide/timolol fixed-combination clinical literature (up to May 18, 2010) and the current comprehensive brinzolamide/timolol literature was reviewed. RESULTS: Compared with another carbonic anhydrase inhibitor-containing product, dorzolamide 2%/timolol 0.5%, brinzolamide/timolol has similar IOP-lowering efficacy. Brinzolamide/timolol also produces superior comfort ratings as assessed by patients who have tried both drugs - this may be explained by the more physiologic pH of brinzolamide/timolol. A recent study reported that brinzolamide/timolol was preferred over dorzolamide/timolol at a ratio of nearly 4:1 among those expressing a preference. CONCLUSION: These results demonstrate that brinzolamide/timolol is equally effective and more comfortable than dorzolamide/timolol, a fact that may positively impact patient adherence, leading to an increased likelihood of reaching target IOP goals.
Keywords: Antihypertensive Agents -- Administration and Dosage; Carbonic Anhydrase Inhibitors -- Administration and Dosage; Glaucoma -- Drug Therapy; Intraocular Pressure -- Drug Effects; Sulfonamides -- Administration and Dosage; Sulfur Compounds -- Administration and Dosage; Timolol -- Administration and Dosage; Antihypertensive Agents -- Adverse Effects; Antihypertensive Agents -- Pharmacodynamics; Carbonic Anhydrase Inhibitors -- Adverse Effects; Carbonic Anhydrase Inhibitors -- Pharmacodynamics; Drug Therapy, Combination; Drug Toxicity; Glaucoma -- Physiopathology; Sulfonamides -- Adverse Effects; Sulfonamides -- Pharmacodynamics; Sulfur Compounds -- Adverse Effects; Sulfur Compounds -- Pharmacodynamics; Timolol -- Adverse Effects; Timolol -- Pharmacodynamics; Treatment Outcomes

Adjunctive glaucoma therapy use associated with travoprost, bimatoprost, and latanoprost. - Covert D; Robin AL; Covert, David; Robin, Alan L (Current Medical Research & Opinion, 2006)
Purpose: This study contrasts the utilization of adjunctive medication associated with travoprost, bimatoprost, or latanoprost, as primary glaucoma therapies.Methods: Patients in the Medco Health database who initiated prostaglandin analog therapy on travoprost, bimatoprost or latanoprost between January 1, 2002 and July 31, 2002 were selected if they had no prostaglandin analog use in the prior 6 months. Patients were also required to have 12 months of prostaglandin therapy subsequent to the initial prescription. Data were available through July 31, 2003. The t-test and chi-square were used where appropriate to calculate p-values and assess significant differences.Results: A total of 13 171 benefit-eligible subjects were identified of which 8381 (64%), 2637 (20%), and 2153 (16%) patients were treated with latanoprost, bimatoprost, and travoprost, respectively. There were no significant differences in mean age or gender between the three study groups with the exception that latanoprost patients were statistically older than travoprost patients (69.0 vs. 68.0). This was not considered a clinically meaningful difference. Overall, patients using travoprost or bimatoprost had a significantly lower rate of adjunctive medication use compared to patients starting on latanoprost monotherapy (22.5%, 23.2%, and 30.2 %, respectively). Therefore, for every 14 patients treated with latanoprost instead of travoprost or bimatoprost, one additional patient would be expected to need adjunctive therapy with another agent. The difference between travoprost and bimatoprost patients was not significant.Conclusions: The use of adjunctive medications to control intraocular pressure was significantly higher for latanoprost patients compared to travoprost and bimatoprost patients. This finding should be interpreted in the context that this study was based only on prescription claims data. It is important to simplify ophthalmic medical regimen as it is more cost effective, better for the patient, and minimizes the washout effect from administering two eye medications within 5 min. Decreasing the complexity of the patients' drug regimen may lead to increased adherence to prescribed therapy and a decreased risk of the incidence of blindness.
Keywords: Bimatoprost -- Therapeutic Use; Glaucoma -- Drug Therapy; Latanoprost -- Therapeutic Use; Travoprost -- Therapeutic Use; Aged; Chi Square Test; Confidence Intervals; Data Analysis Software; Descriptive Statistics; Drug Therapy, Combination; Female; Funding Source; Human; Intraocular Pressure -- Drug Effects; Male; T-Tests

Pharmacotherapy and Adherence Issues in Treating Elderly Patients with Glaucoma. - Broadway, David; Cate, Heidi (Drugs & Aging, 2015)
Glaucoma is a leading cause of visual morbidity throughout the world and is an age-related condition, the prevalence of which rises significantly with increasing age. Glaucoma, a condition affecting the optic nerve, has a variety of subtypes with multiple aetiological factors, the most important of which are intraocular pressure (IOP) and increasing age. Treatment by lowering of IOP is the only current method, for which there is evidence, by which the rate of progressive visual deterioration can be slowed or halted. Although there are surgical and laser treatments that are efficacious in lowering IOP, the most common manner in which patients with glaucoma control their IOP is with administration of daily topical ocular hypotensive drugs (eye drops). The variety of topical drugs utilised in the management of glaucoma all have the potential to have adverse effects and/or interactions with concomitant medications, many of which may be used for other age-related conditions. Adherence with appropriate medicines has a major effect on the outcome of medical conditions and this aspect applies to the management of glaucoma. There are certain specific issues that relate to the administration of topical agents, with respect to both adverse effects and adherence. Although many suspect poor adherence in elderly patients with glaucoma, relative to younger patients, adequate evidence for this is lacking. Furthermore, the manner by which adherence issues could be improved remains inadequately understood and poorly addressed. The aims of this article were to review, from a clinical perspective, the medical therapies currently used for glaucoma and discuss adherence issues with respect to the population of patients with glaucoma, who tend to be relatively elderly.
Keywords: Drug Therapy -- Evaluation; Glaucoma -- Drug Therapy; Medication Compliance; Adrenergic Beta-Antagonists -- Classification; Prostaglandins -- Analogs and Derivatives; Carbonic Anhydrase Inhibitors; Adrenergic Alpha-Agonists; Miotics; Drug Interactions; Aged; Intraocular Pressure; Diuretics; Drug Therapy, Combination; Comorbidity; Age Factors

Overcoming Obstacles to Achieve a Great Scleral Lens Fit: What to do when a lump, bump, or hump is in the way. - Jedlicka, Jason (Contact Lens Spectrum, 2017)
Keywords: Sclera; Contact Lens Fitting; Equipment Design; Pterygium; Patient Attitudes; Cornea; Glaucoma -- Surgery; Postoperative Period; Intraocular Pressure; Shunts, Surgical; Conjunctiva; Slit Lamp Examination; Corneal Topography -- Methods; Software; Patient Satisfaction

Increased first-year contact may improve long-term glaucoma medication adherence. - Kahl, Kristie L. (Ocular Surgery News, 2015)
The article reports on a study presented by Dr. Anne Newman-Casey which notes that educational interventions, disease-management strategies and monitoring of glaucoma patients during the first year they take newly prescribed medications may improve adherence in the long term. According to Newman-Casey, people have a hard time continuing with their glaucoma medications. It notes that the study used group-based trajectory modeling to identify patterns of adherence.
Keywords: Medication Compliance; Disease Management; Glaucoma; Reports; Monitoring, Physiologic

Patients' acceptance of a switch from dorzolamide to brinzolamide for the treatment of glaucoma in a clinical practice setting. - Barnebey H; Kwok SY (Clinical Therapeutics, 2000)
BACKGROUND: The first topically active carbonic anhydrase inhibitor, dorzolamide, was developed to circumvent the adverse systemic effects of oral carbonic anhydrase inhibitors. However, its use has been associated with ocular discomfort. OBJECTIVE: The present study examined the acceptability of brinzolamide, as measured by patients' ratings and stated preferences, in patients with glaucoma previously treated with dorzolamide in the clinical practice setting. METHODS: This was a prospective, open-label, noncomparative study conducted shortly after the approval of brinzolamide. Ophthalmologists in private practice in the continental United States were asked to select patients currently using dorzolamide as their sole or combination therapy for glaucoma. Patients underwent a screening assessment in which they were asked to rate their ocular comfort with dorzolamide on a scale from 1 to 6. Brinzolamide was then substituted for dorzolamide, and patients returned for a follow-up visit approximately 1 to 3 months later. At this visit, patients were asked about ocular comfort, their preferred medication, and whether they thought ocular comfort influenced their adherence to treatment. Intraocular pressure (IOP) was measured at both visits. RESULTS: Valid visit dates (ie, both baseline and follow-up dates) were available for 447 of 501 patients from 68 of 73 sites (range, 1-40 patients per site). Because not all measurements were available for all patients at each visit, the sample size varied for each measurement. Demographic data were not available. The switch to brinzolamide resulted in a mean decrease in IOP of approximately 0.8 mm Hg (P < 0.001, paired t test). Sixty-nine percent of patients (274/397) reported an improvement of > or =1 grade in their comfort rating with brinzolamide versus dorzolamide. The mean (+/- SD) improvement in comfort rating was 1.43 +/- 1.48 grades (P < 0.001, Wilcoxon rank sum test). When patients were asked whether their adherence to treatment was affected by the occurrence of burning and stinging, 43% (173/399) answered affirmatively. Fifty-nine percent (251/424) preferred brinzolamide to dorzolamide. At the end of the study, based on patient preference, physician judgment, and other factors, 73% of responding patients (301/410) continued with brinzolamide therapy. CONCLUSIONS: In this study, the switch from dorzolamide to brinzolamide resulted in overall improvements in comfort and ocular hypotensive efficacy. However, studies using a more rigorous randomized, controlled, crossover design are needed to support these observations.
Keywords: Glaucoma -- Drug Therapy; Descriptive Statistics; Intraocular Pressure -- Drug Effects; Paired T-Tests; Prospective Studies; Scales; Wilcoxon Rank Sum Test; Funding Source; Human

The experiences of patients with suspected glaucoma. A qualitative study. - Burns J; Barrett G; Murdoch I (Ophthalmic Nursing: International Journal of Ophthalmic Nursing, 2001)
Well over three-quarters of the total referrals to ophthalmologists for suspected glaucoma are initiated by optometrists. This study was conducted to investigate the experiences of patients with suspected glaucoma. As very little is known about how this group of people is affected, a qualitative study was chosen to investigate this phenomenon.The participants were identified from referrals by their optometrists or general practitioners to Moorfields Glaucoma Clinic at Ealing General Hospital, London, for investigation of suspected glaucoma. In-depth interviews were conducted to collect primary data and a focus group discussion was carried out in order to expand the interview data.The findings revealed that some patients were unaware of the reason for their referral to the eye clinic and even after of the consultation the outcome was not always clear to them. Furthermore, the combination of downplay of the findings by the optometrist and general practitioners, and lack of knowledge of the condition could be the reason for a significant number of non-attendances to the glaucoma clinic. Communication and collaboration among health professionals could lead to better use of resources and more time could be spent with existing and newly diagnosed glaucoma patients.
Keywords: Glaucoma; Patient Attitudes; England; Purposive Sample; Qualitative Studies; Interviews; Audiorecording; Prospective Studies; Thematic Analysis; Patient Attitudes -- Evaluation; Referral and Consultation; Focus Groups; Middle Age; Aged; Male; Female; Funding Source; Human

Big picture of glaucoma care presents with shades of gray. - Meszaros, Liz (Ophthalmology Times, 2014)
The article reports that only 25 to 50 percent of Americans are aware that they are suffering from glaucoma, which was revealed by a large prevalence survey. Topics discussed include the importance of proper treatment to individuals diagnosed with glaucoma, the state of treatment compliance among patients with glaucoma and the importance of disease identification and surveillance in managing glaucoma.
Keywords: Glaucoma -- Therapy; Eye Care; Patient Compliance

Cost of glaucoma treatment in a developing country over a 5-year period. - Lazcano-Gomez, Gabriel; Ramos-Cadena, María de Los Angeles; Torres-Tamayo, Margarita; Hernandez de Oteyza, Alejandra; Turati-Acosta, Mauricio; Jimenez-Román, Jesús (Medicine, 2016)
The aim of the study was to disclose a realistic estimate of primary open-angle glaucoma treatment, follow-up costs, and patients' monthly glaucoma-economic burden in an ophthalmology hospital in Mexico City.Prospective survey of 462 primary open-angle glaucoma patients from 2007 to 2012 was carried out. Costs from visits, glaucoma follow-up studies, laser, and glaucoma surgical procedures were obtained from hospital pricings. Education, employment, and monthly income were interrogated. Total cost was divided into hypotensive treatment cost, nonpharmacologic treatment cost (laser and surgeries), and follow-up studies and consults. Average wholesale price for drugs analyzed was obtained from IMS Health data; monthly cost was calculated using: Monthly cost  = ([average wholesale price/number of drops per eye dropper] × number of daily applications) × 30 days.Patients were classified according to their glaucoma severity, and data were analyzed based on monthly income (average annual exchange rate: 12.85 Mexican pesos = 1 USD).The mean age was 70 ± 10 years, women = 81%, elementary school = 39%, and unemployed = 53%. Low-income group = 266 patients (57%), 146 with mild glaucoma; moderate-income group = 176 patients (38%), 81 with mild glaucoma; high-income group = 20 patients (4.3%), 10 with mild glaucoma. Patients' monthly average economic burden in glaucoma treatment: low-income patients = 61.5%, moderate-income patients = 19.5%, and high-income patients = 7.9%.Glaucoma-economic burden is substantial not only for health systems, but for the family and the patient. Therefore, screening plans for earlier diagnosis, and health policies that lessen the cost of disease management and increase adherence to treatment, and reduce the prevalence of blindness attributed to glaucoma are essential. These would improve quality of life, reduce personal and national expenditure, and help increase national economy.
Keywords: Glaucoma -- Economics; Health Care Costs; Glaucoma -- Therapy; Severity of Illness Indices; Male; Developing Countries; Female; Prospective Studies; Aged; Mexico; Human

Vision insurance, eye care visits, and vision impairment among working-age adults in the United States. - Li, Yi-Jhen; Xirasagar, Sudha; Pumkam, Chaiporn; Krishnaswamy, Malavika; Bennett, Charles L (JAMA Ophthalmology, 2013)
Objectives: To compare rates of eye care visits and vision impairment among working-age adults with vision insurance vs without, among the total sample of Behavioral Risk Factor Surveillance Survey respondents and among a subsample of respondents who had diagnoses of glaucoma, age-related macular degeneration (ARMD), and/or cataract.Design: Using the Behavioral Risk Factor Surveillance Survey 2008 vision module data, we examined the likelihood of an eye care visit within the past year and of self reported visual impairment among 27 152 adults aged 40 to 65 years and among a subset of 3158 persons (11.6%) with glaucoma, ARMD, and/or cataract. Multivariate logistic regression models were used.Results: About 40% of both the study population and the subsample with glaucoma, ARMD, and/or cataract had no vision insurance. Respondents with vision insurance were more likely than those without to have had eye care visits (general population adjusted odds ratio [AOR], 1.90 [95% CI, 1.89-1.90]; glaucoma-ARMD-cataract subsample AOR, 2.15 [95% CI, 2.13-2.17]), to have no difficulty recognizing friends across the street (general population AOR, 1.24 [95% CI, 1.22-1.26]; eye-disease subsample AOR, 1.45 [95% CI, 1.42-1.49]), and to have no difficulty reading printed matter (general population AOR, 1.34 [95% CI, 1.33-1.35]; eye-disease subsample AOR, 1.37 [95% CI, 1.34-1.39]). Respondents from the total sample who had an eye care visit were better able to recognize friends across the street (AOR, 1.07) and had no difficulty reading printed matter (AOR, 1.70), and respondents from the eye-disease subsample who had an eye care visit also were better able to recognize friends across the street (AOR, 1.71) and had no difficulty reading printed matter (AOR, 1.45).Conclusions: Lack of vision insurance impedes eye care utilization, which, in turn, may irrevocably affect vision. Vision insurance for preventive eye care should cease to be a separate insurance benefit and should be mandatory in all health plans.
Keywords: Health Services -- Utilization; Insurance Coverage -- Statistics and Numerical Data; Office Visits -- Statistics and Numerical Data; Ophthalmology -- Statistics and Numerical Data; Vision Disorders -- Diagnosis; Disabled -- Statistics and Numerical Data; Adult; Aged; Cataract -- Diagnosis; Cataract -- Epidemiology; Cataract -- Prevention and Control; Educational Status; Female; Glaucoma -- Diagnosis; Glaucoma -- Epidemiology; Glaucoma -- Prevention and Control; Health Services Research; Human; Insurance, Health -- Statistics and Numerical Data; Macular Degeneration -- Diagnosis; Macular Degeneration -- Epidemiology; Macular Degeneration -- Prevention and Control; Male; Medically Uninsured; Middle Age; Preventive Health Care; United States; Vision Disorders -- Epidemiology

Management of glaucoma: focus on pharmacological therapy. - Marquis RE; Whitson JT (Drugs & Aging, 2005)
Glaucoma represents a major cause of vision loss throughout the world. Primary open-angle glaucoma, the most common form of glaucoma, is a chronic, progressive disease often, though not always, accompanied by elevated intraocular pressure (IOP). In this disorder, retinal ganglion cell loss and excavation of the optic nerve head produce characteristic peripheral visual field deficits. Patients with normal-tension glaucoma present with typical visual field and optic nerve head changes, without a documented history of elevated IOP. A variety of secondary causes, such as pigment dispersion syndrome and ocular trauma, can result in glaucoma as well. Treatment of all forms of glaucoma consists of reducing IOP. With proper treatment, progression of this disease can often be delayed or prevented. Treatment options for glaucoma include medications, laser therapy and incisional surgery. Laser techniques for the reduction of IOP include argon laser trabeculoplasty and selective laser trabeculoplasty. Both techniques work by increasing outflow of aqueous humour through the trabecular meshwork. Surgical options for glaucoma treatment include trabeculectomy, glaucoma drainage tube implantation and ciliary body cyclodestruction. While each of these types of procedures is effective at lowering IOP, therapy usually begins with medications. Medications lower IOP either by reducing the production or by increasing the rate of outflow of aqueous humour within the eye. Currently, there are five major classes of drugs used for the treatment of glaucoma: (i) cholinergics (acetylcholine receptor agonists); (ii) adrenoceptor agonists; (iii) carbonic anhydrase inhibitors (CAIs); (iv) beta-adrenoceptor antagonists; and (v) prostaglandin analogues (PGAs). Treatment typically begins with the selection of an agent for IOP reduction. Although beta-adrenoceptor antagonists are still commonly used by many clinicians, the PGAs are playing an increasingly important role in the first-line therapy of glaucoma. Adjunctive agents, such as alpha-adrenoceptor agonists and CAIs are often effective at providing additional reduction in IOP for patients not controlled on monotherapy. As with any chronic disease, effective treatment depends on minimising the adverse effects of therapy and maximising patient compliance. The introduction of a variety of well tolerated and potent medications over the past few years now allows the clinician to choose a treatment regimen on an individual patient basis and thereby treat this disorder more effectively.
Keywords: Glaucoma -- Drug Therapy; Adrenergic Beta-Antagonists -- Therapeutic Use; Cholinergic Agents; Clinical Trials; Intraocular Pressure -- Drug Effects; Lasers -- Therapeutic Use; Prostaglandins -- Analogs and Derivatives; Surgery, Operative

Intraocular Pressure-Lowering Combination Therapies with Prostaglandin Analogues. - Aptel, Florent; Chiquet, Christophe; Romanet, Jean-Paul (Drugs, 2012)
Intraocular pressure (IOP) reduction is currently the only therapeutic approach demonstrated to preserve visual function in patients with glaucoma. The first line of glaucoma treatment consists of topical IOP-lowering medications, usually initiated as monotherapy. A significant proportion of patients require more than one medication to reach a target IOP at which optic nerve damage will not progress. As prostaglandin analogues (PGAs) are the most effective class for reducing IOP, one of the other commonly used classes (β-adrenoceptor antagonist [β-blocker], carbonic anhydrase inhibitor or α2-adrenoceptor agonist) is frequently combined with a PGA. In the last decade, the use of fixed combinations containing two medications in a single bottle has steadily increased. Fixed combinations have the potential to simplify the dosing regimen, increase patient adherence, avoid the washout effect of the second drop on the first medication instilled, decrease exposure to preservatives and, sometimes, reduce the cost of treatment. Clinical trials have evaluated PGA-based fixed combinations versus unfixed combinations (individual components administered concomitantly) or versus individual monotherapies; however, any advantage that the fixed combinations may have in terms of IOP-lowering efficacy is still debated. For these reasons, the PGA-based fixed combinations are not approved by regulatory authorities in some countries, such as the US. We review the published studies evaluating the efficacy and tolerability of the IOP-lowering unfixed and fixed combination therapies with PGAs. Regarding unfixed combinations, the review shows that α2-adrenergic agonists-PGA and carbonic anhydrase inhibitor-PGA combinations seem to be at least as effective at reducing IOP as the β-blocker-PGA combinations. As for the fixed combinations, the review shows that the three PGA-timolol fixed combinations are more effective than their component medications used separately as monotherapy and are better tolerated than the three respective prostaglandins. The three PGA-timolol fixed combinations are less effective at reducing IOP than the unfixed combinations but are better tolerated. The advantage of the fixed combinations in terms of patient adherence and persistence is supported by a very small number of studies and remains to be more accurately determined. Most studies, but not all, seem to show that PGA-timolol fixed combinations are more effective than other available β-blocker fixed combinations (dorzolamide-timolol fixed combinations) at reducing IOP and are similarly tolerated
Keywords: Prostaglandins -- Analogs and Derivatives; Intraocular Pressure -- Drug Effects; Glaucoma -- Drug Therapy; Drug Combinations; Adrenergic Beta-Antagonists -- Therapeutic Use; Adrenergic Alpha-Agonists -- Therapeutic Use; Human; France; Medline; Databases; Meta Analysis; Randomized Controlled Trials; Costs and Cost Analysis; Patient Compliance; Quality Improvement

Survey gathers innovative ideas to improve glaucoma compliance. - Boyle EL (Ocular Surgery News, 2008)
The American Glaucoma Society surveyed physicians, staff nd patients for suggestions on how to improve drug adherence.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Glaucoma -- Psychosocial Factors; Memory; Patient Attitudes; Patient Education; Questionnaires; Human

Quality of Life in Glaucoma: A Review of the Literature. - Quaranta, Luciano; Riva, Ivano; Gerardi, Chiara; Oddone, Francesco; Floriano, Irene; Konstas, Anastasios; Konstas, Anastasios G P; Floriani, Irene (Advances in Therapy, 2016)
The ultimate goal of glaucoma management is the preservation of patients' visual function and quality of life (QoL). The disease itself as well as the medical or surgical treatment can have an enormous impact on a patient's QoL. Even the mere diagnosis of a chronic, irreversible, potentially blinding disorder can adversely affect the patient's sense of well-being and QoL by eliciting significant anxiety. Patients with primary open-angle glaucoma rarely present with visual symptoms, at least early in the course of the disease. A better understanding of patient-reported QoL can improve patient-physician interaction and enhance treatment adherence by customizing treatment options based on individual patient profile, thus optimizing long-term prognosis. These aspects are summarized and critically appraised in this article.
Keywords: Patient Care Plans; Glaucoma -- Diagnosis; Glaucoma -- Therapy; Glaucoma -- Psychosocial Factors; Quality of Life; Perimetry; Prognosis; Disease Management

Ocular surface disease and glaucoma. - Ramos-Cadena, María de los Angeles; Spaeth, George L. (Expert Review of Ophthalmology, 2016)
Introduction: The purpose of this review is to consider one downside of topical hypotensive medications. Visual loss can be incapacitating, before subjecting a person to potentially damaging effects of topical medications it is appropriate to be as certain as possible that treatment is actually needed. Areas covered: Research discusses the relationship between ocular surface disease (OSD) and its association with chronic use of glaucoma medication. Studies OSD as a medication-related morbidity, impact on patients’ quality of life, reviews preservative-free glaucoma medication, and OSD treatment. Research includes articles obtained from the keywords dry eye, OSD and glaucoma, preservatives and topical hypotensives, OSD and glaucoma surgery in Medline/PubMed, EMBASE, and Google Scholar. Experts commentary: Glaucoma patients under chronic topical hypotensive treatment with OSD symptoms should be adequately evaluated and receive optimal and timely therapy; offering safe administration of glaucoma treatment, resulting in more comfortable patients, greater adherence, and fewer failed surgical procedures.
Keywords: Eye Diseases -- Therapy; Glaucoma -- Drug Therapy; Antihypertensive Agents -- Adverse Effects; Blindness -- Risk Factors; Eye Diseases -- Chemically Induced; Morbidity; Quality of Life; Dry Eye Syndromes; Glaucoma -- Surgery; Medication Compliance; Treatment Failure; Benzalkonium Compounds

Psychological Aspects of Glaucoma. - Ah Reum Jeong; Chan Yun Kim; Min Hee Kang; Na Rae Kim; Jeong, Ah Reum; Kim, Chan Yun; Kang, Min Hee; Kim, Na Rae (Journal of Nervous & Mental Disease, 2016)
Glaucoma is a group of optic neuropathies that is more prevalent among the elderly population and commonly associates with comorbidities, including mental disorders in that population. This article reviews the relationship between glaucoma and mental disorders. In it, we discuss the coexistence of glaucoma and mental illnesses, including Alzheimer's disease, depression, and personality disorder. We also focus on the proper treatment approaches for glaucoma patients with mental comorbidity and poor treatment adherence. We summarize some cautiously recommended psychotherapeutic medications, while also discussing the psychologically adverse effects of antiglaucoma medications.
Keywords: Mental Disorders -- Psychosocial Factors; Comorbidity; Glaucoma -- Psychosocial Factors; Mental Disorders -- Epidemiology; Glaucoma -- Epidemiology; Glaucoma -- Drug Therapy; Mental Disorders -- Chemically Induced

Creating patient value in glaucoma care: applying quality costing and care delivery value chain approaches--a five-year case study in the Rotterdam Eye Hospital. - de Korne DF; Sol K; Custers T; van Sprundel E; van Ineveld BM; Lemij HG; Klazinga NS (International Journal of Health Care Quality Assurance (09526862), 2009)
Keywords: Glaucoma -- Therapy; Health Care Delivery -- Administration; Patient Satisfaction; Quality of Health Care -- Administration; Quality of Health Care; Clinical Indicators -- Administration; Costs and Cost Analysis; Data Collection; Health Care Costs; Health Services Accessibility -- Administration; Health Services Needs and Demand -- Administration; Netherlands; Process Assessment (Health Care) -- Administration; Quality of Health Care -- Economics; Reimbursement Mechanisms; Retrospective Design; Human

Cataract, phacoemulsification and intraocular pressure: Is the anterior segment anatomy the missing piece of the puzzle? - Masis Solano, Marisse; Lin, Shan C. (Progress in Retinal & Eye Research, 2018)
Cataract extraction is a safe and effective surgery that has a lowering effect on the intraocular pressure. The specific mechanisms for this effect are still unclear. A direct inflammatory effect on the trabecular meshwork, alteration of the blood aqueous barrier, changes in the ciliary body and mechanical changes of the anterior segment anatomy are the key to understand cataract surgery and it's effects on aqueous humor dynamics. Additionally, with the advent of AS OCT, changes in the anterior segment of the eye have been studied and several parameters (such as lens vault, angle opening distance and anterior chamber depth) have been identified as predictors of intraocular pressure change. In eyes with narrow angles there is a greater drop in intraocular pressure after cataract surgery and it is correlated with parameters related to anterior chamber space. It is safe to affirm that cataract surgery is an important part of the modern glaucoma treatment and evidence should be analyzed as part of a bigger picture in order to more accurately understand its clinical relevance.
Keywords: Ocular Hypertension -- Surgery; Cataract -- Physiopathology; Intraocular Pressure -- Physiology; Anterior Eye Segment -- Anatomy and Histology; Phacoemulsification; Ocular Hypertension -- Physiopathology; Glaucoma -- Surgery; Glaucoma -- Physiopathology

The use of teleglaucoma at the University of Alberta. - Kassam, Faazil; Amin, Samreen; Sogbesan, Enitan; Damji, Karim F (Journal of Telemedicine & Telecare, 2012)
The aim of the teleglaucoma service at the University of Alberta is to improve access for people in northern Alberta who have early-stage glaucoma or who are at risk for glaucoma. Two types of teleglaucoma service are offered: remote and in-house. A standardized approach is used to capture patient information (structured histories, examinations and fundus photographs) which is then sent to a tertiary care centre for grading and recommendations. Only one grader reads and makes management recommendations for each case. Reports are sent electronically. A total of 195 cases have been graded through the remote service since 2008. A total of 62 cases have been graded through the in-house service since 2011. The average reporting time for consultations in the in-house service was 7 days, and it was also 7 days for the remote service. We believe that the use of teleglaucoma can improve the way that patients are diagnosed and managed, both in industrialized and developing countries. Teleglaucoma is currently being used as a screening tool at the Aga Khan University Hospital in Nairobi with mobile units equipped with a fundus camera and a visual field machine.
Keywords: Glaucoma -- Diagnosis; Ophthalmology -- Methods; Telemedicine -- Utilization; Africa; Alberta; Blindness -- Diagnosis; Blindness -- Etiology; Canada; Glaucoma -- Complications; Health Services Accessibility; Remote Consultation -- Methods; Rural Population

LITERATURE REVIEW. - Cakiner-Egilmez, Tulay (Insight: The Journal of the American Society of Ophthalmic Registered Nurses, 2014)
Keywords: Research; Ophthalmic Nursing; Intraocular Pressure; Delayed-Action Preparations; Glaucoma -- Drug Therapy; Aging; Home Environment; Lighting; Corneal Transplantation; Age Factors; Aged; Cataract Extraction -- Trends; Health Services Accessibility

Stepwise approach useful for medical treatment of open-angle glaucoma. - Boyle, Erin L.; Mullin, David W. (Ocular Surgery News, 2010)
The article reports on the importance of the establishment of target pressure, selection of the appropriate medication or combination of medications and addressing compliance issues in treating open angle glaucoma patients with medical therapy, which was discussed by physician Douglas J. Rhee at the Asia-Pacific Academy of Ophthalmology Congress held in Beijing, China on September 16-20, 2010.
Keywords: Glaucoma -- Drug Therapy; Prostaglandins -- Therapeutic Use; Decision Making, Clinical; Medication Compliance; Goals and Objectives; Physician-Patient Relations; Counseling

Clinician-Patient Communication in a Glaucoma Clinic in India. - Mocherla, Shobha; Raman, Usha; Holden, Brien (Qualitative Health Research, 2011)
Keywords: Professional-Patient Relations; Communication; Glaucoma; Patient Compliance; India; Academic Medical Centers; Grounded Theory; Thematic Analysis; Constant Comparative Method; Multimethod Studies; Human; Semi-Structured Interview

Improving the prediction of medication compliance: the example of bisphosphonates for osteoporosis. - Curtis JR; Xi J; Westfall AO; Cheng H; Lyles K; Saag KG; Delzell E; Curtis, Jeffrey R; Xi, Juan; Westfall, Andrew O; Cheng, Hong; Lyles, Kenneth; et al. (Medical Care, 2009)
Introduction: Administrative claims data have a limited ability to identify persons with high compliance to oral bisphosphonates. We tested whether adding information on compliance with other drugs used to treat chronic, asymptomatic conditions would improve the predictive ability of administrative data to identify adherent individuals.Methods: Using data from a large, US healthcare organization, we identified new bisphosphonate users and their 1-year compliance to oral bisphosphonates, quantified by the Medication Possession Ratio (MPR). Multivariable logistic regression models evaluated the relationship between high bisphosphonate compliance (MPR >or=80%) and patient demographics, comorbidities, and health services utilization. To these logistic regression models, we evaluated the incremental change in the area under the receiver operator curve (AUC) after adding information regarding compliance with other drug classes. These included antihyperlipidemics (statins), antihypertensives, antidepressants, oral diabetes agents, and glaucoma medications. Results from the logistic regression models were evaluated in parallel using recursive partitioning trees with 10-fold cross-validation.Results: Among 101,038 new bisphosphonate users, administrative data identified numerous nonmedication factors (eg, age, gender, use of preventive services) significantly associated with high bisphosphonate compliance at 1 year. However, all these factors in aggregate had low discriminant ability to identify persons highly adherent with bisphosphonates (AUC = 0.62). For persons who were new users of >or=1 of the other asymptomatic condition drugs, MPR data on the other drugs substantially improved the prediction of high bisphosphonate compliance. The impact on prediction was largest for concomitant statin users (AUC = 0.70).Conclusions: Information on compliance with drugs used to treat chronic asymptomatic conditions improves the prediction of compliance with oral bisphosphonates. This information may help identify persons who should receive targeted interventions to promote compliance to osteoporosis medications.
Keywords: Chronic Disease -- Drug Therapy; Diphosphonates -- Therapeutic Use; Medication Compliance; Osteoporosis -- Drug Therapy; Preventive Health Care -- Utilization; Administration, Oral; Age Factors; Aged; Antidepressive Agents -- Therapeutic Use; Antihypertensive Agents -- Therapeutic Use; Antilipemic Agents -- Therapeutic Use; Comorbidity; Diphosphonates -- Administration and Dosage; Female; Hypoglycemic Agents -- Therapeutic Use; Insurance; Insurance, Pharmaceutical Services; Logistic Regression; Male; Middle Age; Sex Factors; United States; Human

Are you compliant with addressing glaucoma adherence? - Mansberger SL; Mansberger, Steven L (American Journal of Ophthalmology, 2010)
Keywords: Antihypertensive Agents -- Administration and Dosage; Glaucoma -- Drug Therapy; Medication Compliance; Patient Compliance; Antihypertensive Agents -- Economics; Economic Aspects of Illness; Glaucoma -- Psychosocial Factors; Patients -- Psychosocial Factors

The use of prostaglandin analogs in the uveitic patient. - Horsley MB; Chen TC (Seminars in Ophthalmology, 2011)
Glaucoma is a disease process characterized by progressive optic nerve damage and corresponding visual field loss. It may be further categorized into either primary open-angle glaucoma or secondary glaucoma. These secondary glaucomas include glaucomas associated with uveitis and inflammation. Prostaglandin analogs (PGA) have been used to help lower intraocular pressure (IOP) in these often difficult to manage eyes. However, controversy exists concerning their use in uveitic patients due to the theoretically higher risk of anterior uveitis, development of cystoid macular edema (CME), and reactivation of herpes simplex keratitis (HSK). There is little evidence that PGA disrupt the blood-aqueous barrier and only anecdotal evidence suggesting an increased risk of these rare findings. PGA may be used in uveitic glaucoma when other topical treatments have not lowered IOP to the patient's target range.
Keywords: Glaucoma -- Drug Therapy; Intraocular Pressure -- Drug Effects; Prostaglandins, Synthetic -- Therapeutic Use; Uveitis -- Drug Therapy; Glaucoma -- Physiopathology; Prostaglandins, Synthetic -- Adverse Effects; Uveitis -- Physiopathology

A glaucoma equity profile: correlating disease distribution with service provision and uptake in a population in Northern England, UK. - Day F; Buchan JC; Cassells-Brown A; Fear J; Dixon R; Wood F (Eye, 2010)
Keywords: Glaucoma -- Epidemiology; Glaucoma -- Ethnology; Health Services Accessibility -- Administration; Health Services Needs and Demand; Ophthalmology; Age Factors; Aged; Aged, 80 and Over; England; Female; Health Services Accessibility -- Standards; Male; Middle Age; Public Health; Socioeconomic Factors; National Health Programs -- Administration

ECP emerging as viable option for difficult pediatric glaucoma cases. - Misiano J (Ocular Surgery News, 2008)
Cost, time required to learn the technique and patients' reliance on medications are possible obstacles to widespread acceptance.
Keywords: Glaucoma -- Surgery -- In Infancy and Childhood; Laser Therapy -- Methods; Child; Intraocular Pressure

Compliance issues in glaucoma management. (Ocular Surgery News, 2006)
Keywords: Antihypertensive Agents -- Therapeutic Use; Glaucoma -- Drug Therapy; Patient Compliance; Comparative Studies; Disease Progression -- Prevention and Control; Drug Administration; Drug Combinations; Education, Continuing (Credit); Intraocular Pressure -- Drug Effects; Medication Compliance; Ophthalmic Solutions; Timolol -- Administration and Dosage; Timolol -- Therapeutic Use

Practical and Analytic Issues in the Electronic Assessment of Adherence. - Cook, Paul; Schmiege, Sarah; McClean, Margaret; Aagaard, Laurra; Kahook, Malik (Western Journal of Nursing Research, 2012)
Keywords: Medication Compliance -- Evaluation; Electronics -- Utilization; Reminder Systems; Measurement Issues and Assessments; Glaucoma -- Drug Therapy; Research Methodology; Medication Compliance -- Classification; Pilot Studies; Time Factors; Sensitivity and Specificity; T-Tests; Pearson's Correlation Coefficient; Age Factors; Descriptive Statistics; Effect Size; Secondary Analysis; Funding Source

New patient adherence to glaucoma therapy changes little over time. - Hasson, Matt; Kahl, Kristie L. (Ocular Surgery News, 2015)
The article offers information on a study which examined adherence of patient to glaucoma therapy usign group-based trajectory modeling (GBTM).
Keywords: Patient Compliance; Glaucoma -- Therapy; Ophthalmology; Glaucoma -- Diagnosis; After Care; Control Group; Age Factors; Patient Assessment; Race Factors; White Persons; Income -- Evaluation; Patient Care -- Methods; Health Services Accessibility -- Evaluation

Sustained-release bimatoprost implant addresses challenges of adherence. - Dalton, Michelle (Ophthalmology Times, 2016)
The article reviews Phase I/II interim data for a bimatoprost sustained-release (SR) implant showing the device has favorable safety and efficacy and may address the issue of patient nonadherence. Topics include the primary endpoint of research being the intraocular pressure (IOP) change from baseline and the use of rescue medication. Also mentioned are glaucoma specialist Doctor Richard A. Lewis and colleagues undertaking the study as well as several potential barriers to patient adherence.
Keywords: Bimatoprost; Drug Implants; Intraocular Pressure; Glaucoma -- Drug Therapy

Are you at risk for a secondary cataract? (Harvard Heart Letter, 2019)
The article reports on new problems that may bring back the same symptoms after cataracts are successfully removed. Topics mentioned include occurrence of changes in vision from secondary cataracts within the first few years after surgery, circumstances that make people more likely to experience the side effect of cataract surgery, and possible complications of YAG laser capsulotomy.
Keywords: Cataract Extraction -- Adverse Effects; Postoperative Complications -- Risk Factors; Recurrence -- Risk Factors; Cataract -- Risk Factors; Risk Assessment; Lenses, Intraocular; Office Visits; Surgeons; Vision Disorders; Cataract -- Symptoms; Glaucoma -- Complications; Uveitis -- Complications; Cataract Extraction -- Methods; Laser Therapy -- Methods

Age, behavior, environment, and health factors in the soft contact lens risk survey. - Wagner, Heidi; Richdale, Kathryn; Mitchell, G Lynn; Lam, Dawn Y; Jansen, Meredith E; Kinoshita, Beth T; Sorbara, Luigina; Chalmers, Robin L (Optometry & Vision Science, 2014)
Keywords: Contact Lenses -- Adverse Effects; Keratitis -- Epidemiology; Risk Taking Behavior; Social Environment; Adolescence; Adult; Age Factors; Attitude to Health; Child; Ophthalmic Solutions -- Therapeutic Use; Sterilization and Disinfection -- Standards; Female; Surveys; Human; Keratitis -- Etiology; Male; Patient Compliance; Risk Factors; United States; Young Adult

Premium surgeons should help patients navigate vicious maze of care access. - Jackson, Mitchell A. (Ocular Surgery News, 2018)
Keywords: Surgeons; Health Services Accessibility; Professional-Patient Relations; Eye Care; Ophthalmic Solutions; Health Care Costs; Eye Diseases -- Therapy; Patient Satisfaction; Cataract Extraction; Glaucoma; Diabetic Retinopathy; Vision; Insurance, Health; Lenses, Intraocular; America

Compliance an ongoing issue in glaucoma. - Altersitz K (Ocular Surgery News, 2006)
Glaucoma experts continue to look for reasons for noncompliance and ways to increase patient cooperation.
Keywords: Glaucoma -- Therapy; Patient Compliance; Drug Delivery Systems; Glaucoma -- Complications; Medication Compliance; Ophthalmic Solutions; Patient Attitudes

Glaucoma Disparities in the Hispanic Population. - Nathan, Niraj; Joos, Karen M. (Seminars in Ophthalmology, 2016)
The Hispanic population is the United States’ largest minority and one of the fastest growing as well. In the next 30 to 40 years, the proportion of open-angle glaucoma patients represented by Hispanics is expected to dramatically rise. Here we examine the unique considerations and challenges of glaucoma care in this population, from demographics to risk factors to treatments and outcomes. Currently, access to care and the under-diagnosis of glaucoma in this population are significant issues that look only to grow in significance as the glaucoma burden continues to grow. Additionally, utilization of medical and surgical therapy remains lower in Hispanics than in many other ethnic groups. Understanding and proactively addressing the unique challenges in the screening and treatment of Hispanics will be of utmost importance to providing effective care to this population.
Keywords: Hispanic Americans -- Statistics and Numerical Data; Health Status Disparities; Glaucoma -- Ethnology; Health Services Accessibility -- Statistics and Numerical Data; Glaucoma -- Therapy; Risk Factors; Health Services -- Utilization

Special considerations for glaucoma management in the elderly. - Niyadurupola, Nuwan; Broadway, David C. (Expert Review of Ophthalmology, 2016)
Introduction: Glaucoma is principally a disease that affects the elderly population. Although the same treatments are available for the elderly as the young, there are special considerations that have to be made for older patients. Areas covered: This review will discuss the current management options for glaucoma highlighting the factors that particularly apply to the elderly population. The published literature on treatments for glaucoma with the terms ‘age’, ‘aging’, ‘older’ and ‘elderly’ were searched using PubMed. Expert commentary: Topical medication may not be appropriate for all elderly patients due to particular side-effects and other intraocular pressure lowering treatments, including cataract surgery should be considered for these patients. Low target intraocular pressures are not always required in this age group and over-treatment of elderly patients should be avoided.
Keywords: Glaucoma -- Therapy; Disease Management; Gerontologic Care; Glaucoma -- Surgery; Glaucoma -- Drug Therapy; Administration, Topical; Intraocular Pressure; Antihypertensive Agents -- Therapeutic Use; Cataract Extraction; Laser Therapy; Patient Compliance

Geographic and temporal risk factors for interruptions to soft contact lens wear in young wearers. - Richdale, Kathryn; Lam, Dawn Y; Mitchell, G Lynn; Chalmers, Robin L; Jansen, Meredith E; Kinoshita, Beth T; Sorbara, Luigina; Wagner, Heidi (Contact Lens & Anterior Eye, 2013)
Keywords: Blepharitis -- Epidemiology; Conjunctivitis -- Epidemiology; Contact Lenses -- Utilization; Keratitis -- Epidemiology; Patient Compliance; Adolescence; Adult; Demography; Attitude to Health; Child; Comorbidity; Female; Human; Male; North America; Prevalence; Risk Factors; Young Adult

Increasing compliance with glaucoma therapy: 'So, convince me I have something wrong with my eyes.'. - Shaw ME (Insight: The Journal of the American Society of Ophthalmic Registered Nurses, 2005)
Successful management of primary open-angle glaucoma (POAG) depends heavily on patient compliance with the treatment plan. Studies have clearly shown that early treatment will slow the progress of the POAG.Despite this fact, and even when treatment plans are negotiated with the patient, patient behavior may not be conducive to con-serving vision in later life. Poor compliance results from a variety of causes, including lack of understanding of the diagnosis and the progress of POAG.As POAG is a 'silent' condition, unless they are aware of visual loss at the point of presentation, POAG patients need to be convinced that there is actually something wrong with them. This paper explores how health care professionals can better understand their patients' response to a diagnosis of POAG.
Keywords: Attitude to Illness; Glaucoma -- Therapy; Patient Compliance; Patient Attitudes

Racial differences in primary open-angle glaucoma: more than meets the eye. - Racette, Lyne; Ozobu Jr., Lawrence (Expert Review of Ophthalmology, 2013)
Keywords: Glaucoma -- Ethnology; Health Status Disparities; Black Persons; Patient Protection and Affordable Care Act; Health Services Accessibility; Social Justice

Glaucoma medication cost, compliance pose challenges in India. - Boyle EL; Mullin DW (Ocular Surgery News, 2010)
Keywords: Glaucoma -- Drug Therapy -- India; Prostaglandins -- Economics; Costs and Cost Analysis; Medication Compliance; Patient Attitudes; India

Enhancing adherence with glaucoma therapy: practical strategies for superior outcomes. - Friedman DS; Schwartz GF (Johns Hopkins Advanced Studies in Ophthalmology, 2008)
Keywords: Glaucoma -- Drug Therapy; Patient Compliance

S0620 or G0117? Let Form and Severity Drive Your Glaucoma Coding Choice. (Ophthalmology Coding Alert, 2011)
Keywords: Glaucoma; Severity of Illness; Coding; Physical Examination; Current Procedural Terminology; Office Visits; Medicare; Vision Screening

Shared care for chronic eye diseases: perspectives of ophthalmologists, optometrists and patients. - O'Connor PM; Harper CA; Brunton CL; Clews SJ; Haymes SA; Keeffe JE; O'Connor, Patricia M; Harper, C Alex; Brunton, Cathy L; Clews, Sandra J; Haymes, Sharon A; Keeffe, Jill E (Medical Journal of Australia, 2012)
Objective: To report the perspectives of optometrists, ophthalmologists and patients on a model of shared care for patients with chronic eye diseases.Design, Setting and Participants: Qualitative study of a model of shared care between optometrists and ophthalmologists for patients with stable age-related macular degeneration, diabetic retinopathy and glaucoma, trialled by the Royal Victorian Eye and Ear Hospital in Melbourne during 2007–2009. Semi-structured interviews were conducted with optometrists, ophthalmologists and patients at completion of the project to obtain their perspectives on this model.Results: Seventeen optometrists submitted expressions of interest to participate, and 12 completed web-based training modules and clinical observerships and adhered to specified examination and reporting protocols. All five participating ophthalmologists and 11 of the optometrists were interviewed. Ninety-eight patients participated and 37 were interviewed. Optometrists not only met ophthalmologists’ expectations but exceeded them, appropriately detecting and referring patients with additional, previously undetected conditions. Patients reported savings in travel time and were satisfied with the quality of care they received. Optometrists, ophthalmologists and patients indicated a general acceptance of shared care arrangements, although there were some issues relating to interprofessional trust.Conclusions: Shared care between local optometrists and hospital-based ophthalmologists can help to reduce patient waiting time for review and offers an opportunity for these two groups of eye care professionals to collaborate in providing localised care for the benefit of patients. However, trust and relationship building need to be further developed.
Keywords: Attitude to Health; Diagnosis, Eye; Eye Diseases -- Therapy; Multidisciplinary Care Team; Ophthalmology; Optometry; Adult; Aged; Aged, 80 and Over; Attitude of Health Personnel; Chronic Disease; Diabetic Retinopathy -- Diagnosis; Diabetic Retinopathy -- Therapy; Female; Glaucoma -- Diagnosis; Glaucoma -- Therapy; Human; Interprofessional Relations; Macular Degeneration -- Diagnosis; Macular Degeneration -- Therapy; Male; Middle Age; Patient Satisfaction; Qualitative Studies; Referral and Consultation; Surveys; Waiting Lists

Comparison of resident and glaucoma faculty practice patterns in the care of open-angle glaucoma. - Zebardast, Nazlee; Solus, Jason F; Quigley, Harry A; Srikumaran, Divya; Ramulu, Pradeep Y (BMC Ophthalmology, 2015)
Background: Previous studies suggest there are large variations in adherence of ophthalmologists with the American Academy of Ophthalmology's Preferred Practice Patterns (PPPs). The purpose of this study was to compare rates of compliance with glaucoma care guidelines between resident and glaucoma faculty physicians at a single institution.Methods: Charts of resident continuity clinic or glaucoma faculty patients with primary open angle glaucoma (POAG), ocular hypertension (OHTN), or suspicion of glaucoma were reviewed during the 2005-6 academic year. Performance within care measures specified by the 2005 PPP guidelines was compared between resident and faculty physicians using univariate and multivariable logistic regression models.Results: 112 resident and 100 faculty charts were reviewed. The mean compliance rate for all 7 care measures for resident physicians was significantly lower than that of faculty physicians (78% vs. 96%, p < 0.001). As compared to glaucoma faculty, resident physicians were less likely to have documented 6 of the 7 individual care measures (p ≤ 0.001 for all); the exception was optic nerve (ON) description. In multivariable analyses, resident patients were more likely to have at least one undocumented care measure than faculty patients (OR = 10.1, 95% CI = 5.1 to 20.0, p < 0.001). Among resident patients, undocumented care measures were more common among patients with poorer visual acuity (VA) in the better eye.Conclusions: Though unmeasured differences in clinic structure and patient characteristics may have partially contributed to poorer resident performance, residents were more likely than faculty to omit PPP care measures and significantly underperformed faculty in global assessment of glaucoma care. Resident education should focus on integration of PPPs into residency training and monitoring of resident compliance with evidence-based guidelines.

Towards the development of a human glaucoma disease-in-a-dish model using stem cells. - Green, David I; Ou, Yvonne (Expert Review of Ophthalmology, 2015)
Glaucoma, the leading cause of irreversible blindness worldwide, is a degenerative optic neuropathy for which current treatments slow the progression but do not cure the disease. While animal models are useful for studying underlying mechanisms of disease, there is a need for cell culture models of human glaucoma. With the advent of stem cell technology, building a glaucoma 'disease-in-a-dish' model using cells derived from human glaucoma patients is now viable. This review explores current progress and obstacles in generating retinal ganglion cells from human induced pluripotent stem cells, as well as the potential development of four different types of cell culture systems (single cell, co-culture, 3D retina and 3D optic nerve) that will be useful for interrogating cellular mechanisms, identifying therapeutic targets and screening drugs, with the future possibility of clinical translation.
Keywords: Glaucoma -- Physiopathology; Stem Cells; Models, Biological; Glaucoma -- Drug Therapy; Optic Nerve

Pseudomonas aeruginosa growth in Refresh Plus®. - Pinna A; Usai D; Zanetti S; Pinna, Antonio; Usai, Donatella; Zanetti, Stefania (Journal of Ocular Pharmacology & Therapeutics, 2011)
Purpose: To assess Pseudomonas aeruginosa growth in Refresh Plus(®), a unit-dose preservative-free ophthalmic solution indicated for the treatment of dry eye and after laser-assisted in situ keratomileusis (LASIK) surgery, which contains carboxymethylcellulose 0.5% as its active ingredient.Methods: Multiple test tubes of Refresh Plus were inoculated with 3 clinical ocular isolates of P. aeruginosa to achieve a target concentration of ∼100 colony-forming units (CFU)/mL. The tubes were incubated at 25°C and samples were aseptically removed at 6, 12, and 24 h. The samples were cultured to enumerate the population at each time point.Results: After 6 h incubation, the number of CFU/mL was 3,200 for isolate 1, 2,000 for isolate 2, and 6,480 CFU/mL for isolate 3. For all 3 organisms tested, the number of CFU/mL after 12 and 24 h incubation was >10(6) CFU/mL.Conclusions: Under the conditions of this experiment, Refresh Plus appears to support P. aeruginosa growth, suggesting that if the solution in a unit-dose vial of Refresh Plus were contaminated with P. aeruginosa during use, the organism would survive and replicate in the solution over time. Noncompliance with the manufacturer's recommendations (i.e., reuse of an open vial) may result in contamination of the solution with P. aeruginosa, which may cause severe keratitis.
Keywords: Cellulose -- Standards; Ophthalmic Solutions -- Standards; Pseudomonas; Cellulose -- Administration and Dosage; Cellulose; Cellulose -- Therapeutic Use; Drug Contamination; Drug Delivery Systems; Dry Eye Syndromes -- Drug Therapy; Dry Eye Syndromes -- Etiology; Keratitis -- Microbiology; Keratomileusis, Laser in Situ -- Adverse Effects; Ophthalmic Solutions -- Administration and Dosage; Ophthalmic Solutions; Ophthalmic Solutions -- Therapeutic Use; Pharmaceutical Additives

Pharmacotherapy of glaucoma. - Schmidl, Doreen; Schmetterer, Leopold; Garhöfer, Gerhard; Popa-Cherecheanu, Alina (Journal of Ocular Pharmacology & Therapeutics, 2015)
Glaucoma is a group of diseases involving the optic nerve and associated structures, which is characterized by progressive visual field loss and typical changes of the optic nerve head (ONH). The only known treatment of the disease is reduction of intraocular pressure (IOP), which has been shown to reduce glaucoma progression in a variety of large-scale clinical trials. Nowadays, a relatively wide array of topical antiglaucoma drugs is available, including prostaglandin analogues, carbonic anhydrase inhibitors, beta-receptor antagonists, adrenergic agonists, and parasympathomimetics. In clinical routine, this allows for individualized treatment taking risk factors, efficacy, and safety into account. A major challenge is related to adherence to therapy. Sustained release devices may help minimize this problem but are not yet available for clinical routine use. Another hope arises from non-IOP-related treatment concepts. In recent years, much knowledge has been gained regarding the molecular mechanisms that underlie the disease process in glaucoma. This also strengthens the hope that glaucoma therapy beyond IOP lowering will become available. Implementing this concept with clinical trials remains, however, a challenge.

Three reasons why MIGS may replace glaucoma drops as first-line therapy. (Ocular Surgery News, 2016)
The article talks about three reasons why Minimally Invasive Glaucoma Surgery (MIGS) would replace old standard glaucoma drops as first-line therapy for cataract operation including use of preservatives, compliance and success and fast-learning methods of MIGS.
Keywords: Learning Methods; Minimally Invasive Procedures; Glaucoma; Success; Cataract

Consider SLT as first-line treatment in management of glaucoma. (Ocular Surgery News, 2016)
The article discusses that selective laser trabeculoplasty (SLT) should be considered as a primary therapy for glaucoma patients because it is effective as primary glaucoma medications, less expensive and safer than medications with no patient compliance issues, according to physician L. Jay Katz. He opines that there is a problem with outflow in the trabecular meshwork for Schlemms canal in most patients and all the current drugs, used by physicians, really don't address that problem.
Keywords: Glaucoma -- Therapy; Patient Compliance; Glaucoma; Intraocular Pressure; Physicians; Lasers

Improving adherence to glaucoma medication: a randomised controlled trial of a patient-centred intervention (The Norwich Adherence Glaucoma Study). - Cate, Heidi; Bhattacharya, Debi; Clark, Allan; Fordham, Richard; Holland, Richard; Broadway, David C (BMC Ophthalmology, 2014)
Background: Improving adherence to ocular hypertension (OH)/glaucoma therapy is highly likely to prevent or reduce progression of optic nerve damage. The present study used a behaviour change counselling intervention to determine whether education and support was beneficial and cost-effective in improving adherence with glaucoma therapy.Methods: A randomised controlled trial with a 13-month recruitment and 8-month follow-up period was conducted. Patients with OH/glaucoma attending a glaucoma clinic and starting treatment with travoprost were approached. Participants were randomised into two groups and adherence was measured over 8 months, using an electronic monitoring device (Travalert® dosing aid, TDA). The control group received standard clinical care, and the intervention group received a novel glaucoma education and motivational support package using behaviour change counselling. Cost-effectiveness framework analysis was used to estimate any potential cost benefit of improving adherence.Results: Two hundred and eight patients were recruited (102 intervention, 106 control). No significant difference in mean adherence over the monitoring period was identified with 77.2% (CI, 73.0, 81.4) for the control group and 74.8% (CI, 69.7, 79.9) for the intervention group (p = 0.47). Similarly, there was no significant difference in percentage intraocular pressure reduction; 27.6% (CI, 23.5, 31.7) for the control group and 25.3% (CI, 21.06, 29.54) for the intervention group (p = 0.45). Participants in the intervention group were more satisfied with information about glaucoma medication with a mean score of 14.47/17 (CI, 13.85, 15.0) compared with control group which was 8.51 (CI, 7.72, 9.30). The mean intervention cost per patient was GB£10.35 (<US$16) and not cost-effective.Conclusions: Adherence with travoprost was high and not further increased by the intervention. Nevertheless, the study demonstrated that provision of information, tailored to the individual, was inexpensive and able to achieve high patient satisfaction with respect to information about glaucoma medication. Measurement of adherence remains problematic since awareness of study participation may cause a change in participant behaviour.Trial Registration: Current Controlled Trials, ISRCTN89683704.
Keywords: Antihypertensive Agents -- Therapeutic Use; Prostaglandins, Synthetic -- Analogs and Derivatives; Glaucoma -- Drug Therapy; Medication Compliance; Ocular Hypertension -- Drug Therapy; Patient Education -- Economics; Patient Education -- Methods; Patient Education -- Standards; Patient Centered Care -- Methods; Aged; Aged, 80 and Over; Analysis of Variance; Prostaglandins, Synthetic -- Therapeutic Use; Counseling -- Methods; Female; Health Care Costs; Human; Intraocular Pressure; Male; Middle Age; Patient Satisfaction

Experts explore challenges of successful pediatric cataract surgery. - Grassia, Tara (Ocular Surgery News, 2011)
The article explores the challenges of successful pediatric cataract surgery. It notes that cataract surgery is more complex in children, with the presurgical process more involved, and a long term follow-up that involves patching, drops and monitoring changes in eye growth among others. Some of the major issues include compliance, risk of subsequent glaucoma and use of anesthesia, while treatment approach reportedly varies depending on patient age and cataract morphology.
Keywords: Cataract Extraction -- In Infancy and Childhood; Preoperative Care; Decision Making, Clinical; Patient Compliance; Growth; Anesthesia; Lenses, Intraocular -- Equipment and Supplies; Child

Reminder systems, not education, improve glaucoma adherence: a comment on Cook et al. - Quigley, Harry A (Annals of Behavioral Medicine, 2015)

NO BETTER TIME FOR MYOPIA MANAGEMENT. - Aller, Thomas (Optometric Management, 2018)
Keywords: Myopia -- Therapy; Disease Management; Medical Practice, Evidence-Based; Cataract -- Risk Factors; Glaucoma -- Risk Factors; Retinal Detachment -- Risk Factors; Medical Practice; Myopia -- Diagnosis; Patient Compliance; Atropine -- Administration and Dosage; Atropine -- Therapeutic Use; Marketing; Contact Lenses -- Economics; Corneal Topography; Decision Making; Social Media; Optometrists; Myopia -- Complications; Professional Knowledge

Policy implications of regional variations in eye disease detection and treatment on Prince Edward Island: a repeated cross-sectional analysis, 2010-2012. - Khan, A M; Trope, G E; Wedge, R; Buys, Y M; El-Defrawy, S; Chen, Q; Jin, Y P (BMC Health Services Research, 2018)
Background: In Canada, government insurance covers eye care services provided by ophthalmologists and other physicians. However, government coverage for services provided by optometrists, non-medical school trained primary eye care providers, varies regionally. Little is known about the impact of a funding model in which ophthalmologist services are government-insured but services provided by optometrists are not, on eye care utilization and eye disease detection and treatment. We aimed to address this question by examining geographic variations in eye care service utilization on Prince Edward Island (PEI).Methods: PEI physician-billing data from 2010 to 2012 was analyzed across five distinct geographic regions (Charlottetown, Summerside, Prince, Queens & Kings and Stratford). The residential location of patients and practice locations of eye care providers were identified using the first three digits of their respective postal code. Age-standardized rates were computed for comparisons across different regions.Results: There were six ophthalmologists practicing on PEI, five with offices in Charlottetown. Twenty optometrists practiced on the island with offices across the province. Stratford is closest and Prince farthest from Charlottetown. Age-standardized utilization rates of ophthalmologists per 100 populations were 10.44 in Charlottetown and 10.90 in Stratford, which was significantly higher than in other regions (7.74-8.92; p < 0.05). The disparities were most pronounced amongst the elderly. The prevalence of glaucoma visits was higher in Charlottetown (6.10%) and Stratford (6.38%) and lower in other regions. A similar pattern was observed for the prevalence of cataract visits. While the prevalence of diabetes visits was higher in Prince and Summerside, the utilization of ophthalmologists by people with diabetes was almost twice as high in Charlottetown (6.49%) than in Prince (3.88%).Conclusions: The observed discrepancies in vision care utilization across geographic regions were likely attributed to barriers in accessing government-insured, geographically concentrated ophthalmologists, as opposed to a reflection of the true differences in eye disease occurrence. The lower prevalence of glaucoma visits in regions farther away from ophthalmologist offices may result in delayed detection and blindness in this population. Encouraging ophthalmologists to work in other areas of the province and/or to publicly fund services provided by optometrists may mitigate the observed disparities.Trial Registration: Not applicable.
Keywords: Ophthalmology; Glaucoma -- Diagnosis; Cataract -- Diagnosis; Health Services Accessibility -- Statistics and Numerical Data; Optometry; Female; Health Services Research; Cross Sectional Studies; Prince Edward Island; Middle Age; Adult; Human; Male; Cataract -- Therapy; Glaucoma -- Therapy; Aged; Health Personnel; Insurance Coverage; Funding Source

New drugs target multiple mechanisms in glaucoma. - Gebhart, Fred (Ophthalmology Times, 2013)
The article offers the author's insights regarding the new drugs for treating glaucoma. The author says that Acorn Biomedical is developing oral adenosine A3 receptor agonist to reduce problems in compliance. He states that Aeri Pharmaceuticals develops 13324 agent which has dual targets and expected to compete with prostalar timeline. He adds that Amakem has developed rho-associated protein kinase (ROCK) inhibitor AMA0076.
Keywords: Glaucoma -- Drug Therapy; Glaucoma -- Physiopathology; Pharmaceutical Companies; Drug Therapy -- Evaluation

Poor office visit follow-up compliance could affect glaucoma surgical success. - Boyle EL (Ocular Surgery News, 2010)
Clinicians should educate patients about possible implications of missing follow-up appointments.
Keywords: After Care; Glaucoma -- Surgery; Outcomes (Health Care); Patient Compliance; Patient Education; Physician-Patient Relations

Tolerability, quality of life, and persistency of use in patients with glaucoma who are switched to the fixed combination of latanoprost and timolol. - Dunker S; Schmucker A; Maier H; Dunker, Stephan; Schmucker, Achmed; Maier, Hubert (Advances in Therapy, 2007)
This study was undertaken to assess tolerability, quality of life, and persistency of use and to monitor changes in intraocular pressure (IOP) during the first 6 mo after a switch to fixed combination latanoprost/timolol. In Germany, 271 general ophthalmology practices enrolled patients who were switched from previous ocular hypotensive therapies to latanoprost/timolol for medical reasons. Usual care routines were followed, and IOP was measured at baseline and approximately 6 mo later. Adverse events were recorded throughout. Immediately before switching and at follow-up, patients completed a 29-item quality-of-life questionnaire. Of 1052 patients who met analysis criteria, 748 (71%) switched from combination therapy and 304 (29%) from monotherapy. An insufficient IOP reduction with the previous therapy was a reason for switching in 71% of patients; the desire to simplify to once-daily administration was cited in 66%. Ocular adverse events were reported in 19 patients after the switch, and 97% remained on therapy throughout the follow%up period. After switching, patients were less likely to forget to instill their eyedrops or to feel that their drops had adverse effects; they found it easier to include eyedrop administration in their routine; they were more satisfied with the frequency of instillation; and they were more likely to want to continue with the drops. Across all previous therapies, mean IOP decreased from 20.6+/-3.7 mm Hg to 17.2+/-2.8 mm Hg after the switch (P<.001)-a 14.8% difference. Fixed combination latanoprost/timolol is well tolerated and effective in patients who are switched from other monotherapies or combination therapies for medical reasons. Such a switch may be associated with improved quality of life.
Keywords: Glaucoma -- Drug Therapy; Latanoprost -- Therapeutic Use; Patient Compliance; Quality of Life; Timolol -- Therapeutic Use; Aged; Aged, 80 and Over; Descriptive Statistics; Drug Combinations; Female; Funding Source; Human; Intraocular Pressure -- Drug Effects; Latanoprost -- Adverse Effects; Male; Middle Age; Patient Satisfaction; Prospective Studies

Safety and efficacy of fixed combination travoprost-timolol in the lowering of intraocular pressure. - Noecker, Robert J.; Pokabla, Michael J. (Clinical Medicine Insights: Therapeutics, 2010)
The fixed combination eye drop Duotrav is a combination of travoprost 0.004% and timolol maleate 0.5%. Both travoprost and timolol have been used separately for the treatment of glaucoma by lowering intraocular pressure. Multiple studies have demonstrated the efficacy and safety of the fixed combination travoprost/timolol for the treatment of open-angle glaucoma and ocular hypertension. The once daily dosing of this combination offers multiple potential advantages such as patient adherence, potential cost advantages, and reduction in exposure to preservatives. This article discusses the benefits of fixed combination medications and summarizes past and recent studies listed on the online resource PubMed of the fixed combination travoprost/timolol with comparison to both monotherapy and other similar fixed combination ocular hypotensive preparations.
Keywords: Glaucoma -- Drug Therapy; Timolol -- Therapeutic Use; Travoprost -- Therapeutic Use; Glaucoma -- Epidemiology; Intraocular Pressure; Timolol -- Adverse Effects; Timolol -- Pharmacokinetics; Travoprost -- Adverse Effects; Travoprost -- Pharmacokinetics

Clinic waiting time, language barrier leading reasons for glaucoma patients' poor follow-up. (Ocular Surgery News, 2009)
Keywords: After Care; Communication Barriers; Glaucoma -- Prognosis; Waiting Lists; Appointments and Schedules; Outcomes (Health Care)

Glaucoma patients cite long wait times, communication problems as barriers to care. (Ocular Surgery News, 2009)
Keywords: Communication Barriers; Glaucoma -- Therapy; Health Services Accessibility; Waiting Lists; After Care; Appointments and Schedules

Glaucoma drugs may be repurposed with sustained-release implants. - Cimberle, Michela (Ocular Surgery News, 2016)
The article discusses role of sustained-release implants to offer opportunity to repurpose glaucoma drugs to overcome noncompliance issues; and presents the views of James D. Brandt, doctor of medicine, on effectiveness of intraocular implants having advantage of avoiding allergic reactions on ocular surfaces.
Keywords: Glaucoma; Drugs; Physicians; Intraocular Pressure; Medicine; Prostheses and Implants

Vision Loss in Older Adults. - PELLETIER, ALLEN L.; ROJAS-ROLDAN, LEDY; COFFIN, JANIS (American Family Physician, 2016)
Vision loss affects 37 million Americans older than 50 years and one in four who are older than 80 years. The U.S. Preventive Services Task Force concludes that current evidence is insufficient to assess the balance of benefits and harms of screening for impaired visual acuity in adults older than 65 years. However, family physicians play a critical role in identifying persons who are at risk of vision loss, counseling patients, and referring patients for disease-specific treatment. The conditions that cause most cases of vision loss in older patients are age-related macular degeneration, glaucoma, ocular complications of diabetes mellitus, and age-related cataracts. Vitamin supplements can delay the progression of age-related macular degeneration. Intravitreal injection of a vascular endothelial growth factor inhibitor can preserve vision in the neovascular form of macular degeneration. Medicated eye drops reduce intraocular pressure and can delay the progression of vision loss in patients with glaucoma, but adherence to treatment is poor. Laser trabeculoplasty also lowers intraocular pressure and preserves vision in patients with primary open-angle glaucoma, but long-term studies are needed to identify who is most likely to benefit from surgery. Tight glycemic control in adults with diabetes slows the progression of diabetic retinopathy, but must be balanced against the risks of hypoglycemia and death in older adults. Fenofibrate also slows progression of diabetic retinopathy. Panretinal photocoagulation is the mainstay of treatment for diabetic retinopathy, whereas vascular endothelial growth factor inhibitors slow vision loss resulting from diabetic macular edema. Preoperative testing before cataract surgery does not improve outcomes and is not recommended.
Keywords: Cataract -- Therapy; Macular Degeneration -- Therapy; Glaucoma -- Therapy; Diabetic Retinopathy -- Therapy; Vision Disorders -- Therapy; Injections; Antihypertensive Agents -- Therapeutic Use; Vitamins -- Therapeutic Use; Blindness -- Diagnosis; Blindness -- Therapy; Vision, Subnormal -- Etiology; Vision, Subnormal -- Diagnosis; Vision Disorders -- Diagnosis; Vitamin E -- Therapeutic Use; Macular Degeneration -- Complications; Ascorbic Acid -- Therapeutic Use; Practice Guidelines; Blindness -- Etiology; Aged; Diabetic Retinopathy -- Complications; Antilipemic Agents -- Therapeutic Use; Glaucoma -- Complications; Angiogenesis Inhibitors -- Therapeutic Use; Aged, 80 and Over; Vision, Subnormal -- Therapy; Fenofibrate -- Therapeutic Use; Diabetic Retinopathy -- Diagnosis; Glaucoma -- Diagnosis; Cataract -- Complications; Cataract Extraction; Health Screening; Cataract -- Diagnosis; Macular Degeneration -- Diagnosis; Eye Surgery; Vision Disorders -- Etiology

Preventing and managing visual disability in primary care: clinical applications. - Goldzweig CL; Rowe S; Wenger NS; MacLean CH; Shekelle PG; Goldzweig, Caroline L; Rowe, Susannah; Wenger, Neil S; MacLean, Catherine H; Shekelle, Paul G (JAMA: Journal of the American Medical Association, 2004)
Clinicians in primary care settings are well positioned to participate in the prevention and management of visual disability. They can have a significant impact on their patients' visual health by screening for vision problems, aggressively controlling known risk factors for visual loss, ensuring adherence to ophthalmologic treatment and continuity of eye care, and by timely referral of specific patient populations to qualified eye care professionals (eg, ophthalmologists and optometrists). Using their knowledge about common ophthalmic medications, clinicians can detect adverse effects of these agents, including exacerbations of heart or lung disease. They can ensure that appropriate patients are screened for common serious eye diseases, such as glaucoma, and that patients with disabilities related to vision problems are assessed for treatable conditions, such as cataracts or refractive error. Finally, clinicians can direct patients with low vision from any cause to resources designed to help enhance patient function and emotional support.
Keywords: Primary Health Care; Vision Disorders -- Prevention and Control; Vision Screening; Aged; Diabetes Mellitus -- Prevention and Control; Diagnosis, Eye; Eye Diseases -- Therapy; Family Practice; Female; Glaucoma -- Prevention and Control; Hypertension -- Prevention and Control; Macular Degeneration -- Prevention and Control; Male; Middle Age; Ophthalmic Solutions -- Adverse Effects; Ophthalmic Solutions -- Therapeutic Use

Patient considerations in glaucoma therapy. - Noecker RJ (Ocular Surgery News, 2005)
Keywords: Glaucoma -- Drug Therapy; Quality of Life; Antihypertensive Agents -- Adverse Effects; Education, Continuing (Credit); Intraocular Pressure -- Drug Effects; Patient Compliance

Comparison of Self-Reported and Objective Adherence to Antiglaucoma Medications. - Zarnowski, Tomasz; Wyszynska, Anna; Rekas, Marek (Journal of Ocular Pharmacology & Therapeutics, 2016)
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Self Report; Intraocular Pressure

Use of social media can foster glaucoma patient adherence. - Groves, Nancy; Schertzer, Robert M. (Ophthalmology Times, 2015)
Keywords: Social Media; Glaucoma -- Therapy; Physician-Patient Relations; Patient Compliance

New ideas for glaucoma. - Lotery, A (Eye, 2015)
An introduction is presented in which the editor discusses various reports within the issue on topics including novel eye surgical techniques, methods to improve compliance with therapy, and ways to assess glaucoma progression.
Keywords: Optic Nerve Diseases -- Epidemiology; Glaucoma -- Epidemiology; Glaucoma -- Diagnosis; Prevalence; Glaucoma -- Prevention and Control; Vision Disorders -- Epidemiology; Visual Fields; Incidence; Great Britain; Optic Nerve Diseases -- Prevention and Control; Optic Nerve Diseases -- Diagnosis; Ways of Coping Questionnaire

Adherence to drug regimens may increase with generics. - Charters, Lynda; STEIN, JOSHUA D. (Ophthalmology Times, 2015)
The article discusses findings of a study which determined if the availability of latanoprost for open-angle glaucoma had an effect on patient adherence. Topics covered include the compliance rates among patients for their glaucoma medication as reported in several studies, the various reasons cited by patients for their struggle with their regimens and the factors identified by regression analysis that were associated with improved adherence.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance -- Evaluation; Drugs, Generic

Primary open angle glaucoma in northern Nigeria: stage at presentation and acceptance of treatment. - Abdull, Mohammed M; Gilbert, Clare C; Evans, Jennifer (BMC Ophthalmology, 2015)
Background: To determine the stage of primary open angle glaucoma at presentation at a tertiary eye unit, to assess patient's knowledge of glaucoma and acceptance and subsequent adherence to treatment.Method: Information collected prospectively on new glaucoma patients aged 30 or more years included distance from residence and what they knew about glaucoma and its treatment. Treatment offered took account of disease severity and socioeconomic factors. Reasons for not accepting surgery were recorded. At follow up intraocular pressure (IOP) was measured and adherence to medication assessed verbally. Four categories of severity were defined based on visual acuity and visual fields defects in the worse eye.Results: 131 patients were recruited (mean age 52.8 years; 62% male). Most attended because of symptoms (70%). Mean IOP in affected eyes was 31.9+/-SD 12.4 and mean vertical cup:disc ratio was 0.8. 99 eyes (47%) had a visual acuity of light perception or worse. Risk factors for advanced/end-stage disease were age >50 years, living >10 km from the hospital, some awareness of glaucoma, not being literate, being unemployed and presenting with symptoms. In multivariable analysis older age and poor knowledge of glaucoma remained independent risk factors. 75 were offered trabeculectomy: five agreed but only one underwent surgery. Reasons for rejecting surgery were fear (37%), preferred medical treatment (27 %) and cost (15 %). 32/85 (24 %) participants started on topical medication attended follow up. 72% reported excellent compliance but only 56% of glaucomatous eyes had IOPs less than 21 mmHg.Conclusions: To prevent glaucoma blindness strategies are required which promote earlier detection, with counselling to promote acceptance of and adherence to treatment.

Low health literacy hampers compliance, glaucoma outcomes. - Hasson M (Ocular Surgery News, 2008)
Plain language and visual aids can help patients comprehend clinical information, study author says.
Keywords: Disease Progression; Glaucoma; Health Knowledge; Medication Compliance; Health Literacy; Interviews; Patient Education; Race Factors; Readability; Socioeconomic Factors

RECOMMEND SUPPLEMENTATION. (Optometric Management, 2018)
Keywords: Macular Degeneration -- Drug Therapy; Dietary Supplementation; Nutritional Counseling; Diet; Life Style; Glaucoma -- Therapy; Dry Eye Syndromes -- Therapy; Patient Compliance; Cost Benefit Analysis; Health Care Costs; Bevacizumab -- Therapeutic Use; Dexamethasone -- Therapeutic Use; Zeaxanthin -- Therapeutic Use; Treatment Outcomes

Generic latanoprost may improve patients adherence with lower costs vs. brand-name agents. - Kahl, Kristie L. (Ocular Surgery News, 2015)
The article discusses research being done on the benefit of switching to genetic latanoprost in improving patient adherence in the treatment of open-angle glaucoma. It references a study by Joshua D. Stein et al. published in the journal "Ophthalmology." Topics covered include the use of prostaglandin analogues for open-angle glaucoma and the difficulty in quantifying how cost plays a role in patient adherence to a glaucoma medication regimen.
Keywords: Latanoprost; Medication Compliance; Health Care Costs; Glaucoma; Minority Groups; Race Factors; Cost Benefit Analysis; Drugs, Generic

Safety, efficacy and cost fac to r into physicians' decisions regarding glaucoma medication. - Bacharach, Jason (Ocular Surgery News, 2015)
The article focuses on the advantages and disadvantages of brand-name and generic medications for glaucoma. It discusses the safety, efficacy, and cost of medications that need to be considered when prescribing glaucoma medications. Comments from Jason Bacharach of North Bay Eye Associates are provided.
Keywords: Glaucoma; Safety; Physicians; Eye; Office Visits

Office management of corneal ulcer relies on topical fluoroquinolones. - Kronemyer B (Ocular Surgery News, 2008)
Patient compliance is key; adjunctive measures include cycloplegic agents, collagen shields and bandage contact lenses.
Keywords: Ambulatory Care; Antibiotics -- Therapeutic Use; Corneal Diseases -- Drug Therapy; Ulcer; Bandages and Dressings; Contact Lenses; Corneal Diseases -- Epidemiology; Corneal Diseases -- Therapy; Keratomileusis, Laser in Situ -- Adverse Effects; Medication Compliance; Postoperative Complications

Study: Regional differences appear to be costliest disparity in US glaucoma care. - Boyle EL; Bechtel B; Hasson M; Master J; Mullin DW (Ocular Surgery News, 2010)
Keywords: Glaucoma -- Therapy -- United States; Geographic Factors; Health Services Accessibility; United States; Health Care Costs

Study: Regional differences appear to be costliest disparity in US glaucoma care. - Boyle, Erin L.; Bechtel, Bryan; Hasson, Matt; Master, Joe; Mullin, David W. (Ocular Surgery News, 2010)
Keywords: Glaucoma -- Therapy -- United States; Geographic Factors; Health Services Accessibility; United States; Health Care Costs

Ocular hypotensive efficacy of travoprost in patients unsuccessfully treated with latanoprost. - Kaback M; Geanon J; Katz G; Ripkin D; Przydryga J; Kaback, Martin; Geanon, John; Katz, Gregory; Ripkin, Douglas; Przydryga, Johan (Current Medical Research & Opinion, 2004)
Objective: To evaluate the efficacy of travoprost 0.004% monotherapy in patients unsuccessfully treated with latanoprost monotherapy.Research Design and Methods: Open-label, noncomparative study conducted at US academic and private practice clinics in adult patients with ocular hypertension or primary open-angle glaucoma who required a change in therapy (due to either inadequate efficacy or safety issues) as judged by the investigator. Intraocular pressure (IOP) was measured at entry and 30 days later.Main Outcome Measures: Mean change in intraocular pressure (mm Hg).Results: Reported here are 488 per-protocol patients from 330 centers who were using latanoprost monotherapy prior to study entry, and who received travoprost monotherapy during the study. Patients had a mean age of 69 years, were approximately two-thirds Caucasian, 60% female, predominantly brown or blue eyes, and 91% were diagnosed as having primary open-angle glaucoma. The mean days in treatment were 31.9 +/- 6.4. Mean IOP at study entry was 21.2 mm Hg. Following travoprost monotherapy, this was reduced by a mean of 3.2 mm Hg to 18 mm Hg (p < 0.0001, paired t-test). There were 21 adverse events reported in the intent-to-treat (ITT) population for an incidence of 3.5%. There were some limitations to the current study including: no washout period, no control therapy, single IOP determinations at the beginning and the end of the study; patient compliance with the initial therapy was not measured, and the study was not masked. This study reflects a real-life situation of what a clinician can expect when he changes a patient from latanoprost monotherapy to travoprost monotherapy.Conclusion: This study showed that travoprost provided a statistically and clinically significant reduction (p < 0.0001) in IOP of 3.2 mm Hg for patients who had not been successfully treated with latanoprost monotherapy. The results of this trial demonstrate the potential benefit of using travoprost as a replacement therapy in order to ensure adequate IOP control.
Keywords: Glaucoma -- Drug Therapy; Ocular Hypertension -- Drug Therapy; Travoprost -- Therapeutic Use; Adult; Aged; Aged, 80 and Over; Clinical Trials; Data Analysis Software; Descriptive Statistics; Female; Funding Source; Human; Intraocular Pressure; Latanoprost; Male; Middle Age; T-Tests; Treatment Failure; Treatment Outcomes; United States

First-year treatment patterns among new initiators of topical prostaglandin analogs. - Schmier JK; Covert DW; Robin AL; Schmier, Jordana K; Covert, David W; Robin, Alan L (Current Medical Research & Opinion, 2009)
Objective: To evaluate treatment patterns and costs among new initiators of topical prostaglandin analogs in a managed-care population.Research Design and Methods: Annual costs were modeled using multiple inputs. A retrospective cohort design was used to identify treatment patterns for pharmacotherapy. The study population was identified from pharmacy claims for patients who met study inclusion criteria (patients initiating prostaglandin analog monotherapy). Published studies were used to estimate visit-related resource use and costs were obtained from published and standard sources.Results: In the cohort analysis, a total of 12 202 patients met study criteria: 2275 received bimatoprost, 7347 received latanoprost and 2580 received travoprost (1808 used the original formulation and 772 used the newer preservative formulation). Of patients meeting study criteria, 50% stopped all glaucoma therapy, 6% switched from their initial prostaglandin therapy, and the remaining 44% stayed on their initial prostaglandin for 1 year. Of patients remaining on prostaglandin analog monotherapy for 1 year, 22.7% of bimatoprost patients, 19.8% of latanoprost patients and 17.9% of travoprost patients (19.7% for the original formulation and 13.7% for the new formulation) required adjunctive therapy. Of those requiring adjunctive therapy, the median number of days until starting adjunctive therapy was 53 days for bimatoprost patients, 63 days for latanoprost patients and 83 days for travoprost patients (70.5 days for the original formulation and 109 days for the new formulation). The resources used at each visit were estimated at $424 for an initial visit and $70 for follow-up visits. Estimated first-year costs were $1294, $1199, and $1186 for patients initiating therapy with bimatoprost, latanoprost, and travoprost, respectively. Estimated travoprost costs were higher for the original formulation ($1203) than for the new formulation ($1160). Sensitivity analyses suggested that the cost estimates are robust to changes in costs and use of adjunctive therapies.Limitations: The use of a claims database without compliance data or clinical outcomes and the selection of new initiators of topical prostaglandin analogs limits the findings and does not allow projecting outcomes to all glaucoma patients.Conclusions: Use of adjunctive therapy in glaucoma is an important driver of glaucoma management costs. Based on the results of this study, it is possible that longer duration of monotherapy with prostaglandin analogs may be associated with lower annual costs. Further study should be conducted to validate these findings.
Keywords: Administration, Topical; Glaucoma -- Drug Therapy; Glaucoma -- Economics; Health Care Costs; Prostaglandins -- Administration and Dosage; Prostaglandins -- Analogs and Derivatives; Prostaglandins -- Economics; Aged; Billing and Claims; Comparative Studies; Female; Funding Source; Male; Middle Age; Prospective Studies; Record Review; Retrospective Design; Human

Intraocular pressure reduction in the untreated fellow eye after selective laser trabeculoplasty. - Rhodes KM; Weinstein R; Saltzmann RM; Aggarwal N; Kooner KS; Petroll WM; Whitson JT; Rhodes, Kyle M; Weinstein, Rebecca; Saltzmann, Robert M; Aggarwal, Nalini; Kooner, Karanjit S; et al. (Current Medical Research & Opinion, 2009)
Objective: To investigate the effect of selective laser trabeculoplasty (SLT) on the intraocular pressure (IOP) of untreated fellow eyes in patients with open-angle glaucoma.Study Design: Retrospective chart review.Patients and Methods: Charts of all patients who underwent SLT at the University of Texas Southwestern Medical Center at Dallas between September 2003 and May 2006 were reviewed. Each patient had IOP measurements by Goldmann applanation tonometry in both eyes preoperatively, and at 1 hour, 2 weeks, 3 months, and 6 months postoperatively. Patient age, gender, diagnosis, central corneal thickness (CCT), previous intraocular surgeries, and degrees of laser treatment were tabulated for each patient. Patients with a history of previous glaucoma surgery in either eye were excluded as were those who underwent any change in glaucoma medications or further laser or surgical intervention in either eye within 6 months of SLT. Data were analyzed using a paired two-tailed t-test, an unpaired two-tailed t-test, ANOVA, and linear regression.Results: A total of 43 patients were included through 6 months of follow-up. Mean reduction in IOP in the treated eye was 3.9 +/- 0.6 mmHg or 18.8% (p < 0.001) at final exam. Mean IOP reduction in the fellow untreated eye was 2.1 +/- 0.5 mmHg or 11.2% (p < 0.01). Patients with higher preoperative IOPs had a greater reduction in IOP in both eyes (p < 0.001 for treated eyes, and p = 0.02 for untreated eyes). Patients who were on a larger number of glaucoma medications preoperatively had a greater response in both eyes (treated eye p = 0.002, untreated eye p = 0.008). There was no significant difference in IOP response in either eye based on age, gender, CCT, degrees of treatment, or phakic status.Conclusions: SLT produces a sustained and statistically significant IOP reduction in the fellow untreated eyes of patients with open-angle glaucoma. The results of our study support a biological mechanism of action for SLT. Limitations of this study include its retrospective design, relatively small sample size, a possible effect of increased compliance with medical therapy following SLT, and an inherent bias of excluding patients who underwent a change in medications or further laser or surgical therapy during the period under review.
Keywords: Eye -- Physiology; Glaucoma -- Surgery; Intraocular Pressure; Laser Therapy -- Methods; Eye Surgery -- Methods; Academic Medical Centers; Aged; Aged, 80 and Over; Descriptive Statistics; Female; Funding Source; Linear Regression; Male; Middle Age; Paired T-Tests; Record Review; Retrospective Design; Texas; Two-Way Analysis of Variance; Unpaired T-Tests; Human

Statins and the risk of lung, breast, and colorectal cancer in the elderly. - Setoguchi S; Glynn RJ; Avorn J; Mogun H; Schneeweiss S (Circulation, 2007)
BACKGROUND: Although most randomized trials and meta-analyses suggest a slight or no increase in the risk of cancer in statin users, results from observational studies have been conflicting, and some have even suggested a large protective effect of statins on certain cancers. Long-term statin users tend to be healthier, less frail, and more adherent to therapy than nonusers, however. This could explain such apparent 'protective' effects. METHODS AND RESULTS: We conducted the present cohort study by linking data from a large state drug benefit program with cancer registry data and Medicare healthcare utilization data. We identified all initiators of statins; initiators of glaucoma medications, another preventive drug, served as a comparison group. Outcomes included all registry-identified cases of colorectal, lung, and breast cancer. Multivariable Cox proportional models were used to adjust for confounding. Patient characteristics were similar in both groups, but statin initiators (n=24,439) were slightly younger and used some services more frequently than glaucoma drug initiators (n=7284). The mean follow-up was 2.9 years, with the longest follow-up being 8.4 years. Incidence rates of colorectal, lung, and breast cancers in both groups were very similar to rates in the general population. Adjusted hazard ratios were 0.96 (95% CI, 0.70 to 1.31) for colorectal cancer, 1.11 (95% CI, 0.77 to 1.60) for lung cancer, and 0.99 (95% CI, 0.74 to 1.33) for breast cancer. CONCLUSIONS: These data from a large population of typical older patients who began using statins indicate that it is unlikely that statins confer a clinically important decrease or increase in the risk of colorectal, lung, or breast cancer over the durations studied.
Keywords: Antilipemic Agents -- Adverse Effects; Breast Neoplasms -- Epidemiology; Colorectal Neoplasms -- Epidemiology; Lung Neoplasms -- Epidemiology; Aged; Aged, 80 and Over; Breast Neoplasms -- Chemically Induced; Colorectal Neoplasms -- Chemically Induced; Comparative Studies; Confidence Intervals; Female; Lung Neoplasms -- Chemically Induced; Male; Medicare; Prospective Studies; Registries, Disease; Risk Factors; Human

Compliance with medicine. - Shaya FT (Ophthalmology Clinics of North America, 2005)
Compliance with medication regimens is critical in assessing the effectiveness of treatments. As new drugs are approved for marketing and prescribed to diverse patient populations, the FDA now recommends further observational studies to continuously monitor unforeseen side effects or efficacy. More research is needed to develop valid and reliable tools to assess adherence of patients to treatment recommendations and adherence of patients to treatment guidelines, when applicable. Information on adherence is a relevant to physicians and their patients as it is to insurers and payers, who need to implement cost-effective disease management programs. This review also has highlighted examples in the adherence literature specific to glaucoma medications and based on longitudinal survival analyses of claims data. Such results may be best complemented by primary, survey-based data collected from patients in observational studies. Copyright © 2005 by Elsevier Inc.
Keywords: Disease Management; Drug Approval; Medication Compliance; Glaucoma; United States; United States Food and Drug Administration

Assessing medication adherence in the elderly: which tools to use in clinical practice? - MacLaughlin EJ; Raehl CL; Treadway AK; Sterling TL; Zoller DP; Bond CA (Drugs & Aging, 2005)
Adherence to prescribed medication regimens is difficult for all patients and particularly challenging for the elderly. Medication adherence demands a working relationship between a patient or caregiver and prescriber that values open, honest discussion about medications, i.e. the administration schedule, intended benefits, adverse effects and costs.Although nonadherence to medications may be common among the elderly, fundamental reasons leading to nonadherence vary among patients. Demographic characteristics may help to identify elderly patients who are at risk for nonadherence. Inadequate or marginal health literacy among the elderly is common and warrants assessment. The number of co-morbid conditions and presence of cognitive, vision and/or hearing impairment may predispose the elderly to nonadherence. Similarly, medications themselves may contribute to nonadherence secondary to adverse effects or costs. Especially worrisome is nonadherence to 'less forgiving' drugs that, when missed, may lead to an adverse event (e.g. withdrawal symptoms) or disease exacerbation.Traditional methods for assessing medication adherence are unreliable. Direct questioning at the patient interview may not provide accurate assessments, especially if closed-ended, judgmental questions are posed. Prescription refill records and pill counts often overestimate true adherence rates. However, if elders are asked to describe how they take their medicines (using the Drug Regimen Unassisted Grading Scale or MedTake test tools), adherence problems can be identified in a nonthreatening manner.Medication nonadherence should be suspected in elders who experience a decline in functional abilities. Predictors of medication nonadherence include specific disease states, such as cardiovascular diseases and depression. Technological aids to assessing medication adherence are available, but their utility is, thus far, primarily limited to a few research studies. These computerised devices, which assess adherence to oral and inhaled medications, may offer insight into difficult medication management problems. The most practical method of medication adherence assessment for most elderly patients may be through patient or caregiver interview using open-ended, nonthreatening and nonjudgmental questions.
Keywords: Medication Compliance -- Evaluation -- In Old Age; Prescriptions, Drug; Program Evaluation; Aged; Aged, 80 and Over; Breast Neoplasms -- Drug Therapy; Cardiovascular Diseases -- Drug Therapy; Clinical Trials; Glaucoma -- Drug Therapy; Lung Diseases, Obstructive -- Drug Therapy

Brinzolamide-brimonidine may benefit patients who have contraindications to beta-blocker. - Krader, Cheryl Guttman (Formulary, 2013)
Keywords: Drug Combinations; Glaucoma -- Drug Therapy; Adrenergic Beta-Antagonists -- Contraindications; Brinzolamide -- Administration and Dosage; Brimonidine Tartrate-Timolol Maleate -- Administration and Dosage; Patient Compliance; Intraocular Pressure -- Evaluation; Adverse Drug Event

Survey: identifying factors to improve compliance among glaucoma patients. - Boyle EL (Ocular Surgery News, 2007)
Response included suggestions for memory aids, closer doctor-patient relationships.
Keywords: Ophthalmology; Alternative Therapies; Antioxidants -- Therapeutic Use; Biological Markers; Blood Pressure -- Physiology; Congresses and Conferences; Glaucoma -- Drug Therapy; Glaucoma -- Familial and Genetic; Glaucoma -- Prevention and Control; Glaucoma -- Rehabilitation; Glaucoma -- Surgery; Glaucoma -- Therapy; Health Screening -- Methods; Intraocular Pressure -- Physiology; Louisiana; Medication Compliance; Organizations; Phacoemulsification -- Methods; Plants, Medicinal -- Therapeutic Use; Posture -- Physiology; Quality of Life; Rehabilitation -- Methods; Sleep -- Physiology; Stents -- Equipment and Supplies; Eye Surgery -- Methods

IN THE JOURNALS. (Ocular Surgery News, 2012)
Keywords: Strabismus -- Surgery; Anesthesia, General; Child; Head; Nerve Fibers; Corneal Transplantation; Eye Surgery; Cataract Extraction; Meningoencephalitis; Recurrence; Keratomileusis, Laser in Situ; Cornea -- Surgery; Visual Fields; Patient Compliance; Glaucoma -- Drug Therapy; Dry Eye Syndromes -- Drug Therapy; Growth Substances -- Therapeutic Use; Lenses, Intraocular; Infant, Premature; Tomography; Intraocular Pressure; Blood Circulation

Hand hygiene prior to contact lens handling is problematical. - McMonnies CW (Contact Lens & Anterior Eye, 2012)
Keywords: Contact Lenses -- Microbiology; Eye Infections, Bacterial -- Epidemiology; Eye Infections, Bacterial -- Prevention and Control; Eye Infections, Bacterial -- Transmission; Guideline Adherence; Handwashing -- Methods; Hygiene -- Standards; Keratitis -- Prevention and Control; Patient Compliance; Handwashing -- Standards; Health Personnel; Keratitis -- Epidemiology

Patient persistency with ocular prostaglandin therapy: a population-based, retrospective study. - Reardon G; Schwartz GF; Mozaffari E (Clinical Therapeutics, 2003)
BACKGROUND: Open-angle glaucoma affects an estimated 33 million individuals worldwide. An intraocular pressure >21 mm Hg in individuals with no evidence of optic nerve damage is termed ocular hypertension, a risk factor for glaucoma that has been estimated to affect as many as 10% of individuals 40 years of age or older. OBJECTIVE: The purpose of this research was to assess persistency (time on therapy) with prostaglandin analogues in the treatment of glaucoma or ocular hypertension. METHODS: This population-based, retrospective cohort study used the Protocare Sciences managed care database, which includes prescription and medical claims data from multiple managed care organizations. Patients 20 years of age or older who initiated therapy with latanoprost, bimatoprost, or travoprost (index drugs) between April 2001 and June 2002 were included. Patients were required to be continuously enrolled in the same plan for the 180 days preceding index prescription fill. Follow-up continued through June 30, 2002. Two outcome measures were analyzed: (1) discontinuation of the index prostaglandin and (2) either discontinuation or change in the index prostaglandin regimen. Changing therapy was defined as switching to or adding another ocular hypotensive agent. Cox regression models were used to compare rate ratios of discontinuation and discontinuation/change. Patient data were censored on termination of insurance coverage or at the end of the study period. RESULTS: Overall, 7527 patients were prescribed a prostaglandin analogue; 4356 patients met the inclusion criteria (n = 2376, 993, and 987 for latanoprost, bimatoprost, and travoprost, respectively). A total of 58% of patients were women, and 74% were 65 years of age or older. Compared with latanoprost, those treated with bimatoprost were 38% more likely to discontinue and 31% more likely to discontinue/change therapy, and patients treated with travoprost were 36% more likely to discontinue and 29% more likely to discontinue/change therapy (P < 0.001 for each comparison). CONCLUSION: Latanoprost-treated patients demonstrated significantly (P < 0.001) greater persistency than did those treated with either bimatoprost or travoprost.
Keywords: Medication Compliance; Prostaglandins -- Analysis; Prostaglandins -- Therapeutic Use; Adult; Aged; Billing and Claims; Chi Square Test; Comparative Studies; Cox Proportional Hazards Model; Female; Glaucoma -- Drug Therapy; Male; Middle Age; Patient Compliance; Retrospective Design; Survival Analysis; Treatment Outcomes -- Evaluation; Human

Bimatoprost adherence, persistence superior in prior latanoprost users. - Guttman Krader, Cheryl; Schwartz, Gail F. (Ophthalmology Times, 2015)
The article looks at the results of a retrospective observational study on the effectiveness of adherence and persistence with glaucoma medication among previous latanoprost users. Topics mentioned include the development of bimatoprost to provide more efficient drug delivery and reduce hyperemia, more consistent intraocular pressure control associated with bimatoprost formulations, and challenges encountered with adhering to glaucoma therapy.
Keywords: Latanoprost; Bimatoprost; Glaucoma -- Drug Therapy; Guideline Adherence -- Evaluation; Medication Compliance -- Evaluation

Burden and predictors of undetected eye disease in Mexican-Americans: the Los Angeles Latino Eye Study. - Varma R; Mohanty SA; Deneen J; Wu J; Azen SP; Varma, Rohit; Mohanty, Sarita A; Deneen, Jennifer; Wu, Joanne; Azen, Stanley P (Medical Care, 2008)
Background: Latinos have one of the highest rates of visual impairment associated with eye disease in the United States. Although little is known about the prevalence and risk of undetected eye disease (UED) in this population, it is known that Latinos encounter disproportionate barriers in accessing health care, which may influence the burden of UED.Objective: To estimate the burden and to evaluate factors associated with UED among Latinos, a majority of whom were Mexican-American.Research Design: Population-based, cross-sectional study. A detailed interview and eye examination were performed on participants.Subjects: A sample of 6,357 Latinos (95% of whom had Mexican ancestry), aged >or=40, in 6 census tracts in Los Angeles, California.Main Outcome Measure: UED (macular degeneration, glaucoma, diabetic retinopathy, cataract, and refractive error) was defined as those persons with eye disease and no reported history of that eye disease.Results: Fifty-three percent (3,349 of 6,357) of the participants had eye disease. Sixty-three percent (2,095 of 3,349) of them had UED. Major risk factors for UED included older age [odds ratio (OR): 4.7 (age >or=80)], having diabetes mellitus (OR: 3.3), never having had an eye examination (OR: 2.4), being uninsured (OR: 1.6), lower educational attainment (OR: 1.4), and low acculturation (OR: 1.3).Conclusions: These findings provide evidence of the burden of UED among Latinos. Interventions that address the modifiable risk factors (lack of insurance, never having had an eye examination, etc.) may improve detection of eye disease and decrease the burden of visual impairment in this high-risk minority population.
Keywords: Eye Diseases -- Epidemiology -- California; Hispanic Americans; Acculturation; Adult; Aged; Aged, 80 and Over; California; Chi Square Test; Confidence Intervals; Cross Sectional Studies; Data Analysis Software; Data Analysis, Statistical; Descriptive Statistics; Eye Diseases -- Risk Factors; Female; Funding Source; Interviews; Male; Mexico; Middle Age; Odds Ratio; P-Value; Scales; Socioeconomic Factors; Step-Wise Multiple Regression; Vision Screening; Human

Glaucoma. - Lan LK (Singapore Nursing Journal, 2000)
This paper examines patient compliance in glaucoma treatment, which is affected by different psychosocial factors, including patient's health belief, social support they have and several cognitive and emotional conditions operating at the time they receive the medical advice.
Keywords: Glaucoma; Glaucoma -- Epidemiology; Glaucoma -- Therapy; Patient Compliance; Nursing Practice, Theory-Based

Exfoliation syndrome. - Ritch R (Techniques in Ophthalmology, 2004)
Exfoliation syndrome (XFS) is characterized by the production and progressive accumulation of a fibrillar extracellular material in many ocular tissues. It has only recently been recognized to be the overall most common identifiable cause of glaucoma worldwide. 1 Exfoliative glaucoma (XFG) comprises over 50% of open-angle glaucomas in some countries and is now considered one of the leading causes of visual loss in elderly patients. 2 It causes not only severe, chronic open-angle glaucoma, but also lens subluxation, angle-closure glaucoma, blood-aqueous barrier impairment, and serious complications at the time of cataract extraction, such as zonular dialysis, capsular rupture, and vitreous loss.Based on the recent identification of accumulations in orbital tissues, skin specimens, and visceral organs, XFS is now recognized as a generalized disorder of the extracellular matrix. Preliminary information suggests a relationship with transient ischemic attacks, stroke, and heart disease. The potential ramifications of this disorder appear to be far more important than ever before realized.Exfoliation syndrome (XFS) is the most common identifiable cause of glaucoma worldwide. Exfoliative glaucoma (XFG) comprises over 50% of open-angle glaucomas in some countries and is now considered one of the leading causes of visual loss in elderly patients.
Keywords: Exfoliation Syndrome; Exfoliation Syndrome -- Epidemiology; Exfoliation Syndrome -- Symptoms; Glaucoma -- Etiology

Improving medication compliance among glaucoma patients. - Lewis RA (Ocular Surgery News, 2005)
Keywords: Glaucoma; Medication Compliance

Protocol for a randomised controlled trial to estimate the effects and costs of a patient centred educational intervention in glaucoma management. - Cate, Heidi; Bhattacharya, Debi; Clark, Allan; Fordham, Richard; Notley, Caitlin; Broadway, David C (BMC Ophthalmology, 2012)
Background: Poor glaucoma education is thought to be a causative factor of non-adherence to glaucoma therapy. However, the multi-factorial nature of non-adherent behaviour may explain the failure of purely educational interventions to achieve significant improvement in adherence. Behaviour Change Counselling (BCC) allows both the imparting of information and assessment of patient ambivalence to medication use and may elicit behaviour change in order to achieve better adherence. The chronic and complex nature of glaucoma means that patient non-adherence to glaucoma therapy does not easily correlate with measureable objective clinical endpoints. However, electronic medication monitoring offers an objective method of measuring adherence without reliance on clinical endpoints.Methods/design: The study is a randomised controlled trial (RCT) with glaucoma (open angle) or ocular hypertension patients attending a glaucoma clinic and prescribed travoprost. The study will determine whether additional glaucoma education using BCC is beneficial and cost effective in improving adherence with glaucoma therapy. An 8-month follow-up period, using an electronic adherence monitoring device (Travalert dosing aid, TDA), will indicate if the intervention is likely to be sustained in the longer term. Additionally, a cost-effectiveness framework will be used to estimate the cost benefit of improving adherence. The development of a novel intervention to deliver glaucoma education using BCC required practitioner training and fidelity testing. Five practitioners were successfully trained to become Glaucoma Support Assistants able to deliver the BCC intervention. The research group had prior clinical and investigative experience in this setting, and used multiple strategies to design a method to address the study objectives.Discussion: This RCT, using BCC to improve adherence to ocular hypotensive therapy, to our knowledge is the first within this disease area. Using a variety of adherence measures allows examination of the known inaccuracies of patient self-report with respect to glaucoma medication. The novel BCC component has undergone fidelity testing using BECCI and the BCC template will ensure conformity to a standardised intervention.Trial Registration: Current Controlled Trials: ISRCTN89683704.
Keywords: Cognitive Therapy -- Economics; Glaucoma -- Therapy; Medication Compliance; Ocular Hypertension -- Therapy; Patient Education -- Methods; Prostaglandins, Synthetic -- Analogs and Derivatives; Protocols; Antihypertensive Agents -- Economics; Antihypertensive Agents -- Therapeutic Use; Cost Benefit Analysis; Glaucoma -- Economics; Human; Ocular Hypertension -- Economics; Patient Education -- Economics; Prospective Studies; Prostaglandins, Synthetic -- Therapeutic Use; Randomized Controlled Trials

Device helps monitor patient eye drop regimen, adherence. - Charters, Lynda; Eaton, Alexander M. (Ophthalmology Times, 2015)
Keywords: Glaucoma -- Drug Therapy; Medication Compliance -- Evaluation; Digital Imaging -- Equipment and Supplies; Ophthalmic Solutions -- Administration and Dosage

Device helps monitor patient eye drop regimen, adherence. - Charters, Lynda; Eaton, Alexander M. (Ophthalmology Times, 2015)
The article offers information on a video imaging device that can be used for the instillation of eye drops by patients in both clinic and at-home settings. Topics covered include the features of the device, including a video camera, recording device and light source, and the views of Dr. Alexander M. Eaton on the potential use of the device in assessing the efficiency of eye drop use of patients.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance -- Evaluation; Digital Imaging -- Equipment and Supplies; Ophthalmic Solutions -- Administration and Dosage

Cumulative effect of risk factors on short-term surgical success of mitomycin augmented trabeculectomy. - Agarwal HC; Sharma TK; Sihota R; Gulati V (Journal of Postgraduate Medicine, 2002)
CONTEXT: Risk factors for failure of trabeculectomy may have a cumulative effect on the outcome. AIMS: To study the effect of preoperative ocular risk factors on the surgical outcome of trabeculectomy augmented with 2 commonly used doses of Mitomycin C. SETTINGS AND DESIGN: In a prospective cohort study, cases were recruited over an 18 month period. 92 eyes of 83 patients with one to three known risk factors for failure of trabeculectomy underwent Mitomycin-C (MMC) augmented trabeculectomy. METHODS AND MATERIAL: Trabeculectomy was done with a randomly chosen MMC dose of 0.2 mg/ml or 0.4 mg/ml. All cases were followed up for a period of at least 3 months. Surgical success was defined as the lowering of intraocular pressure (IOP) below 21 mmHg during the follow up period. STATISTICAL ANALYSIS USED: Chi square test, paired t test, odds ratio, effect size. RESULTS: Eyes with two or three risk factors (out of aphakic glaucoma, failed trabeculectomy, neovascular glaucoma, post uveitic glaucoma, traumatic glaucoma, adherent leucoma, juvenile glaucoma, prolonged medical therapy, steroid induced glaucoma, post penetrating keratoplasty glaucoma and developmental glaucoma) had a significantly poorer surgical success rate (88% and 78%) than eyes with one risk factor (100%). 0.4 mg/ml MMC used sub-sclerally had a statistically similar effect on lowering the IOP as 0.2 mg/ml in all groups. The rate of complications was significantly higher in the 0.4 mg/ml subgroup. CONCLUSIONS: The presence of more than one preoperative ocular risk factor, affects the surgical success of MMC augmented trabeculectomy in high-risk cases. Because of the significantly higher rate of complications with the higher dose of MMC, this should be used sparingly, only in cases with more than two risk factors.
Keywords: Glaucoma -- Drug Therapy; Glaucoma -- Surgery; Mitomycins -- Administration and Dosage; Adult; Chemotherapy, Adjuvant; Clinical Trials; Dose-Response Relationship, Drug; Drug Administration Schedule; Female; Intraocular Pressure; Male; Middle Age; Odds Ratio; Postoperative Complications; Preoperative Care; Probability; Prospective Studies; Risk Factors; Treatment Outcomes; Human

Tele-ophthalmology and conventional ophthalmology using a mobile medical unit in remote Greece. - Labiris G; Fanariotis M; Christoulakis C; Petounis A; Kitsos G; Aspiotis M; Psillas K (Journal of Telemedicine & Telecare, 2003)
We evaluated the quality of medical services delivered to remote glaucoma patients from a mobile unit. A four-wheel-drive vehicle containing the necessary equipment visited five different remote locations in Greece. During a three-year prospective study, 1205 patients were examined, of whom 230 had glaucoma. The majority of the subjects were examined by the unit's medical staff using the available instrumentation (e.g. slit-lamp and tonometer), while 56 glaucoma subjects were telemedically examined by consultants at the Patissia General Hospital, in Athens. Control data were obtained from a random sample of 260 urban glaucoma patients. A significantly greater proportion of the remote patients had an inadequate awareness of glaucoma (77%) compared with the urban patients (20%). Significantly more remote patients had poorer compliance (68%) in comparison with urban patients (23%). A significantly larger proportion of the remote patients had high intra-ocular pressure (21%) compared with the urban patients (5%). Technical difficulties occurred in the 13 of the 56 telemedical examinations. Mobile medical units can enhance access to medical services and contribute to the health-care of under-served populations.
Keywords: Ophthalmology; Telemedicine -- Methods -- Greece; Adult; Aged; Aged, 80 and Over; Female; Glaucoma; Greece; Health Knowledge; Male; Middle Age; Random Sample; Rural Health Services; Human

First patient office visit vital to establishing effective glaucoma medical therapy. (Ocular Surgery News, 2009)
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Office Visits; Patient Education; Physician-Patient Relations

Contact lens-related corneal infection: Intrinsic resistance and its compromise. - Fleiszig, Suzanne M.J.; Kroken, Abby R.; Nieto, Vincent; Grosser, Melinda R.; Wan, Stephanie J.; Metruccio, Matteo M.E.; Evans, David J. (Progress in Retinal & Eye Research, 2020)
Contact lenses represent a widely utilized form of vision correction with more than 140 million wearers worldwide. Although generally well-tolerated, contact lenses can cause corneal infection (microbial keratitis), with an approximate annualized incidence ranging from ~2 to ~20 cases per 10,000 wearers, and sometimes resulting in permanent vision loss. Research suggests that the pathogenesis of contact lens-associated microbial keratitis is complex and multifactorial, likely requiring multiple conspiring factors that compromise the intrinsic resistance of a healthy cornea to infection. Here, we outline our perspective of the mechanisms by which contact lens wear sometimes renders the cornea susceptible to infection, focusing primarily on our own research efforts during the past three decades. This has included studies of host factors underlying the constitutive barrier function of the healthy cornea, its response to bacterial challenge when intrinsic resistance is not compromised, pathogen virulence mechanisms, and the effects of contact lens wear that alter the outcome of host-microbe interactions. For almost all of this work, we have utilized the bacterium Pseudomonas aeruginosa because it is the leading cause of lens-related microbial keratitis. While not yet common among corneal isolates, clinical isolates of P. aeruginosa have emerged that are resistant to virtually all currently available antibiotics, leading the United States CDC (Centers for Disease Control) to add P. aeruginosa to its list of most serious threats. Compounding this concern, the development of advanced contact lenses for biosensing and augmented reality, together with the escalating incidence of myopia, could portent an epidemic of vision-threatening corneal infections in the future. Thankfully, technological advances in genomics, proteomics, metabolomics and imaging combined with emerging models of contact lens-associated P. aeruginosa infection hold promise for solving the problem - and possibly life-threatening infections impacting other tissues.
Keywords: Bacteria; Antibiotics -- Therapeutic Use; Prosthesis-Related Infections -- Microbiology; Cornea -- Microbiology; Keratitis -- Etiology; Contact Lenses; Eye Infections, Bacterial -- Etiology; Keratitis -- Drug Therapy; Eye Infections, Bacterial -- Microbiology; Prosthesis-Related Infections -- Diagnosis; Eye Infections, Bacterial -- Drug Therapy; Keratitis -- Microbiology; Scales

Glaucoma specialists should focus on retention of patients. - Mullin DW; Altersitz K (Ocular Surgery News, 2009)
Keywords: After Care; Disease Surveillance; Glaucoma -- Drug Therapy; Physician's Role; Blindness -- Prevention and Control; Health Services Accessibility; Specialties, Medical

Providing education, options important to treating indigent glaucoma patients. - Tsai JC (Ocular Surgery News, 2008)
Keywords: Glaucoma -- Therapy; Indigent Persons; Patient Education; Health Knowledge; Medication Compliance; Patient Compliance

Four factors can help determine best initial glaucoma therapy. (Ocular Surgery News, 2008)
Keywords: Glaucoma -- Therapy; Decision Making, Clinical; Glaucoma -- Drug Therapy; Glaucoma -- Surgery; Laser Therapy; Patient Compliance; Quality of Life; Severity of Illness; Eye Surgery

Glaucoma patients need guidance when using eye drops. - Boyle EL (Ocular Surgery News, 2008)
More than half noncomplaint, with one-third having an improper eye drop instillation technique.
Keywords: Glaucoma -- Rehabilitation; Ophthalmic Solutions -- Administration and Dosage; Ophthalmic Solutions -- Therapeutic Use; Glaucoma -- Drug Therapy; Ophthalmic Solutions -- Adverse Effects; Ophthalmology -- Methods; Patient Compliance; Treatment Outcomes

MOVERS & SHAKERS. - Bennett, Talitha (Ocular Surgery News, 2016)
The article announces the appointments of Doctor Ron Kurtz, president of PrimaPharma, to the board of directors of Allegro Ophthalmics and Clayton Edwards as senior vice president for operations and Eric Rice as vice president for client relations at Imprimis Pharmaceuticals.
Keywords: Dry Eye Syndromes -- Drug Therapy; Intraocular Pressure; Glaucoma -- Drug Therapy; Governing Board; Appointments and Schedules; ERIC Database; Rice; Physicians

New technology promising in addressing noncompliance. - Lewis RA (Ocular Surgery News, 2006)
Keywords: Drug Monitoring -- Trends; Glaucoma -- Drug Therapy; Patient Compliance -- Evaluation; Administration, Topical; Drug Monitoring -- Equipment and Supplies; Drug Monitoring -- Methods; Electronics; Intraocular Pressure; Medication Compliance; Patient Attitudes; Pupil; Risk Factors; Self Administration; Self Report

Physician shares pearls, indications for laser trabeculoplasty. - Boyle, Erin L.; Mullin, David W. (Ocular Surgery News, 2010)
The article reports on the claim of physician Paul Healey that laser trabeculoplasty provides a viable treatment option for effective lowering of intraocular pressure (IOP) with improved compliance in early to moderate glaucoma.
Keywords: Glaucoma -- Surgery; Eye Surgery -- Methods; Decision Making, Clinical; Intraocular Pressure; Patient Compliance

Practical considerations for the treatment of elderly patients with migraine. - Sarchielli P; Mancini ML; Calabresi P (Drugs & Aging, 2006)
Treatment of migraine presents special problems in the elderly. Co-morbid diseases may prohibit the use of some medications. Moreover, even when these contraindications do not exist, older patients are more likely than younger ones to develop adverse events. Managing older migraine patients, therefore, necessitates particular caution, including taking into account possible pharmacological interactions associated with the greater use of drugs for concomitant diseases in the elderly. Paracetamol (acetaminophen) is the safest drug for symptomatic treatment of migraine in the elderly. Use of selective serotonin 5-HT(1B/1D) receptor agonists ('triptans') is not recommended, even in the absence of cardiovascular or cerebrovascular risk, and NSAID use should be limited because of potential gastrointestinal adverse effects. Prophylactic treatments include antidepressants, beta-adrenoceptor antagonists, calcium channel antagonists and antiepileptics. Selection of a drug from one of these classes should be dictated by the patient's co-morbidities. Beta-adrenoceptor antagonists are appropriate in patients with hypertension but are contraindicated in those with chronic obstructive pulmonary disease, diabetes mellitus, heart failure and peripheral vascular disease. Use of antidepressants in low doses is, in general, well tolerated by elderly people and as effective, overall, as in young adults. This approach is preferred in patients with concomitant mood disorders. However, prostatism, glaucoma and heart disease make the use of tricyclic antidepressants more difficult. Fewer efficacy data in the elderly are available for selective serotonin reuptake inhibitors, which can be tried in particular cases because of their good tolerability profile. Calcium channel antagonists are contraindicated in patients with hypotension, heart failure, atrioventricular block, Parkinson's disease or depression (flunarizine), and in those taking beta-adrenoceptor antagonists and monoamine oxidase inhibitors (verapamil). Antiepileptic drug use should be limited to migraine with high frequency of attacks and refractoriness to other treatments. Promising additional strategies include ACE inhibitors and angiotensin II type 1 receptor antagonists because of their effectiveness and good tolerability in patients with migraine, particularly in those with hypertension. Because of its favourable compliance and safety profile, botulinum toxin type A can be considered an alternative treatment in elderly migraine patients who have not responded to other currently available migraine prophylactic agents. Pharmacological treatment of migraine poses special problems in regard to both symptomatic and prophylactic treatment. Contraindications to triptan use, adverse effects of NSAIDs, and unwanted reactions to some antiemetics reduce the list of drugs available for the treatment of migraine attacks in elderly patients. The choice of prophylactic treatment (beta-adrenoceptor antagonists, calcium channel antagonists, antiepileptics, and more recently, some antihypertensive drugs) is influenced by co-morbidities and should be directed at those drugs that are believed to have fewer adverse effects and a better safety profile. Unfortunately, for most of these drugs, efficacy studies are lacking in the elderly.
Keywords: Migraine -- Drug Therapy; Adrenergic Beta-Antagonists -- Administration and Dosage; Analgesics -- Administration and Dosage; Anticonvulsants -- Administration and Dosage; Antidepressive Agents -- Administration and Dosage; Antiemetics -- Administration and Dosage; Antiinflammatory Agents, Non-Steroidal -- Administration and Dosage; Calcium Channel Blockers -- Administration and Dosage; Drug Interactions; Migraine -- Prevention and Control

Vision. (Mayo Clinic Health Letter, 2010)
The article offers information on age-related eye problems, treatment options and preventive measures. It describes how the brain process human vision. A discussion on age-related eye problems like presbyopia and dry eyes is detailed. The methods used for cataract surgery include using an ultrasound probe to break up the lens for removal and making an incision in the eye and removing the lens. Also discussed are the forms of glaucoma, age-related macular degeneration and other tests and procedures during an eye exam. INSETS: When it's an emergency;Nonprescription reading glasses;Eye floaters;When vision improves
Keywords: Vision; Aging; Vision -- Physiology; Presbyopia; Dry Eye Syndromes; Cataract; Glaucoma; Macular Degeneration; Office Visits; Diagnosis, Eye; Emergencies; Eyeglasses; Foreign Bodies; Ophthalmic Solutions; Dietary Supplements; Diabetes Mellitus

Medical treatment of open-angle glaucoma. - Kyari, Fatima; Abdull, Mohammad; Kiage, Dan; Ogunro, Adunola (Community Eye Health Journal, 2012)
The article discusses the recommended approach in choosing the treatment for open-angle glaucoma. It cites the need to consider the availability, good quality, affordability, and well tolerance of patient in choosing the medical treatment for patient. It also mentions the different way the five main groups of glaucoma drugs act in reducing intraocular pressure (IOP) and the side effects of each drug patient's who are pregnant, with asthma, and sickle-cell anaemia. INSET: How to avoid fake glaucoma drugs: top tips.
Keywords: Glaucoma -- Drug Therapy; Prostaglandins -- Therapeutic Use; Prostaglandins -- Adverse Effects; Costs and Cost Analysis; Health Services Accessibility; Adrenergic Beta-Antagonists; Adrenergic Alpha-Antagonists; Parasympathomimetics; Carbonic Anhydrase Inhibitors; Counterfeit Drugs -- Adverse Effects

Detecting possible glaucoma with only limited equipment: a crucial first step. - 1Philippin, Heiko; Shah, Peter; Burton, Matthew (Community Eye Health Journal, 2012)
The article discusses the basic eye assessment procedures for possible glaucoma with only limited equipment. It recommends the need to know the family history of the patient because primary open-angle glaucoma has a significant inheritable component. It also cites the significance use of Snellen chart, confrontational visual field testing, and hand-held torch to test the visual acuity and visual field defects.
Keywords: Glaucoma -- Diagnosis; Diagnosis, Eye -- Equipment and Supplies; Health Services Accessibility; Patient History Taking; Visual Acuity; Lighting; Visual Fields; Patient Education; Cataract -- Diagnosis

Patients and glaucoma: what are the challenges? (Community Eye Health Journal, 2012)
An interview with Mohammed Abdull, the head of the ophthalmology department at Abubakar Tafawa Balewa University Teaching hospital in Bauchim Nigeria, is presented. When asked on the understanding of people about glaucoma, he states that glaucoma was not known. Abdul explains that the lack of symptoms and poor awareness are some of the reasons that prevent early diagnosis of the disease. He also shares the hospital's effort to encourage people to come forward to diagnose the disease early. INSET: Gender and glaucoma.
Keywords: Glaucoma -- Therapy; Patient Care -- Methods; Health Services Accessibility; Help Seeking Behavior; Patient Attitudes; Health Beliefs

92081-92083 With Modifier 50? Not So Fast. (Ophthalmology Coding Alert, 2011)
Keywords: Glaucoma -- Diagnosis; Coding; Billing and Claims; Current Procedural Terminology; Visual Fields; Office Visits

Telemedicine for eye care. - Tang RA; Morales M; Ricur G; Schiffman JS; Tang, Rosa Ana; Morales, Marlene; Ricur, Giselle; Schiffman, Jade S (Journal of Telemedicine & Telecare, 2005)
Tele-ophthalmology has been employed mainly for patients in under-served rural areas in need of specialty care, but other applications such as telementoring have also been used. In certain populations, cost containment is a significant issue and telemedicine is a solution. Tele-ophthalmology can be performed in realtime, by store-and-forward mode, or by hybrid techniques. After appropriate modification, a range of peripherals may be used for tele-ophthalmology, including the direct ophthalmoscope, indirect ophthalmoscope, slit lamp or retinal camera. Tele-ophthalmology applications include: detecting, screening and diagnosing diabetic retinopathy; anterior segment imaging; glaucoma screening; low vision consultation; telementoring. Tele-ophthalmology shows great promise for improving patient care and increasing access to specialty care not available in under-served areas. In developing countries tele-ophthalmology may be a cost-effective method by which richer countries can assist them.
Keywords: Eye Care -- Methods; Telemedicine; Developing Countries; Health Services Accessibility; Medically Underserved Area; Ophthalmology

Risk factors for contact lens bacterial contamination during continuous wear. - Szczotka-Flynn LB; Bajaksouzian S; Jacobs MR; Rimm A; Szczotka-Flynn, Loretta B; Bajaksouzian, Saralee; Jacobs, Michael R; Rimm, Alfred (Optometry & Vision Science, 2009)
Purpose: Microbial contamination of contact lenses is associated with corneal infection and inflammation. This study determined the microbiological, clinical, and demographic factors that are associated with bacterial contamination of a silicone hydrogel contact lens when worn for continuous wear (CW).Methods: Two hundred five healthy subjects were enrolled in the Longitudinal Analysis of Silicone Hydrogel Contact Lens Study and were fitted with lotrafilcon A lenses for monthly CW and followed for 1 year. Lenses were aseptically removed after 1 week and 4 months of wear and cultured using an agar sandwich technique. Lids and conjunctiva were routinely cultured at baseline and after 1 week and 4 months of CW. Lenses and ocular sites were considered to have substantial microbial bioburden when they harbored pathogenic organisms or high levels of commensal organisms. Univariate and multivariate logistic regression analyses were conducted to examine whether substantial conjunctival or lid bioburden, subject demographics, lens-wearing history, symptoms, and biomicroscopic signs were associated with lens bioburden.Results: About one third (32.4%) of subjects had substantial bacterial bioburden in either eye across multiple visits. Over half (53.2%) and about one tenth (11.7%) of subjects had substantial lid and conjunctival bioburden, respectively, and 11.2% discontinued because of discomfort. The adjusted odds ratios (and 95% confidence intervals) for presence of substantial lens bioburden were 2.49 (1.17-5.30), 4.24 (1.45-12.40), and 4.11 (1.17-14.46) for substantial lid bioburden, substantial conjunctival bioburden, and lens discomfort, respectively.Conclusions: Bacterial contamination of silicone hydrogel contact lenses is common during CW. Substantial lens bioburden is associated with discomfort precluding successful CW. The presence of substantial lid and conjunctival bioburden is associated with a 2.5-fold and more than fourfold greater risk of substantial lens bioburden and is likely the major route of contamination.
Keywords: Bacteria; Contact Lenses, Extended-Wear; Contact Lenses; Equipment Contamination; Adolescence; Adult; Prospective Studies; Colony Count, Microbial; Conjunctiva -- Microbiology; Eyelids -- Microbiology; Human; Gels; Middle Age; Multivariate Analysis; Office Visits; Risk Factors; Silicones; Young Adult

Systemic side effects of ophthalmic drops. - Levy Y; Zadok D (Clinical Pediatrics, 2004)
Topical application of ocular drugs may cause serious adverse ocular or systemic side effects. Children are at greater risk for systemic side effects because ocular dosing is not weight-adjusted, and infants are especially vulnerable as a consequence of the inability to efficiently metabolize the drug, and/or an immature blood-brain barrier. Four pediatric patients are reported in whom treatment with topical brimonidine, a selective alpha-2 adrenoceptor agonist, indicated for the treatment of glaucoma, produced somnolence. Anti-glaucoma eyedrops that are not approved for use in children are still used frequently in pediatrics. Therefore, physicians should be aware of possible systemic side effects of ophthalmic drops.
Keywords: Glaucoma -- Drug Therapy -- In Infancy and Childhood; Ophthalmic Solutions -- Adverse Effects -- In Infancy and Childhood; Child, Preschool; Infant

LED stereo slit lamp biomicroscope provides long bulb life with low heat radiation...including commentary by Hovanesian JA - Houck K; Hovanesian JA (Ocular Surgery News, 2010)
The system can be useful in teleophthalmology, and in the future, it may be used for remote treatment.
Keywords: Diagnosis, Eye -- Equipment and Supplies; Equipment Design; Diabetic Retinopathy -- Diagnosis; Glaucoma -- Diagnosis; Macular Degeneration -- Diagnosis; Patient Compliance; Telemedicine

Adherence, Predicting Factors and Satisfaction of Patients on Glaucoma Therapy: Findings From a Cross-Sectional Study in Korea. - Park, K.H.; Cha, J.H. (Value in Health, 2014)

Medication Adherence and Discontinuation Predicted by Disease Duration in Glaucoma Patients: Findings From A Cross-Sectional Study in Korea. - Park, K.H.; Cha, J.H. (Value in Health, 2014)

The use of 5-fluorouracil in glaucoma filtration surgery. - Langseth FG (Insight: The Journal of the American Society of Ophthalmic Registered Nurses, 1993)
Failure of glaucoma filtration surgery usually results from scarring at the surgical site. Studies have shown that fibroblast proliferation plays an important role in scar formation which results in a mechanical barrier to filtration (Gressel, Parrish, & Folberg, 1984). Fibroblasts are immature collagen-producing cells which proliferate at the site of chronic inflammation. The antimetabolite 5-fluorouracil (5-FU) can inhibit fibroblast activity. Over the past ten years, the adjunctive use of 5-FU in filtration surgery has met with increased success and is particularly indicated in those patients at greatest risk of filtration failure.
Keywords: Glaucoma -- Surgery; Fluorouracil -- Therapeutic Use; Cicatrix -- Prevention and Control; Clinical Trials; Middle Age; Aged; Male; Female; Human

Adherence to NICE guidelines for new glaucoma referrals. - Chaudhary, R; Dhillion, N; Jones, L; Dhillon, N (Eye, 2013)
Keywords: Glaucoma -- Diagnosis; Guideline Adherence -- Standards; Practice Guidelines; Great Britain; National Health Programs

Psychometric properties of the glaucoma treatment compliance assessment tool in a multicenter trial. - Barker, Gordon T; Cook, Paul F; Schmiege, Sarah J; Kahook, Malik Y; Kammer, Jeffrey A; Mansberger, Steven L (American Journal of Ophthalmology, 2015)
Keywords: Antihypertensive Agents -- Administration and Dosage; Glaucoma -- Drug Therapy; Health Behavior; Medication Compliance; Models, Psychological; Psychometrics; Questionnaires; Aged; Attitude to Health; Clinical Assessment Tools; False Positive Results; Female; Glaucoma -- Psychosocial Factors; Human; Male; Middle Age; Models, Statistical; Ocular Hypertension -- Drug Therapy; Ocular Hypertension -- Psychosocial Factors; Ophthalmic Solutions; Patient Attitudes; Predictive Value of Tests; Reproducibility of Results; Scales

Compliance and persistency in glaucoma follow-up treatment. - Schwartz, Gail F (Current Opinion in Ophthalmology, 2005)
Purpose Of Review: To summarize research published between 1980 and October 2004 regarding compliance (the extent to which patients' behaviors correspond with providers' recommendations) and persistency (total time on therapy) in patients diagnosed with open-angle glaucoma or ocular hypertension; to suggest approaches ophthalmologists might consider to improve compliance and persistency; and to identify areas warranting future research.Recent Findings: Medication compliance, the focus of most compliance-related research, has been measured using a variety of methods including patient self-reports, the medication possession ratio, and electronic monitoring. Noncompliance rates of at least 25% commonly have been reported. The primary obstacles to medication compliance appear to be situational/environmental (e.g., being away from home or a change in routine) or related to the medication regimen (e.g., side effects or complexity). Persistency with ocular hypotensive therapies has been found to be poor. Retrospective cohort studies using survival analyses have reported that fewer than 25% of patients are persistent over 12 months.Summary: Accurately assessing patient compliance and persistency is important to optimizing patient care. Physicians may mistake either medication noncompliance or lack of persistency with poor efficacy. Such errors would likely increase health care costs if they result in unnecessary changes to a patient's therapeutic regimen or in surgery.
Keywords: Antihypertensive Agents -- Therapeutic Use; Glaucoma -- Drug Therapy; Patient Compliance; Patient Dropouts -- Statistics and Numerical Data; Treatment Outcomes; Physician-Patient Relations; Retrospective Design; Health Care Delivery -- Standards; Prospective Studies; Health Care Delivery -- Methods

Medication adherence in glaucoma: approaches for optimizing patient compliance. - Tsai, James C. (Current Opinion in Ophthalmology, 2006)
PURPOSE OF REVIEW: To summarize recent literature regarding medication adherence with a focus on the complexities inherent in glaucoma management. RECENT FINDINGS: Adherence to medications can be enhanced by undertaking the following strategies: enhanced patient education; improved dosing schedules; increased accessibility to healthcare (including longer hours, evening hours, and shorter wait times), and improved provider-patient relationships (e.g. increased trust). Patients may be less likely to forgo medication use due to cost pressures if the physician trust level is high. Recent studies suggest a role for baseline screening for adherence predictors and focused interventions in addressing modifiable risk factors for poor adherence (such as depression, stress, and lower education). SUMMARY: Many factors are associated with the lack of medication adherence in patients. The solution is likely to be multi-dimensional and employ combination strategy (must be individualized for the patient). Educational interventions involving patients, family members, or both can be effective in improving adherence.
Keywords: Medication Compliance -- Evaluation; Patient Compliance -- Evaluation; Disease Management -- Methods; Drug Administration Schedule; Glaucoma -- Therapy; Health Services Accessibility -- Evaluation; Ophthalmology; Patient Education -- Methods; Physician-Patient Relations

Impact of patient access to internet health records on glaucoma medication: randomized controlled trial. - Kenji Kashiwagi; Shigeo Tsukahara (Journal of Medical Internet Research, 2014)
BACKGROUND: Glaucoma is one of the leading causes of blindness. Reduction of intraocular pressure is the only proven way to prevent progression of glaucomatous optic neuropathy. The majority of glaucoma patients need to use antiglaucoma ophthalmic solutions over the course of their life. Thus, good adherence and persistency of glaucoma treatment are important factors for better glaucoma care. OBJECTIVE: The purpose of this study was to investigate the impact of an Internet-based glaucoma care support system on glaucoma medication use. METHODS: Patients were randomly divided into two groups. The non-Internet access (NIA) group consisted of patients who had access to the Internet-based glaucoma care support system during the 4-year period only when they were examined by ophthalmologists. The Internet access (IA) group consisted of patients who had the same Internet-based glaucoma care support system access as the NIA group for the first 2 years following enrollment but who were also given free access to the glaucoma care support system for the remaining 2 years. Changes in glaucoma medication use were investigated. RESULTS: In total, 81 patients in the IA group and 90 patients in the NIA group satisfied the study protocol. The number of antiglaucoma ophthalmic solutions used during the study period significantly increased in the NIA group (P<.03) but not in the IA group. The percentages of patients with unchanged, increased, and decreased antiglaucoma ophthalmic solution use during the study period were 61.1% (55/90), 17.8% (16/90), and 3.3% (3/90), respectively, in the NIA group, and 56.8% (46/81), 8.6% (7/81), and 13.6% (11/81), respectively, in the IA group (P<.001). Internet access significantly shifted from an increasing intraocular pressure trend to a decreasing trend in the IA group (P=.002) among the patients who did not have any medication changes. CONCLUSIONS: Allowing patients to browse their medical data may reduce the use and improve the effectiveness of glaucoma medication. TRIAL REGISTRATION: UMIN-CTR Clinical Trial Number: UMIN000006982; https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr.cgi?function=bro ws&action=brows&type=summary&recptno=R000008238&language=E (Archived by WebCite at http://www.webcitation.org/6MRPQeEAv).
Keywords: Access to Information; Glaucoma -- Drug Therapy; Internet; Human; Ophthalmic Solutions; Prospective Studies; Single-Blind Studies

POINT / COUNTER. (Ocular Surgery News, 2018)
Keywords: Glaucoma -- Therapy; Drug Delivery Systems; Patient Compliance

Biomechanics of Schlemm's canal endothelium and intraocular pressure reduction. - Stamer, W Daniel; Braakman, Sietse T; Zhou, Enhua H; Ethier, C Ross; Fredberg, Jeffrey J; Overby, Darryl R; Johnson, Mark (Progress in Retinal & Eye Research, 2015)
Ocular hypertension in glaucoma develops due to age-related cellular dysfunction in the conventional outflow tract, resulting in increased resistance to aqueous humor outflow. Two cell types, trabecular meshwork (TM) and Schlemm's canal (SC) endothelia, interact in the juxtacanalicular tissue (JCT) region of the conventional outflow tract to regulate outflow resistance. Unlike endothelial cells lining the systemic vasculature, endothelial cells lining the inner wall of SC support a transcellular pressure gradient in the basal to apical direction, thus acting to push the cells off their basal lamina. The resulting biomechanical strain in SC cells is quite large and is likely to be an important determinant of endothelial barrier function, outflow resistance and intraocular pressure. This review summarizes recent work demonstrating how biomechanical properties of SC cells impact glaucoma. SC cells are highly contractile, and such contraction greatly increases cell stiffness. Elevated cell stiffness in glaucoma may reduce the strain experienced by SC cells, decrease the propensity of SC cells to form pores, and thus impair the egress of aqueous humor from the eye. Furthermore, SC cells are sensitive to the stiffness of their local mechanical microenvironment, altering their own cell stiffness and modulating gene expression in response. Significantly, glaucomatous SC cells appear to be hyper-responsive to substrate stiffness. Thus, evidence suggests that targeting the material properties of SC cells will have therapeutic benefits for lowering intraocular pressure in glaucoma.
Keywords: Kinematics -- Physiology; Epithelial Cells -- Physiology; Glaucoma -- Physiopathology; Intraocular Pressure -- Physiology; Anterior Eye Segment -- Physiology; Aqueous Humor -- Metabolism; Cell Physiology; Perfusion

Glaucoma treatment adherence difficult to measure, improve. (Ocular Surgery News, 2012)
Keywords: Glaucoma -- Drug Therapy; Medication Compliance -- Evaluation

Injectable glaucoma medicine: a possible answer to compliance issues. (Ocular Surgery News, 2014)
Keywords: Glaucoma -- Therapy; Injections; Patient Compliance -- Evaluation; Ophthalmology; Serial Publications; Administration, Topical; Patient Care; Intraocular Pressure; Bimatoprost -- Administration and Dosage

Injectable glaucoma medicine: a possible answer to compliance issues. (Ocular Surgery News, 2014)
The article reports that a sustained-release version of bimatoprost is in phase 3 U.S. Food and Drug Administration trials that if proven safe and effective can be applied by anterior segment surgeons in the same way anti-VEGF solutions are injected for neovascular age-related macular degeneration.
Keywords: Glaucoma -- Therapy; Injections; Patient Compliance -- Evaluation; Ophthalmology; Serial Publications; Administration, Topical; Patient Care; Intraocular Pressure; Bimatoprost -- Administration and Dosage

Simple communication techniques help physicians address glaucoma medication compliance. (Ocular Surgery News, 2014)
Keywords: Medication Compliance; Glaucoma -- Drug Therapy; Communication -- Methods; Physicians

Simple communication techniques help physicians address glaucoma medication compliance. - Cimberle, Michela (Ocular Surgery News, 2014)
The article highlights a 1-day course undertaken by a group of physicians intended to improve communication skills in a clinical setting where a speaker indicated that learning communication skills allow physicians to improve patients' risk awareness.
Keywords: Medication Compliance; Glaucoma -- Drug Therapy; Communication -- Methods; Physicians

Role of ophthalmic nurses with visually impaired patients. - Barton W (Insight: The Journal of the American Society of Ophthalmic Registered Nurses, 1998)
In 1987, it was estimated that over 13 million people in the world were visually impaired, and more than 27 to 35 million were classified as blind. Greater than 6 million visually impaired people live in the United States. There are many causes of visual impairment, including age-related macular degeneration, cataracts, glaucoma, diabetic retinopathy, autoimmune deficiency syndrome, and trauma. Some patients may be helped or visual loss delayed with surgery. Many may have dramatic visual improvement with optical devices, large-print publications, and improved lighting. The ophthalmic nurse may assist in accurately assessing the patient's vision and identifying his or her lifestyle and ability to function independently. Assisting the patient to overcome psychosocial and economic barriers and helping to obtain assistance is critical to enable patients to function independently. Ophthalmic nurses may be instrumental in increasing patients' awareness of community resources and services available to those who are visually impaired.
Keywords: Vision Disorders -- Nursing; Ophthalmic Nursing; Nursing Role; Vision Disorders -- Classification; Rehabilitation of Vision Impaired; Vision Disorders -- Etiology

Gradual loss of vision. - Reich J (Australian Family Physician, 1998)
BACKGROUND: With the increasing age of our population many of the causes of vision loss are becoming more frequent. Not all gradual loss of vision can be considered non urgent and those patients requiring early attention are highlighted. OBJECTIVE: This article discusses the tools available to the general practitioner for the assessment of visual loss as well as the common causes. DISCUSSION: Advances in cataract surgery with improved visual outcome, minimally invasive surgery and a reduction in surgical risk have made this operation the commonest performed in Australia. Blindness from chronic open angle glaucoma and diabetes can be mostly prevented by early diagnosis and compliance with treatment. Age related macular degeneration apart from a small subgroup, is still largely untreatable.
Keywords: Vision Disorders -- Etiology; Refractive Errors; Vision Disorders -- Diagnosis; Vision Tests; Ophthalmoscopy; Myopia; Astigmatism; Amblyopia; Diabetic Retinopathy; Cataract; Glaucoma; Macular Degeneration

Infections after keratoprosthesis. - Davies, Emma; Chodosh, James (Current Opinion in Ophthalmology, 2016)
Purpose Of Review: The purpose is to provide an overview of the recent advancements in the diagnosis and treatment of microbial keratitis and endophthalmitis after keratoprosthesis implantation.Recent Findings: The addition of vancomycin daily to a fluoroquinolone in the postoperative management of keratoprosthesis patients successfully reduced the number of cases of bacterial keratitis and endophthalmitis with an increased number of fungal infections now documented both in the United States and abroad.Summary: Compliance with the regimen of a fluoroquinolone and vancomycin daily for life after keratoprosthesis implantation should be stressed with the patient. Further research is needed to investigate whether intermittent use of 5% povidone-iodine and frequent replacement of the bandage contact lens could reduce fungal infection after keratoprosthesis surgery. Future advancements in the Boston keratoprosthesis design and/or postoperative management are needed to further reduce infection after keratoprosthesis placement.
Keywords: Prostheses and Implants -- Adverse Effects; Keratitis -- Etiology; Antibiotics -- Therapeutic Use; Eye Infections, Bacterial -- Etiology; Eye Infections, Fungal -- Etiology; Endophthalmitis -- Etiology; Postoperative Complications -- Microbiology; Eye Infections, Fungal -- Diagnosis; Eye Infections, Bacterial -- Diagnosis; Endophthalmitis -- Therapy; Eye Infections, Fungal -- Therapy; Keratitis -- Therapy; Eye Infections, Bacterial -- Therapy; Endophthalmitis -- Diagnosis; Cornea -- Surgery; Keratitis -- Diagnosis; Artificial Organs

Expert: knowing guidelines will help avoid audit trap. - Asbell RL (Ocular Surgery News, 2008)
Each subspecialty has its own guidelines that must be followed.
Keywords: Insurance, Health, Reimbursement; Medicare; Ophthalmology -- Standards; Audit; Cataract Extraction; Coding; Corneal Diseases -- Surgery; Current Procedural Terminology; Diagnosis, Eye; Documentation; Fees and Charges; Glaucoma; International Classification of Diseases; Office Visits -- Economics; Retinal Diseases -- Surgery; Surgery, Plastic

Understanding why patients with cataract refuse free surgery: the influence of rumours in Kenya. - Briesen S; Geneau R; Roberts H; Opiyo J; Courtright P (Tropical Medicine & International Health, 2010)
Keywords: Literature; Cataract -- Psychosocial Factors; Cataract Extraction -- Psychosocial Factors; Treatment Refusal -- Psychosocial Factors; Adult; Aged; Cataract -- Economics; Cataract Extraction -- Economics; Communication; Decision Making; Female; Glaucoma -- Economics; Glaucoma -- Therapy; Attitude to Health; Health Services Accessibility -- Economics; Human; Kenya; Male; Middle Age; Qualitative Studies; Quality of Life; Treatment Refusal -- Statistics and Numerical Data; Visual Acuity

Physician-patient relationship is among the keys to better compliance. - Gonzalez JM (Ocular Surgery News, 2003)
Glaucoma subspecialists and others share tips for improving patient compliance. Communication is key.
Keywords: Glaucoma -- Therapy; Patient Compliance; Physician-Patient Relations; Ophthalmic Solutions -- Therapeutic Use; Patient Education

You be the coder. - Mac MM (Ophthalmology Coding Alert, 2010)
Keywords: Coding; Glaucoma -- Surgery; Office Visits; Operating Rooms

Travoprost/timolol : a viewpoint by Robert J. Noecker. - Noecker RJ (Drugs & Aging, 2006)
Keywords: Drug Combinations -- Therapeutic Use; Glaucoma -- Drug Therapy; Timolol -- Therapeutic Use; Travoprost -- Therapeutic Use; Patient Compliance

Travoprost/timolol: a viewpoint by Anastasios G.P. Konstas. - Konstas AG (Drugs & Aging, 2006)
Keywords: Drug Combinations -- Therapeutic Use; Glaucoma -- Drug Therapy; Timolol -- Therapeutic Use; Travoprost -- Therapeutic Use; Drug Administration Schedule; Drug Combinations -- Administration and Dosage; Glaucoma -- Complications; Intraocular Pressure; Patient Compliance; Timolol -- Administration and Dosage; Travoprost -- Administration and Dosage

Research on fear appeals to enhance compliance for patients with glaucoma to topical medication. - Limei, Chen (Chinese Nursing Research, 2012)
Objective: To probe into the influence of the fear appeal on topical medication compliance behavior of glaucoma patients. Methods: A quasi -experimental design.192 cases of glaucoma patients were selected conveniently in our hospital from ophthalmology outpatient from January to June in 2010. These patients were divided into experimental group and control group by throwing a coin law studies. after the routine outpatient process finished. the experimental group received fear appeals through the way of interpretation of poster information by nurses. the control group were not given a fear appeal messages. 2 weeks later. the two groups were called return about compliance to doctor's advice. compared two groups of patients'compliance behavior difference. Results: The two groups of patients' data baseline have comparability. After two weeks. the patients in the experimental group compliance scored higher than the control group. the difference was statistically significant. Conclusion: Fear appeals can promote the local medication compliance of glaucoma patients.
Keywords: Fear; Glaucoma -- Drug Therapy; Patient Compliance; Administration, Topical; Chi Square Test; Convenience Sample; Data Analysis Software; Human; Quasi-Experimental Studies

The impact of ocular adverse effects in patients treated with topical prostaglandin analogs: changes in prescription patterns and patient persistence. - Zimmerman TJ; Hahn SR; Gelb L; Tan H; Kim EE (Journal of Ocular Pharmacology & Therapeutics, 2009)
Keywords: Antihypertensive Agents -- Adverse Effects; Patient Compliance; Practice Patterns -- Statistics and Numerical Data; Prostaglandins, Synthetic -- Adverse Effects; Administration, Topical; Adult; Amides -- Adverse Effects; Amides -- Therapeutic Use; Antihypertensive Agents -- Therapeutic Use; Drugs, Prescription; Glaucoma -- Drug Therapy; Hyperemia -- Chemically Induced; Ophthalmic Solutions; Pharmacy Service; Prostaglandins, Synthetic -- Analogs and Derivatives; Prostaglandins, Synthetic -- Therapeutic Use; Resource Databases; Retrospective Design; Human

Best practice contact lens care: a review of the Asia Pacific Contact Lens Care Summit. - Sweeney D; Holden B; Evans K; Ng V; Cho P (Clinical & Experimental Optometry, 2009)
Keywords: Contact Lenses -- Adverse Effects; Hygiene; Practice Guidelines; Eye Infections -- Etiology; Eye Infections -- Prevention and Control; Keratitis -- Etiology; Keratitis -- Prevention and Control; Ophthalmic Solutions; Patient Compliance; Patient Education

Communication key to addressing noncompliance with medication. (Ocular Surgery News, 2009)
Keywords: Communication; Glaucoma -- Drug Therapy; Medication Compliance; Physician-Patient Relations

Not all medication adherence issues apparent to ophthalmologists. (Ocular Surgery News, 2010)
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Communication; Patient Attitudes; Physician-Patient Relations

Monitoring visual status: why patients do or do not comply with practice guidelines. - Sloan FA; Brown DS; Carlisle ES; Picone GA; Lee PP; Sloan, Frank A; Brown, Derek S; Carlisle, Emily Streyer; Picone, Gabriel A; Lee, Paul P (Health Services Research, 2004)
Objective: To determine factors affecting compliance with guidelines for annual eye examinations for persons diagnosed with diabetes mellitus (DM) or age-related macular degeneration (ARMD).Data Sources/study Setting: Nationally representative, longitudinal sample of individuals 65+ drawn from the National Long-Term Care Survey (NLTCS) with linked Medicare claims records from 1991 to 1999.Study Design: Medicare beneficiaries were followed from 1991 to 1999, unless mortality intervened. All claims data were analyzed for presence of ICD-9 codes indicating diagnosis of DM or ARMD and the performance of eye exams. The dependent variable was a binary indicator for whether a person had an eye exam or not during a 15-month period. Independent variables for demographics, living conditions, supplemental insurance, income, and other factors affecting the marginal cost and benefit of an eye exam were assessed to determine reasons for noncompliance.Data Collection/extraction Methods: Panel data were created from claims files, 1991-1999, merged with data from the NLTCS.Principal Findings: The probability of having an exam reflected perceived benefits, which vary by patient characteristics (e.g., education, no dementia), and factors associated with the ease of visit. African Americans were much less likely to be examined than were whites.Conclusions: Having an exam reflects multiple factors. However, much of the variation in the probability of an exam remained unexplained as were reasons for the racial differences in use.
Keywords: Diabetic Retinopathy -- Prevention and Control -- In Old Age; Macular Degeneration -- Prevention and Control -- In Old Age; Patient Compliance -- In Old Age; Vision Screening -- Utilization -- In Old Age; Aged; Comorbidity; Confidence Intervals; Descriptive Statistics; Diabetes Mellitus -- Complications; Diabetic Retinopathy -- Epidemiology; Diagnosis, Eye; Eye Diseases -- Prevention and Control; Funding Source; Glaucoma -- Prevention and Control; Macular Degeneration -- Epidemiology; Medicare; Odds Ratio; Practice Guidelines; Probability; Prospective Studies; Regression; Socioeconomic Factors; Vision Tests; Human

Generic latanoprost may improve patients adherence with lower costs vs. brand-name agents. - Kahl, Kristie L. (Ocular Surgery News, 2015)
Keywords: Latanoprost; Medication Compliance; Health Care Costs; Glaucoma; Minority Groups; Race Factors; Cost Benefit Analysis; Drugs, Generic

Several factors increase risk of severe keratitis due to contact lens use. - Bechtel B; Boyle EL; Hasson M; Mullin DW (Ocular Surgery News, 2009)
Keywords: Contact Lenses -- Adverse Effects; Keratitis -- Risk Factors; Environment; Keratitis -- Physiopathology; Keratitis -- Symptoms; Patient Compliance; Time Factors

Guidelines empower practitioners, encourage compliance. - Vasta S (Ocular Surgery News, 2010)
Preferred practice pattern guidelines support opthalmologists in making decisions about appropriate care.
Keywords: Empowerment; Ophthalmology -- Standards; Practice Guidelines; Professional Compliance; Glaucoma -- Therapy

Lowering IOP With Stents...IntraOcular Pressure - Schweitzer, Justin (Optometric Management, 2014)
Keywords: Glaucoma -- Surgery; Minimally Invasive Procedures; Stents; Patient Safety; Eye Hemorrhage; Patient Compliance; Coding; Disease Progression -- Prevention and Control

Vision. (Mayo Clinic Health Letter, 2010)
Keywords: Vision; Aging; Vision -- Physiology; Presbyopia; Dry Eye Syndromes; Cataract; Glaucoma; Macular Degeneration; Office Visits; Diagnosis, Eye; Emergencies; Eyeglasses; Foreign Bodies; Ophthalmic Solutions; Dietary Supplements; Diabetes Mellitus

Re: Adherence to NICE guidelines for new glaucoma referrals...Eye (Lond). 2013 Apr;27(4):571-2 - Sullivan, L; Burton, D; Bong, C; Galloway, P (Eye, 2014)
Keywords: Glaucoma -- Diagnosis; Guideline Adherence -- Standards; Practice Guidelines

Complications never fully eliminated, despite unprecedented technologies. - Wolkoff L; Cruz D (Ocular Surgery News, 2006)
Keywords: Administration, Intraocular -- Adverse Effects; Cataract Extraction; Glaucoma -- Surgery; Laser Therapy -- Methods; Postoperative Complications; Postoperative Pain -- Prevention and Control; Refractive Errors -- Surgery; Eye Surgery -- Legislation and Jurisprudence -- United States; Intraocular Pressure; Iris -- Pathology; Keratomileusis, Laser in Situ -- Equipment and Supplies; Legal Procedure -- Economics; Lenses, Intraocular; Meetings -- New York; New York; Ophthalmology -- Trends; Patient Compliance; Patient Satisfaction; Presbyopia -- Surgery; Surgeons; Eye Surgery -- Adverse Effects; Eye Surgery -- Economics; Eye Surgery -- Methods; United States

Discuss medication costs with patients to reduce adherence issues. (Ocular Surgery News, 2009)
Keywords: Costs and Cost Analysis; Drugs, Prescription -- Economics; Medication Compliance; Counseling; Decision Making, Clinical; Glaucoma -- Drug Therapy; Medical Orders; Physician-Patient Relations

Ocular surface disease management. The role of next generation combination agents. - Lindstrom RL; Donnenfeld ED; Lane SS; Holland EJ; Sheppard JD (Ocular Surgery News, 2006)
Keywords: Drug Combinations -- Therapeutic Use; Eye Diseases -- Drug Therapy; Administration, Topical; Adrenal Cortex Hormones -- Administration and Dosage; Adrenal Cortex Hormones -- Adverse Effects; Adrenal Cortex Hormones -- Pharmacodynamics; Adrenal Cortex Hormones -- Therapeutic Use; Animal Studies; Antibiotics -- Adverse Effects; Antibiotics -- Therapeutic Use; Antiinflammatory Agents -- Therapeutic Use; Clinical Trials; Conjunctivitis -- Drug Therapy; Conjunctivitis -- Microbiology; Contact Lenses -- Adverse Effects; Dexamethasone -- Adverse Effects; Diagnosis, Eye -- Methods; Drug Combinations -- Economics; Drug Resistance, Microbial; Drugs, Generic; Dry Eye Syndromes -- Complications; Eye Diseases -- Complications; Eye Diseases -- Microbiology; Infection -- Drug Therapy; Inflammation -- Drug Therapy; Inflammation -- Etiology; Intraocular Pressure -- Drug Effects; Keratitis -- Drug Therapy; Keratitis -- Microbiology; Microbial Culture and Sensitivity Tests; Ophthalmic Solutions; Patient Compliance; Patient Satisfaction; Patient Selection; Physician Attitudes; Risk Assessment; Surgeons; Tobramycin -- Administration and Dosage; Tobramycin -- Pharmacodynamics; Tobramycin -- Therapeutic Use; Treatment Outcomes; Uveitis -- Drug Therapy

APAO's 'Vision for the future' meeting sees continued growth. - Mullin DW; Schultz J (Ocular Surgery News, 2006)
The Asia-Pacific Academy of Ophthalmology meeting held in conjunction with the AAO and APACRS was large i nattendance and program scope.
Keywords: Amnion; Corneal Diseases -- Surgery; Diabetic Retinopathy; Dry Eye Syndromes; Fluorouracil -- Therapeutic Use; Glaucoma -- Surgery; Keratomileusis, Laser in Situ; Lenses, Intraocular; Patient Compliance; Phacoemulsification -- Methods; Photodynamic Therapy; Polymers -- Adverse Effects; Retinal Diseases -- Diagnosis; Eye Surgery -- Methods; Congresses and Conferences -- Singapore; Contact Lenses -- Adverse Effects; Disease Outbreaks; Glaucoma -- Drug Therapy; Intraocular Pressure -- Drug Effects; Laser Therapy -- Equipment and Supplies; Ophthalmology -- Organizations; Patient Education; Presbyopia -- Surgery; Retinal Diseases -- Familial and Genetic; Retinal Diseases -- Surgery; Singapore; Surgeons

Addressing new risk factors could improve patient management. - Samples JR (Ocular Surgery News, 2006)
Keywords: Glaucoma -- Risk Factors; Blood Pressure; Circadian Rhythm; Cornea -- Pathology; Disease Progression; Glaucoma -- Drug Therapy; Glaucoma -- Familial and Genetic; Intraocular Pressure -- Drug Effects; Ocular Hypertension; Patient Compliance

DEALING WITH NON-COMPLIANCE. - MILLER, JASON R. (Optometric Management, 2018)
Keywords: Contact Lenses -- Adverse Effects; Patient Compliance; Eye Care -- Education; Corneal Ulcer -- Risk Factors; Eye Infections -- Risk Factors

Clinical trials for glaucoma neuroprotection are not impossible. - Quigley HA; Quigley, Harry A (Current Opinion in Ophthalmology, 2012)
Purpose Of Review: To discuss issues that affect development of new glaucoma treatments known as neuroprotection.Recent Findings: There are barriers to neuroprotection trials for glaucoma.Summary: With design features discussed in the review, neuroprotection trials can be effectively carried out.
Keywords: Glaucoma -- Therapy; Neuroprotective Agents; Clinical Trials -- Evaluation; Glaucoma -- Diagnosis; Glaucoma -- Physiopathology; Ophthalmology; Outcomes (Health Care); Retina -- Anatomy and Histology; Visual Fields -- Evaluation

Theoretical and empirical dimensions of the Aberdeen Glaucoma Questionnaire: a cross sectional survey and principal component analysis. - Prior, Maria; Ramsay, Craig R; Burr, Jennifer M; Campbell, Susan E; Jenkinson, David J; Asoaka, Ryo; Francis, Jillian J (BMC Ophthalmology, 2013)
Background: To develop patient-reported outcome instruments, statistical techniques (e.g., principal components analysis; PCA) are used to examine correlations among items and identify interrelated item subsets (empirical factors). However, interpretation and labelling of empirical factors is a subjective process, lacking precision or conceptual basis. We report a novel and reproducible method for mapping between theoretical and empirical factor structures. We illustrate the method using the pilot Aberdeen Glaucoma Questionnaire (AGQ), a new measure of glaucoma-related disability developed using the International Classification of Functioning and Disability (ICF) as a theoretical framework and tested in a sample representing the spectrum of glaucoma severity.Methods: We used the ICF to code AGQ item content before mailing the AGQ to a UK sample (N = 1349) selected to represent people with a risk factor for glaucoma and people with glaucoma across a range of severity. Reflecting uncertainty in the theoretical framework (items with multiple ICF codes), an exploratory PCA was conducted. The theoretical structure informed our interpretation of the empirical structure and guided the selection of theoretically-derived factor labels. We also explored the discrimination of the AGQ across glaucoma severity groups.Results: 656 (49%) completed questionnaires were returned. The data yielded a 7-factor solution with a simple structure (using cut-off point of a loading of 0.5) that together accounted for 63% of variance in the scores. The mapping process resulted in allocation of the following theoretically-derived factor labels: 1) Seeing Functions: Participation; 2) Moving Around & Communication; 3) Emotional Functions; 4) Walking Around Obstacles; 5) Light; 6) Seeing Functions: Domestic & Social Life; 7) Mobility. Using the seven factor scores as independent variables in a discriminant function analysis, the AGQ scores resulted in correct glaucoma severity grading of 32.5% of participants (p < 0.001).Conclusions: This paper addresses a methodological gap in the application of classical test theory (CTT) techniques, such as PCA, in instrument development. Labels for empirically-derived factors are often selected intuitively whereas they can inform existing bodies of knowledge if selected on the basis of theoretical construct labels, which are more explicitly defined and which relate to each other in ways that are evidence based.
Keywords: Disability Evaluation; Glaucoma -- Diagnosis; Questionnaires; Self Report -- Standards; Aged; Cross Sectional Studies; Empirical Research; Female; Health Status; Human; Male; Middle Age; Pilot Studies; Factor Analysis; Reproducibility of Results; Severity of Illness Indices

Patients report better understanding of compliance after program. (Ocular Surgery News, 2009)
Keywords: Community Programs; Glaucoma -- Drug Therapy; Medication Compliance; Patient Education; Patient Attitudes

Group offers services to Zambians with little access to eye care. - Boyle EL (Ocular Surgery News, 2008)
Nonprofit organization seeks to address need in Africa for congenital cataract surgery in children and glaucoma and cataract treatment in adults
Keywords: Health Services Accessibility; Eye Surgery -- Methods -- Zambia; Cataract Extraction; Drugs, Prescription -- Economics; Glaucoma -- Drug Therapy; Glaucoma -- Surgery; Health Facilities; Medication Compliance; Organizations; Poverty; Volunteer Workers; Zambia

Study finds majority of patients instill glaucoma drops improperly. - Kronemyer, Bob (Ocular Surgery News, 2012)
The article discusses a study which finds that the majority of patients with glaucoma tend to apply the drops improperly aiding to non-compliance with therapy, wherein the drop fell out of their eye or they touched the tip of the bottle unlike recommended.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Ophthalmic Solutions -- Administration and Dosage

Adherence to drug regimens may increase with generics. - Charters, Lynda; Stein, Joshua D. (Ophthalmology Times, 2015)
Keywords: Glaucoma -- Drug Therapy; Medication Compliance -- Evaluation; Drugs, Generic

Bimatoprost adherence, persistence superior in prior latanoprost users. - Guttman Krader, Cheryl; Schwartz, Gail F. (Ophthalmology Times, 2015)
Keywords: Latanoprost; Bimatoprost; Glaucoma -- Drug Therapy; Guideline Adherence -- Evaluation; Medication Compliance -- Evaluation

Compliance still often a missing link in glaucoma therapy. - Boyle EL (Ocular Surgery News, 2006)
Economics and patient education can play a role in patients' adherence to glaucoma treatment regimes.
Keywords: Glaucoma -- Therapy; Patient Compliance; Communication; Comorbidity; Glaucoma -- Drug Therapy; Glaucoma -- Economics; Glaucoma -- Surgery; Medication Compliance; Patient Education; Physician's Role; Physician-Patient Relations; Surgeons

Physicians should employ dialogue strategies to enhance compliance. - Kahook MY (Ocular Surgery News, 2008)
Keywords: Communication; Glaucoma -- Drug Therapy; Medication Compliance; Health Knowledge; Patient Attitudes; Physician-Patient Relations

Older adults with glaucoma more prone to cognitive impairment, depression. - Kronemyer, Bob (Ocular Surgery News, 2012)
The article reports on the results of a study by Brian P. Yochim published in the "Journal of Glaucoma" which showed that older adults with glaucoma have higher rates of cognitive impairment and depression compared with healthy counterparts. The tests for detecting dementia used in the study are cited. The implication of the study results for the patients' adherence to a treatment regimen is tackled.
Keywords: Glaucoma -- Complications -- In Old Age; Dementia -- Risk Factors -- In Old Age; Depression -- Risk Factors -- In Old Age; Aged; Patient Compliance

The availability and affordability of selected essential medicines for chronic diseases in six low- and middle-income countries. (Bulletin of the World Health Organization, 2007)
OBJECTIVE: To assess the availability and affordability of medicines used to treat cardiovascular disease, diabetes, chronic respiratory disease and glaucoma and to provide palliative cancer care in six low- and middle-income countries. METHODS: A survey of the availability and price of 32 medicines was conducted in a representative sample of public and private medicine outlets in four geographically defined areas in Bangladesh, Brazil, Malawi, Nepal, Pakistan and Sri Lanka. We analysed the percentage of these medicines available, the median price versus the international reference price (expressed as the median price ratio) and affordability in terms of the number of days wages it would cost the lowest-paid government worker to purchase one month of treatment. FINDINGS: In all countries<or=7.5% of these 32 medicines were available in the public sector, except in Brazil, where 30% were available, and Sri Lanka, where 28% were available. Median price ratios varied substantially, from 0.09 for losartan in Sri Lanka to 30.44 for aspirin in Brazil. In the private sector in Malawi and Sri Lanka, the cost of innovator products (the pharmaceutical product first given marketing authorization) was three times more than generic medicines. One month of combination treatment for coronary heart disease cost 18.4 days wages in Malawi, 6.1 days wages in Nepal, 5.4 in Pakistan and 5.1 in Brazil; in Bangladesh the cost was 1.6 days wages and in Sri Lanka it was 1.5. The cost of one month of combination treatment for asthma ranged from 1.3 days wages in Bangladesh to 9.2 days wages in Malawi. The cost of a one-month course of intermediate-acting insulin ranged from 2.8 days wages in Brazil to 19.6 in Malawi. CONCLUSION: Context-specific policies are required to improve access to essential medicines. Generic products should be promoted by educating professionals and consumers, by implementing appropriate policies and incentives, and by introducing market competition and/or price regulation. Improving governance and management efficiency, and assessing local supply options, may improve availability. Prices could be reduced by improving purchasing efficiency, eliminating taxes and regulating mark-ups. Copyright © 2007 World Health Organization
Keywords: Chronic Disease -- Drug Therapy; Developing Countries; Drugs, Essential -- Economics; Drugs, Essential; Health Services Accessibility -- Economics; Business -- Administration; Health Services Accessibility -- Administration; Palliative Care; Private Sector; Public Sector; World Health; Human

Novel drug delivery systems for glaucoma. - Lavik E; Kuehn MH; Kwon YH; Lavik, E; Kuehn, M H; Kwon, Y H (Eye, 2011)
Reduction of intraocular pressure (IOP) by pharmaceutical or surgical means has long been the standard treatment for glaucoma. A number of excellent drugs are available that are effective in reducing IOP. These drugs are typically applied as eye drops. However, patient adherence can be poor, thus reducing the clinical efficacy of the drugs. Several novel delivery systems designed to address the issue of adherence and to ensure consistent reduction of IOP are currently under development. These delivery systems include contact lenses-releasing glaucoma medications, injectables such as biodegradable micro- and nanoparticles, and surgically implanted systems. These new technologies are aimed at increasing clinical efficacy by offering multiple delivery options and are capable of managing IOP for several months. There is also a desire to have complementary neuroprotective approaches for those who continue to show progression, despite IOP reduction. Many potential neuroprotective agents are not suitable for traditional oral or drop formulations. Their potential is dependent on developing suitable delivery systems that can provide the drugs in a sustained, local manner to the retina and optic nerve. Drug delivery systems have the potential to improve patient adherence, reduce side effects, increase efficacy, and ultimately, preserve sight for glaucoma patients. In this review, we discuss benefits and limitations of the current systems of delivery and application, as well as those on the horizon.
Keywords: Drug Delivery Systems -- Methods; Glaucoma -- Drug Therapy; Ophthalmic Solutions -- Administration and Dosage; Intraocular Pressure -- Drug Effects; Medication Compliance; Neuroprotective Agents -- Administration and Dosage

Glaucoma risk factors, patient compliance can be improved. - Mullin DW; Dalton M; Boyle EL; Byrne J (Ocular Surgery News, 2006)
At Glaucoma Day and throughout the ASCRS meeting, physicians and industry alike emphasized early disease detection and patient compliance.
Keywords: Glaucoma; Patient Compliance; Adrenergic Beta-Antagonists -- Therapeutic Use; Age Factors; Attitude to Illness; Diagnosis, Eye -- Methods; Glaucoma -- Chemically Induced; Glaucoma -- Diagnosis; Glaucoma -- Drug Therapy; Glaucoma -- Risk Factors; Glaucoma -- Surgery; Intraocular Pressure -- Drug Effects; Iris -- Pathology; Optic Nerve; Patient Education; Physician-Patient Relations; Steroids -- Adverse Effects; Eye Surgery -- Methods

Physician shares pearls, indications for laser trabeculoplasty. (Ocular Surgery News, 2010)
Keywords: Glaucoma -- Surgery; Eye Surgery -- Methods; Decision Making, Clinical; Intraocular Pressure; Patient Compliance

Medical treatment of open-angle glaucoma. - Kyari, Fatima; Abdull, Mohammad; Kiage, Dan; Ogunro, Adunola (Community Eye Health Journal, 2012)
Keywords: Glaucoma -- Drug Therapy; Prostaglandins -- Therapeutic Use; Prostaglandins -- Adverse Effects; Costs and Cost Analysis; Health Services Accessibility; Adrenergic Beta-Antagonists; Adrenergic Alpha-Antagonists; Parasympathomimetics; Carbonic Anhydrase Inhibitors; Counterfeit Drugs -- Adverse Effects

Detecting possible glaucoma with only limited equipment: a crucial first step. - 1Philippin, Heiko; Shah, Peter; Burton, Matthew (Community Eye Health Journal, 2012)
Keywords: Glaucoma -- Diagnosis; Diagnosis, Eye -- Equipment and Supplies; Health Services Accessibility; Patient History Taking; Visual Acuity; Lighting; Visual Fields; Patient Education; Cataract -- Diagnosis

Patients and glaucoma: what are the challenges? (Community Eye Health Journal, 2012)
Keywords: Glaucoma -- Therapy; Patient Care -- Methods; Health Services Accessibility; Help Seeking Behavior; Patient Attitudes; Health Beliefs

THERAPEUTIC FOCUS. MANAGE GLAUCOMA. - GONZALEZ, AUGUSTIN L. (Optometric Management, 2018)
Keywords: Optometrists -- Psychosocial Factors; Glaucoma -- Drug Therapy; Ophthalmic Solutions; Health Care Costs; Medical Practice; Patient Education; Blindness -- Risk Factors; Latanoprost -- Therapeutic Use; Timolol -- Therapeutic Use; Patient Compliance; Patient Care; Chemistry, Pharmaceutical; Medication Compliance

Glaucoma medications. How to improve compliance and adherence. - Cakiner-Egilmez, Tulay; Lara-Smalling, Agueda (Insight: The Journal of the American Society of Ophthalmic Registered Nurses, 2012)
Keywords: Antihypertensive Agents -- Administration and Dosage; Glaucoma -- Drug Therapy; Intraocular Pressure -- Drug Effects; Medication Compliance; Patient Compliance

Novel telemedicine device for diagnosis of corneal abrasions and ulcers in resource-poor settings. - Maamari, Robi N; Ausayakhun, Somsanguan; Margolis, Todd P; Fletcher, Daniel A; Keenan, Jeremy D (JAMA Ophthalmology, 2014)
Keywords: Wireless Communications -- Equipment and Supplies; Corneal Ulcer -- Diagnosis; Epithelium -- Pathology; Health Services Accessibility; Photography -- Equipment and Supplies; Telemedicine -- Equipment and Supplies; Developing Countries; Fluorophotometry; Health Resource Utilization; Human; Sensitivity and Specificity; Telemedicine -- Methods; Thailand

Simple regimen aids adherence. - Stamper, Robert L.; Krader, Cheryl Guttman (Ophthalmology Times, 2013)
The article offers information about the management of glaucoma, an eye disease in which the optic nerve is damaged. It mentions that preventing the loss of vision is one of the primary goals of glaucoma management. Further, it mentions that detailed studies regarding intraocular pressure in such patients can help in better understanding of glaucoma and also emphasizes on the relationship between quality of life and the occurrence of glaucoma disease.
Keywords: Glaucoma -- Therapy; Intraocular Pressure; Glaucoma -- Trends; Vision Disorders -- Prevention and Control; Medication Compliance

Improved communication may increase patients' adherence to glaucoma medication. (Ocular Surgery News, 2011)
The article offers the insights of physician David S. Friedman during the Richard A. Ellis Lecture which states that enhanced physician-patient discourse is helpful in increasing patients' adherence to glaucoma therapy.
Keywords: Medication Compliance; Professional-Patient Relations; Glaucoma -- Drug Therapy; Communication; Research; Reminder Systems -- Evaluation

Physician offers simple ways to improve glaucoma regimen adherence. (Ocular Surgery News, 2011)
The article reports that reducing the complexity of dosing is deemed beneficial to adherence to a medication regimen which may be problematic for some patients with glaucoma, according to the Automated Dosing Reminder Study.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Physician-Patient Relations; Communication

SLT as initial glaucoma treatment addresses compliance issues, eye drop sensitivity. - Boyle EL (Ocular Surgery News, 2006)
Making selective laser trabeculoplasty the initial treatment for glaucoma allows patients to return to their every day lives without requiring drop compliancy.
Keywords: Glaucoma -- Surgery; Laser Therapy -- Methods; Patient Compliance; Antihypertensive Agents -- Therapeutic Use; Clinical Trials; Intraocular Pressure -- Drug Effects; Ophthalmic Solutions; Surgeons; Treatment Outcomes

Glaucoma may transition to surgery-first management. (Ocular Surgery News, 2012)
Keywords: Glaucoma -- Surgery; Eye Surgery; Patient Compliance; Primary Health Care; Hypertension -- Surgery

Letter to the Editor: Is the quality of patient education interventions associated with efficacy? A reflection from the field of glaucoma. - Lamiani, Giulia; Borghi, Lidia; Moja, Egidio A. (Therapeutic Patient Education / Education Therapeutique du Patient, 2012)
Keywords: Glaucoma -- Education; Outcomes (Health Care); Patient Education; Quality Assurance; Behavioral Changes; Health Knowledge; Patient Compliance; Predictive Validity

Point/counter. - Samuelson TW; Barton K (Ocular Surgery News, 2009)
Keywords: Blindness -- Prevention and Control; Cost Benefit Analysis; Glaucoma -- Complications; Drugs, Prescription -- Therapeutic Use; Geographic Locations; Glaucoma -- Classification; Glaucoma -- Drug Therapy; Glaucoma -- Physiopathology; Health Services Accessibility

Epidemiological Properties of Primary Open Angle Glaucoma in Nigeria. - Abdu, Lawan (Journal of Ophthalmology, 2013)
Keywords: Glaucoma -- Epidemiology -- Nigeria; Nigeria; Glaucoma -- Complications; Blindness -- Risk Factors; Glaucoma -- Physiopathology; Glaucoma -- Symptoms; Glaucoma -- Prevention and Control; Health Screening -- Methods; Health Services Accessibility; Glaucoma -- Drug Therapy

Improving the care of glaucoma patients. - Wilson RP (Journal of Ophthalmic Nursing & Technology, 1998)
The most common reason for a glaucoma medication to be ineffective is that the patient does not take the medicine reliably. Instead of general questions, it is much more effective to try to elicit compliance by asking specific questions. If instruction as to how to instill topical medications is not effective, then the patient should be asked to use a drop guide.
Keywords: Glaucoma -- Drug Therapy; Patient Compliance; Aged; Female

Risk and risk factors for blindness from glaucoma. - Chen, Philip P (Current Opinion in Ophthalmology, 2004)
Purpose Of Review: Estimates of blindness from glaucoma and risk factors for blindness remain of interest for all ophthalmologists.Recent Findings: Long-term retrospective studies of patients with open-angle glaucoma in developed countries have noted that progression to bilateral blindness among treated patients is relatively uncommon. Risk factors for development of blindness include advanced visual field loss at presentation and noncompliance with the treatment regimen. Age is a risk factor in some studies. Many of those with blindness are blind at presentation. Untreated rates of blindness are higher. Population-based studies of glaucoma in developing countries have highlighted the obstacles to prevention of blindness in such settings, with astonishingly high rates of blindness noted.Summary: The risk of blindness from glaucoma is very high among patients in developing countries, the vast majority of whom do not know they are afflicted. When considering all glaucoma worldwide, the greatest risk factor for blindness is almost certainly being an average citizen of a developing country. Among those with open-angle glaucoma in developed countries, more advanced visual field loss at presentation and noncompliance are risk factors for development of blindness, as well as advanced age. Effective public education about glaucoma and targeted screening of those most likely to have glaucoma are necessary if the number of blind from glaucoma is to be reduced worldwide. Better treatment options for those in developing countries must also be developed.
Keywords: Blindness -- Etiology; Blindness -- Epidemiology; Glaucoma -- Complications; Glaucoma -- Epidemiology; Human; Risk Factors; Risk Assessment; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

Clinic-based glaucoma care in the era of surgical subspecialization. - Campbell, Robert J; Bell, Chaim M; Gill, Sudeep S; Whitehead, Marlo; Campbell, Erica de L P; Xu, Kunyong; El-Defrawy, Sherif R (American Journal of Ophthalmology, 2014)
Keywords: Glaucoma -- Surgery; Health Care Delivery -- Statistics and Numerical Data; Ophthalmology -- Statistics and Numerical Data; Practice Patterns -- Statistics and Numerical Data; Eye Surgery -- Statistics and Numerical Data; Antihypertensive Agents -- Therapeutic Use; Human; Intraocular Pressure; Laser Therapy -- Statistics and Numerical Data; Office Visits; Ontario; Referral and Consultation; Retrospective Design; Specialties, Surgical

Immune privilege in corneal transplantation. - Hori, Junko; Yamaguchi, Takefumi; Keino, Hiroshi; Hamrah, Pedram; Maruyama, Kazuichi (Progress in Retinal & Eye Research, 2019)
Corneal transplantation is the most successful solid organ transplantation performed in humans. The extraordinary success of orthotopic corneal allografts, in both humans and experimental animals, is related to the phenomenon of "immune privilege". Inflammation is self-regulated to preserve ocular functions because the eye has immune privilege. At present, three major mechanisms are considered to provide immune privilege in corneal transplantation: 1) anatomical, cellular, and molecular barriers in the cornea; 2) tolerance related to anterior chamber-associated immune deviation and regulatory T cells; and 3) an immunosuppressive intraocular microenvironment. This review describes the mechanisms of immune privilege that have been elucidated from animal models of ocular inflammation, especially those involving corneal transplantation, and its relevance for the clinic. An update on molecular, cellular, and neural interactions in local and systemic immune regulation is provided. Therapeutic strategies for restoring immune privilege are also discussed.
Keywords: Corneal Transplantation; Fetal Development -- Physiology; Immune Tolerance -- Physiology; T Lymphocytes -- Immunology; Graft Survival -- Immunology

Baby boomers will increase demand for eye care. (Ocular Surgery News, 2008)
Keywords: Aging; Eye Care -- Utilization; Cataract -- Risk Factors; Glaucoma -- Risk Factors; Health Resource Utilization; Health Services Accessibility; Macular Degeneration -- Risk Factors; Ophthalmology; Workforce

Compliance and adherence in glaucoma management. - Robin, Alan; Grover, Davinder S (Indian Journal of Ophthalmology, 2011)
Keywords: Antihypertensive Agents -- Administration and Dosage; Glaucoma -- Drug Therapy; Patient Compliance; Blindness -- Prevention and Control; Ophthalmic Solutions; Socioeconomic Factors

Switching within glaucoma medication class. - Law SK (Current Opinion in Ophthalmology, 2009)
PURPOSE OF REVIEW: In the current medical care environment, switching within class is often demanded by cost consideration, medical insurance coverage, or formulary restriction. With many choices of drugs available within a glaucoma medication class, questions exist whether switching within class is beneficial. The purpose of this article is to provide a clinical update on the feasibility of switching among the frequently used drugs within glaucoma medication class. RECENT FINDINGS: Although efficacies of medications within a therapeutic class are similar and significant differences are generally not observed in clinical trials, response to medication often varies among individual patients in a clinical practice. Such variation may be secondary to differences in drug-receptor interactions, patient's compliance and tolerability to medical treatment, or bioavailability of the medication in individual ocular condition. In addition, switching within class is often necessary to minimize the systemic or local adverse reactions from the active or inactive ingredients of the medication. SUMMARY: In addition to keeping up-to-date with the efficacy and safety profiles of drugs within each glaucoma medication class, clinicians should familiarize themselves with the different formulations available, preservative systems used, generics availability and compatibility, and the local insurance formulary restriction to deliver an effective glaucoma management.
Keywords: Drugs -- Therapeutic Use; Glaucoma -- Therapy; Adrenergic Antagonists -- Therapeutic Use; Carbonic Anhydrase Inhibitors -- Therapeutic Use; Ophthalmology; Prostaglandins -- Therapeutic Use

Glaucoma medication treatment nonadherence: correlates and consequences. (Communicating Nursing Research, 2012)
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Adult; Aged, 80 and Over; Colorado; Coping; Descriptive Statistics; Female; Funding Source; Human; Male; Middle Age; Motivation; Oregon; Self Report; Self-Efficacy; Support, Psychosocial

Improving Eye Drop Treatment for Glaucoma through Better Adherence. - Quigley HA (Optometry & Vision Science, 2008)
Keywords: Glaucoma -- Drug Therapy; Ophthalmic Solutions -- Therapeutic Use; Patient Compliance; Blindness -- Prevention and Control; Glaucoma -- Psychosocial Factors; Patient Dropouts

Obstacles remain for innovative sustained glaucoma drug delivery systems. (Ocular Surgery News, 2012)
Keywords: Glaucoma -- Drug Therapy; Drug Delivery Systems; Problem Solving

Obstacles remain for innovative sustained glaucoma drug delivery systems. (Ocular Surgery News, 2012)
The article discusses the challenges that need to be addressed in the ongoing development of sustained drug release devices including the limitations of extraocular delivery to small, lipophilic molecules, and adverse side effects like endopththalmitis, retinal detachment, and vitreous hemorrhage.
Keywords: Glaucoma -- Drug Therapy; Drug Delivery Systems; Problem Solving

Glaucoma screening: current trends, economic issues, technology, and challenges. - Nduaguba, Constance; Lee, Richard K. (Current Opinion in Ophthalmology, 2006)
PURPOSE OF REVIEW: Glaucoma is one of the leading causes of irreversible blindness worldwide. Early glaucoma detection and treatment are currently the only known methods for preventing blindness and low vision resulting from this frequently asymptomatic disease. RECENT FINDINGS: New technologies for detecting early glaucomatous damage are important in diagnosing optic nerve disease, not only in community screening settings but also in clinics. Imaging of the optic nerve head and macula and retinal nerve fiber layer analysis can provide quick, automated, and quantitative measurements in agreement with clinical estimates of optic disc structure and visual function. In the area of perimetry, frequency-doubling technology is a promising and feasible mass-screening method with reasonable sensitivity for detecting visual field loss. Central corneal thickness has emerged as a new risk factor for the development and progression of glaucoma, thereby complicating the role of tonometry and measurement of intraocular pressure as screening parameters for glaucoma. Along with technological advances, strides are also being made with public policy and legislative efforts to bring glaucoma onto the national and global health care agenda. These initiatives incorporate vision-screening goals into national disease prevention programs emphasizing the need for early glaucoma detection and treatment. SUMMARY: Glaucoma awareness needs to be increased through better education, and compliance with follow-up care needs to be improved to decrease the economic and social costs from glaucoma. In addition, screening models need to be developed that will be effective in developing countries where the risk of blindness from glaucoma is highest.
Keywords: Glaucoma -- Diagnosis; Technology, Medical; Vision Screening -- Economics; Vision Screening -- Methods; Blindness -- Prevention and Control; Corneal Diseases -- Diagnosis; Glaucoma -- Complications; Glaucoma -- Education; Glaucoma -- Prevention and Control; Ophthalmology; Optic Nerve Diseases -- Diagnosis; Patient Education; Perimetry -- Methods; Retina -- Anatomy and Histology; Vision Tests -- Methods

At issue: latanoprost and glaucoma management. - Crandall AS; Lewis RA; Rhee DJ; Shingleton BJ; Spaeth GL (Ocular Surgery News, 2006)
At Issue posed the following questions to a panel of experts: 'How has the availability of latanoprost affected glaucoma management, and why?'
Keywords: Glaucoma -- Drug Therapy; Latanoprost -- Therapeutic Use; Glaucoma -- Complications; Intraocular Pressure -- Drug Effects; Latanoprost -- Administration and Dosage; Latanoprost -- Analogs and Derivatives; Latanoprost -- Pharmacodynamics; Ophthalmic Solutions; Patient Compliance; Surgeons; Treatment Outcomes

Glaucoma medication persistence low in all age groups, study finds. - Altersitz K (Ocular Surgery News, 2006)
Glaucoma medication persistence in Medicare-aged patients was comparable to persistence in all other age groups.
Keywords: Glaucoma -- Drug Therapy; Patient Compliance -- Evaluation; Aged; Medicare; Medication Compliance; Patient Attitudes

DRY EYE. LEARN FROM GLAUCOMA: DETERMINE WHICH TESTS TO PERFORM, AND HOW OFTEN TO PERFORM THEM. - HAUSER, WHITNEY (Optometric Management, 2017)
Keywords: Glaucoma -- Diagnosis; Glaucoma -- Therapy; Glaucoma -- Prevention and Control; Dry Eye Syndromes; Tonometry; Ophthalmoscopy; Diagnosis, Eye -- Methods; Perimetry; Ophthalmic Solutions; Patient Compliance; Osmolar Concentration

Lowering IOP With Stents...IntraOcular Pressure - SCHWEITZER, JUSTIN (Optometric Management, 2014)
Keywords: Glaucoma -- Surgery; Minimally Invasive Procedures; Stents; Patient Safety; Eye Hemorrhage; Patient Compliance; Coding; Disease Progression -- Prevention and Control

Survey: compliance poor with multiple glaucoma medications. - McNeil R (Ocular Surgery News, 2002)
A pan-European survey found that improved communication between physicians and patients may increase compliance rates.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Surveys; Blindness -- Etiology; Communication -- Methods; Drug Combinations; Physician-Patient Relations

Barriers challenge development of aqueous outflow drugs. - Kronemyer, Bob (Ocular Surgery News, 2013)
Keywords: Glaucoma -- Drug Therapy; Drug Design; Intraocular Pressure; Problem Solving; Patient Safety

Convenience, efficacy boost popularity of new combination glaucoma therapies: less toxicity to the reduction of preservative and increased compliance are primary benefits, specialists say. - Schultz J (Ocular Surgery News, 2005)
Keywords: Drug Combinations; Glaucoma -- Drug Therapy

Education an ongoing effort with glaucoma patients. - Gonzalez JM (Ocular Surgery News, 2004)
Physicians watched their glaucoma patients speak candidly about their disease. They learned that patients lack knowledge but want to know more.
Keywords: Glaucoma; Patient Education; Patient Compliance

Corticosteroid use for diabetic macular edema: old fad or new trend? - Stewart MW; Stewart, Michael W (Current Diabetes Reports, 2012)
Diabetic retinopathy is the leading cause of blindness in working age individuals in developed countries. Most cases of diabetes related vision loss result from breakdown of the blood-retinal barrier with resultant diabetic macular edema (DME). For over 30 years, laser photocoagulation has been the standard therapy for DME, but most eyes do not experience significant improvements in visual acuity. Intravitreal injections of drugs that inhibit the action of vascular endothelial growth factor (VEGF) lead to gains in vision, but can be expensive and need to be repeated frequently. In addition to VEGF-mediated breakdown of the blood-retinal barrier, recent evidence suggests that inflammation plays an important role in the development of DME. Recognizing this, physicians have injected steroids into the vitreous and developers have created sustained release implants. Intravitreal injections of triamcinolone acetonide lead to rapid resolution of macular edema and significant short-term improvements in visual acuity, but unfortunately, visual acuities diminish when treatment is continued through 2 years. However, intravitreal triamcinolone remains an attractive treatment option for eyes that are pseudophakic, scheduled to undergo cataract surgery, resistant to laser photocoagulation, or require urgent panretinal photocoagulation for proliferative retinopathy. In controlled trials, intraocular implants that slowly release dexamethasone and fluocinolone show promise in reducing macular edema and improving visual acuity. The high incidences of drug related cataracts and glaucoma, however, require that corticosteroids be used cautiously and that patients be selected carefully. The increasing number of patients with DME, the burgeoning cost of medical care and the continuing development of intravitreal steroids suggest that the use of these agents will likely increase in coming years.
Keywords: Antiinflammatory Agents -- Administration and Dosage; Dexamethasone -- Administration and Dosage; Diabetic Retinopathy -- Drug Therapy; Steroids -- Administration and Dosage; Macular Degeneration -- Drug Therapy; Triamcinolone -- Administration and Dosage; Diabetic Retinopathy -- Physiopathology; Drug Administration Schedule; Drug Implants -- Administration and Dosage; Female; Injections; Macular Degeneration -- Physiopathology; Male; Visual Acuity -- Drug Effects

Improving compliance with glaucoma eye-drop treatment. - Cooper J (Nursing Times, 1996)
Many older patients attending ophthalmic out-patient clinics have been prescribed eye drops for long-term use to treat glaucoma but do not continue with their treatment. This review looks at chronic simple glaucoma, the problems of compliance with long-term medical treatment in older people and the current and future treatment of glaucoma. Recommendations are made on the nurses' role in supporting these patients.
Keywords: Glaucoma -- Drug Therapy; Patient Compliance; Administration, Intraocular -- Education; Patient Education; Glaucoma -- Nursing; Ophthalmic Nursing

Why a successful task substitution in glaucoma care could not be transferred from a hospital setting to a primary care setting: a qualitative study. - Holtzer-Goor, Kim M; Plochg, Thomas; Lemij, Hans G; van Sprundel, Esther; Koopmanschap, Marc A; Klazinga, Niek S (Implementation Science, 2013)
Keywords: Glaucoma -- Therapy; Hospitalization; Optometry; Transfer, Discharge -- Utilization; Primary Health Care -- Utilization; Attitude of Health Personnel; Pilot Studies; Health Services Accessibility; Human; Netherlands; Optometry -- Standards; Qualitative Studies; Quality of Health Care

Simple regimen aids adherence. - Stamper, Robert L.; Krader, Cheryl Guttman (Ophthalmology Times, 2013)
Keywords: Glaucoma -- Therapy; Intraocular Pressure; Glaucoma -- Trends; Vision Disorders -- Prevention and Control; Medication Compliance

Older adults with glaucoma more prone to cognitive impairment, depression. - Kronemyer, Bob (Ocular Surgery News, 2012)
Keywords: Glaucoma -- Complications -- In Old Age; Dementia -- Risk Factors -- In Old Age; Depression -- Risk Factors -- In Old Age; Aged; Patient Compliance

Improved communication may increase patients' adherence to glaucoma medication. (Ocular Surgery News, 2011)
Keywords: Medication Compliance; Professional-Patient Relations; Glaucoma -- Drug Therapy; Communication; Research; Reminder Systems -- Evaluation

Physician offers simple ways to improve glaucoma regimen adherence. (Ocular Surgery News, 2011)
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Physician-Patient Relations; Communication

Treatment of advanced glaucoma aims for target pressure of 12 mm Hg. - Cimberle M (Ocular Surgery News, 2006)
Prostaglandins are the best option, but should not be used alone. The need for multiple medications raises the problem of compliance.
Keywords: Glaucoma -- Drug Therapy; Intraocular Pressure -- Drug Effects; Prostaglandins -- Therapeutic Use; Disease Progression -- Prevention and Control; Drug Therapy, Combination; Glaucoma -- Complications; Glaucoma -- Trends; Medication Compliance; Practice Guidelines; Surgeons; Surveys

CONTACT LENS CARE & COMPLIANCE. A GLOBAL PERSPECTIVE ON OTC CONTACT LENSES. - Savla, Keyur; Pucker, Andrew D. (Contact Lens Spectrum, 2018)
Keywords: Contact Lenses -- Education; Health Personnel; Eye Care; Patient Compliance; Business; Eye Injuries; Keratitis -- Economics; Contact Lens Fitting; Keratitis -- Therapy

Improving compliance with glaucoma treatment requires patient-focused approach. - Boyle E (Ocular Surgery News, 2006)
Regardless of lifestyle and patient-dependent factors, glaucoma specialists must monitor patients for disease progression.
Keywords: Disease Progression; Glaucoma; Patient Compliance; Accidental Falls -- Risk Factors; Adrenergic Beta-Antagonists -- Adverse Effects; Clinical Competence; Diagnosis, Eye -- Methods; Education, Medical; Glaucoma -- Complications; Glaucoma -- Therapy; Intraocular Pressure; Life Style; Medication Compliance; Monitoring, Physiologic; Ophthalmology -- Education; Patient Education; Physician-Patient Relations

Color-coded grid helps glaucoma patient compliance, doctor says. - Boyle EL (Ocular Surgery News, 2006)
Glaucoma patients understand dosages more easily with grid that is color-coded to correspond to medications' caps.
Keywords: Assistive Technology Devices -- Utilization; Glaucoma -- Drug Therapy; Medication Compliance; Aged; Assistive Technology Devices -- Education; Color; Equipment Design; Health Personnel -- Education; Patient Compliance; Product Evaluation

Study: factors associated with poor treatment compliance in glaucoma patients. - Cimberle M (Ocular Surgery News, 2007)
Non-adherence is mostly due to lack of motivation by younger patients and to poor eye-drop application technique by older patients.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Aging; Motivation; Patient Compliance; Prospective Studies; Quality of Life; Questionnaires; Self Care -- Methods; Human

A novel approach to glaucoma screening and education in Nepal. - Thapa SS; Kelley KH; Rens GV; Paudyal I; Chang L (BMC Ophthalmology, 2008)
Glaucoma is a major cause of blindness worldwide and an increasingly significant global health problem. Glaucoma prevention and management efforts have been challenging due to inherent difficulty in developing a simple and cost-effective screening plan, limited access to health care and educational resources, poverty, and inadequate knowledge of the disease, particularly in developing countries. Starting in 2004 the Tilganga Eye Centre in Kathmandu, Nepal has provided targeted glaucoma screening, treatment, and education through a combination of clinical outreach programs and educational activities for patients.~Background~Background~A simple, age-based glaucoma screening algorithm was incorporated into three one-day cataract screening clinics. Using this algorithm, patients who were newly diagnosed with glaucoma were referred to TEC, where medication and surgery were provided free of charge through private donor funding. In addition, we describe two ongoing educational programs for increasing glaucoma awareness: an annual Glaucoma Awareness Week (which includes free screening, treatment, and counseling), and a repeating lecture series which generates new counselors.~Methods~Methods~From 2004 to 2007 screening at the annual Glaucoma Awareness Week resulted in the diagnosis of 120 individuals with glaucoma, or 7.6% of total registrants. Attendance increased annually with a trend toward an increasing number of returning patients but a decreasing percentage of newly diagnosed patients, though the absolute numbers have remained relatively stable (range 21 to 38). Data from the three one-day screening clinics in 2006 show that approximately 2 to 4% of patients 50 years of age or older per clinic were newly diagnosed with POAG.~Results~Results~This multi-faceted approach appears to successfully identify individuals with glaucoma and provide treatment to those who would otherwise not be able to afford it. While more data is needed to validate this model, specifically regarding the effectiveness of educational activities, long-term visual outcomes, and medication compliance, it may serve as a useful framework for other developing countries with similarly limited resources.~Conclusion~Conclusions
Keywords: Glaucoma -- Diagnosis; Health Education -- Methods; Health Screening -- Methods; Patient Education -- Methods; Algorithms; Counseling; Glaucoma -- Drug Therapy; Glaucoma -- Surgery; Health Screening -- Statistics and Numerical Data; Middle Age; Nepal; Referral and Consultation; Uncompensated Care

Amebic meningoencephalitides and keratitis: challenges in diagnosis and treatment. - Visvesvara GS (Current Opinion in Infectious Diseases, 2010)
PURPOSE OF REVIEW: Acanthamoeba spp., Balamuthia mandrillaris, and Naegleria fowleri, although free-living amebae, also cause devastating diseases in humans leading to death. Acanthamoeba spp. and B. mandrillaris cause granulomatous amebic encephalitis, cutaneous and nasopharyngeal as well as disseminated infection. Acanthamoeba also causes a vision-threatening infection of the cornea, Acanthamoeba keratitis, principally in contact lens wearers. N. fowleri causes an acute, fulminating infection of the central nervous system, primary amebic meningoencephalitis, in healthy children and young adults who indulge in aquatic activities in fresh water. This review focuses on the recent developments in the diagnosis and treatment and clinical management of the diseases caused by these amebae. RECENT FINDINGS: Development of a multiplex real-time PCR test has made it possible to simultaneously detect all the three free-living amebae in a sample. It is a rapid assay with a short turn-around time of just 4-5 h. An early diagnosis would be helpful in initiating potentially effective treatment. A recent study reported exciting results indicating that loading of rokitamycin in chitosan microspheres improves and prolongs the in-vitro anti-Acanthamoeba activity of the drug. SUMMARY: Diagnoses of these infections are challenging and antimicrobial therapy is empirical, which often results in fatalities. Further research is needed to explore the possibility of a better drug delivery system that crosses the blood-brain barrier and effectively reach the central nervous system.
Keywords: Amebiasis -- Physiopathology; Encephalitis -- Diagnosis; Keratitis -- Diagnosis; Meningococcal Infections -- Diagnosis; Amebiasis -- Diagnosis; Amebiasis -- Therapy; Communicable Diseases -- Prevention and Control; Keratitis -- Therapy

Patient adherence decreased with addition of second drug. - Gonzalez JM (Ocular Surgery News, 2005)
Glaucoma specialists should consider the patient's adherence to one drug before adding another, researchers suggest.
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Drugs, Prescription -- Economics

Managing chronic simple glaucoma. - Field D (Nursing Standard, 1992)
Chronic simple glaucoma, which affects two per cent of the population, is the most common preventable cause of blindness in the world. This article explores the causes and two of the medical treatments available, examining some of the reasons for non-compliance with treatment. Heightened awareness among clinical nurses who may have glaucoma sufferers in their care will help to ensure appropriate therapeutic interventions for this group of patients.
Keywords: Glaucoma; Glaucoma -- Drug Therapy; Patient Education; Pilocarpine -- Pharmacodynamics; Timolol -- Pharmacodynamics; Glaucoma -- Nursing; Ophthalmic Nursing

Multidisciplinary approach needed for childhood glaucoma. - Boyle EL (Ocular Surgery News, 2006)
Coordination with primary caregivers and others is essential for a good prognosis, one specialist noted.
Keywords: Glaucoma -- Therapy -- In Infancy and Childhood; Multidisciplinary Care Team; Child; Diagnosis, Eye; Glaucoma -- Diagnosis; Glaucoma -- Education; Glaucoma -- Physiopathology; Glaucoma -- Prevention and Control -- In Infancy and Childhood; Glaucoma -- Surgery; Health Screening; Patient Compliance; Risk Assessment; Students, Medical

Intervention program improves glaucoma medication adherence. (Insight: The Journal of the American Society of Ophthalmic Registered Nurses, 2010)
Keywords: Glaucoma -- Drug Therapy; Medication Compliance

Scoring and psychometric properties of the Eye-Drop Satisfaction Questionnaire (EDSQ), an instrument to assess satisfaction and compliance with glaucoma treatment. - Regnault A; Viala-Danten M; Gilet H; Berdeaux G (BMC Ophthalmology, 2010)
Keywords: Glaucoma -- Drug Therapy; Patient Compliance; Patient Satisfaction -- Statistics and Numerical Data; Psychometrics -- Methods; Questionnaires; Adolescence; Adult; Aged; Aged, 80 and Over; Cross Sectional Studies; Drug Delivery Systems -- Equipment and Supplies; Female; Human; Male; Middle Age; Ophthalmic Solutions -- Administration and Dosage; Physician-Patient Relations; Factor Analysis; Reproducibility of Results; Retrospective Design; Young Adult

Study finds higher than expected medical glaucoma treatment rate in France. - Cimberle M (Ocular Surgery News, 2006)
Compliance and quality of life decline with the number of daily doses of glaucoma medications.
Keywords: Glaucoma -- Epidemiology -- France; Ocular Hypertension -- Epidemiology -- France; Adrenergic Beta-Antagonists -- Therapeutic Use; Age Factors; France; Glaucoma -- Drug Therapy; Glaucoma -- Economics; Intraocular Pressure -- Drug Effects; Medication Compliance; Prevalence; Prostaglandins -- Therapeutic Use; Quality of Life

BUSINESS: THE CEO CHECKLIST. REDUCE PATIENT NO-SHOWS. - VARGO, STEVE (Optometric Management, 2018)
Keywords: Business; Administrative Personnel; Checklists; Attitude of Health Personnel; Appointments and Schedules; Diagnosis, Eye; Diabetes Mellitus; Glaucoma; Hypersensitivity; Telecommuting; Waiting Lists; Patient Attitudes; Optometrists -- Psychosocial Factors

DELIVERING THE GOODS. - SCHWEITZER, JUSTIN (Optometric Management, 2018)
Keywords: Drug Delivery Systems; Patient Compliance; Glaucoma -- Drug Therapy; Administration, Intraocular; Bimatoprost -- Administration and Dosage; Intraocular Pressure; Drug Implants; Bimatoprost -- Adverse Effects; Hyperemia -- Chemically Induced; Timolol -- Administration and Dosage; Treatment Outcomes; Nanotechnology; Travoprost -- Administration and Dosage

Study yields no difference in IOP between SLT, drugs as initial therapy. - Kronemyer, Bob (Ocular Surgery News, 2012)
The article discusses a study by L.Jay Katz and colleagues, which evaluated patients with open angle glaucoma or ocular hypertension, and found that the mean intra-ocular pressure (IOP) did not differ between selective laser trabeculopaslty (SLT) or medical therapy.
Keywords: Treatment Outcomes; Intraocular Pressure; Keratectomy, Laser; Glaucoma -- Therapy; Ocular Hypertension -- Therapy; Glaucoma -- Drug Therapy; Ocular Hypertension -- Drug Therapy; Patient Compliance

POINT/COUNTER. (Ocular Surgery News, 2013)
The article presents arguments for and against the public health implications for optical coherence tomography (OCT) screening for glaucoma. Professor Anne L. Coleman points out the need for OCT to meet screening criteria and cites some considerations for screening with any device. Assistant professor Joshua D. Stein points out the need for improved compatibility between OCT devices and models to allow longitudinal monitoring of patients for glaucoma progression.
Keywords: Tomography; Interferometry; Glaucoma -- Diagnosis; Health Screening; Public Health; Cost Benefit Analysis; Quality of Health Care; Health Services Accessibility; Technology; Socioeconomic Factors

Exploring glaucoma awareness and the utilization of primary eye care services: community perceived barriers among elderly African Caribbeans in Chapeltown, Leeds...Eye. 2007 Jul;21(7):912-20 - Awobem JF; Cassels-Brown A; Buchan JC; Hughes KA (Eye, 2009)
Keywords: Black Persons; Glaucoma -- Therapy; Patient Attitudes -- Ethnology; Aged; Attitude to Health; England; West Indies -- Ethnology

Vision health disparities in the United States by race/ethnicity, education, and economic status: findings from two nationally representative surveys. - Zhang X; Cotch MF; Ryskulova A; Primo SA; Nair P; Chou CF; Geiss LS; Barker LE; Elliott AF; Crews JE; Saaddine JB; Zhang, Xinzhi; et al. (American Journal of Ophthalmology, 2012)
Purpose: To assess vision health disparities in the United States by race/ethnicity, education, and economic status.Design: Cross-sectional, nationally representative samples.Methods: We used national survey data from the National Health and Nutrition Examination Survey (NHANES) and the National Health Interview Survey (NHIS). Main outcome measures included, from NHANES, age-related eye diseases (ie, age-related macular degeneration [AMD], cataract, diabetic retinopathy [DR], glaucoma) and from NHIS, eye care use (ie, eye doctor visits and cannot afford eyeglasses when needed) among those with self-reported visual impairment. The estimates were age- and sex-standardized to the 2000 US Census population. Linear trends in the estimates were assessed by weighted least squares regression.Results: Non-Hispanic whites had a higher prevalence of AMD and cataract surgery than non-Hispanic blacks, but a lower prevalence of DR and glaucoma (all P < .001 in NHANES 2005-2008). From 1999 to 2008, individuals with less education (ie, <high school vs >high school) and lower income (poverty income ratio [PIR] <1.00 vs ≥ 4.00) were consistently less likely to have had an eye care visit in the past 12 months compared with their counterparts (all P < .05). During this period, inability to afford needed eyeglasses increased among non-Hispanic whites and Hispanics (trend P = .004 and P = .007; respectively), those with high school education (trend P = .036), and those with PIR 1.00-1.99 (trend P < .001).Conclusions: Observed vision health disparities suggest a need for educational and innovative interventions among socioeconomically disadvantaged groups.
Keywords: Educational Status; Ethnic Groups; Eye Diseases -- Ethnology; Health Services Accessibility; Health Services -- Utilization; Population; Socioeconomic Factors; Adult; Cataract -- Ethnology; Cross Sectional Studies; Diabetic Retinopathy -- Ethnology; Glaucoma -- Ethnology; Human; Interview Guides; Macular Degeneration -- Ethnology; Resource Databases; Surveys; United States

Physicians, patients must work as team. - Charters, Lynda; Rhee, Douglas J. (Ophthalmology Times, 2012)
Keywords: Glaucoma -- Drug Therapy; Patient Compliance; Patients; Physicians; Teamwork

Glaucoma patient can serve as conduit to reach out to family members at risk. - Altersitz K (Ocular Surgery News, 2006)
Physicians can use patients to reach family members, who are at high risk of glaucoma.
Keywords: Glaucoma -- Familial and Genetic; Risk Assessment; Glaucoma -- Prevention and Control; Glaucoma -- Risk Factors; Health Knowledge; Health Services Accessibility; Intraocular Pressure; Patient Education; Race Factors; Surveys; Vision Screening -- Methods

Glaucoma surgery rates higher in blacks than whites, study finds. - Boyle EL (Ocular Surgery News, 2006)
A study of Medicare beneficiaries found that blacks were 78% more likely to undergo surgical procedures for glaucoma than whites.
Keywords: Glaucoma -- Surgery; Race Factors; Eye Surgery -- Utilization; Age Factors; Black Persons; Glaucoma -- Diagnosis; Glaucoma -- Ethnology; Health Services Accessibility; Health Services -- Utilization; Medicare; Prospective Studies; Severity of Illness; White Persons; Human

Measurements of therapeutic effect, IOP control unreliable over time...including commentary by Rhee DJ - Correa, Mark; Hasson, Matt (Ocular Surgery News, 2013)
The article reports a study which demonstrated poor repeatability of intraocular pressure (IOP) measurements in patients with untreated glaucoma; comments on the study emphasize the unreliability of a single test for management purposes.
Keywords: Intraocular Pressure -- Drug Effects; Treatment Outcomes -- Evaluation; Decision Making, Clinical; Research; Tonometry; Office Visits

Medical interventions for fungal keratitis. - FlorCruz NV; Peczon IV; FlorCruz, Nilo Vincent; Evans, Jennifer R (Cochrane Database of Systematic Reviews, 2015)
Background: Fungal keratitis is a fungal infection of the cornea. It is common in lower income countries, particularly in agricultural areas but relatively uncommon in higher income countries. Although there are medications available, their effectiveness is unclear.Objectives: To assess the effects of different antifungal drugs in the management of fungal keratitis.Search Methods: We searched CENTRAL (which contains the Cochrane Eyes and Vision Group Trials Register) (2015, Issue 2), Ovid MEDLINE, Ovid MEDLINE In-Process and Other Non-Indexed Citations, Ovid MEDLINE Daily, Ovid OLDMEDLINE (January 1946 to March 2015), EMBASE (January 1980 to March 2015), Latin American and Caribbean Health Sciences Literature Database (LILACS) (January 1982 to March 2015), the ISRCTN registry (www.isrctn.com/editAdvancedSearch), ClinicalTrials.gov (www.clinicaltrials.gov) and the World Health Organization (WHO) International Clinical Trials Registry Platform (ICTRP) (www.who.int/ictrp/search/en). We did not use any date or language restrictions in the electronic searches for trials. We last searched the electronic databases on 16 March 2015.Selection Criteria: We included randomised controlled trials of medical therapy for fungal keratitis.Data Collection and Analysis: Two review authors selected studies for inclusion in the review, assessed trials for risk of bias and extracted data. The primary outcome was clinical cure at two to three months. Secondary outcomes included best-corrected visual acuity, time to clinical cure, compliance with treatment, adverse outcomes and quality of life.Main Results: We included 12 trials in this review; 10 trials were conducted in India, one in Bangladesh and one in Egypt. Seven of these trials were at high risk of bias in one or more domains, two of these studies were at low risk of bias in all domains. Participants were randomised to the following comparisons: topical 5% natamycin compared to topical 1% voriconazole; topical 5% natamycin compared to topical 2% econazole; topical 5% natamycin compared to topical chlorhexidine gluconate (0.05%, 0.1% and 0.2%); topical 1% voriconazole compared to intrastromal voriconazole 50 g/0.1 mL (both treatments combined with topical 5% natamycin); topical 1% voriconazole combined with oral voriconazole compared to both oral voriconazole and oral itraconazole (both combined with topical 5% natamycin); topical 1% itraconazole compared to topical 1% itraconazole combined with oral itraconazole; topical amphotericin B compared to topical amphotericin B combined with subconjunctival injection of fluconazole; intracameral injection of amphotericin B with conventional treatment compared to conventional treatment alone (severe fungal ulcers); topical 0.5% and 1% silver sulphadiazine compared to topical 1% miconazole. Overall the results were inconclusive because for most comparisons only one small trial was available. The exception was the comparison of topical natamycin and topical voriconazole for which three trials were available. In one of these trials clinical cure (healed ulcer) was reported in all 15 people allocated to natamycin and in 14/15 people allocated to voriconazole (risk ratio (RR) 1.07; 95% confidence interval (CI) 0.89 to 1.28, low quality evidence). In one trial people randomised to natamycin were more likely to have a microbiological cure at six days (RR 1.64; 95% CI 1.38 to 1.94, 299 participants). On average, people randomised to natamycin had better spectacle-corrected visual acuity at two to three months compared to people randomised to voriconazole but the estimate was uncertain and the 95% confidence intervals included 0 (no difference) (mean difference -0.12 logMAR, 95% CI -0.31 to 0.06, 434 participants; 3 studies, low quality evidence) and a decreased risk of corneal perforation or therapeutic penetrating keratoplasty, or both (RR 0.61; 95% CI 0.40 to 0.94, 434 participants, high quality evidence). There was inconclusive evidence on time to clinical cure. Compliance with treatment and quality of life were not reported. One trial comparing natamycin and voriconazole found the effect of treatment greater in Fusarium species, but this subgroup analysis was not prespecified by this review.Authors' Conclusions: The trials included in this review were of variable quality and were generally underpowered. There is evidence that natamycin is more effective than voriconazole in the treatment of fungal ulcers. Future research should evaluate treatment effects according to fungus species.
Keywords: Antifungal Agents -- Therapeutic Use; Keratitis -- Drug Therapy; Mycoses -- Drug Therapy; Chlorhexidine; Clinical Effectiveness; Clinical Trials; Comparative Studies; Developing Countries; Itraconazole; Keratitis -- Etiology -- Developing Countries; Miconazole; Ointments; Silver Sulfadiazine; Treatment Failure; Human

New glaucoma drug may encourage compliance. (Geriatrics, 1991)
The article cites a study which finds that Metipranolol HCl 0.3% (Opti-Pranolol), a new topical beta blocker for the treatment of openangle glaucoma and ocular hyper tension, may offer the additional benefit of improved patient compliance because of lower cost. Mark B. Abelson, MD, assistant clinical professor of ophthalmology, Harvard Medical School, found that metipranolol's ability to control intraocular pressure was similar to that of other beta-blockers. He recommends metipranolol as a first-line agent for elderly patients with no cardiac or respiratory problems.

Medical treatment of glaucoma reaches surgical effectiveness. - Herskovits B (Ocular Surgery News, 2003)
Recent studies change thinking on how to manage, treat glaucoma.
Keywords: Glaucoma -- Drug Therapy; Glaucoma -- Surgery; Patient Compliance; Quality of Life; Treatment Outcomes

Preservative toxicity part of poor glaucoma compliance: when possible, glaucoma medications without preservatives or with nontoxic preservatives should be prescribed, one clinician says. - Gonzalez JM (Ocular Surgery News, 2003)
Keywords: Quaternary Ammonium Compounds -- Adverse Effects; Glaucoma -- Drug Therapy; Medication Compliance

Keeping an eye on glaucoma treatment. (Johns Hopkins Medical Letter: Health After 50, 2006)
Keywords: Glaucoma -- Complications; Glaucoma -- Drug Therapy; Hypertension -- Complications; Ophthalmic Solutions -- Therapeutic Use; Adrenergic Beta-Antagonists -- Therapeutic Use; Glaucoma -- Prevention and Control; Hypertension -- Drug Therapy; Ophthalmic Solutions -- Administration and Dosage; Patient Compliance

Compliance case studies. Glaucoma screening exam. - Rose EA (Ocular Surgery News, 2003)
Medicare has specific requirements for covering annual screening.
Keywords: Glaucoma -- Prevention and Control; Health Screening -- Economics; Medicare -- Economics; Billing and Claims -- Economics; Insurance, Health, Reimbursement -- Economics

Cost-effectiveness of monitoring glaucoma patients in shared care: an economic evaluation alongside a randomized controlled trial. - Holtzer-Goor, Kim M; van Sprundel, Esther; Lemij, Hans G; Plochg, Thomas; Klazinga, Niek S; Koopmanschap, Marc A (BMC Health Services Research, 2010)
Keywords: Glaucoma -- Therapy; Hospitals, Special -- Economics; Ophthalmology -- Economics; Optometry -- Economics; Quality of Health Care -- Standards; Aged; Appointments and Schedules; Cost Benefit Analysis; Economic Aspects of Illness; Female; Glaucoma -- Economics; Health Care Costs; Human; Intraocular Pressure; Male; Middle Age; Netherlands; Ophthalmology -- Manpower; Optometry -- Manpower; Patient Satisfaction; Prospective Studies; Randomized Controlled Trials; Referral and Consultation -- Economics; Travel; Workload

Interventions for improving adherence to ocular hypotensive therapy. - Waterman H; Evans JR; Gray TA; Henson D; Harper R (Cochrane Database of Systematic Reviews, 2013)
Poor adherence to therapy is a significant healthcare issue, particularly in patients with chronic disease such as open-angle glaucoma. Treatment failure may necessitate unwarranted changes of medications, increased healthcare expenditure and risk to the patient if surgical intervention is required. Simplifying eye drop regimes, providing adequate information, teaching drop instillation technique and ongoing support according to the patient need may have a positive effect on improving adherence. To summarise the effects of interventions for improving adherence to ocular hypotensive therapy in people with ocular hypertension (OHT) or glaucoma. We searched CENTRAL (which contains the Cochrane Eyes and Vision Group Trials Register) (The Cochrane Library 2012, Issue 6), MEDLINE (June 1946 to June 2012), EMBASE (June 1980 to June 2012), Cumulative Index to Nursing and Allied Health Literature (CINAHL) (June 1937 to June 2012), PsycINFO (1806 to June 2012), PsycEXTRA (1908 to June 2012), Web of Science (1970 to June 2012), ZETOC (1993 to June 2012), OpenGrey (System for Information on Grey Literature in Europe) (www.opengrey.eu/), the metaRegister of Controlled Trials (mRCT) (www.controlled-trials.com), ClinicalTrials.gov (www.clinicaltrials.gov) and the WHO International Clinical Trials Registry Platform (ICTRP) (www.who.int/ictrp/search/en). We did not use any date or language restrictions in the electronic searches for trials. The electronic databases were last searched on 26 June 2012. We did not search the National Research Register (NNR) as this resource has now been now archived. We contacted pharmaceutical manufacturers to request unpublished data and searched conference proceedings for the Association for Research in Vision and Ophthalmology (ARVO), and the Annual Congress for the Royal College of Ophthalmologists (RCO). We included randomised controlled trials (RCTs) and quasi-RCTs that compared interventions to improve adherence to ocular hypotensive therapy for patients with OHT or glaucoma. At least two authors independently assessed the search results for eligibility and extracted data for included trials onto specifically designed forms. We did not pool data due to clinical and methodological heterogeneity. Sixteen trials (1565 participants) met the inclusion criteria. Seven studies investigated some form of patient education. In six of these studies this education was combined with other behavioural change interventions including tailoring daily routines to promote adherence to eye drops. Eight studies compared different drug regimens (one of these trials also compared open and masked monitoring) and one study investigated a reminder device. The studies were of variable quality and some were at considerable risk of bias; in general, the length of follow-up was short at less than six months with only two studies following up to 12 months. Different interventions and outcomes were reported and so it was not possible to produce an overall estimate of effect. There was some evidence from three studies that education combined with personalised interventions, that is, more complex interventions, improved adherence to ocular hypotensive therapy. There was less information on other outcomes such as persistence and intraocular pressure, and no information on visual field defects, quality of life and cost. There was weak evidence as to whether people on simpler drug regimens were more likely to adhere and persist with their ocular hypotensive therapy. A particular problem was the interpretation of cross-over studies, which in general were not reported correctly. One study investigated a reminder device and monitoring but the study was small and inconclusive. Although complex interventions consisting of patient education combined with personalised behavioural change interventions, including tailoring daily routines to promote adherence to eye drops, may improve adherence to glaucoma medication, overall there is insufficient evidence to recommend a particular intervention. The interventions varied between studies and none of the included studies reported on the cost of the intervention. Simplified drug regimens also could be of benefit but again the current published studies do not provide conclusive evidence. Future studies should follow up for at least one year, and could benefit from standardised outcomes.[CINAHL Note: The Cochrane Collaboration systematic reviews contain interactive software that allows various calculations in the MetaView.]
Keywords: Glaucoma -- Drug Therapy; Medication Compliance; Clinical Trials; Meta Analysis; Ocular Hypertension -- Drug Therapy; Relative Risk; Human

Adherent ocular bandage may help close, protect trabeculectomy wounds. - Pagnani, Michelle (Ocular Surgery News, 2011)
Keywords: Glaucoma -- Surgery; Surgical Wound; Bandages and Dressings; Treatment Outcomes

Association between intraocular pressure and adherence: is there one?...Eye (Lond). 2010 Aug;24(8):1338-43 - Cate H; Broadway DC (Eye, 2011)
Keywords: Antihypertensive Agents -- Administration and Dosage; Prostaglandins, Synthetic -- Analogs and Derivatives; Drug Monitoring -- Equipment and Supplies; Glaucoma -- Drug Therapy; Medication Compliance; Female; Male

A history of intraocular pressure and its measurement. - Stamper RL; Stamper, Robert L (Optometry & Vision Science, 2011)
Doctors have not always associated elevated intraocular pressure with the vision loss from glaucoma. Although several individuals appear to have noted firmness of the eye in this condition as far back as the 10th century, elevated intraocular pressure was not routinely assessed until the latter part of the 19th century. von Graefe developed the first instrument for measuring intraocular pressure in 1865. The first reasonably accurate instrument was the Maklakoff applanation tonometer of the late 19th century; it was in widespread use throughout Eastern Europe until relatively recently. Schiötz developed an indentation tonometer that was widely used throughout the world during the first two thirds of the 20th century. Goldmann's applanation tonometer of 1950 began the era of truly accurate intraocular pressure measurement. It is still the most widely used tonometer in the world. Other devices such as the McKay-Marg tonometer (or its offspring the Tono-Pen), the pneumatonometer, and airpuff applanation tonometers are gaining adherents. The dynamic contour tonometer is the first totally new concept in tonometry in over 100 years. It is probably the most accurate of all the tonometers and is relatively independent of corneal biomechanical properties unlike its predecessors. Transpalpebral tonometers are attractive as they do not require topical anesthesia; however, they add the biomechanical properties of the eyelid to the list of potential errors and have not proven very accurate. The future should, hopefully, bring tonometers that can give diurnal or even longer indications of intraocular pressure variation. Although intraocular pressure elevation (or its absence) no longer can be counted on for diagnostic purposes, the role of intraocular pressure in the management of glaucomatous optic neuropathy remains critical.
Keywords: Glaucoma -- History; Intraocular Pressure; Tonometry -- History; Equipment Design -- History; Glaucoma -- Physiopathology; History; Tonometry -- Equipment and Supplies; Tonometry -- Methods; Maklakoff; McKay; von Graefe; Goldmann, H; Marg; Schiötz

Tele-screening can help identify vision-threatening diseases. - Szirth B; Shahid K; Khouri A; Patel N; Horan C; Giliberti F; Kaiser R; Bhagat N (Ocular Surgery News, 2005)
Left untreated, diseases such as AMD, diabetic retinopathy and glaucoma can progress to an advanced stage where preventive measures are no longer effective.
Keywords: Blindness -- Prevention and Control; Diabetic Retinopathy -- Diagnosis; Digital Imaging -- Methods; Glaucoma -- Diagnosis; Macular Degeneration -- Diagnosis; Telemedicine; Vision Screening -- Utilization; Age Factors; Diabetic Retinopathy -- Risk Factors; Diagnosis, Eye; Geographic Factors; Health Services Accessibility; Health Services Needs and Demand; Intraocular Pressure; Funding Source; Human

Tear dysfunction and the cornea: LXVIII Edward Jackson Memorial Lecture. - Pflugfelder SC; Pflugfelder, Stephen C (American Journal of Ophthalmology, 2011)
Purpose: To describe the cause and consequence of tear dysfunction-related corneal disease.Design: Perspective on effects of tear dysfunction on the cornea.Methods: Evidence is presented on the effects of tear dysfunction on corneal morphology, function, and health, as well as efficacy of therapies for tear dysfunction-related corneal disease.Results: Tear dysfunction is a prevalent eye disease and the most frequent cause for superficial corneal epithelial disease that results in corneal barrier disruption, an irregular optical surface, light scattering, optical aberrations, and exposure and sensitization of pain-sensing nerve endings (nociceptors). Tear dysfunction-related corneal disease causes irritation and visual symptoms such as photophobia and blurred and fluctuating vision that may decrease quality of life. Dysfunction of 1 or more components of the lacrimal functional unit results in changes in tear composition, including elevated osmolarity and increased concentrations of matrix metalloproteinases, inflammatory cytokines, and chemokines. These tear compositional changes promote disruption of tight junctions, alter differentiation, and accelerate death of corneal epithelial cells.Conclusions: Corneal epithelial disease resulting from tear dysfunction causes eye irritation and decreases visual function. Clinical and basic research has improved understanding of the pathogenesis of tear dysfunction-related corneal epithelial disease, as well as treatment outcomes.
Keywords: Cornea -- Physiopathology; Lacrimal Apparatus Diseases -- Physiopathology; Tears -- Physiology; Corneal Diseases -- Physiopathology

Glaucoma Screening App May Benefit Patients Who Lack Access to Eye Care. (Optometric Management, 2014)
Keywords: Vision Screening; World Wide Web Applications -- Utilization; Health Services Accessibility -- Central America; Glaucoma; Wireless Communications; Central America

Glaucoma Screening App May Benefit Patients Who Lack Access to Eye Care. (Optometric Management, 2014)
Keywords: Vision Screening; World Wide Web Applications -- Utilization; Health Services Accessibility -- Central America; Glaucoma; Wireless Communications; Central America

Effective glaucoma screening strategies should include involvement of medical students. - Boyle EL (Ocular Surgery News, 2006)
More evidence of efficacy is needed to garner support for screening programs, one expert says.
Keywords: Glaucoma -- Prevention and Control; Students, Medical; Vision Screening -- Education; Curriculum; Disease Progression -- Prevention and Control; Eye Care; Health Services Accessibility; Intraocular Pressure; Patient Education; Socioeconomic Factors

POINT/COUNTER. (Ocular Surgery News, 2013)
Keywords: Tomography; Interferometry; Glaucoma -- Diagnosis; Health Screening; Public Health; Cost Benefit Analysis; Quality of Health Care; Health Services Accessibility; Technology; Socioeconomic Factors

Study yields no difference in IOP between SLT, drugs as initial therapy. - Kronemyer, Bob (Ocular Surgery News, 2012)
Keywords: Treatment Outcomes; Intraocular Pressure; Keratectomy, Laser; Glaucoma -- Therapy; Ocular Hypertension -- Therapy; Glaucoma -- Drug Therapy; Ocular Hypertension -- Drug Therapy; Patient Compliance

Disparities in adult vision health in the United States. - Zambelli-Weiner A; Crews JE; Friedman DS (American Journal of Ophthalmology, 2012)
Keywords: Eye Diseases -- Epidemiology; Health Services Accessibility -- Trends; Health Services Accessibility -- Statistics and Numerical Data; Ophthalmology -- Trends; Disabled -- Statistics and Numerical Data; Adult; Cataract -- Epidemiology; Diabetic Retinopathy -- Epidemiology; Female; Glaucoma -- Epidemiology; Surveys; Human; Macular Degeneration -- Epidemiology; Male; Population Surveillance; Refractive Errors -- Epidemiology; United States

Task force report offers contact lens solution safety warnings. - Moskowitz A (Ocular Surgery News, 2007)
Members assert that many patients affected by the recent Acanthamoeba keratitis outbreak did not practice proper contact lens hygiene.
Keywords: Cleaning Compounds -- Adverse Effects; Contact Lenses; Patient Safety; Amebiasis; Keratitis -- Diagnosis; Keratitis -- Drug Therapy; Keratitis -- Microbiology; Keratitis -- Prevention and Control; Neomycin -- Therapeutic Use; Patient Compliance; Product Recall

Seeing the problem. - Spinks-Chamberlain, Paula (Learning Disability Today, 2011)
The article reports on a high rate of vision problems which is commonly seen in people with learning disabilities. A discussion of barriers which people with learning disabilities often face when attempting to access eye care, and of the importance of detecting vision problems at an early stage, is presented.
Keywords: Mentally Disabled Persons; Vision Disorders -- Prevention and Control; Vision Disorders -- Diagnosis; England; Glaucoma; Self-Advocacy; Middle Age

Contact Lens Care & Compliance. Can Media Sensationalism Help Reinforce Compliance? - WARD, MICHAEL A. (Contact Lens Spectrum, 2016)
Keywords: Contact Lenses; Caring; Centers for Disease Control and Prevention (U.S.); Acanthamoeba Keratitis; Lenses

Contact Lens Care & Compliance. GPs and Acanthamoeba. - WARD, MICHAEL A. (Contact Lens Spectrum, 2016)
Keywords: Contact Lenses; Centers for Disease Control and Prevention (U.S.); Global Positioning System; Caring; Acanthamoeba Keratitis

Smoothing the intraocular pressure roller coaster: a new goal? - Jay Katz L; Myers JS; Jay Katz, L; Myers, Jonathan S (American Journal of Ophthalmology, 2009)
Keywords: Antihypertensive Agents -- Therapeutic Use; Glaucoma -- Drug Therapy; Intraocular Pressure -- Drug Effects; Prostaglandins, Synthetic -- Therapeutic Use; Timolol -- Therapeutic Use; Patient Compliance; Risk Factors; Tonometry; Treatment Outcomes

In-office diagnostic equipment rental. (Optometry -- Journal of the American Optometric Association, 2009)
Keywords: Glaucoma -- Diagnosis; Laboratory Equipment and Supplies -- Economics; Office Visits; Optometry -- Economics; Optometry -- Equipment and Supplies; Product Acquisition -- Administration

Aerobic exercise, resistance training help lower IOP, experts say. - Nader N (Ocular Surgery News, 2004)
After 3 months of routine weekly exercise, IOP can be reduced by up to 20%. But compliance is low.
Keywords: Ocular Hypertension -- Prevention and Control; Therapeutic Exercise

Endothelial keratoplasty: DSEK/DSAEK or DMEK--the thinner the better? - Dapena I; Ham L; Melles GRJ (Current Opinion in Ophthalmology, 2009)
PURPOSE OF REVIEW: Endothelial keratoplasty has been adopted worldwide as an alternative to penetrating keratoplasty in the treatment of corneal endothelial disorders. Descemet stripping (automated) endothelial keratoplasty (DSEK/DSAEK) may be the current standard, whereas Descemet membrane endothelial keratoplasty (DMEK), that is, isolated transplantation of Descemet membrane, may allow further improvement of clinical outcome. RECENT FINDINGS: DSEK/DSAEK may still have three major challenges: suboptimal visual acuity and relatively slow visual rehabilitation, limited accessibility due to required investments in equipment or the purchase of predissected tissue, and a drop in donor endothelial cell density in the early postoperative phase. Although DMEK may allow much quicker and (near) complete visual rehabilitation as well as easier logistics in donor preparation, the surgical technique may initially require more training to obtain consistent outcomes. SUMMARY: Compared with DSEK/DSAEK, DMEK may have higher clinical potential with 75% of cases reaching 20/25 or better (> or =0.8) within 1-3 months. Furthermore, preparation of isolated Descemet grafts does not require large investments and may increase overall donor tissue availability. Hence, corneal surgeons may consider 'to make the switch' from DSEK/DSAEK to DMEK.
Keywords: Corneal Transplantation -- Methods; Eye Surgery; Endothelium -- Physiology; Glaucoma -- Etiology; Graft Rejection; Grafts -- Adverse Effects; Ophthalmology; Surgery, Operative -- Methods; Transplant Donors; Visual Acuity -- Evaluation

Study: SLT has contralateral eye effect. - Bacharach J (Ocular Surgery News, 2006)
IOP was lowered 10% in the fellow eye of SLT-treated eyes, even if the treated eye was nonresponsive to SLT.
Keywords: Glaucoma -- Surgery; Intraocular Pressure -- Drug Effects; Laser Therapy -- Methods; Circadian Rhythm; Glaucoma -- Complications; Glaucoma -- Diagnosis; Patient Compliance; Patient Satisfaction; Surgeons; Time Factors; Treatment Outcomes

Panel addresses questions about Fusarium investigation. - Byrne J (Ocular Surgery News, 2006)
The panel meeting, convened by Bausch & Lomb at the AOA Congress, addressed questions about the outbreak and the product recall.
Keywords: Disease Outbreaks; Keratitis -- Microbiology; Mycoses -- Physiopathology; Product Recall; Contact Lenses -- Adverse Effects; Eye Care; Patient Compliance; Patient Safety; Solutions -- Adverse Effects

After years of international sanctions, Libya opens to 'Flying Eye' hospital. - Lewis RA (Ocular Surgery News, 2006)
One surgeon describes a recent Project Orbis mission to bring much-needed eye care to North Africa.
Keywords: Eye Diseases -- Education; Health Services Needs and Demand; Missions and Missionaries; Mobile Health Units; Volunteer Workers; Aircraft; Diabetes Mellitus -- Complications; Diabetic Retinopathy -- Prevention and Control; Glaucoma -- Therapy; Health Services Accessibility; Hospitals; International Agencies; Libya; Physician Attitudes; Public Health; Surgeons -- Education

Dual sensory loss in adults: an overview for audiologists. - Busacco D (AudiologyOnline, 2010)
Keywords: Audiology; Hearing Disorders -- In Old Age; Vision Disorders -- In Old Age; Age Factors; Aged; Assistive Technology Devices; Cataract; Diabetic Retinopathy; Glaucoma; Health Services Accessibility; Hearing Disorders -- Complications; Hearing Loss, Sensorineural; Macular Degeneration; Male; Rehabilitation of Hearing Impaired; Rehabilitation of Vision Impaired; Vision Disorders -- Classification -- In Old Age; Vision Disorders -- Complications

Laser suitable as first-line treatment for glaucoma: alternative to eye drops avoids compliance problems, side effects. - Tamkins T (Medical Tribune, 1996)
Keywords: Glaucoma -- Therapy; Lasers -- Therapeutic Use; Lasers -- Adverse Effects

Strategies to improve compliance include patient education. - Boyle EL (Ocular Surgery News, 2006)
Electronic monitoring devices may soon provide ophthalmologists with more accurate information about patient compliance.
Keywords: Patient Compliance -- Evaluation; Patient Education; Physician-Patient Relations; Electronics; Glaucoma -- Therapy; Intraocular Pressure; Medication Compliance -- Evaluation; Monitoring, Physiologic -- Equipment and Supplies

Contact lenses and keratitis. - Guillon, M; Benjamin, W J (Lancet, 1991)
Keywords: Corneal Ulcer -- Microbiology; Contact Lenses -- Adverse Effects; Patient Compliance; Risk Factors

From the OSNSuperSite.com. (Ocular Surgery News, 2002)
Keywords: Angiogenesis Inhibitors; Cornea -- Surgery; Dry Eye Syndromes -- Symptoms; Keratitis -- Immunology; Keratomileusis, Laser in Situ; Appointments and Schedules; Equipment Design; Lenses; Marketing; Pharmaceutical Companies; Phototherapy; Eye Surgery -- Equipment and Supplies

Hydroxyzine may be safe and effective in generalised anxiety disorder. - Akhondzadeh S (Evidence Based Mental Health, 2003)
QUESTION: Is hydroxyzine safe and effective for generalized anxiety disorder in adult outpatients?DesignRandomised trial. Investigators and participants were blind to treatment allocation.Setting89 French general practices (supervised by psychiatrists); January 1998-March 1999.Participants334 outpatients diagnosed with generalised anxiety disorder (DSM-IV criteria) and a Hamilton Rating Scale for Anxiety (HAM-A) total score of at least 20. All were aged 18-65 years (mean 45 years); 68% women. Exclusion criteria were alcohol or drug dependence; major depressive episode within 6 months; score of 7 or above on the Raskin Severity of Depression and Mania scale; psychotic or delusional disorders within 3 years; chronic disease; prostate cancer; closed angle glaucoma; antidepressants, neuroleptics, mood regulators, morphine or derivatives, hydroxyzine, or bromazepam within 4 weeks; benzodiazepines more than 2 days per week during the past 30 days; benzodiazepines during the previous 2 weeks; need for psychotherapy; contraindication to study medication; and women who were pregnant, breastfeeding or not using contraception.InterventionAfter a 2 week placebo run in phase, participants received 12 weeks of 50 mg hydroxyzine per day, 6 mg bromazepam per day or placebo. Treatment was divided into three daily doses. Treatment was followed by 4 weeks of run out placebo. 83% of participants completed treatment. Adherence to medication was 85%.Main outcome measuresResponse (mean change in HAM-A total score); remission; adverse effects.Main resultsCompared with placebo, after 3 months of treatment the hydroxyzine group had superior response rates (P=0.003); remission rates (P=0.028); changes in Clinical Impressions Severity score (P=0.001); maintenance of efficacy (P=0.022), and Hospital Anxiety and Depression scale score on day 84 (P=0.008). There was no significant difference in efficacy between hydroxyzine and bromazepam. Safety was comparable between groups. Drowsiness was the most commonly reported adverse effect in the hydroxyzine group, although drowsiness was twice as common with bromazepam (see table).ConclusionsHydroxyzine appears to be safe and effective in adults with generalised anxiety disorder.
Keywords: Anxiety Disorders -- Drug Therapy; Hydroxyzine -- Therapeutic Use; Treatment Outcomes; Clinical Trials

Relate to patients to improve compliance, clinician says. - Nader N (Ocular Surgery News, 2005)
By engaging in dialogue, identifying patients who are noncompliant, and monitoring one's own practices, surgeons can improve outcomes.
Keywords: Glaucoma; Patient Compliance; Physician-Patient Relations

Socioeconomic factors affect patient compliance. (Ocular Surgery News, 2003)
Keywords: Patient Compliance; Socioeconomic Factors; Glaucoma -- Prevention and Control

Study: SLT procedures lowered IOP. - Boyle EL (Ocular Surgery News, 2006)
The laser procedure also reduced the mean number of medications needed and assisted in patient compliance and tolerance.
Keywords: Glaucoma -- Surgery; Intraocular Pressure; Laser Therapy -- Methods; Patient Compliance; Record Review; Retrospective Design; Surgeons; T-Tests; Treatment Outcomes; Human

A New Treatment Algorithm for EHK...Epithelial Herpetic Keratitis - Tertel, Zack (Optometric Management, 2013)
Keywords: Ganciclovir -- Administration and Dosage; Keratitis, Herpetic -- Drug Therapy; Algorithms; Patient Satisfaction; Patient Compliance

A New Treatment Algorithm for EHK...Epithelial Herpetic Keratitis - TERTEL, ZACK (Optometric Management, 2013)
Keywords: Ganciclovir -- Administration and Dosage; Keratitis, Herpetic -- Drug Therapy; Algorithms; Patient Satisfaction; Patient Compliance

Some surgeons unconvinced of advantages of MICS. - Wolkoff L (Ocular Surgery News, 2005)
Techniques and patient compliance issues were the main focus of the Argentinean Society of Ophthalmology's Annual Course this year.
Keywords: Cataract Extraction -- Methods; Microsurgery; Surgeons; Age Factors; Diagnosis, Eye; Drugs -- Economics -- Latin America; Glaucoma -- Surgery; Infant; Intraocular Pressure; Latin America; Patient Compliance; Physician Attitudes; Socioeconomic Factors; Strabismus -- Surgery -- In Infancy and Childhood

Written Educational Materials Improve Lens Compliance. - GROMACKI, SUSAN J. (Contact Lens Spectrum, 2012)
The article discusses the importance of written patient education materials in contact lens hygiene compliance, particularly in the prevention of Acanthoemba keratitis from lens contamination. Recommendations are presented for a patient education program for optometry practitioners which includes written and verbal instructions, video content, and reinforcement at later patient visits.
Keywords: Teaching Materials -- Evaluation; Writing for Publication; Patient Compliance -- Evaluation; Optometry; Contact Lenses; Patient Education; Acanthamoeba Keratitis -- Risk Factors; Hygiene; Access to Information -- Evaluation; Internet

Intraocular pressure: modulation as treatment for glaucoma. - Caprioli J; Varma R; Caprioli, Joseph; Varma, Rohit (American Journal of Ophthalmology, 2011)
Purpose: To review the role of intervisit intraocular pressure (IOP) fluctuation as an independent risk factor for glaucoma.Design: Perspective after literature review.Methods: Analysis of pertinent publications in the peer-reviewed literature.Results: Disparate findings regarding the role of intervisit IOP variation have been published. IOP variation was a significant risk factor in the Advanced Glaucoma Intervention Study (AGIS), the Collaborative Initial Glaucoma Treatment Study, and other smaller studies. These studies have in common low IOPs (often after surgery) and moderately advanced disease. In the AGIS, when patients were stratified by mean IOP, only those patients with low IOPs showed the detrimental effects of IOP variation. IOP variation was not a significant risk factor in the Early Manifest Glaucoma Treatment Trial, and in 2 separate studies of ocular hypertensives. These studies have in common generally higher IOPs and an earlier stage of glaucoma (or no glaucoma at all). We believe these results are complementary rather than contradictory: existing data suggest that the effects of IOP variation depend on the characteristics of the patient, the baseline IOP, their stage of damage, the type of glaucoma, and other as-yet unknown factors.Conclusions: Practitioners should consider whether patients who are progressing at low mean IOP may benefit from having IOP variation reduced. Single elevated measures of IOP may not be an anomaly or may not be related to compliance, but may identify patients who are at high risk for progressive glaucomatous damage, and thus should be monitored more carefully and potentially treated more aggressively.
Keywords: Glaucoma -- Drug Therapy; Glaucoma -- Physiopathology; Intraocular Pressure -- Drug Effects; Antihypertensive Agents -- Therapeutic Use; Intraocular Pressure -- Physiology; Risk Factors; Tonometry; Vision Disorders -- Physiopathology; Visual Acuity -- Physiology

Treatment Plan. Managing Corneal Neovascularization. - Miller, William L. (Contact Lens Spectrum, 2015)
Keywords: Corneal Diseases -- Therapy; Neovascularization, Pathologic -- Therapy; Neovascularization, Pathologic -- Complications; Cornea -- Anatomy and Histology; Neovascularization, Pathologic -- Risk Factors; Neovascularization, Pathologic -- Etiology; Keratitis, Herpetic -- Diagnosis; Keratitis, Herpetic -- Complications; Trachoma -- Diagnosis; Trachoma -- Complications; Blood Vessels -- Anatomy and Histology; Patient Compliance; Contact Lenses -- Evaluation; Hyperemia -- Diagnosis; Contact Lens Fitting; Steroids -- Administration and Dosage; Steroids -- Adverse Effects; Vascular Endothelial Growth Factors -- Therapeutic Use

Treatment Plan. Managing Corneal Neovascularization. - MILLER, WILLIAM L. (Contact Lens Spectrum, 2015)
Keywords: Corneal Diseases -- Therapy; Neovascularization, Pathologic -- Therapy; Neovascularization, Pathologic -- Complications; Cornea -- Anatomy and Histology; Neovascularization, Pathologic -- Risk Factors; Neovascularization, Pathologic -- Etiology; Keratitis, Herpetic -- Diagnosis; Keratitis, Herpetic -- Complications; Trachoma -- Diagnosis; Trachoma -- Complications; Blood Vessels -- Anatomy and Histology; Patient Compliance; Contact Lenses -- Evaluation; Hyperemia -- Diagnosis; Contact Lens Fitting; Steroids -- Administration and Dosage; Steroids -- Adverse Effects; Vascular Endothelial Growth Factors -- Therapeutic Use

Introduction. - Lindstrom RL (Ocular Surgery News, 2006)
Keywords: Glaucoma -- Therapy; Congresses and Conferences -- Hawaii; Glaucoma -- Risk Factors; Glaucoma -- Trends; Hawaii; Patient Compliance

A Fitting Discussion. - Miller, Jason R. (Optometric Management, 2014)
Keywords: Contact Lens Fitting -- Education; Patient Education; Corneal Ulcer -- Prevention and Control; Patient Compliance; Patient Satisfaction; Professional-Patient Relations

A Fitting Discussion. - MILLER, JASON R. (Optometric Management, 2014)
Keywords: Contact Lens Fitting -- Education; Patient Education; Corneal Ulcer -- Prevention and Control; Patient Compliance; Patient Satisfaction; Professional-Patient Relations

Topping Off Happens: Disinfection Efficacy Matters. - DeNaeyer, Gregory W. (Contact Lens Spectrum, 2014)
Keywords: Sterilization and Disinfection -- Methods; Contact Lenses; Sterilization and Disinfection -- Evaluation; Infection -- Prevention and Control; Acanthamoeba Keratitis -- Diagnosis; United States Food and Drug Administration; Cleaning Compounds; Patient Compliance -- Evaluation; Outcomes (Health Care)

Topping Off Happens: Disinfection Efficacy Matters. - DeNaeyer, Gregory W. (Contact Lens Spectrum, 2014)
Keywords: Sterilization and Disinfection -- Methods; Contact Lenses; Sterilization and Disinfection -- Evaluation; Infection -- Prevention and Control; Acanthamoeba Keratitis -- Diagnosis; United States Food and Drug Administration; Cleaning Compounds; Patient Compliance -- Evaluation; Outcomes (Health Care)

Written Educational Materials Improve Lens Compliance. - Gromacki, Susan J. (Contact Lens Spectrum, 2012)
Keywords: Teaching Materials -- Evaluation; Writing for Publication; Patient Compliance -- Evaluation; Optometry; Contact Lenses; Patient Education; Acanthamoeba Keratitis -- Risk Factors; Hygiene; Access to Information -- Evaluation; Internet

State law to give wider purview to optometrists. - Lee G (Los Angeles Times -- Southern California Edition (Front Page), 2000)
Keywords: Optometry -- Legislation and Jurisprudence -- California; Prescriptive Authority; Health Services Accessibility; Scope of Practice -- Legislation and Jurisprudence -- California; California; Glaucoma -- Drug Therapy; Referral and Consultation; Drugs, Prescription -- Administration and Dosage; Eye Care